Inclinometer-Based Reconstruction of Near-Bed Logarithmic Velocity Profiles in Shallow Coastal Waters: Field Evaluation Against an Acoustic Doppler Velocimeter - Sergio Hernández-Casas; Daniel B. Lluch-Cota; Sergio S. González-Peláez; Salvador E. Lluch-Cota; J. Jesús Bautista-Romero (Oceans, 2026)
Near-bed mean-flow structure is important to bottom-boundary-layer exchange and sediment-related processes in shallow coastal waters, but vertically resolved observations often require costly acoustic instrumentation. This proof-of-concept study evaluates a scalable framework using one or two tilt current meters (TCMs) for near-bed logarithmic-profile reconstruction. A short (L1) and long (L2) inclinometer were evaluated individually, and their simultaneous measurements at different effective heights were combined into a two-height reconstruction (L3). Reference profiles were obtained from eight sequential Nortek Vector acoustic Doppler velocimeter (ADV) profiles in Bahia de La Paz, Mexico. Reconstructions used a baseline hydraulic roughness length z0 = 0.015 m, with sensitivity over 0.001–0.015 m. L1 and L2 showed median absolute point-wise velocity errors of 0.0281 and 0.0290 m s−1, while L3 reduced this metric to 0.0213 m s−1. Friction–velocity ratios relative to the ADV were 1.13, 0.91, and 0.99 for L1, L2, and L3, respectively, indicating that relative performance depended on the metric considered. An individual TCM represented approximately 9–10% of the quoted ADV instrument price. The framework supports tiered, spatially replicated monitoring when logarithmic-profile assumptions are appropriate.

Morphodynamic Classification of Non-Estuarine Beaches of Morocco Using Multivariate Methods: A Contribution to the North African Typology of Coastal Wetlands - Ismail Farhaoui; Mohamed Dakki (Oceans, 2026)
The Moroccan littoral stretches on 3500 km, including 500 km on the Mediterranean side; this explains the considerable extent of the country’s coastal wetlands. The great variability in the geology and morphology of these littorals has led to a wide diversity of coastal landscapes, including more than 1500 km of beaches and 1000 km of rocky coastlines, interrupted by about 300 estuaries, and five large lagoons. This study aims to develop a primary classification of Morocco’s non-estuarine beaches, which number about 163 units. Referring to their descriptive inventory, based on four categories of physiographic criteria (morphology, geology, hydrodynamic, and sediments), we built a binary matrix ‘beaches × criteria’ that was treated using two statistical tools, k-means hierarchical clustering algorithm (HCA) and factorial correspondence analysis (CA). The main result of these treatments lies in a classification of the Moroccan non-estuarine beaches in fourteen clusters that can be explained by five determinant parameters: beach dimensions (width and length), slope, sediment grain size and spring tidal height. This classification could serve as a reference scheme for a more advanced classification of North African beaches, based on both satellite imagery and field measurements. With this in mind, the data collected in Morocco could serve as the basis for a larger database covering all North African coasts and built using the methodology presented in this article. In addition, this database would contribute significantly to the national inventory of wetlands, which is a fundamental step in their conservation.

A Review of the Costs and Benefits of Deep Sea Mining and the Ways Pollution Charges Could Work - Paul Hallwood (Oceans, 2026)
The potential benefits of deep sea mining for the International Seabed Authority members and the wider world economy are explained. However, deep sea mining is controversial because of its uncertain effects on deep sea ecology, with severe negative effects being possible. As a countermeasure it is argued that the existing royalty and tax system operated through the ISA could be used to manage pollution levels should these turn out to be serious, which at present is not clearly known.

Experimental Study on the Extreme Wave Run-Up Phenomenon of a Semi-Braceless Floating Wind Turbine Foundation Under Focusing Waves - Yanjun Mao; Yu-Fei Wu; Xiaoxu Huang; Xiaozhou Ma; Guohai Dong (Oceans, 2026)
A series of physical model tests of a semi-braceless floating wind turbine foundation (FOWT) under freak waves was conducted in the present work. The extreme wave run-up phenomenon on the FOWT columns was reported and investigated. The back column exhibits a median wave run-up amplification factor of 1.65 (a 65% rise from the baseline condition), with the maximum recorded value hitting 3.18, marking a 218% amplification compared to the reference wave run-up. Four factors contribute to this phenomenon, including the wave-trapped mode between columns, the shoaling effect of the pontoons, the relative motion between the platform and the wave surface, and nonlinear wave run-up. The extreme wave run-up corresponds to violent wave dynamic pressures, showing nonlinear column pressure distributions. Steeper local freak waves can lead to higher wave dynamic pressures on the columns, and slamming pressures occur under breaking waves in some harsh wave conditions. The peak slamming pressure on the back column reaches 300% of that on other columns. The wave run-up and wave pressures on the columns are relevant to the structure’s load level, which is crucial to the safety of the engineering design.

Environmental Variability and Chlorophyll-a Are Associated with Immature Whale Shark Surface Sightings in Nosy Be, Madagascar - Francesca Romana Reinero; Andrea Marsella; Antonio Pacifico; Isabella Buttino; Emilio Sperone; Stefano Aicardi; Francesca Ellero; Primo Micarelli (Oceans, 2026)
Whale shark aggregations in tropical coastal systems are linked to environmental variability and prey dynamics, yet the drivers of surface sightings remain poorly understood. In Nosy Be, Madagascar, a seasonal aggregation of immature whale sharks occurs within a productive coastal ecosystem. This study investigated the relationship between daily environmental conditions and whale shark surface sighting probability while accounting for heterogeneous sampling effort. Boat-based survey data collected from 2019 to 2025 were aggregated by sampling day, and daily whale shark surface sighting probability was analysed using a bias-reduced grouped binomial Generalized Linear Model. Environmental covariates included sea surface temperature, sea surface chlorophyll-a concentration, cloud cover, wind speed, and precipitation, while El Niño–Southern Oscillation variability was assessed as an interannual climatic descriptor. Using data from 103 recorded whale shark surface sightings, chlorophyll-a emerged as the strongest predictor, showing a positive association with daily sighting probability, whereas other environmental variables exhibited weaker and inconsistent effects. These findings suggest that whale shark surface sightings in Nosy Be are primarily associated with prey aggregation processes driven by local productivity rather than with direct responses to local physical environmental conditions. By integrating environmental variability and sampling effort into ecological models, this study provides insights into whale shark habitat use and supports ecosystem-based management of sustainable whale shark tourism in tropical coastal ecosystems.

Trends, Biases, and Knowledge Gaps in Glass Sponge (Porifera: Hexactinellida) Research - Alfredo Marchiò; Todd Bond; Alan J. Jamieson (Oceans, 2026)
Glass sponges (Porifera: Hexactinellida) have been the subject of scientific investigation for over two centuries, yet the temporal and thematic structure of this research effort has never been quantitatively evaluated. Here, we assessed taxonomic activity, geographical and bathymetric coverage, and keyword trends extracted from the indexed literature. We found two different periods of intense taxonomic activity occurring in the late 19th century and early 20th century, and then following World War II, with a steady increase in currently indexed publication output following the establishment of the modern peer-review system. However, research has been disproportionately concentrated on mesophotic and bathyal depths, whereas shallow and abyssal glass sponges have received comparatively little attention, while hadal records remained largely confined to the non-indexed literature until very recently. Furthermore, we found a decline in the number of active experienced glass sponge taxonomists, with few new experts being trained. This mismatch occurs as abyssal and hadal environments become increasingly accessible, potentially constraining our ability to adequately study the taxonomy and ecology of ultra-deep glass sponges.

Stokes Drift Drives the Intensification of Nearshore Submesoscale Fronts in the Northern South China Sea - Cheng Peng; Jiehua Wu; Peng Wang; Dongxiao Wang (Oceans, 2026)
Submesoscale processes in marginal seas are central to the ocean’s energy cascade, mixed-layer dynamics, and biogeochemical exchanges and are typically driven by complex mechanisms influenced by local background currents as well as external forcings such as winds, tides, and topography. Among these drivers, however, the role of surface gravity waves has received comparatively little attention. In this study, we investigate the influence of surface waves on nearshore submesoscale processes in the northern South China Sea using high-resolution nested simulations with the Coastal and Regional Ocean COmmunity model (CROCO). The model implements the Eulerian wave-averaged current equations based on the vortex-force formalism, accounting for wave-induced effects. Our results reveal that onshore Stokes drift induces an onshore transport of water masses, thereby raising the nearshore sea level and intensifying nearshore currents. The strengthened currents, in turn, enhance convergence- and strain-induced frontogenesis, leading to the intensification of nearshore submesoscale fronts. These findings elucidate a specific mechanistic link between wave-induced sea-level changes and submesoscale dynamics, contributing to a better understanding of the role of surface waves in shaping coastal circulation.

Enzymatic Preparation and Regeneration of Protoplasts from the Red Microalga Porphyridium purpureum - Bingqi Xu; Yiyang Wu; Wenzhou Xiang; Yaqi Geng; Liang Wei; Lingyu Ouyang; Houbo Wu; Hualian Wu; Jin Xu; Tao Li (Oceans, 2026)
Gene editing techniques are well-developed for model microalgae like Chlorella and Chlamydomonas. However, for the high-value species Porphyridium purpureum, its thick cell wall poses a significant barrier to genetic manipulation. Overcoming this challenge requires a robust method for preparing highly viable protoplasts. To generate protoplasts of P. purpureum, a targeted enzymatic lysis was applied based on the structural composition of the cell wall in this study. The results of single-factor experiments showed that a high protoplast yield (up to 43.55%) could be achieved under the following conditions: a total cellulase and macerozyme concentration of 2%, a cellulase-to-macerozyme ratio of 3:7, and a treatment time of 8 h in 0.2 mol/L KCl. Subsequently, Response Surface Methodology further optimized the enzymatic lysis conditions, yielding the optimal combination: a fixed combined concentration of cellulase and macerozyme at 2.2% in 0.2 mol/L KCL solution, a ratio of approximately 1:3, and an 8 h treatment, achieving a protoplast yield of 49.44%. Transmission electron microscopy, field emission scanning electron microscopy and Evans Blue staining confirmed that the protoplasts had smooth surfaces, no extracellular polysaccharide residues, and intact membranes and organelles. Furthermore, the optimal regeneration medium was ASW medium supplemented with 0.2 mol/L KCl, which might create a stable microenvironment for protoplast regeneration by balancing baseline osmotic pressure and ionic environment. This study established an effective protocol for protoplast preparation and regeneration, thereby facilitating the development of gene-editing tools for P. purpureum.

Stable Isotopes and Fatty Acids Reveal Diet Plasticity and Trophic Interactions of Small Pelagic Fishes in a Coastal Upwelling System - Rita García-Seoane; Inés G. Viana; Antonio Bode; Hilary G. Close (Oceans, 2026)
Small pelagic fishes play a crucial role in structuring marine food webs, yet their trophic flexibility and feeding interactions remain poorly understood in highly dynamic, nutrient-rich systems such as upwelling regions. This study combines bulk stable isotope analysis (δ13C and δ15N), compound-specific nitrogen isotope analysis of amino acids (CSIA-AA), and fatty acid (FA) profiles to assess feeding patterns and trophic overlap among four planktivorous species in the North Iberian shelf (Galicia and the Cantabrian Sea). The combined trophic indicators reveal clear niche partitioning between clupeids (sardine and anchovy) and scombrids (mackerel and chub mackerel), with the latter exhibiting higher CSIA-AA-derived trophic positions and distinct FA composition. Our analysis further shows that fatty acid biomarkers are essential for resolving finer-scale differences within each group, driven by variable contributions of phytoplankton and zooplankton to species diets. Although all species shared resources within the same food web, isotopic baselines indicate a decoupling between carbon and nitrogen pathways. For sardine, we compared neutral and polar lipid fractions with the total lipid extract in terms of FA composition and key dietary markers. Our results suggest that separating lipid fractions can improve dietary resolution, especially when lipid content is low. Overall, our findings highlight the value of integrating classical and emerging biochemical tracers to better resolve trophic dynamics in coexisting planktivorous fishes.

Hydraulic Performance of Coral Reefs for Coastal Protection: Wave Transmission and Setup Characteristics - Izqi Yustina Ammylia Yusuf; Tomoaki Nakamura; Xin Liu; Yong-Hwan Cho; Norimi Mizutani (Oceans, 2026)
This study experimentally investigated the wave transmission and setup characteristics of biomimetic submerged structures as Nature-based Solutions (NbSs) for coastal protection. A non-porous monolithic pillar and a highly porous, multi-branched staghorn coral replica were tested in a 2D flume featuring a 1:20 foreshore slope representative of Kuta Beach, Bali. The results revealed a highly divergent, period-dependent hydrodynamic response. Under short-period waves (T=0.8 s), attenuation was density dependent; the porous replica gradually dissipates energy through canopy micro-turbulence, yielding transmission coefficients (Kt) ranging from 0.25 to 1.18. Conversely, under long-period waves (T=1.6 s), the attenuation mechanism shifted to density-independent, depth-induced breaking. This establishes a critical hydrodynamic trade-off: higher wave attenuation (lower Kt) inherently generates a higher coastal wave setup due to momentum transfer. Crucially, while both structures reduced transmission, the internal porosity of the multi-branched replica facilitated sub-surface return flow, effectively capping the maximum normalized wave setup at 0.09. This represents an 18% reduction in setup-induced coastal hazards compared to the monolithic baseline. To facilitate practical engineering design, new empirical equations (R2≈0.80) for predicting Kt were derived, integrating the frontal area index (λf). Ultimately, these findings demonstrate that multi-branched biomimetic structures provide an optimal NbS design, balancing effective wave energy attenuation with the mitigation of secondary setup hazards for vulnerable coastal regions.

Form Meets Function: Role of Macroalgal Morphology in Structuring Mobile Epifaunal Assemblages in Selected Algae from the Central Mediterranean - Emma Borg; Patrick J. Schembri; Julian Evans (Oceans, 2026)
Quantitative measurement of macroalgal thallus morphology and its link with epifaunal communities remains largely unexplored in the central Mediterranean. This paper explores the link between thallus morphology and the associated mobile epifaunal assemblages of three common macroalgae native to the Maltese Islands (central Mediterranean Sea): Ellisolandia elongata, Jania rubens, and Dictyota spp. (D. dichotoma, D. mediterranea, and D. fasciola in mixed assemblages). We hypothesised that macroalgal species exhibiting distinct morphological characteristics support mobile epifaunal assemblages that differ significantly in structure and composition. Using a full factorial framework, macroalgal beds dominated by each target species were sampled from shallow water in three localities on the northeastern coast of Malta, using SCUBA diving. Dry biomass and fractal dimensions were used to characterise the distinct morphological traits of the three macroalgal species. A total of 85 epifaunal taxa were associated with Dictyota spp., 98 taxa with E. elongata, and 112 taxa with J. rubens. Excluding the disproportionately abundant invasive foraminiferan Amphistegina lobifera, 911 individuals were recorded on E. elongata, 1224 on Dictyota spp., and 2233 on J. rubens. Of the 152 taxa identified across all macroalgae studied, Arthropoda (44 taxa) and Mollusca (39 taxa) dominated, with individuals occupying the small inter-frond spaces as shelters that provide refuge from predators and hydrodynamic stress. Multivariate analysis revealed that the structure and composition of mobile epifaunal assemblages were associated with the interaction between macroalgal morphology and site-specific environmental conditions. The more structurally complex, articulated, calcified, and densely branched forms of E. elongata and J. rubens supported more varied epifaunal communities that differed from those associated with the compressed and leafier thalli of Dictyota spp., which were instead dominated by surface-associated taxa. Notably higher richness and diversity values were recorded in sheltered sites, especially in the case of J. rubens, showing that the effect of habitat architecture may be modulated by wave exposure.

Oceanographic Indicators of Seasonal Variability in the Guajira Upwelling System and Their Relationship with Phytoplankton - Jhon Carlos Salon-Barros; Rafael Ricardo Torres-Parra; Digna Rueda-Roa; Frank Muller-Karger (Oceans, 2026)
The Guajira Upwelling System (GUS) is located between 10–12.5° N and 61–75.5° W in the Southern–Central Caribbean Sea. This study examines its spatial and seasonal variability using upwelling indices derived from surface differences in temperature, salinity, density, and absolute dynamic topography between the GUS and a nearby Caribbean region (78–68° W, 10–16° N) not affected by coastal upwelling. Weekly time series from 1998 to 2022 were analyzed. The difference-based indices were compared with Ekman transport, a conventional proxy for upwelling intensity, and with satellite-derived chlorophyll-a to evaluate the phytoplankton response. Seasonal cycles were further examined at four representative grid points along the system. Among the indices, sea surface temperature most effectively delineated the spatial extent and seasonal variability of the GUS. Comparisons with chlorophyll-a revealed a strong upwelling–biomass relationship in the northern sector (east of 73.5° W), whereas productivity in the southern sector was not primarily driven by coastal upwelling. Correlation maps indicated that the weakening of upwelling influence coincided with the region affected by the Magdalena River plume.

Neural-Network-Based Prediction of Wave Heights and Periods Southeast of Fujian Province - Ting Zhang; Min Liu; Zhenwei Su (Oceans, 2026)
The prediction of ocean wave heights and periods is crucial for reducing maritime accidents. The application of neural networks to predictive modeling eliminates the need for complex parameter schemes that describe specific physical processes, thereby reducing computational costs. This study presents two single and three fusion models based on neural-network architectures: Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM), LSTM with an attention mechanism (LSTM+Attention), LSTM fused with a CNN (CNN+LSTM), and LSTM with Ensemble Empirical Mode Decomposition (EEMD+LSTM). The models were compared on multiple prediction lengths based on multivariate datasets from two oceanographic stations southeast of Fujian Province. All models performed well for prediction lengths of less than 24 h, with the coefficients of determination for wave height and period prediction higher than 0.7 and 0.6, respectively. For prediction lengths longer than 24 h, the predictive capability of EEMD+LSTM was superior to that of the other models. For a 48 h prediction length, the predictive results at each time step were compared with the true values across four typhoons. At the 24th and 48th time steps, phase lags were observed in the results from the CNN and LSTM. In contrast, EEMD+LSTM better captured the trends of the true values.

JPS-TEB Fusion Path Planning Based on COLREGs - Hongxiao Yu; Qiaoyan Cai; Jianqiang Zhang (Oceans, 2026)
To address the lack of compliance with the International Regulations for Preventing Collisions at Sea (COLREGs) in conventional timed elastic band (TEB)—based dynamic path planning for autonomous surface vessels (ASVs), this study proposes an intelligent path-planning framework that integrates an improved jump point search (JPS) algorithm with a COLREGs-aware TEB approach. At the global planning layer, an enhanced JPS algorithm incorporating redundant-node elimination and cubic Bezier curve smoothing is developed to construct the JPS–PB method, thereby reducing path redundancy and improving trajectory continuity. At the local planning layer, COLREGs encounter rules are reformulated as differentiable cost functions and embedded into the TEB optimization framework, enabling rule-compliant collision avoidance in typical maritime encounter scenarios, including head-on, crossing, and overtaking situations. Simulation results demonstrate that, compared with the conventional JPS algorithm, the proposed JPS-PB method reduces the path length by up to 8.6%, decreases the cumulative steering angle by 58.6%, and lowers the maximum steering angle by 88.6% on a 12 × 12 grid environment. Furthermore, compared with the conventional TEB algorithm, the proposed COLREGs–aware TEB (CTEB) increases the Distance at the Closest Point of Approach (DCPA) by 543%, 20.5%, 4.8%, and 13.8% in starboard-crossing encounters, head-on, overtaking, and special port-side-crossing encounter scenarios, respectively. Parameter sensitivity analyses further indicate that CTEB maintains stable collision-avoidance performance and rule-compliance capability under variations in the danger–distance threshold, danger–time threshold, and COLREGs cost weight. The results verify that the proposed JPS–PB+CTEB hybrid framework effectively improves path quality, dynamic obstacle-avoidance safety, and navigation-rule compliance for autonomous ASV operations.

Revisiting Satellite Chlorophyll–a Retrievals in the River-Influenced Coastal Upwelling Area off Central-Southern Chile - Gonzalo S. Saldías; Richard Muñoz; Alexander Galán; Roberto Aedo-Garcia; Carlos Lara; Fabián J. Tapia (Oceans, 2026)
Satellite chlorophyll–a (Chla) products are widely used to study coastal productivity, but their performance often degrades in river-influenced and optically complex waters. We evaluated MODIS-Aqua Chla retrievals in the coastal upwelling area off central-southern Chile, a region strongly affected by seasonal river plumes, using monthly in situ Chla and hydrographic observations from Station 18 (August 2002 to September 2011), daily MODIS products, and matchup analyses based on 3 × 3 pixel windows and 1-, 3-, 5-, and 7-day composites. MODIS Chla and normalized Fluorescence Line Height (nFLH) reproduced the broad seasonal cycle, with maxima during spring–summer, but default MODIS Chla systematically exceeded in situ observations, particularly during periods of enhanced turbidity and river-influenced optical complexity. Among the raw satellite products, 1-day MODIS Chla matchups showed the strongest agreement with in situ Chla (r = 0.77, RMSE = 8.5 mg m−3), whereas 5-day composites increased matchup availability to 95% but reduced the correlation (r = 0.46, RMSE = 10.5 mg m−3). In contrast, nFLH showed more stable performance across composite lengths, although it underestimated high Chla values and should therefore be interpreted as a complementary fluorescence-based diagnostic rather than as a direct substitute for locally validated Chla retrievals. A gradient boosting model trained with MODIS remote-sensing reflectances improved the correspondence between satellite and in situ Chla relative to the default MODIS product within the available Station 18 matchup dataset. Because this model was evaluated using cross-validation rather than an independent regional validation dataset, the machine-learning results should be interpreted as a local proof of concept rather than a fully validated regional algorithm. These results indicate that standard MODIS algorithms overestimate Chla in this river-influenced upwelling system and highlight the value of local correction approaches, including machine-learning methods, for improving coastal ocean color products, provided that future applications include independent spatially distributed validation and improved bio-optical characterization of river-influenced waters.

A Millennium-Scale Iberian Margin Chronology Validates the 1755 Lisbon Tsunami Record and Reveals Faro Record - Fatima Abrantes; Sandra Gomes; Marta Salvado; Vitor Magalhães; Emilia Salgueiro; Teresa Drago; Livia Cordeiro; Filipa Naughton (Oceans, 2026)
This work presents new data and several age–depth reconstructions based on distinct approaches to improve previously published age models for sedimentary sequences collected on the Iberian Margin middle shelf: PO287 6-1B, 2G (Porto); PO287 26-1B, 3G, and D13902 (Lisbon); and POPEI VC2B (Algarve). The new age models are constructed using radiocarbon dates calibrated with the IntCal20 calibration curve and smooth-spline regressions from the CLAM (non-Bayesian) and Bacon (Bayesian) models. A comparison of the age–depth models generated by the different approaches shows that, beyond the distinct solutions produced by CLAM and Bacon for each site, the differences between the two methods are inconsistent across sites. Furthermore, neither model yielded reliable results for the discontinuous sedimentary sequence with reworked older sediments and a hiatus. In this specific case, the “classical” linear regression (best-fit) approach appears to yield the results that enable intercomparison across all sequences. This exercise confirms the record of the 1755 earthquake and tsunami in the Lisbon core splice and a potential record of the same event in the Eastern Algarve, although the collected data indicate a more distal or lower-energy wave deposit.

Latitudinal Artifacts in Altimetry-Based Sea Level Records: Sources, Consequences, and Mitigation - Emeline Cadier; Claire Maraldi; François Bignalet-Cazalet; Nicolas Cuvillon; Geoffroy Bracher; François Boy; Bastien Courcol; Cécile Kocha; Victor Quet; Franck Octau; Pierre Prandi; Aurélien Deniau; et al. (Oceans, 2026)
Over the past three decades, five satellites have succeeded one another on the reference orbit, building the longest continuous climate record of global sea level measurements. Its continuity is ensured thanks to tandem flights between consecutive satellites. In this paper, we demonstrate that the first satellite of the Sentinel-6 series (Sentinel-6 Michael Freilich) has enabled the detection of a processing anomaly in the Jason-1/2/3 ground segment. An inconsistency in the altimeter range reconstruction has been identified, causing its underestimation by 3.65 mm. At certain latitudes, determined by the satellite’s orbital velocity, the altimeter range shows no effect from the anomaly. For the reference orbit, the range is not affected at the poles, around the equator and, for ascending tracks, at 40° S. All Jason Geophysical Data Record (GDR) versions prior to GDR-G are impacted by the described processing anomaly. While a full reprocessing of the Jason data with the GDR-G standard is pending, this paper presents a latitudinal empirical correction to be applied to Jason datasets generated with GDR-F and earlier ground segments. This correction, to be applied on the altimeter range, is derived from one month of patched Jason-3 data and is intended for reference orbit only. Additionally, SWOT Nadir ground processing is also affected by the same processing error and has been corrected from the GDR-S2 version onward. Finally, our analysis shows a negligible impact of this processing anomaly on Jason Level-2-derived products, models and metrics.

Predictive Maintenance in Maritime Operations: A Data-Driven Approach for Early Warning Systems - Nick Z. Zacharis; Kyriakos N. Sgarbas; George Leventakis; Petros Savvidis; Dimitris Papachristos; Nikitas Nikitakos; Iosif Progoulakis (Oceans, 2026)
This study outlines a comprehensive analytical methodology applied to a vessel’s operational data to establish a rigorously validated, data-driven baseline for the Marine and Health Usage Monitoring System (MHUMS) algorithmic modules. By correlating a continuous three-month dataset of sensor telemetry with historical alarm logs, the primary objective was to develop and train a robust predictive model. This study addresses the critical challenge of converting continuous marine sensor telemetry into actionable early warnings by establishing a validated predictive baseline. The proposed baseline predictive architecture achieved a Recall of 0.924 and an area under the ROC curve (AUC) of 0.939 for a 15 min forward prediction window, proving the feasibility of transitioning from reactive diagnostic monitoring to proactive early warnings.

Thermal and Osmotic Tolerance of the Medusa Stage of ‘Irukandji’ Jellyfish: Cubozoa; Carukia barnesi - Robert L. Courtney; Danica Lennox-Bulow; Tobin D. Northfield; Jamie E. Seymour (Oceans, 2026)
Carukia barnesi is a small tropical Cubozoan that causes painful and potentially fatal stings (Irukandji syndrome) along the north-eastern coast of Australia during the summer monsoonal months between November and May. This research establishes the thermal and osmotic tolerance of the medusa stage of the Irukandji jellyfish C. barnesi to determine if environmental parameters influence the marked seasonality of this species. By quantifying oxygen consumption over a range of temperatures, the theoretical minimum thermal requirement for the long-term persistence of C. barnesi medusae (i.e., theoretical zero) was estimated at 21.5 °C, which does not explain the seasonal occurrence of this species. The highest bell contraction frequency was determined to fall between 27.5 °C and 30.9 °C, which encompassed the typical thermal regime in situ. This research concludes that the deleterious effects of reduced performance associated with a departure from suitable environmental temperatures may better describe the seasonal pattern of this species than the theoretical thermal limits. Conversely, departure from suitable thermal regimes did not explain the southern distribution limits of this species, suggesting that C. barnesi could theoretically persist further south than their loosely defined southern distribution limits. Salinity also had a significant effect on C. barnesi medusae whereby the highest bell contraction frequency occurred at salinity levels above 33.6‰. Salinity levels below 29‰ reduced swimming capacity and became lethal below 25‰. This result supports the hypothesis that C. barnesi medusae are oceanic and/or neritic and cannot persist in estuarine environments where low salinity conditions commonly occur. Furthermore, the respiration rate of C. barnesi was lower at night, providing further evidence that this species is less active during night conditions, presumably to conserve energy.

Deep Learning-Based Bias Correction Model for Spatiotemporal Significant Wave Height Prediction Using Multi-Channel VMRNN - Bao Wang; Jie Xiao; Chuhan Feng; Xishan Pan; Bin Wang (Oceans, 2026)
Accurate prediction of significant wave height (SWH) is essential for fisheries management, coastal socioeconomic activities, and marine ecological conservation. In recent years, deep learning-based bias correction has shown considerable potential for improving numerical wave forecasts. However, many existing approaches are still constrained by limited receptive fields and often struggle to capture long-range spatiotemporal dependencies in wave forecast errors. To deal with this issue, we adapt and improve a video prediction framework, namely the Vision Mamba Recurrent Neural Network (VMRNN), to model and correct the spatiotemporal patterns of SWH prediction biases. Comprehensive evaluations show that the multi-channel VMRNN achieves consistently high predictive accuracy across different forecast lead times and sea-state conditions. When validated against reanalysis data, the proposed model reduces the root mean square error (RMSE) of WAVEWATCH III forecasts by 28.2%, 26.1%, and 24.7% at lead times of 24, 48, and 72 h, respectively. It also preserves the spatial structure of SWH fields quite well, with the spatial structural similarity index remaining as high as 0.945 even at the 72 h lead time. Regional assessments over high-wave areas further indicate that VMRNN can effectively reduce both the mean error and the systematic overestimation commonly found in numerical wave models. Additional validation using in situ buoys observations confirms that the model has a robust ability to correct systematic positive biases, especially for wave heights ranging from 0.5 m to 2 m. Taken together, these results suggest that VMRNN has strong spatiotemporal modeling capability and can serve as a promising post-processing framework for improving operational physics-based wave forecasting systems.

Research on Data-Driven Linear Prediction and Real-Time Control Method for Ship Rolling Control System in Beam Sea - Tongtong Qie; Jianyong Zheng; Jianzheng Zhang; Hongyu Wei; Haolin Yang; Kun Wei (Oceans, 2026)
Predicting a ship’s motion trend in waves is crucial for safe navigation and operation. Existing prediction models are mostly based on the assumption of local linear dynamics, which can achieve great performance in idealized ocean environments. However, ships typically sail in real marine environments with regular or irregular waves, which makes the robustness and real-time performance of ship motion estimation models particularly important. To address this limitation, this paper proposes a global linear predictor (GLP) based on the Koopman operator, which can effectively represent the nonlinear rolling dynamics of ships. Furthermore, the GLP model is used to predict and control the rolling motion of a ship in real time. The proposed method is validated in both regular and irregular wave environments. The simulation experiment results show that the accuracy of the proposed method is about 14% higher than that of other classical methods on ships’ rolling dynamics. And it achieves a more than 91% rolling reduction efficiency in all wave conditions, significantly decreasing the amplitude of a ship’s rolling.

Assessing Coastal Vulnerability in Al Hoceima Bay, Morocco, Using a GIS-Based Coastal Vulnerability Index (CVI) - Youssef Fannassi; Younes Oubaki; Zhour Ennouali; Titus Karderic Williams; Aicha Benmohammadi; Ali Masria (Oceans, 2026)
Coastal zones are facing rising exposure to climate-related hazards alongside intensifying human pressures, which highlights the need for robust tools to assess vulnerability. This study uses a GIS-based Coastal Vulnerability Index (CVI) to quantify and map relative vulnerability along ~13 km of shoreline in Al Hoceima Bay (northern Morocco). The proposed CVI integrates eight geological and physical indicators, including geomorphology, shoreline erosion and accretion rates, coastal slope, elevation, natural habitats, relative sea-level rise, significant wave height, and tidal range. Spatial analyses were performed using remote sensing data, historical records, field measurements, and Geographic Information Systems (GIS). The analysis reveals that 37% of the shoreline is categorized as high vulnerability, 44% is moderate, and 19% is low. Highly vulnerable sectors are primarily associated with low elevations, gentle coastal slopes, sandy beach systems, limited natural habitat protection, and proximity to river mouths. These findings demonstrate that the applied CVI provides a rapid and cost-effective framework for identifying priority areas for coastal management and climate adaptation. The proposed approach offers valuable decision-support insights for sustainable coastal planning in Al Hoceima Bay and other Mediterranean coastal environments characterized by limited data availability.

Recruitment of the Subtidal Kelp Eisenia bicyclis in Northeastern Japan: Effects of Multiple Environmental Factors - Haruka Suzuki; Tomoya Aoki; Masakazu N. Aoki (Oceans, 2026)
To determine the factors influencing juvenile recruitment of the kelp Eisenia bicyclis, a seven-year monitoring survey was conducted in an area affected by seismic subsidence caused by the 2011 earthquake and subsequent breakwater restoration. Juvenile recruitment was high in September 2011 and in May to June of 2013–2015, but low in 2012, 2016 and 2017. Analysis of the relationship between environmental factors and juvenile recruitment revealed that recruitment was associated with light intensity, with lower water temperature two months prior, and an increase in nutrients four months prior. The seasonal increase in nutrient concentrations during winter may have been influenced by the seasonal northwestward coastal current. In contrast, despite elevated nutrient concentrations, recruitment was relatively poor in 2016–2017. This might be attributed to the unstable seabed environment associated with the breakwater construction. Our monthly monitoring of both the number of E. bicyclis juvenile recruitments and environmental factors at the same site demonstrated that a time-lagged increase in nutrient concentrations and a decrease in water temperature are associated with Eisenia bicyclis juvenile recruitment. This study provides fundamental information on kelp recruitment that will contribute to predicting the recovery of kelp communities following disturbances and recruitment dynamics under environmental change.

Determining the Diversity and Environmental Structuring of Fish Larvae in an Amazonian Coastal Protected Estuary - Denise Sodré; Aurycéia Costa; Elton Silva; Luci Pereira; Rauquírio Costa (Oceans, 2026)
The Amazon coastal zone exhibits remarkable habitat diversity and species richness, with nutrient-rich estuaries playing a crucial role in local food webs and supporting fish and other aquatic organisms. To examine the distribution of fish larvae and juveniles in the Taperaçu Estuary and their relationship with environmental variables, monthly sampling was conducted at two fixed stations in 2008. Samples were collected during flood and ebb spring tides using 500 μm mesh nets. In situ measurements of salinity, temperature, and dissolved oxygen were recorded, while pH and turbidity were determined in the laboratory. Abiotic variables did not differ significantly between tides, but salinity and dissolved oxygen were higher during the dry season. A total of 5175 individuals were identified, representing 17 families and 37 species. The ichthyoplankton community was dominated by Rhinosardinia amazonica, Anchovia clupeoides, Stellifer stellifer, and Microgobius meeki. Stations 1 and 2 showed differing abundance ranges, with higher values at station 1 during the rainy season. Preflexion stages were abundant at both stations, indicating the estuary’s importance as a nursery and development area for several fish species. Multivariate analyses revealed spatial and seasonal structuring of larval assemblages along the estuarine gradient, driven primarily by salinity, temperature, and turbidity. Our results emphasize the role of upper estuary sectors of eastern Amazonia as areas of spawning, larval development, and subsequent juvenile settlement, contributing to the dispersal of fish species throughout the estuary and adjacent coastal environments. The present findings also reinforce the ecological value of the studied Extractive Reserve and other protected areas along the Amazon littoral as essential habitats for larval refuge and development. The need for continued monitoring and preservation of these protected zones is evident.

Adaptive Extraction of the Main Axis of the Kuroshio Current in the Northwest Pacific and Analysis of Multiscale Variability Mechanisms in the Front Zone - Xiang Wan; Lei Zhang; Maolin Li (Oceans, 2026)
Accurately capturing the Kuroshio’s main axis and its multiscale frontal variations remains challenging due to the constraints of traditional fixed-section extraction methods. Here, we develop an adaptive iterative tracking algorithm utilizing high-resolution reanalysis data (2002–2024) that dynamically adjusts search directions and cross-sections via local velocity vectors, integrated with a dynamic step size and two-dimensional validation. Applying a multiscale variability decomposition framework across four key regions reveals distinct spatiotemporal dynamics. The North Equatorial Current bifurcation zone exhibits a significant strengthening trend driven by seasonal zonal and decadal meridional flows. Conversely, the Kuroshio east of Taiwan is dominated by high-frequency mesoscale processes (~70%) with a semi-annual cycle and no long-term trend. The East China Sea front maintains a highly stable seasonal meridional signal (25%). Crucially, the Luzon Strait intrusion shows a significant long-term weakening trend (~0.0029 m·s−1·a−1, p < 0.01), characterized by eastward strengthening and northward weakening, with ENSO significantly modulating its seasonal cycle. This approach substantially reduces systematic extraction errors compared to traditional fixed-section methods, as independently verified using satellite SST frontal gradients (median deviation < 0.2°), providing critical observational evidence for understanding western boundary current–marginal sea interactions and their dynamical responses under global warming.

Spatiotemporal Dynamics of the Liaohe Delta (1987–2017) Using an Integrated Classification and Feature Selection Approach - Jihong Sun; Guohui Su; Huairong Song; Jingpeng Liu; Wenrong Lin; Qi Xu; Zonghua Liu (Oceans, 2026)
Wetland landscape classification is fundamental to monitoring changes in ecosystem patterns. This study proposes an ensemble classification approach that integrates Maximum Likelihood Classification (MLC) and Decision Tree (DT) methods with optimized feature selection for long-term wetland monitoring in the Liaohe Delta, China. Based on four periods of Landsat remote sensing images from 1987, 1997, 2007, and 2017, multi-dimensional features including PCA1, TCT, NDVI, and MNDWI were extracted to construct a hierarchical classification system comprising 13 landscape types. The results show that the integrated method achieved an overall classification accuracy of 87.71% and a Kappa coefficient of 0.85, improving by 16.50% and 19.72%, respectively, compared with the single MLC approach. The classification results reveal significant spatiotemporal variations in landscape patterns. Reed wetlands decreased from 1284.44 km2 in 1987 to 1006.70 km2 in 1997, followed by a recovery to 1275.53 km2 in 2017. In contrast, Suaeda communities experienced severe degradation, declining sharply from 227.48 km2 in 1987 to 30.52 km2 in 2017. Meanwhile, the coastline advanced landward by 263.24 km2, with the proportion of artificial shoreline increasing from 12.4% to 38.7%. The changes in wetland landscape types in the Liaohe Delta from 1987 to 2017 were mainly influenced by urbanization processes and ecological restoration policies. These findings indicate that the proposed method can effectively support long-term wetland landscape dynamics analysis and provide a useful reference for coastal wetland management.

Environmental Drivers of the Epipelagic Pteropod Community Structure in the Deep-Water Basin of the Southern Gulf of Mexico During Summer - Erik Coria-Monter; Adolfo Gracia; Elizabeth Durán-Campos; César Flores-Coto; Zayra López-Cabello; Magali Roa-Venicio; Alejandra Itzel Domínguez-Tavera (Oceans, 2026)
Holoplanktonic mollusks (Mollusca: Gastropoda: Pteropoda) are vital structural and functional components of marine zooplankton communities, characterized by high sensitivity to physicochemical shifts in the water column. Consequently, multidisciplinary assessments are essential to elucidate their community dynamics. This study investigated the epipelagic pteropod community structure in the deep-water basin of the southern Gulf of Mexico (sGoM) in relation to hydrographic features and circulation patterns. During the summer (September) of 2016, we collected high-resolution hydrographic data and zooplankton samples using CTD casts and oblique bongo net tows. Hydrographic data revealed intense temperature and density gradients, including a cold-dense core associated with a well-defined cyclonic eddy. The pteropod assemblage comprised 25 species from 13 genera and 10 families. Heliconoides inflatus (947.5 ind 100 m−3) and Limacina trochiformis (396.8 ind 100 m−3) were the most abundant species, whereas Cavolinia gibbosa (0.4 ind 100 m−3) and Cymbulia sp. (0.3 ind 100 m−3) were the least abundant. Horizontal distribution analyses revealed that the peak population densities occurred within the influence of the cyclonic eddy, particularly at its periphery where strong currents (>0.5 m/s) were recorded. A Canonical Correspondence Analysis identified temperature and salinity as the primary environmental drivers of community variability, while current systems significantly influenced the horizontal distribution of key species. Although pteropod research in the sGoM spans decades, most studies have been limited to taxonomic checklists, often overlooking environmental drivers and hydrographic influences. By applying a multidisciplinary approach to examine physical–biological coupling, this study advances the ecological understanding of this group within the historically underrepresented deep-water basin of the sGoM.

Winter Nutrient Dynamics in Funka Bay, Japan: A Multi-Year Observation Study - Tianchang Cui; Hiroto Abe; Tetsuya Takatsu; Kenshi Kuma; Yoshihiko Kamei; Naoto Kobayashi; Takahiro Iida; Atsushi Ooki (Oceans, 2026)
We investigated the autumn-to-winter evolution of water-mass structure and nutrient concentrations in Funka Bay, southwestern Hokkaido, Japan, from October to February (2012–2019). Hydrographic and biogeochemical profiles show a recurrent seasonal transition from strongly stratified conditions in October, with low surface nutrients and bottom enrichment, to increasingly homogeneous distributions by mid-winter as vertical mixing intensifies. Depth-averaged nutrient concentrations generally decreased from October to December and increased from December to February, except during December 2015–February 2016. To assess whether February nutrient levels can be explained by Oyashio supply alone, we calculated February nutrient concentrations using a two-endmember mixing model (Oyashio endmember and December Funka Bay water) with an additional regeneration term that assumes nutrients consumed during the October–December autumn bloom were fully regenerated during December–February and redistributed by winter mixing. Under this framework, the expected February concentrations agreed with observations in all winters except 2015, when observed nutrients were lower than expected nutrients, consistent with additional biological drawdown after the early onset of the bloom by late February. These results indicate that the pre-bloom winter nutrient environment in Funka Bay is shaped by variable Oyashio intrusion superimposed on seasonal mixing and internal regeneration processes.

Inversion of Sound Speed Profile Controlled by Sparse Observations: Research Background, Current Status and Technical Analysis - Haopeng Fan; Shuling Xie; Shuqiang Xue (Oceans, 2026)
The sound speed profile (SSP) is a core environmental parameter for underwater acoustic detection, navigation, communication, and other applications. However, its accurate acquisition is constrained by the sparsity of observational data and the ill-posed nature of inversion problems. This paper systematically reviews the research progress of SSP inversion under sparse observation constraints. The review traces the technical evolution from early physical models to current intelligent paradigms, classifies and compares mainstream inversion methods, presents typical application scenarios with quantitative case studies, provides a comparison of all kinds of SSP acquisition routes, and discusses critical challenges and future trends. The review reveals that current AI-driven methods achieve a practical accuracy of approximately 1–2 m/s but face bottlenecks in interpretability, cross-regional generalization, and extreme-condition robustness. Fusing physical constraints with multi-source sparse data (remote sensing, in-situ discrete measurements) emerges as the core direction for balancing inversion accuracy, efficiency, and cost. This paper provides a comprehensive reference for technical selection in marine acoustics, ocean observation, and underwater operations.

Economic Cycles and Regulatory Compliance: A Bidirectional Analysis of Vessel Detentions Under Port State Control - George Kokosalakis; Xakousti Afroditi Merika; Theodore Syriopoulos (Oceans, 2026)
Port State Control (PSC) inspections play a critical role in enforcing international maritime safety and environmental standards, yet little is known about how compliance behaviour interacts with economic cycles. This study examines the relationship between vessel detentions and freight market conditions using monthly data from the Paris and Tokyo Memoranda of Understanding (MoUs) over the period 2010–2021. A system of simultaneous equations is estimated using the Generalized Method of Moments (GMM) and Three-Stage Least Squares (3SLS) to address the bidirectional relationship between detention activity and freight market conditions, proxied by the Baltic Dry Index (BDI) and, for tanker specifications, the Baltic Dirty Tanker Index (BDTI). The results are consistent with a positive and statistically significant bidirectional relationship: vessel detentions increase during periods of strong freight market conditions, while past detentions are positively associated with freight rates, a pattern consistent with a signalling and sentiment channel. Institutional factors, including flag state quality, classification society affiliation, and ISM-related deficiencies, are also found to significantly influence detention risk, though their direction and magnitude vary across MoUs and vessel segments. These findings are consistent with the presence of opportunistic incentives during economic upswings, challenging the conventional expectation that stronger market conditions promote higher compliance. The study contributes to the literature by linking regulatory compliance with economic cycles and highlighting the importance of adaptive, risk-based enforcement strategies. It is important to note, however, that the aggregate nature of the data does not permit direct identification of firm-level behavioural mechanisms, and the findings should be interpreted as associational evidence consistent with these theoretical mechanisms.

Evolution and Challenges of Marine Oil Spill Governance in Taiwan over Two Decades - Chih-Wei Chang; Shiau-Yun Lu; Chun-Pei Liao; Wen-Yan Chiau; Yi-Che Shih (Oceans, 2026)
Marine oil spills pose critical challenges to environmental sustainability and socioeconomic stability. Taking four pivotal cases as the entry point, this study uses comparative case analysis, semi-structured stakeholder interviews, policy analysis and international gap comparison to systematically analyze the evolution of marine oil spill governance in the Taiwan region of China over two decades, aiming to identify systemic gaps and propose actionable reforms. By integrating and explicitly detailing these multiple methodologies, this research not only identifies but also systematically examines the Taiwan region of China’s unique challenges as a non-UN-member entity navigating international conventions like the international convention for the prevention of pollution from ships, 1973, as modified by the protocol of 1978 relating thereto (MARPOL 73/78). Key findings reveal persistent issues in decision-support tools, fragmented inter-agency coordination, and legal inadequacies in compensation mechanisms. The study’s novelty lies in its rigorous synthesis of localized case-driven insights compared with global best practices, proposing a concrete, phased model for a unified task force and context-aware, data-driven contingency plans to enhance real-time response efficiency. It further advocates for pragmatic steps to align the Taiwan region of China’s Marine Pollution Control Act with international standards while critically addressing the transboundary collaboration barriers imposed by its political status, exploring potential pathways through sub-national and regional partnerships. Notably, the 2023 Angel Container case underscores the urgency of modernizing enforcement capacities and integrating advanced technologies. By bridging gaps in governance, legal accountability, and practical international engagement, this research not only advances the Taiwan region of China’s preparedness but also offers a nuanced and adaptable blueprint for coastal regions facing similar geopolitical and environmental constraints. Its recommendations hold significant implications for global marine pollution management, emphasizing the interplay of policy innovation, technological adoption, and pragmatic cross-jurisdictional cooperation.

Anthropogenic and Storm Impacts on a Marine Benthic Ecosystem in an Urbanised Coastal Region of Northwestern Italy - Cristina Misic; Anabella Covazzi-Harriague (Oceans, 2026)
Marine benthic ecosystems along urbanised coastlines face heightened vulnerability due to the cumulative effects of chronic anthropogenic stressors. Climate change intensifies these pressures through more frequent and severe storms, while ongoing coastal development adds further stress through infrastructure projects. This study examined how soft-bottom communities in the coastal NW Mediterranean responded to two major disturbances: an exceptional storm in 2018 and the construction of a new wastewater pipeline in 2019. Sediment grain size, organic content, bacterial abundance and enzymatic activity, and metazoan communities were analysed during summer of 2018, 2019 and 2020 and in the following spring period. Hydrodynamic forcing caused a general increase in the grain size in 2019. Meiobenthos responded with a strong decline in abundance, especially crustaceans, while macrobenthos changed from a mixed deposit-feeder community to a suspension-feeder dominated one. In 2020, the improved trophic value of sediment organic matter in the pipe area favoured bacterial increase. While meiobenthos abundance slowly recovered, the differentiation increased due to macrobenthic juveniles, resulting from increased macrobenthic abundance and diversity (mainly pure deposit-feeders). A clear shift towards organic enrichment-tolerant taxa due to wastewater release was not observed, given the contemporary presence of very sensitive organisms, indicating that co-occurring stressors can lead to nonlinear responses of the communities.:

Distribution and First Insights into Habitat Preferences of the Armless Snake Eel Dalophis imberbis (Delaroche, 1809) (Anguilliformes: Ophichthidae) from New Occurrence Sites in the Central Mediterranean Sea - Matteo Battiata; Benedetto Sirchia; Sabrina Lo Brutto (Oceans, 2026)
The armless snake eel, Dalophis imberbis, is a fossorial rare species. It is considered to be a non-target fishery resource with elusive behavior, and there is a paucity of knowledge regarding its distribution and biology. This study reports three new documented occurrence records of D. imberbis along the northern and southeastern coastal areas of Sicily (central Mediterranean Sea) during 2025. Specimens were collected at depths ranging from 43 m to an unusually shallow depth of 5.4 m, extending the known upper vertical limit of the species, which was previously considered a 20 m depth. Environmental parameters were collected through a multiparametric probe and integrated with products from the Copernicus Marine Service (CMS), providing new insights which highlight the presence of the species in relatively warm (17.6–20.8 °C) and moderately oxygen-undersaturated (6.9–8.5 mg/L) waters. A global distributional analysis was performed by aggregating the field data with literature records and datasets published in the Global Biodiversity Information Facility (GBIF), refining the distribution of the species in the Mediterranean and Atlantic Ocean. Thus, the three new records expand the known distribution of the species in the center of the Mediterranean Sea, providing an updated bathymetric range and the first preliminary insights into the environmental preferences of this data-deficient ophichthid. This work underscores the importance of combining traditional surveys with big-data repositories and remote sensing to monitor rare marine biodiversity.

Balancing Convective and Langmuir Turbulence: An Enhanced Mixing Scheme for Ocean Models - Qian Fang; Xiaoyu Yu; Peng Wang (Oceans, 2026)
Langmuir turbulence is a key and common process in the ocean surface boundary layer, playing a major role in vertical mixing, heat flux, and material transport. However, because direct simulation of Langmuir turbulence demands considerable computational resources, parameterizations within established schemes like the K-profile parameterization (KPP) offer a practical alternative for representing its effects in ocean and climate models. However, Langmuir turbulence parameterizations based on KPP may overestimate vertical mixing when convection is significant. To address this, we introduce a dynamic weighting factor, based on characteristic velocity scales, to balance the contributions of convective and Langmuir turbulence. The improved scheme shows a significant enhancement in performance, especially under strong convective conditions. We compare and evaluate the new parameterization schemes against other widely used schemes in three typical scenarios. Additionally, we validate it using large-eddy simulation results and field observation data. Our enhanced mixing scheme is highly competitive and performs robustly under a variety of conditions.

Strong Effects of Sun Exposure on Oyster Shell Corrosion and Compensatory Calcification: A Factor Confounding Coastal Acidification Responses - David J. Marshall; Natasha Khairul; Naziratul Syaziyah Yahya; Norazimah Duraman; James R. Jennings (Oceans, 2026)
The dynamics of calcium carbonate structures in marine organisms (skeletons and shells) has become increasingly important due to heightened interest in marine environmental acidification. Research into molluscan shell corrosion and calcification in response to acidification is typically carried out in laboratory-controlled settings, which often overlooks the intricate interactions found in natural environments. Mollusks inhabiting intertidal zones are especially susceptible to intense shell weathering caused by tidal cycles of heating, cooling, wetting, and drying, exacerbated by solar radiation during periods of air exposure. We investigated the effect of sun exposure (solar radiative heating) on both outer shell corrosion and inner shell compensatory calcification in the tropical oyster, Saccostrea scyphophilla. Shell properties were compared between oysters from neighboring populations in sun-exposed and shaded habitats. Habitat temperatures were measured using iButtons, and right shell valve corrosion was quantified. Compensatory calcification was assessed through measurements of shell thickness, shell density, shell compression strength, and mineralogical properties. Our results revealed that oysters in the sun that experience global irradiance, higher temperature peaks and broader daily temperature ranges (averaging an increase of 10 °C) show considerably greater outer shell surface corrosion (87%) compared to shaded oysters (31%) that experience only diffuse irradiance. Sun-exposed shells also become thickened in the midsection and around the adductor muscle, and they are slightly stronger, indicating compensation for the outer shell loss. These findings highlight the need for caution when interpreting molluscan shell dynamics based on laboratory marine acidification protocols that fail to account for the many natural environmental factors influencing shell formation and dissolution.

Nexus of Ecosystem Services and Hilsa (Tenualosa ilisha) Genetic Diversity to Strengthen Wetland Conservation Policy Within the SDG Framework - Atiqur Rahman Sunny; Md. Shishir Bhuyian; Sharif Ahmed Sazzad; Md. Faruque Miah; Md. Ashrafuzzaman; Kamrul Islam; Md. Abdullah Al Mamun; Shamsul Haque Prodhan (Oceans, 2026)
The present study examined fish biodiversity, livelihood dependence, cultural importance, and genetic connectivity in two ecologically linked habitats of the Sylhet region, Bangladesh: Hakaluki Haor and the Surma River. Surveys documented 60 fish species with distinct assemblage patterns between sites. Hakaluki Haor was dominated by floodplain spawners and small indigenous species that contribute to year-round subsistence harvests, whereas the Surma River supported a greater proportion of migratory and pelagic species, most notably Tenualosa ilisha. These ecological contrasts reflected differences in hydrology, habitat diversity, and fishing intensity. Household surveys confirmed the central role of fisheries in sustaining income and food security, while cultural practices surrounding hilsa consumption reinforced local stewardship norms. Mitochondrial cytochrome b sequence analysis of T. ilisha revealed low genetic differentiation between sites, indicating a single, well-connected stock maintained by seasonal flooding and the absence of major migration barriers. This convergence of ecological and genetic evidence supports treating the two sites as an integrated management unit. Effective conservation will require protecting hydrological connectivity, safeguarding dry season refugia, coordinating seasonal fishing restrictions across habitats, and incorporating cultural values into policy frameworks. The findings strengthen the scientific basis for national and regional conservation strategies and demonstrate the value of combining biological, socio-economic, and cultural dimensions in managing connected wetland–river systems. This approach can serve as a transferable model for other tropical floodplain–river complexes facing similar ecological and livelihood challenges.

Research Trends on Invasive Marine Species in the Mediterranean: A Bibliometric and Topic Modeling Analysis - Dimitris Klaoudatos; Stefanos Gkourtsoulis; Dimitris Pafras; Alexandros Theocharis (Oceans, 2026)
The Mediterranean Sea is both a global biodiversity hotspot and the world’s most heavily invaded marine region, where non-indigenous species arrivals are accelerating under intensifying shipping, Suez Canal traffic, aquaculture, and climate warming. Yet, despite rapidly growing research activity, a comprehensive synthesis of the scientific literature on Mediterranean marine invasions has been lacking. This study provides the first Mediterranean-wide combined bibliometric and topic-modeling analysis of invasive marine species research, using 3521 unique documents retrieved from Scopus and Web of Science. We quantify temporal growth in publications and citations, map the conceptual structure of the field through co-citation, co-word, and topic modeling, and reveal pronounced regional and thematic biases. Latent Dirichlet Allocation resolves 13 coherent topics, dominated by first records of non-native species, invasive macroalgae, alien species diversity, and ecological impacts, with strong signals for Lessepsian migration and climate-driven range shifts, particularly in the Eastern Mediterranean. Spatial and thematic analyses reveal pronounced regional biases, with invasion hotspots in the Aegean and Levantine seas contrasted by comparatively sparse coverage of western and central sub-basins, and notable gaps in predictive modeling and socioeconomic assessments. The results underscore the need to rebalance effort toward under-studied regions and themes, while leveraging existing collaboration networks and methodological advances to support MSFD (Marine Strategy Framework Directive) implementation, International Maritime Organization (IMO) instruments, and broader ecosystem-based management. The reproducible framework presented here offers a baseline for periodically tracking research evolution and guiding adaptive, transboundary governance of Mediterranean marine bio-invasions.

The Role of Citizen Science Data Standardization for the Marine Strategy Framework Directive Implementation - Vasiliki Myrintzou; Nikolaos Kokkos; Dor Edelist; Garabet Kazanjian; Georgios Sylaios (Oceans, 2026)
Over the past two decades, Citizen Science (CS) has experienced rapid growth, driven by technological advancements and the rise of digital platforms. This work examines the necessity for standardization in Citizen Science data management and discusses how existing data standards can enhance the impact of citizen-generated data. CS standardization ensures data quality, comparability, reusability, and interoperability, making data suitable for contributing to the Marine Strategy Framework Directive (MSFD) and the United Nations Sustainable Development Goals (SDGs). This paper examined 130 Citizen Science publications and found that most collected data referred to the MSFD Descriptor 1 (Biodiversity—44.96%) and Descriptor 10 (Marine Litter—20.93%), followed by the alien species distribution (D2—11.63%), hydrography (D7—6.20%), eutrophication (D5—6.20%), and marine pollution (D8—3.10%). Analysis of 108 publications on SDG alignment revealed that the majority (35.58%) focused on reducing marine pollution. This paper reviews the best practices for effective Citizen Science data management, including standards for data structures, content, values, and exchange. Based on this review, Darwin Core, Ecological Metadata Language (EML), and the OGC SensorThings API appear to be the most suitable standards for MSFD-relevant CS data. Therefore, policymakers could enable the formal integration of standardized CS datasets into MSFD monitoring workflows.

Balancing Accuracy and Efficiency in the Temporal Resampling of Met-Ocean Data - Sara Ramos-Marin; C. Guedes Soares (Oceans, 2026)
Harmonising heterogeneous met-ocean time series to a common temporal resolution is a prerequisite for integrated marine renewable energy assessments. Such datasets often differ in their sampling frequency, statistical distribution, and non-stationarity, complicating joint analysis. This study presents a practical multi-criteria framework for selecting temporal interpolation strategies for met-ocean datasets, explicitly balancing prediction accuracy and computational efficiency. Six environmental variables relevant to offshore renewable energy—wind speed, significant wave height, energy period, peak period, global horizontal irradiance, and upper-ocean thermal gradients—are analysed using ten-year reanalysis datasets for the Madeira Archipelago. Six commonly used deterministic time-domain interpolation methods are evaluated within a unified validation framework combining training–test splits, k-fold cross-validation, and Monte Carlo resampling. Their performances are quantified using the relative root mean square error and computational time, integrated through a composite performance score. The results show that makima interpolation provides the most consistent compromise between accuracy and efficiency for most variables in dense, regularly sampled met-ocean datasets, while spline-based approaches perform better for highly skewed solar irradiance. Preprocessing steps, such as detrending and distribution normalisation, yield only marginal improvements for dense, regularly sampled datasets, and method rankings remain stable under moderate changes in accuracy–speed weightings. Rather than proposing a universal interpolator, this work delivers a reproducible decision-support workflow for temporal resampling of multi-variable met-ocean datasets, supporting early-stage marine renewable energy assessments.

Safety Maneuvering Envelope for Towed Line Arrays Under Steady-State Conditions - Zhibo Wang; Qikun Li (Oceans, 2026)
To ensure safe and stable operation of towed array systems in complex marine environments, the concept of a Safe Maneuvering Envelope (SME) for towing maneuvers is proposed based on flexible cable dynamics theory. The dynamic equations of the towed array are established using the Lumped Mass Method. Using diving depth and breaking tension as boundaries, array configuration data sets are calculated for combinations of main cable outer diameter, vessel speed, and deployed cable length. Mapping relationships between vessel speed, cable deployment length, diving depth, and breaking strength are presented to construct the maneuvering safety envelope. This envelope defines the operational range where the array meets design maneuverability criteria. The safety envelope concept provides quantitative operational guidelines for towed array systems and offers crucial theoretical foundations and methodological support for safe system design and risk assessment.

Physical Coastal Vulnerability Assessment of the Monrovia Coastline (Liberia) Using a Multi-Parameter Coastal Vulnerability Index - Titus Karderic Williams; Youssef Fannassi; Zhour Ennouali; Abdelahq Aangri; Tarik Belrhaba; Isaac Tukpah; Aıcha Benmohammadi; Ali Masria (Oceans, 2026)
This study presents a city-scale physical coastal vulnerability assessment of the 21 km Monrovia coastline (Liberia) using a multi-parameter coastal vulnerability index (CVI). Nine physical parameters—geology/geomorphology, shoreline change rate, elevation, slope, bathymetry, wave height, tidal range, relative sea level rise, and coastal landform characteristics—were integrated within an equal-weight ranking framework. The results identify spatially concentrated high vulnerability segments associated with low elevation, sandy geomorphology, and persistent shoreline retreat. The CVI represents a relative exposure screening rather than a predictive risk model. Limitations related to parameter weighting, classification dependency, and temporal heterogeneity are acknowledged. The findings support preliminary spatial prioritization for coastal adaptation planning

Marine Litter Monitoring on Apulian Beaches in the Decade 2014–2023: Some Evidence of a Decreasing Trend - Nicola Ungaro; Federica Lefons; Annamaria Pastorelli; Enrico Barbone (Oceans, 2026)
In recent decades, the issue of marine litter has emerged as a major environmental concern, particularly with regard to plastic litter. The European Marine Strategy Framework Directive (MSFD, 2008/56/EC) requires member states to monitor marine litter along the coast, in the water, and on the seabed. Since 2014, beach litter monitoring has been carried out in Italy’s coastal regions, an activity entrusted to the Regional Environmental Agencies System (ARPA). ARPA Puglia is responsible for monitoring the Apulian coastline, and this paper summarizes the main results obtained from 2014 to 2023. The monitoring, which was repeated twice a year, consists of a visual census of litter items along a 100-meter stretch of beach in six different locations across the Puglia region. During this period, an average of 506 litter items per 100 m were observed on the six target beaches in Puglia, 90% of which were plastic ones. Among these, single-use plastic items (SUPs) accounted for 37%. A trend analysis reveals a decline in the aggregate quantity of marine litter on Apulian beaches over the past decade, a phenomenon that is particularly evident when considering the SUP subcategory in isolation. This decreasing trend is consistent with the overall pattern observed along the Italian coastline and the coastlines of European seas. Consequently, it can be hypothesized that an increase in awareness of the issue, in conjunction with the implementation of European Directive 2019/904 for the reduction in single-use plastics, has resulted in more responsible practices. However, further efforts are needed to achieve the goal of 20 litter items per 100 m of beach to attain the Good Environmental Status under the Marine Strategy Framework Directive. The findings emphasize the importance of constant monitoring of litter items along the shoreline, as well as the integration of new and alternative methodologies (e.g., drone surveys) to evaluate the efficacy of European regulatory implementation.

Spatial–Temporal Distribution and Ecological Risks of Quinolone Antibiotics in Coastal Wetlands - Haotian Chen; Hashmi Kaiser; Jun Wang; Xuexia Zhu (Oceans, 2026)
Quinolone antibiotic (QA) residues in various natural environments have recently received massive scientific attention. Nevertheless, there is limited information on the distribution characteristics and potential hazards of antibiotics in coastal wetlands. Here, the occurrence, spatial and seasonal distribution, and ecological risk assessment of eight QAs including pipemidic acid (PPA), ofloxacin (OFL), enrofloxacin (ENR), ciprofloxacin (CIP), sarafloxacin (SAL), lomefloxacin (LOM), flumequine (FLU), and oxolinic acid (OA) in coastal wetland were investigated through collected water, sediment, benthos, and plant samples along the Jiangsu coastline in four seasons. The results demonstrated that all selected QAs were detected with varying frequencies and degrees, and their mean concentrations in water, sediment, plants, and benthos ranged from n.d. to 6.11 ng L−1, 3.10 μg kg−1, 6.14 μg kg−1, and 17.13 μg kg−1, respectively. The seasonal differences in antibiotic concentration indicated higher values in winter and significantly lower values in summer, while no significant variations were observed between spring and autumn. Based on the risk quotient (RQ) method, the ecological risk assessment revealed medium risks for OFL, ENR, CIP, and LOM, and low or no risks of other QAs. It is suggested that the differences in PNEC values between seasons and toxicity of antibiotic mixtures should be considered in future studies for better illustration of actual risk levels. This research provides fundamental data and an assessment pattern that governments and other scientific groups all over the world could use as reference to evaluate QA residues in coastal wetlands.

A Spatio-Temporal Study of the Presence of Vessels Within a Natura 2000 Marine Protected Area of the Maltese Islands - Sarah Anne Abela; Alan Deidun; Adam Gauci; Ritienne Gauci (Oceans, 2026)
Marine Protected Areas (MPAs) are essential for preserving marine biodiversity; yet they face challenges from various human pressures, including vessel activities. This study examines the extent, spatial distribution, and temporal variability of vessel activity within the Southwest Marine Protected Area (MT101), a Natura 2000 site off the Maltese Islands, with the aim of identifying where and to what degree different vessel categories overlap with protected marine habitats. Using Automatic Identification System (AIS) data spanning 2017–2022, a cumulative, normalised vessel density approach was applied to five vessel types: passenger, fishing, cargo, tanker, and tug and towing vessel, and spatially integrated with the distribution of four Annex I habitat types, including sandbanks, Posidonia oceanica meadows, reefs, and sea caves. The analysis reveals distinct spatial and temporal hotspots of vessel presence, with passenger and fishing vessels showing consistently high overlap with ecologically sensitive habitats, particularly within bay areas and along sections of the MPA boundary, while cargo, tanker, and tug activities are more concentrated offshore. While direct ecological impacts were not quantified and vessel density serves as a proxy for potential pressure, the results highlight areas where vessel-related pressures are likely to be most pronounced and where management intervention is most urgently required. By linking long-term vessel activity patterns with habitat distribution, this study delivers a spatially explicit and transferable framework for assessing cumulative maritime pressures, providing an evidence base to support targeted, habitat-specific management measures, improved enforcement, and marine spatial planning within MPAs.

A Comparative Study on Ocean Front Detection in the Northwestern Pacific Using U-Net and Mask R-CNN - Caixia Shao; Dianjun Zhang; Xuefeng Zhang (Oceans, 2026)
Ocean fronts play a vital role in modulating climate variability, driving material transport, and maintaining the stability of marine ecosystems. Therefore, accurate identification of ocean fronts is of great significance for marine environmental monitoring and resource management. This study focuses on the Northwestern Pacific region and conducts a systematic comparison between two representative deep learning models—U-Net and Mask R-CNN—for automated ocean front detection. The objective is to evaluate the adaptability and strengths of different network architectures in handling multi-scale features, complex background conditions, and boundary delineation, thereby providing a theoretical basis for model selection and application-specific deployment. Experimental results show that U-Net achieves superior spatial consistency in large-scale frontal segmentation, with an IoU of 0.81 and a Dice coefficient of 0.76, while maintaining relatively high computational efficiency. In contrast, Mask R-CNN demonstrates stronger boundary modeling capabilities in detecting small-scale fronts and handling heterogeneous backgrounds, achieving an IoU of 0.78 and a Dice score of 0.73, though at the cost of increased computational demand. Overall, U-Net is more suitable for broad-scale automatic detection of ocean fronts, whereas Mask R-CNN exhibits greater potential in complex scene recognition. Integrating the structural advantages of both models holds promise for further enhancing the stability and accuracy of frontal detection, thereby offering robust technical support for ocean remote sensing analysis and environmental forecasting.

Spatial Priorities for Protecting the Black Sea Harbour Porpoise: Abundance and Habitat Suitability in Bulgarian Waters - Venceslav Delov; Krastio Dimitrov; Konstantin Mihaylov; Georgi Terziyski; Yana Stoyanova; Petar Dimov; Nikolay Nedyalkov; Gergana Nikolova; Boris Karakushev; Nikolay Natchev (Oceans, 2026)
The Black Sea harbour porpoise (Phocoena phocoena relicta Abel, 1905) is an endemic cetacean with poorly understood spatial ecology in Bulgarian waters. This study aimed to update knowledge on its distribution, abundance, and habitat use throughout the Bulgarian Exclusive Economic Zone (EEZ). We conducted systematic aerial line-transect surveys in all four seasons between October 2022 and October 2023, combined with distance sampling and MaxEnt habitat modelling. Porpoises were present year-round across the EEZ, with marked seasonal shifts in distribution and habitat preferences. Highest densities were observed in spring, while winter distributions were concentrated offshore. Habitat suitability was dynamic, with key high-use areas identified near Cape Emine and in southern offshore waters near the Turkish border. Overall, about 40% of the EEZ represented high-suitability habitat. These findings provide the first comprehensive, year-round baseline for P. p. relicta in Bulgarian waters, highlighting the species’ flexible habitat use and seasonality. The study was conducted under extraordinary conditions due to regional military activity, which may have influenced porpoise behaviour and spatial patterns. The provided results are critical for designing effective conservation and management measures in the face of both natural and anthropogenic pressures and threats.

The Alien Jellyfish Cassiopea andromeda in the Mediterranean Sea: Invasion Dynamics and Management Strategies - Patrizia Perzia; Serena Zampardi; Teresa Maggio; Manuela Falautano; Luca Castriota (Oceans, 2026)
Cassiopea andromeda is an invasive alien jellyfish that is increasingly reported across the Mediterranean Sea, yet its invasion dynamics and ecological implications remain poorly understood. This study provides an updated assessment of its spatial and temporal distribution, evaluates its potential impacts on ecosystem services and biodiversity, and explores management options through the 8Rs framework. An aggregated dataset of georeferenced records (1886–2025) was compiled from scientific literature and citizen-science platforms. Spatio–temporal analyses—including kernel density, key spatial distribution characteristics, spatial autocorrelation, and local hotspot detection—were applied to identify invasion phases, aggregation patterns, and directional dispersion. Results reveal two distinct invasion stages: a century-long arrival phase confined to the Levantine Basin, followed by an accelerated expansion since 2008, with a persistent hotspot in the eastern Mediterranean Sea and a westward dispersal trajectory. Evidence of ecological impacts within the Mediterranean Sea remains limited, however studies from other regions indicate both potential benefits and localized negative interactions with marine organisms. Application of the 8Rs model highlights implemented, feasible and challenging coordinated basin-wide strategies to support adaptive management of this alien resource.

Model Prediction of Macroplastic Distributions in European Marine Basins: Comparison with Beach and Floating Macroplastic Observations and Estimation of Model Accuracy - Elisa Garcia-Gorriz; Diego Macias-Moy; Daniel González-Fernández; Antonella Arcangeli; Nuno Ferreira-Cordeiro; Olaf Duteil; Svetla Miladinova; Ove Pärn; Luis Francisco Ruiz-Orejón; Eugenia Pasanisi; Roberto Crosti; Léa David (Oceans, 2026)
Accumulation of plastic litter in the marine environment is a pressing global concern. To study this issue, we use the Blue2 Modelling Framework (Blue2MF), an integrated modelling tool developed by the Joint Research Centre (JRC) of the European Commission. Our study uses the Lagrangian model LTRANS-Zlev (LTRANS) in the Blue2MF to simulate the trajectories, distribution, and accumulation of macroplastics in five European marine basins: the Baltic Sea, Black Sea, Mediterranean Sea, Atlantic Northwest European Shelf, and Atlantic Southwest European Shelf. By incorporating model-estimated macroplastic inputs from land and estimations of maritime (fishing) sources, we simulate distribution patterns of marine macroplastics between 2016 and 2018. Our study addresses the challenges involved in modelling the spatial distribution and abundances of macroplastics with the LTRANS model and the factors that may condition the estimation of the model accuracy when model results are compared/validated with marine litter observations available. We compare our model results with available observations, achieving a good agreement between predicted and observed macroplastic distributions and abundances and estimating the model accuracy for both beached and floating macroplastics. Our study provides a basis for future forecast runs to evaluate the impact of policy/management options on marine macroplastic pollution in European Seas.

Research on Wake Characteristics of Dynamic Yawing Offshore Wind Turbine by Proper Orthogonal Decomposition - Oussama Sabbar; Bowen Zhang; Jie Ge; Longyan Wang (Oceans, 2026)
The wake that forms behind a yawing wind turbine is a complex flow region that can affect the performance of downstream turbines in offshore wind farms. It contains various flow features, including velocity deficit, shear layers, and vortex structures, which evolve in both time and space. Understanding this behavior is important for the design and operation of large-scale offshore wind farms. In this work, large-eddy simulations combined with proper orthogonal decomposition are used to study the wake development behind the National Renewable Energy Laboratory five-megawatt offshore wind turbine under both aligned and yawed inflow conditions. The results indicate that yawing the rotor leads to a lateral shift in the wake and increased asymmetry, with a stronger shear layer forming on one side. This asymmetry promotes enhanced mixing between the wake and the surrounding flow, contributing to a faster downstream recovery of the velocity field. The proper orthogonal decomposition analysis shows that the most energetic modes are associated with large-scale wake deflection and meandering, while higher-order modes correspond to smaller and less stable flow structures within the shear layer. The temporal evolution of these modes illustrates how the wake responds to the yaw maneuver and gradually reaches a new quasi-steady state. Overall, the study provides insight into the influence of yaw on wind turbine wake dynamics and demonstrates the applicability of combining large-eddy simulation with proper orthogonal decomposition for wake analysis in offshore wind farm studies.

Long-Term Trend and Influencing Factors of Diurnal Sea Surface Temperature in the South China Sea - Xiang Li; Jiaqi Luo; Yunfei Zhang; Zhen Shi; Jian Wang (Oceans, 2026)
The characteristics and causes of the long-term trends of diurnal variation of sea surface temperature (DSST) in the South China Sea (SCS) are investigated in this study based on the global hourly sea surface temperature data generated by the mixed layer model (MLSST) from the National Marine Environmental Forecasting Center (NMEFC) of China. Validation of the MLSST dataset demonstrates excellent agreement with in-situ buoy observations in the SCS with a correlation coefficient of 0.951, confirming its reliability in the SCS. Based on this dataset, the long-term trend of DSST in the SCS exhibits significant seasonal variations with the strongest magnitude in spring and the weakest in winter. Specifically, a significant decreasing trend of −0.0014 °C yr−1 during 1982–2009 transitioned to a pronounced increasing trend of 0.0057 °C yr−1 from 2010–2019. Both climatic factors and local atmospheric variables jointly modulate the DSST in the SCS. On the long-term timescale, the Pacific Decadal Oscillation (PDO) served as the dominant factor driving DSST changes in most areas of the SCS. After 2010, the PDO shifted to a persistent positive phase, providing a crucial climatic background for the basin-wide DSST increase. While the El Niño–Southern Oscillation (ENSO) showed enhanced correlation with DSST post-2010, the Indian Ocean Dipole (IOD) had negligible influence overall. In addition, the SCS summer monsoon played an important regulatory role in shaping the long-term trend of summer DSST by altering air–sea heat exchange processes. Among local atmospheric variables, sea surface wind speed was significantly negatively correlated with DSST, and net heat flux was significantly positively correlated with DSST, with their effects showing regional differentiation. The regulatory role of wind speed dominated in the western SCS, whereas the net heat flux exerted a more prominent impact in parts of the eastern SCS. This work clarifies the spatiotemporal patterns and multi-driver framework governing DSST variability in the SCS, providing a basis for understanding regional ocean–atmosphere interactions.

Coherent Sea Level Variability Between the Sicily Channel and the Ionian Sea: Evidence of a Dynamical Coupling in the Mediterranean Sea - Ernesto Napolitano; Adriana Carillo; Roberto Iacono; Gianluca Eusebi Borzelli; Maria Vittoria Struglia (Oceans, 2026)
This study uses satellite altimeter data from the new AVISO dataset to investigate the coupling between sea level variability in the Sicily Channel and the Ionian Sea. The dataset spans the last three decades (1993–2024) and provides high spatial resolution coverage of the Mediterranean Sea (1/16°, or approximately 7 km). We analyze the variability of the sea surface height through Empirical Orthogonal Function and Singular Value Decomposition techniques applied to the Absolute Dynamic Topography. While the dominant modes of long-term variability reflect the known dynamics of the North Ionian Gyre, the singular value analysis allows us to identify a coherent spatial structure extending from the Sicily Channel to the Northern Ionian Sea. This provides the first observation-based, robust evidence of a dynamical coupling between the two basins, indicating that in the last thirty years the Northern Ionian Gyre is part of a broader, dynamically connected regional system integrating flows from the Sicily Channel. These findings are consistent with previous work, based on a hindcast simulation covering 1980–2010, in which we highlighted the key role of the Atlantic Ionian Stream in shaping interannual to decadal variability in the Northern Ionian Sea. Here, we extend the analysis to the present day, providing the most up-to-date, observation-based assessment of the regional dynamics.

Baited-Associated Aggregation of Spinner Sharks in Hulhumale, Maldives: Preliminary Observations and Photo-Identification Tools - Francesca Romana Reinero; Marco Pireddu; Giacomo Ridella; Lorenzo Valenti; Antonio Pacifico; Francesca Ellero; Primo Micarelli (Oceans, 2026)
The spinner shark is a widely distributed coastal species that faces significant anthropogenic pressures, yet information on its ecology in the western Indian Ocean remains poorly documented. This study provides preliminary baseline observations on temporal occurrence, sex ratio, and size distribution of a bait-attracted spinner shark aggregation in Hulhumale (North Malé Atoll, Maldives) and presents the first individual-level photo-identification (photo-ID) catalogue for the species based on underwater observations. Surveys were conducted in November 2024 and November 2025 using underwater photography, video recordings, and laser photogrammetry. In total, 69 individual spinner sharks were identified using the standard photo-ID protocol which proved to be valid. On the contrary, the preliminary application of the semi-automatic Identifin software indicated possible effectiveness for individual recognition; however, its performance cannot be reliably validated in this area because of poor image quality and environmental turbidity. Six individuals were re-sighted across years, demonstrating the feasibility of non-invasive repeated, long-term monitoring through photo-ID. Although interannual variation in sex ratio of sharks observed was detected (χ2 = 10.56, p = 0.0012), this pattern should be interpreted cautiously due to provisioning-related sampling bias and unequal sampling effort across years. Total length measurements (n = 28) indicated predominantly adult and subadult individuals, with no apparent interannual differences in size distributions. Overall, this study establishes a methodological baseline for spinner shark photo-ID in the Maldives and highlights the importance of multi-year and multi-season monitoring to robustly evaluate aggregation dynamics, site fidelity, and population-level patterns in this region.

Spring Phytoplankton Bloom Phenology in the Bering Sea and Surrounding Waters Based on MODIS Data - Kirill Kivva; Aleksandra Malysheva; Aleksandra Sumkina (Oceans, 2026)
The Bering Sea and its surrounding waters are commercially and ecologically important ecosystems. Knowledge of phytoplankton phenology is crucial for understanding ecosystem dynamics. However, estimates of phenological parameters of spring phytoplankton bloom are sparse for this region. We used the Moderate Resolution Imaging Spectroradiometer (MODIS) daily data from 2003–2024 to assess the climatology of phenological parameters. A combination of data regriding, spatial interpolation, and temporal smoothing was applied. Three methods of spatial interpolation for missing data acquisition are compared: iterative first-order neighbor, inverse distance weighted interpolation, and data interpolating empirical orthogonal functions (DINEOF). We suggest that the first outcompetes the other two methods when compared to initial data. Date of the bloom initiation, bloom peak, chlorophyll-a maximum, and duration of the bloom before its peak are evaluated. The spatial distribution of mentioned phenological parameters is presented and discussed. We show that bloom starts early in Bristol Bay, in the narrow band along the eastern shelf, along the Kamchatka Peninsula, and south of the Aleutians and Alaska Peninsula. In the deep Bering Sea, bloom starts surprisingly later considering the latitude of the region. The main reason for this may be the wind mixing during the spring. The first phase of the bloom is generally longer in the deep southern areas (up to 60 days) and shorter in the northern shelf areas (less than 2 weeks in some cases).

The Risks That Cirolanid Isopods Pose to Ocean Resources - Murray Thomson (Oceans, 2026)
Marine isopods are the ancestors of the harmless herbivorous woodlouse species often found in piles of leaves. In contrast to woodlice, marine isopods of the family Cirolanidae (cirolanid isopods) are scavengers and predatory carnivores that form swarms and can cause damage to fishing and aquaculture industries. Furthermore, these animals are known to bite swimming and diving humans and therefore may have negative effects on recreational activities in areas where swarms form. One cirolanid isopod species, Cirolana harfordi, displays social behaviour, an attribute that may facilitate the formation of swarms. This species gives live birth, a highly unusual mode of reproduction for an invertebrate and isopod. The rate of viviparous reproduction in C. harfordi is sped up by warmer conditions, indicating the threat that cirolanid isopods pose to ocean resources may intensify with global warming.

Reorganization of the Arabian Sea Oxygen Minimum Zone in Response to Monsoon Fluctuations During Dansgaard–Oeschger Events 12–11 - Patricia Silva Rodrigues; Wilfried Bauer; Marlon Carlos França (Oceans, 2026)
Understanding the impact of monsoonal oscillations during past climatic changes in the Arabian Sea is crucial for improving climate model predictions under ongoing global warming. This study investigates whether millennial-scale climate shifts in Greenland, specifically Dansgaard–Oeschger events 12–11, affected the Indian Ocean monsoon system and the associated productivity and oxygen minimum zone (OMZ) dynamics in the northwestern Arabian Sea. In the Arabian Sea, DO stadials correspond to reduced water-surface productivity, well-ventilated intermediate water masses, and a weakened or absent OMZ. Contrarily, DO interstadials are distinguished by enhanced water-surface productivity, a reorganization of intermediate water masses, and a reinvigoration of the OMZ. Eleven sediment samples from ODP Site 721A were analyzed using a multiproxy approach combining total organic carbon, C/N ratios, bulk-sediment isotopes (δ15N, δ13C), and the relative abundances of Globigerina bulloides and Globigerinoides ruber, complemented by isotopic data (δ13C, δ18O) from G. ruber shells. Further Mg/Ca–δ18O and δ18Osw measurements were included to refine the reconstruction of surface-water hydrography linked to productivity changes. Results reveal significant oscillations in water-surface productivity and OMZ intensity, modulated by shifts in monsoon strength and water-column ventilation. Enriched δ15N values, elevated TOC, and increased G. bulloides relative abundances reflect intensified denitrification and organic matter preservation under a stronger southwest monsoon, whereas depleted δ15N, reduced TOC, and higher G. ruber abundance indicate enhanced ventilation and a weaker OMZ under northeast monsoon dominance. These findings provide new evidence that refines the paleoceanographic history of the Arabian Sea. Additionally, they demonstrate that high-latitude climatic forcing during DO events modulated Arabian Sea monsoon dynamics and oxygenation through strong interhemispheric teleconnections.

A Burning Issue: Interactions of the Bearded Fireworm Hermodice carunculata with Artisanal Fisheries—A Case Study from Malta (Central Mediterranean) - Antonia Scicluna; Patrick J. Schembri (Oceans, 2026)
The bearded fireworm Hermodice carunculata (Polychaeta) has become increasingly problematic in Mediterranean artisanal fisheries, yet remains understudied. This study provides a detailed analysis of interactions between H. carunculata and artisanal fishers in Marsaxlokk, Malta’s largest fishing village. Combining fisher interviews (local ecological knowledge) and field data, the study reveals that fishing practices inadvertently sustain and amplify local fireworm populations by discarding worms and by-catch nearshore, thereby providing abundant food sources. The highest fisher activity correlated with significantly denser fireworm populations and smaller-sized individuals, indicating population growth driven by fisher practices. Fireworm predation significantly impacts fishers economically, causing an estimated direct loss of 52.5% of the expected profit across the five onboard sessions, due to damaged catch, along with additional indirect losses from reduced gear efficiency and increased labor. The worm’s painful sting adds further nuisance and discomfort for fishers who frequently handle infested gear. Despite awareness of fireworm behavior, fishers largely did not recognize their practices as exacerbating the issue, creating a feedback loop perpetuating the problem. Behavioral experiments suggested that modifying fishing practices and gear design might mitigate fireworm impacts. Addressing this socio-ecological challenge requires further targeted research, education, and policy support to break the cycle that benefits fireworm proliferation in the region to the detriment of fishers.

Assessment of the Growth of Juvenile Oysters Crassostrea tulipa (Lamarck, 1819) in the Coastal Waters of the Gulf of Guinea: Case of the Coastal Lagoon in Southern Benin - Yaovi Zounon; Zacharie Sohou; Manuel Vargas-Yáñez; Dogbè Clément Adjahouinou; Legrand Sylvère Debleo; Théophile Godome; Francina Moya Ruiz; M. Carmen García Martínez (Oceans, 2026)
The coastal zone of the Gulf of Guinea is characterised by the intensive harvesting of Crassostrea tulipa oysters, locally known as ‘Adakpin’ or ‘Atcha’, which serve as a vital source of income for local communities. This study aims to identify the optimal areas, depths, and seasonal periods that favour the growth of juvenile C. tulipa oysters in the coastal lagoon waters of southern Benin. Relatively uniform juvenile oysters were cultured at three depths (surface, mid-water, and bottom) in three production zones (Ahouandji, Dégouè, and Djondji) over the course of one year, covering the four climatic seasons of southern Benin. Juvenile oyster growth (in length, width, height, and weight) was monitored monthly. Simultaneously, key environmental variables (salinity, temperature, pH, water transparency, and dissolved oxygen) were measured in situ to evaluate their influence. A three-way ANOVA revealed that the month of the year had a significant main effect on oyster growth, defining two main growth periods: from October to December 2022 and from March to May 2023. Growth rates decreased during December 2022 to January 2023 and showed no growth from January to March 2023. Growth stopped again from May to September 2023, after the second growth period. Although the main effects of the farming level and production zone were not individually significant, significant two-way interactions were found for ‘Month × Depth’ and ‘Month × Production Zone’. This indicates that the effect of the month on growth depended on both the depth (farming level) and the location (production zone). Survival was highest at the mid-water column (97%) and at the surface (95%). Throughout the study period, survival rates remained consistently high, with the lowest monthly value at or above 80%.

Numerical Simulation of Hydrodynamics and Sediment Transport for Coastal Protection with Artificial Reefs - Zhuo Fang; Chen Shen; Xun Han; Cun Hu (Oceans, 2026)
Artificial reefs (ARs) are eco-friendly coastal protection infrastructures that mitigate wave-induced erosion while maintaining hydrodynamic connectivity and supporting ecological functions. This study evaluates the protective efficacy of a shellfish-algae reef system—a new type of AR—within the Houlong Bay coastal restoration project (Quanzhou, China) using an integrated numerical modeling approach. A coupled model system was established, incorporating MIKE 21 FM for hydrodynamics, MIKE 21 SW for waves, and MIKE ZERO ST for sediment transport, using unstructured triangular grids to resolve complex coastal topography. The model was validated against field data, including tidal currents and wave heights, showing good agreement. Pre-implementation simulations identified key coastal issues: insufficient wave attenuation in the southern fishery port segment, which results in localized erosion. Post-project simulations demonstrate that the novel integrated system—comprising shellfish-algae reefs, broad gentle beaches, and coastal vegetation—effectively reduced nearshore current speeds by approximately 0.15 m/s and attenuated significant wave heights by up to 70% during typhoon events. Short-term (1-year) sediment evolution showed mild deposition (0.1–0.8 m) at the toe of the artificial beach, which is consistent with design expectations. Long-term (10-year) simulations further confirmed coastal stability, with minimal long-term shoreline retreat (maximum 15 m) and low net alongshore sediment transport (annual average: 800 m3). This study provides a validated, data-driven reference for the design and implementation of AR-based restoration strategies in semi-enclosed bays, highlighting their dual role in erosion control and sustainable coastal management.

Monitoring the Ecological and Geochemical Impacts of Coastal Development and Management on the Oualidia Lagoon - Hafssa Bensemlali; Khalid El Khalidi; Abdenaim Minoubi; Nezha Mejjad; Mohammed Bouchkara; Hamid Nasrellah; Bendahhou Zourarah (Oceans, 2026)
Oualidia lagoon, known as the oyster capital, is one of the most important coastal ecosystems along Morocco’s Atlantic coast. Over the past few decades, this ecosystem has faced numerous ecological challenges caused by both human activities and natural conditions, affecting its environmental quality. The present study aims to assess the impact of management projects implemented in the lagoon over the last eleven years on its health, especially in the sediment-trap area. In this context, a field mission was conducted in 2022, during which 15 surface samples were collected and analyzed using ICP-OES methods to determine metal concentrations. However, environmental indicators suggest that the ecological quality of the lagoon remains low, with significant and moderate contamination showing different trends, mainly for arsenic As (1–41.16 mg/kg); cobalt Co (2.01–7.2 mg/kg); molybdenum Mo (0–112.2 mg/kg); cadmium Cd (0.93–1.73 mg/kg); iron Fe (2433.36–19,721.55 mg/kg); and aluminum Al (640.7–11,600.57 mg/kg). The hotspots for these elements are mainly found at stations 13 and 15, which cover the upstream area of the lagoon near of the sediment trap. Comparing the results with those of previous studies conducted in the lagoon, there has been a decrease in sediment contamination since the sediment trap was created in 2011. The analysis suggests that different sources of these metals are entering the lagoon. This study provides updated data on metal concentrations in Oualidia lagoon sediments, one of the most diverse and biodiverse ecosystems in the Moroccan Atlantic. These results provide a scientific basis for targeted environmental management of the Oualidia lagoon, supporting priority monitoring and control of pollution sources. They also highlight the importance of developing awareness programs for residents, fishermen, farmers, food businesses, hotels, and guesthouse owners, alongside the continuation of management projects in the lagoon.

Beyond Single Stressors: Integrated Physiological and Transcriptomic Responses of Argopecten irradians Exposed to Polystyrene and Toxic Dinoflagellates - Weijia Song; Jianguo Ding; Liling Guan; Jie Ma; Huixuan Liu; Hongli Zhang; Yangjun Chen; Kaiqin Jiang (Oceans, 2026)
Toxic dinoflagellate blooms and microplastics are widespread coastal pollutants. In this study, the scallop, Argopecten irradians, was selected as an experimental organism to systematically investigate the single and combined toxic effects of polystyrene (PS) and the toxic dinoflagellate, Alexandrium pacificum. The results showed that both PS and algal cells could be ingested by A. irradians. The survival rate of A. irradians remained above 90% in both the single and combined treatment groups, indicating that 1 mg/L PS and 1500 cells/mL A. pacificum cells did not pose a serious threat to scallop survival in the short term. However, CAT, SOD, and GSH-ST activities, as well as MDA content, were all elevated in the combined treatment group. Transcriptomic analysis further revealed that A. pacificum primarily affected immune-related pathways, whereas PS might interfere with endocrine function through the release of additives. Combined exposure to PS and A. pacificum induced more complex synergistic effects, reflected in the metabolic stress of exogenous substances, and the disruption of developmental and homeostasis regulatory pathways. This study provides important theoretical support for assessing the threats posed by composite coastal pollution to aquaculture and marine ecological security.

Reproductive Biology and Biochemical Composition of the Reared European Clam Ruditapes decussatus (Mollusca: Bivalvia) in Oualidia Lagoon, Morocco - Mouhcine Medlouh; Ibtissam Doukilo; Ahmed Errhif; Mohamed Id Halla; Oum Keltoum Belhsen (Oceans, 2026)
The reproductive cycle of the European clam Ruditapes decussatus reared in suspended double-net trays in the Oualidia Lagoon was investigated from October 2017 to February 2019. This study aimed to characterize gonadal development through histological analysis, gonadal index assessment, and the biochemical composition of key macromolecules (proteins, lipids, and carbohydrates) over an annual cycle. The results revealed that R. decussatus undergoes a prolonged spawning period from April to December, with a peak in October when 100% of the population reached the maturation stage (stage IIIA). A sexual rest phase was observed between November 2017 and December 2017. An overall sex ratio of 1:0.8 was observed, indicating a slight female bias, with no significant deviations. Statistical analyses highlighted a correlation between the gonadal index and seawater temperature, suggesting that temperature plays a crucial role in regulating reproductive activity. Biochemical analyses showed that proteins were the predominant macromolecule in clam tissues, followed by lipids and carbohydrates. Seasonal variations in biochemical composition were observed; however, no direct correlation was found between biochemical compound levels and the gonadal index (p > 0.05). These findings provide valuable insights into the reproductive biology of R. decussatus under suspended aquaculture conditions, contributing to improved management and optimization of farming practices.

Strandings of Tuna Remains Along Italian Coasts: Insights from Citizen Science into Potential Illegal Fishing - Alessandro Nota; Thomas Hesselberg; Francesco Tiralongo (Oceans, 2026)
The Atlantic bluefin tuna (Thunnus thynnus) is a high-value species subject to strict catch quotas and seasonal closures in the Mediterranean Sea. However, detecting illegal, unreported, and unregulated fishing remains challenging, particularly for small-scale activities. The aim of this study is to investigate whether citizen-reported strandings of tuna remains along Italian coasts can provide potential indirect indications of illegal fishing activities. To address this question, we collected and verified photographic records of stranded tuna remains (e.g., skulls, vertebral elements, complete specimens) reported on social networks. A similar search was conducted for two other conspicuous fishes, the ‘dusky grouper’ (Epinephelus marginatus) and the ‘greater amberjack’ (Seriola dumerili), as controls. Thirty-two strandings of tuna remains were recorded, with no records of amberjacks and only one of dusky grouper. Most strandings involved tuna heads or neurocrania, some of which showed clear mechanical cuts indicating post-capture processing. Several remains were older and degraded, suggesting long-term persistence in the sea. Overall, our results indicate that citizen-reported strandings could provide low-cost, spatially broad potential indications of discards resulting from illegal fishing activities. Wider adoption of standardised public reporting could not only engage the public in marine conservation, but also provide valuable data for policymakers tackling illegal fishing and complement traditional fisheries monitoring.

VSJE: A Variational-Based Spatial–Spectral Joint Enhancement Method for Underwater Image - Bing Long; Shuhan Chen; Jingchun Zhou; Dehuan Zhang; Deming Zhang (Oceans, 2026)
Underwater imaging suffers from significant degradation due to scattering by suspended particles, selective absorption by the medium, and depth-dependent noise, leading to issues such as contrast reduction, color distortion, and blurring. Existing enhancement methods typically address only one aspect of these problems, relying on unrealistic assumptions of uniform noise, and fail to jointly handle the spatially heterogeneous noise and spectral channel attenuation. To address these challenges, we propose the variational-based spatial–spectral joint enhancement method (VSJE). This method is based on the physical principles of underwater optical imaging and constructs a depth-aware noise heterogeneity model to accurately capture the differences in noise intensity between near and far regions. Additionally, we propose a channel-sensitive adaptive regularization mechanism based on multidimensional statistics to accommodate the spectral attenuation characteristics of the red, green, and blue channels. A unified variational energy function is then formulated to integrate noise suppression, data fidelity, and color consistency constraints within a collaborative optimization framework, where the depth-aware noise model and channel-sensitive regularization serve as the core adaptive components of the variational formulation. This design enables the joint restoration of multidimensional degradation in underwater images by leveraging the variational framework’s capability to balance multiple enhancement objectives in a mathematically rigorous manner. Experimental results using the UIEBD-VAL dataset demonstrate that VSJE achieves a URanker score of 2.4651 and a UICM score of 9.0740, representing a 30.9% improvement over the state-of-the-art method GDCP in the URanker metric—a key indicator for evaluating the overall visual quality of underwater images. VSJE exhibits superior performance in metrics related to color uniformity (UICM), perceptual quality (CNNIQA, PAQ2PIQ), and overall visual ranking (URanker).

Amphipod Fauna Enhances Understanding of Eastern Mediterranean Deep-Sea Biodiversity - Davide Iaciofano; Hadas Lubinevsky; Sabrina Lo Brutto (Oceans, 2026)
Knowledge of deep-sea amphipods remains much more limited compared to that of shallow-water or more accessible marine habitats, although there has been an increasing scientific interest in recent decades. Deep-sea amphipods are mainly scavengers and detritivores, playing a role in organic matter recycling; however, their species richness may be underestimated, especially in understudied realms like the deep Mediterranean Sea. Long-term monitoring data are limited, hindering understanding of trends or human impacts. The present work aims to address this gap. In a previous study (1993–1996), twenty-two species of amphipods were identified from samples collected at depths between 734 and 1558 m along the Israeli coast. After twenty years, 16 sites were sampled in 2013 at depths ranging from 198 to 1812 m. Amphipod assemblage and its bathymetric distribution were analyzed to enhance knowledge of the taxon’s occurrence.

Environmental Constraints and Resilience of Organisms in Abyssal Plain, Whale Fall, Cold Seep and Hydrothermal Vent Environments in the Deep Sea - Esha Nauman; Richard A. Lutz (Oceans, 2026)
The deep sea is often depicted as a barren environment. Using the abyssal plain as a baseline system characterized by high pressure, extreme nutrient limitation, and slow growth rates, this review contrasts these conditions with specialized habitats that serve as oases of life such as whale falls, cold seeps, and hydrothermal vents. These environments retain the high-pressure characteristic of deep-sea habitats, but other unique environmental factors select for organisms with distinct life-history strategies and growth rates. This review examines the environmental constraints, organism physiological adaptations, and life-history strategies that define each habitat. Through synthesizing these factors, we identify patterns that influence not only growth and succession, but broader ecosystem vulnerability and resilience, defined here as the capacity of these communities to recover from disturbance. By evaluating how biological traits contribute to resilience across the four habitats in response to specific environmental constraints, this comparative framework identifies trade-offs between growth specialization and habitat stability. Understanding these environmental factors is critical in evaluating the resilience of these habitats to growing anthropogenic disturbances and determining future directions of study. This review concludes that while hydrostatic pressure and temperature impose fundamental metabolic constraints, nutrient availability and habitat stability are the primary determinants of organismal growth rates and life-history strategies. In the context of each ecosystem, both these variables can play a large role in the ability and time to recover from disturbance and may be good indicators of resilience at both a community and an organismal level. Consequently, slow-growing, long-lived fauna may possess far lower intrinsic resilience to anthropogenic disturbance compared to rapidly growing organisms with shorter life histories. Varying resilience of these habitats may necessitate habitat-specific strategies for assessment and protection.

Public Perceptions of Marine and Coastal Restoration in Ireland - Geraldine Doolan; Grace M. Cott; Stephen Hynes (Oceans, 2026)
Under the requirements of the EU Nature Restoration Regulation, significant investment in the restoration of marine and coastal ecosystems will be necessary in EU Member States. A certain level of knowledge among the population will be required to ensure authorities have the required social license to pursue marine ecosystem restoration activities, and awareness raising campaigns will likely be a part of the body of actions taking place to support the delivery of the EU Nature Restoration Regulation. This survey assesses the baseline awareness, attitudes and support for marine and coastal restoration amongst the Irish adult population. Relatively low levels of awareness of both restoration initiatives and the regulation are documented, with approximately 15% of respondents aware of restoration activities and 19% aware of the regulation. While distance to the coast isn’t always strongly correlated with awareness and support, connection to the marine—represented by visiting the coast and being concerned about the marine environment—is strongly correlated with these metrics. The results indicate that information campaigns around marine and coastal restoration should attempt to highlight the benefits society receives from the marine and coastal environment and foster a sense of connection with it.

The Track-Long Scale Response Modes of Sea Surface Temperature Identified by the Western North Pacific Typhoons - Rui Liu; Liang Sun; Haihua Liu; Mengyuan Xu; Gaopeng Lu; Xiuting Wang; Youfang Yan (Oceans, 2026)
Although previous studies composited response of sea surface temperature (SST) to typhoon sea surface wind (SSW) forcing around typhoon center, how SST responded spatiotemporally along the typhoon track over the ocean remains unclear. Through Empirical Orthogonal Function (EOF) analysis, several isolated typhoons in the Western North Pacific (WNP) from 2021 to 2024 were investigated. Two SSW forcing modes and two SST response modes were identified. The first SSW mode spatially reflects the overall distribution of SSW along the track, centering at its maturation position. And the first SST mode exhibits a high spatial correlation (|R|>0.85) with this SSW mode. The second SSW mode displays a distinct track-long scale dipole pattern along the path of the typhoon, representing its intensity variation during the “development–maturation–decay” lifecycle. Similarly, the second SST response mode shows a significant but lower correlation with this second SSW mode. Both corresponding SST response modes typically lag behind their respective wind-forcing by approximately 2 to 4 days, indicating that these SST response modes are direct reactions to SSW forcing. These cases implies that two track-long scale SSW modes are generally present during the lifecycle of typhoons and that their corresponding SST responses are dominated accordingly.

Coastal Circulation and Eddies Generation in the Southwest Mexican Pacific - Federico Angel Velázquez-Muñoz; Raul Candelario Cruz-Gómez; Cesar Monzon (Oceans, 2026)
We use 29 years of altimeter-derived sea level anomalies and geostrophic velocities (1993–2021) from the Copernicus Marine Service to identify the Mexican Coastal Current (MCC) and to examine how it interacts with the coastline. Variance-ellipse and empirical orthogonal function analyses isolate a narrow alongshore jet with a mean width of about 95 km and average speeds near 0.3 m s−1 that reverses direction semiannually: poleward in June and July and equatorward in the rest of the year. When the MCC impinges on broad concavities in the coast, the boundary layer separates, forming recirculation cells that intensify and detach as coherent eddies. These near-shore eddies have similar radii (from ∼30 km) and relative vorticity of ±0.5×10−5s−1 at the beginning of their generation, and they propagate offshore once the current weakens. A simple numerical model reproduces the observed behavior and suggests that eddy formation is controlled by flow separation rather than generic instability. The semiannual change in direction of the MCC indicate a link with the larger-scale North Equatorial Countercurrent and Costa Rica Coastal Current systems of the eastern tropical Pacific.

Resilient Anomaly Detection in Ocean Drifters with Unsupervised Learning, Deep Learning Models, and Energy-Efficient Recovery - Claire Angelina Guo; Jiachi Zhao; Eugene Pinsky (Oceans, 2026)
Changes in climate and ocean pollution has prioritized monitoring of ocean surface behavior. Ocean drifters, which are floating sensors that record position and velocity, help track ocean dynamics. However, environmental events such as oil spills can cause abnormal behavior, making anomaly detection critical. Unsupervised learning, combined with deep learning and advanced data handling, is used to detect unusual behavior more accurately on the NOAA Global Drifter Program dataset, focusing on regions of the West Coast and the Mexican Gulf, for time periods spanning 2010 and 2024. Using Density-Based Spatial Clustering of Applications with Noise (DBSCAN), pseudo-labels of anomalies are generated to train both a one-dimensional Convolutional Neural Network (CNN) and a Long Short-Term Memory (LSTM) network. The results of the two models are then compared with bootstrapping with block shuffling, as well as 10 trials with bar chart summaries. The results show nuance, with models outperforming the other in different contexts. Between the four spatiotemporal domains, a difference in the increasing rate of anomalies is found, showing the relevance of the suggested pipeline. Beyond detection, data reliability and efficiency are addressed: a RAID-inspired recovery method reconstructs missing data, while delta encoding and gzip compression cut storage and transmission costs. This framework enhances anomaly detection, ensures reliable recovery, and reduces energy consumption, thereby providing a sustainable system for timely environmental monitoring.

Harnessing Marine Bacterial Lipopeptides for Sustainable Disease Management in Open Sea Cage Aquaculture - Sumit Kumar; Ajit Kumar; Akshatha Soratur; Ankit Sarkar; Balu Alagar Venmathi Maran (Oceans, 2026)
The open ocean cage aquaculture system is facing considerable challenges with disease outbreaks resulting from over-farming and the rise of resistance to antimicrobial treatment. However, the environmental consequences of antibiotic usage, including ecological contamination and the acceleration of antimicrobial resistance, underscore the urgent need for sustainable alternatives in aquaculture disease management. Lipopeptides, which are a compound that can be produced by marine bacteria such as Bacillus amyloliquefaciens or Bacillus subtilis, could represent a new solution. This review article comprehensively evaluates the feasibility of marine bacterial lipopeptides for sustainable disease management in open sea cage aquaculture. Lipopeptides, including surfactins, fengycins, iturins, and the clinically used daptomycin, have notable antiviral, antifungal, and antimicrobial properties, and can have positive effects on the immune system. Notably, lipopeptides have a remarkable antioxidant profile and excellent free radical scavenging ability, making them interesting candidates for improving disease resistance in fish relating to oxidative stress. The surfactins and iturins have amphiphilic structure and can destabilize pathogen cell membranes, inhibit biofilm formation and elicit host immune responses. This represents a paradigm shift in targeting multiple pathogens of aquaculture like Vibrio spp. and Aeromonas spp. Surfactins and iturins show broad-spectrum activity, while fengycins are selectively active against fungal threats. Daptomycin, which is primarily derived from Streptomyces, demonstrates the potential of the lipopeptide class to be developed therapeutically, which is something that tends to be overlooked. Unlike synthetic antibiotics, they are also biodegradable; therefore, there is much less environmental impact from lipopeptides. The complexity of the structure may have also some impact on the rate of development of resistance, if any. Their commercialization is possible; however, the main hurdles that need to be solved to improve aquaculture are the biologically scalable production, the economically viable purification, and the stability for practical application at sea. Integrating lipopeptides into disease management systems could also ensure the sustainability of open ocean cage aquaculture and reduce unnecessary antibiotic application.

Essential, Non-Essential, and Toxic Elements in the Muscle of Meagre (Argyrosomus regius) from the Tagus Estuary (Portugal) - André F. Jorge; Carla Rodrigues; Bernardo Quintella; Marco Gomes da Silva; Maria João Lança (Oceans, 2025)
Monitoring trace metals in commercially important fish species provides an early warning of anthropogenic contamination and potential risk to consumers. This study semi-quantified and quantified essential, non-essential, and toxic elements in the muscle of wild meagre (Argyrosomus regius) captured in the Tagus estuary (Portugal), which is used as a nursery and spawning aggregation area. Dry muscle was microwave-digested and analyzed using inductively coupled plasma–optical emission spectroscopy. Semi-quantified screening detected Al, B, Ca, Fe, K, Mg, Na, P, S, Si, Sr, and Ti, and eight elements were determined using multielement calibration (As, Cr, Cu, Hg, Mn, Ni, Se, and Zn); Cd, Pb (toxic elements), Co, and Mo were not detected in this study. Arsenic was detected in all individuals, with a minimum value of 0.348 mg/kg wet weight. A mercury level above the European Commission regulatory limit (0.5 mg/kg wet weight) was only detected in one individual, corresponding to 2% of the samples. Although other metals remain well below regulatory limits, continued biomonitoring is recommended to track temporal trends and safeguard seafood safety in transitional coastal systems, which is important for commercially relevant fish species.

Preliminary Analysis of the GDR-G Data Products of Jason-3 Satellite Altimeter - Xi-Yu Xu; Zhiyong Huang; Tingting Shi; Qiankun Liu; Mengyao Li (Oceans, 2025)
In early 2025, the Jason-3 satellite’s orbit shifted from an “interleaved” to a tandem configuration with Sentinel-6A, and its Geophysical Data Records (GDR) were upgraded from Version F to G. This study evaluated GDR-G via eight processing approaches, using Jason-3’s last six GDR-F cycles (#394–#399) and first six GDR-G cycles (#501–#506), integrating histogram/geographical distribution analyses of Sea Surface Height Anomaly (SSHA), Significant Wave Height (SWH), Wind Speed (WS), and multi-method validation (e.g., self-cross-calibration). Key findings include the following: GDR-G had significantly lower SSHA noise than GDR-F, with up to ~4 cm SSHA bias from different retrackers/corrections; Adaptive retracker + 3D Sea State Bias (SSB) correction achieved optimal accuracy. Adaptive retracker’s SWH/WS anomalies linked to invalid MLE4 results and non-Brownian waveforms (coastal/sea ice). A detrending method was proposed, and the 41-point Lanczos window was optimal for smoothing. The results from the “detrending method” were consistent with the results based on the SSHA spectrum and classic self-cross-calibration methods. A ~5 mm drop was observed in Jason-3 GDR-G MLE4 baseline SSHA, probably caused by GDR upgrade or geographic sampling mismatch, while Sentinel-6A’s GDR-G upgrade might induce ~1 cm jump. The jumps along with GDR version upgrade highlighted the value of timely in situ absolute calibration.

Using Tourist Diver Images to Estimate Coral Cover and Bleaching Prevalence in a Remote Indian Ocean Coral Reef System - Anderson B. Mayfield; Alexandra C. Dempsey (Oceans, 2025)
Citizen science approaches for monitoring, and even restoring, coral reefs have grown in popularity though tend to be restricted to those who have taken courses that expose them to the relevant methodologies. Now that cheap (~10 USD), waterproof pouches for smart phones are widely available, there is the potential for mass acquisition of coral reef images by non-scientists. Furthermore, with the emergence of better machine-learning-based image classification approaches, high-quality data can be extracted from low-resolution images (provided that key benthic organisms, namely corals, other invertebrates, & algae, can be distinguished). To determine whether informally captured images could yield comparable ecological data to point-intercept + photo-quadrat surveys conducted by highly proficient research divers, we trained an artificial intelligence (AI), CoralNet, with images taken before and during a bleaching event in 2015 in Chagos (Indian Ocean). The overall percent coral covers of the formal, “gold standard” method and the informal, “tourist diver” approach of 38.7 and 35.1%, respectively, were within ~10% of one another; coral bleaching percentages of 30.5 and 31.8%, respectively, were statistically comparable. Although the AI was prone to classifying bleached corals as healthy in ~one-third of cases, the fact that these data could be collected by someone with no knowledge of coral reef ecology might justify this approach in areas where divers or snorkelers have access to waterproof cameras and are keen to document coral reef condition.

Annotated Checklist and Biodiversity of Sea Cucumbers (Holothuroidea) in Indian Waters - Karthika Padmini; Ameen Ummath; Atikulla Shaikh; Balu Alagar Venmathi Maran (Oceans, 2025)
Holothuroids play a vital role in nutrient cycling and bioturbation to enhance the marine ecosystem. They enhance the biodiversity for various symbiotic marine organisms by providing essential shelter and spawning grounds. This review focuses on the Class Holothuroidea (Phylum Echinodermata) in Indian waters, encompassing a total of 187 species organized into 7 orders and 21 families. Notably, the order Holothuriida represents the largest proportion of species, accounting for 27%. These species are well-distributed across India, with the Andaman and Nicobar Islands exhibiting the highest level of species richness (107 species), followed by the East Coast (102 species), Lakshadweep (39 species), and the West Coast (34 species). Species diversity was assessed using the Shannon–Weiner diversity index. Results indicate that the Andaman and Nicobar Islands (H’ = 2.23) and the West Coast (H’ = 2.14) demonstrate the highest levels of diversity. This review provides a comprehensive and precise inventory of all species of Holothuroidea reported in Indian waters, which is provided to facilitate understanding of the reported species, their systematics, and distribution. In addition, a significant insight for both conservation and management of sea cucumbers in India has also been provided.

Trophic Ecology of the Devil Firefish Pterois miles in the Eastern Mediterranean: An Integrated Study Based on Stomach Content and Stable Isotope Analyses - Kassandra Zannaki; Ioannis E. Batjakas; Gerasimos Kondylatos; Maria Corsini-Foka; Chrysoula Gubili; Evangelia Krasakopoulou; Ernesto Azzurro; Emanuela Fanelli (Oceans, 2025)
Τhe trophic ecology of Pterois miles in the Mediterranean Sea was performed by integrating data from stomach contents (SCA) and stable isotopes analyses (SIA), based on samples caught off the Greek island of Rhodes, SE, Aegean Sea, for the first time. This combined approach provides information on ingested (SCA) and assimilated (SIA) food and thus allows for the depiction of predator–prey relationships. Specimens of devil firefish, including both juveniles and adults (total length of analyzed specimens spanned from 11.40 to 31.50 cm), were collected from different sites around Rhodes. Their diet consisted of bony fish, cephalopods, crustaceans, and gastropods. The δ13C and δ15N values ranged from −18.0 ‰ to −14.4 ‰ and from 7.2 ‰ to 9.2 ‰, respectively. SIA data allowed for the estimation of the trophic position of devil firefish from Rhodes Island, which showed a mean value of 3.1 ± 0.6 and confirms that the species primarily relies on a benthic baseline. Further, our isotopic values approach those obtained in North Carolina and Bermuda, confirming its role as a mesopredator in the Mediterranean benthic food webs. Although preliminary, such results can provide an important baseline for future investigations on the species and the potential impact on the Mediterranean food webs.

The Effect of ‘Roughness’ on Upwelling North of Cape Town in Austral Summer - Mark R. Jury (Oceans, 2025)
Cape Town, South Africa, experiences coastal upwelling during austral summer. In this study, the effects of kinematic and thermal ‘roughness’ on wind stress are analyzed using 5–25 km resolution multi-satellite and coupled reanalysis datasets in the period 2010–2024. Average conditions for austral summer (December–February) are calculated to identify east–west gradients in sensible heat flux, wave height, and equatorward winds and to assess their consequences for the drag coefficient, wind-driven Ekman transport, and entrainment over the shelf from 16.9 to 18.7° E, north of Cape Town (33.7° S). Statistical and numerical outcomes are compared for austral summer and during active coastal upwelling in January 2018 with chlorophyll concentrations > 3 mg/m3. A subtropical anticyclone generated shallow equatorward winds next to a wind shadow north of Cape Town. Sharp cross-shore gradients in momentum flux were amplified by shoreward reductions in sensible heat flux and wave height, which suppressed the drag coefficient 10-fold. The inclusion of kinematic and thermal roughness in wind stress calculations results in a higher average cyclonic curl (−2.4 × 10−6 N/m3), which translates into vertical entrainment > 3 m/day at 33.7° S, 18° E. The research links coastal upwelling leeward of a mountainous cape with cross-shore gradients in air–sea fluxes that support recirculation and phytoplankton blooms during austral summer.

Two New Species of Free-Living Marine Nematodes (Nematoda) from the Yellow Sea, China - Xiaoyi Sun; Yong Huang (Oceans, 2025)
Two new species of free-living marine nematodes were collected in the Yellow Sea, China, and they are described herein as Actinonema sinica sp. nov. and Comesoma zhangi sp. nov. Actinonema sinica sp. nov. is characterized by short cephalic setae; lateral differentiation consisting of a row of longitudinal sclerotized bars and beginning at the level of anterior third of the pharyngeal region; horn-shaped telamons; a curved rod-shaped gubernaculum; and an elongate conical tail with a smooth, pointed tip. Comesoma zhangi sp. nov. is characterized by long, thick cephalic setae, reaching up to 28 µm in length; a cup-shaped buccal cavity lacking a tooth and narrowing posteriorly with small projections; an amphidial fovea with two turns; slender, arcuate spicules 2.6 times the cloacal body diameter in length, lacking a proximal capitulum; a plate-like gubernaculum without apophysis; and the absence of precloacal supplements. Updated keys to the valid species of the genus Actinonema and the genus Comesoma are provided. A comparative morphological table of all currently accepted species of Comesoma is also provided.

Predicting Chlorophyll-a in the Mauritanian–Senegalese Coastal Upwelling from Tropical Sea Surface Temperature - Elena Calvo-Miguélez; Belén Rodríguez-Fonseca; Víctor Galván-Fraile; Iñigo Gómara (Oceans, 2025)
The Mauritanian–Senegalese Coastal Upwelling exhibits strong interannual variability, which has been found to be driven by El Niño-Southern Oscillation (ENSO). In addition, ENSO has been shown to be triggered by the Indian Ocean and Atlantic Sea Surface Temperature (SST) variability. Nevertheless, how all these basins impact on the upwelling predictability has not been analyzed so far. Using a satellite product of surface chlorophyll-a as a proxy of marine productivity, this work makes an assessment of the predictability of the Mauritanian–Senegalese Coastal Upwelling marine ecosystem. Different statistical approaches are used to evaluate the relative contribution of the tropical basins, including the Pacific, Indian, equatorial and Tropical North Atlantic SSTs. The results indicate that although most of the upwelling variability stands for ENSO, the Atlantic contributions play an important role in shaping the seasonal prediction skill. These results may have strong implications for fisheries and marine ecosystem management in the region.

Persistent Geographic Patterns of Coral Recruitment in Hawaiʻi - Gregory P. Asner; Rachel R. Carlson; Caleb Labo; Dominica E. Harrison; Roberta E. Martin (Oceans, 2025)
Coral life cycle dynamics are poorly understood in most reefs, especially at the large geographic scales commensurate with ocean transport, genetic flow, and other synoptic scale processes. We present a spatially explicit, large-scale, and multi-temporal study of coral settlement along a 30 km long reef system in the Southwest portion of Hawaiʻi Island. Here, we focused on interannual variability in coral recruitment from 2021 to 2024, a period without a major marine heatwave. We used stratified random site selection to place 320 coral settlement tiles at 32 sites (10 tiles per site) at 10 ± 3 m water depth annually to monitor recruitment of the three most common coral genera found in the region (Montipora, Pocillopora, Porites). Site-level interannual variability in coral recruitment was high yet the overall geographic distribution of recruits was consistent through time. This occurred despite a decrease in benthic temperature and recruitment rates during the study period. Persistent geographic patterns in coral recruitment strengthen our understanding of mechanisms and conditions that drive reef resilience. They also strongly suggest a need to protect areas of high recruitment while studying drivers of low recruitment in contrasting habitats. This approach will further increase support of coral production in an era of climate- and coastal pollution-driven declines in coral reefs.

Role of Salinity on Phosphorous Removal by Chaetoceros muelleri - Glacio S. Araújo; Clarice S. Santigado; Lucas C. B. Silva; João Cotas; Leonel Pereira (Oceans, 2025)
The present work aims to verify the growth (estimated with optical density) of the dry biomass after proper flocculation and weighing, and removal of phosphorus by the microalga Chaetoceros muelleri (Mediophyceae), at six different salinities. Cultivations were carried out with constant volume, for a period of eight days, consisting of six treatments with three repetitions each, at different salinities (30, 25, 20, 15, 10, and 5) (seawater = 34). We observed that the best results were obtained when the microalgae were grown at salinity 30, that is, we observed better performances for this microalga at higher salinities. At this same salinity, the microalgae presented the best results of phosphorus removal (46.08 ± 0.67%). Regarding biomass recovery by microalgae, after drying the flocculate, the best result was obtained at salinity 25, with a final value of 3.47 ± 0.04 g dry mass L−1. Therefore C. muelleri is a promising solution for increasing demand by the blue economy with the associated circular economy, promoting rehabilitation of ecological sites with economic output. Thus, this work aims to evaluate the effect of salinity on phosphorus removal using C. muelleri.

Dolphins ‘Orient-Against-Current’: Foraging in Dredged Channels - Eliza M. M. Mills; Sarah Piwetz; Dara N. Orbach (Oceans, 2025)
Bottlenose dolphins (Tursiops sp.) are opportunistic foragers with global distributions that utilize diverse feeding tactics based on environmental factors, habitat features, prey behavior, group dynamics, and genetics. We describe a unique foraging tactic regularly observed in the confluence of dredged shipping channels with high anthropogenic disturbance, and explore potential abiotic (temporal, tidal, habitat) drivers of the behavior. A shore-based digital theodolite was used from 2021 to 2022 to observe common bottlenose dolphins (T. truncatus) foraging within a current in a technique we term Orient-Against-Current (OAC). During OAC, dolphins position themselves facing into the flow of a current, swimming at a speed to maintain a stationary position within the current, and feed while prey move with the current towards them. Orient-Against-Current occurred in all seasons and throughout daylight hours, particularly during the winter and spring. Dolphins engaged in OAC during ebb tides and intermediate current speeds (1–2 knots), but not during slack tides. As OAC occurred closer to shoreline structures (i.e., seawalls, concrete blocks) than to mangroves and natural seagrass beds, it appears that hard human-engineered structures aid in prey capture during OAC. Knowledge of dolphin foraging techniques can aid in understanding behavioral plasticity shaped by anthropogenically altered environments in industrialized coastal areas.

Role of Lee Wave Turbulence in the Dispersion of Sediment Plumes - Alban Souche; Ebbe H. Hartz; Lars H. Rüpke; Daniel W. Schmid (Oceans, 2025)
Sediment plumes threatening benthic ecosystems are one of the environmental hazards associated with seafloor interventions such as bottom trawling, cabling, dredging, and marine mining operations. This study focuses on sediment plume release from hypothetical future deep-sea mining activities, emphasizing its interaction with turbulent ocean currents in regions characterized by complex seafloor topography. In such environments, turbulent lee waves may significantly enhance the scattering of released sediments, pointing to the clear need for appropriate impact assessment frameworks. Global-scale models are limited in their ability to resolve sufficiently high Reynolds numbers to accurately represent turbulence generated by seafloor topography. To overcome these limitations and effectively assess lee wave dynamics, models must incorporate the full physics of turbulence without simplifying the Navier–Stokes equations and must operate with significantly finer spatial discretization while maintaining a domain large enough to capture the full topographic signal. Considering a seamount in the Lofoten Basin of the Norwegian Sea as an example, we present a novel numerical analysis that explores the interplay between lee wave turbulence and sediment plume dispersion using a high-resolution Large Eddy Simulation (LES) framework. We show that the turbulence occurs within semi-horizontal channels that emerge beyond the topographic highs and extend into sheet-like tails close to the seafloor. In scenarios simulating sediment release from various sites on the seamount, our model predicts distinct behavior patterns for different particle sizes. Particles with larger settling velocities tend to deposit onto the seafloor within 50–200 m of release sites. Conversely, particles with lower settling velocities are more susceptible to turbulent transport, potentially traveling greater distances while experiencing faster dilution. Based on our scenarios, we estimate that the plume concentration may dilute below 1 ppm at about 2 km distance from the release site. Although our analysis shows that mixing with ambient seawater results in rapid dilution to low concentrations, it appears crucial to account for the effects of topographic lee wave turbulence in impact assessments related to man-made sediment plumes. Our high-resolution numerical simulations enable the identification of sediment particle size groups that are most likely affected by turbulence, providing valuable insights for developing targeted mitigation strategies.

Chaetognaths (Chaetognatha: Sagittoidea) at the Boundary of the Pacific Ocean and the Gulf of California: Their Relationship with the Summer Circulation Pattern - Mitzi Paulina de La Rosa-Bernal; Elizabeth Durán-Campos; María Adela Monreal-Gómez; Erik Coria-Monter; David Alberto Salas-de-León; Sergio Cházaro-Olvera (Oceans, 2025)
Chaetognaths play an essential role in zooplankton communities and significantly contribute to their overall biomass. Changes in the hydrographic properties of the water column, driven by hydrodynamic processes, affect their species richness and abundance. This study investigates the species richness and abundance of chaetognaths, as well as their relationship with circulation patterns at the boundary of the Pacific Ocean and the Gulf of California, Mexico. The analysis is based on high-resolution hydrographic data and zooplankton samples collected during the early summer of 2019. The results revealed a cyclonic circulation pattern that impacted the chaetognath community at depths greater than 200 m. This pattern resulted in higher chaetognath densities along the peninsular coast compared to the mainland coast. A total of 15 species from three different families were identified. Among these, Flaccisagitta enflata had the highest density, recorded at 16,143 ind 100 m−3, while Aidanosagitta neglecta exhibited a significantly lower density of only 48 ind 100 m−3. Multivariate statistical analyses indicated that hydrographic variables were key factors influencing the distribution of the chaetognath community during the sampling period. Given the significant research gap regarding this group in the region, our findings contribute to a deeper understanding of chaetognath communities and their relationship with circulation patterns in the Southern Gulf of California, recognized as an oasis of marine life.

The Large-Scale Geostrophic Circulation Around Cuba: Insights from Altimeter Data - Roberto Iacono; Massimiliano Palma; Ernesto Napolitano; Alain Muñoz Caravaca (Oceans, 2025)
Due to the scarcity of in situ observations, the current description of the circulation around Cuba is far from complete. For example, the structure and variability of the flow through the Windward Passage, which hosts a significant fraction of the transport from the Atlantic to the Caribbean Sea, are still unclear. In this study, we use a recent, high-resolution Copernicus product based on satellite altimeter observations to obtain new insights into the large-scale geostrophic circulation around the eastern and southern coasts of Cuba. Among other results, we uncover a robust seasonal variability of the circulation around the Windward Passage, related to the presence of a cyclone to the south of the passage. Through most of the year the cyclone, with a companion anticyclone to the west, hinders the Atlantic inflow, but in autumn a strong stream crosses the western side of the passage and deeply penetrates the northern Caribbean Sea. The last part of the work deals with the time variability of the sea level in the Caribbean. We find that an apparent change in trend advocated in the recent literature has been reabsorbed in the last decade, yielding a local average sea level trend over the last thirty years in line with that for the global ocean.

A Bayesian Model Based on the Bow-Tie Causal Framework (BT-BN) for Maritime Accident Risk Analysis: A Case Study of the Bohai Sea - Junmei Ou; Shuangxin Wang; Chuanhao Sun; Wenyu Zhao; Chenglong Jiang (Oceans, 2025)
Maritime accidents are low-probability, high-consequence events, making mechanism analysis crucial for risk mitigation. Existing studies often focus on single scenarios or factors and frequently mix pre-incident observational data with subjective unsafe behavior labels, limiting causal-chain construction for proactive risk prediction. To address these issues, this study proposes a Bow-Tie-based causal-chain Bayesian network, establishing a hierarchical inference chain of “observed parameters–unsafe causes–accident types” to capture causal interactions among multiple factor categories and enable inference from pre-incident data to potential unsafe causes and accident types. Applied to the Bohai Sea region, sensitivity analysis quantified the effects of risk factors under varying conditions on collision, sinking, and grounding probabilities. The results show that the method can infer accident types and unsafe causes using only pre-incident data, achieving over 70% accuracy and closely matching accident investigation findings. Moreover, it reveals layer-by-layer mechanisms of key contributing factors and provides targeted management interventions, supporting quantitative decision-making for maritime regulators and shipping companies, with significant practical applicability.

Tidal-Phase Discharge Strategy Significantly Enhances Sewage Dilution Trapped in Deep Tidal Passages - Qinsi Chen; Yingyu Tan; Song Hu; Xiaohua Wang; Heng Zhao; Pengxia Liu; Xing Liu (Oceans, 2025)
Tidal dynamics substantially govern nearshore circulation patterns. The discharge of sewage at different tidal stages may have a significant impact on the dilution of pollutants. However, discussions on tidal phase sewage discharge strategy are still rare. This study focuses on the narrow tidal passage in the Ningbo-Zhoushan sea area, which receives a large amount of coastal wastewater, but the role of the unique hydrodynamic processes in the dilution of pollutants in this region remains unclear. By using a combination of on-site measurements and the FVCOM-dye simulation method, the scenario of high-concentration sewage retention in the tidal passage was demonstrated. The coastal residual circulation formed by strong tidal currents confined over 78% of the tracers within a 3 km range near the shore, and a subsurface dye accumulation zone emerged along the 25–50 m isobaths. Monsoon transitions regulated pollution plumes, inducing 5–8% seasonal variability in pollution footprints controlled by wind-tide-stratification interplay. The tidal phase discharge strategy was revealed to be highly effective in this study; both submerged discharge in deep-water zones and intermittent discharge strategies implemented in shallow-water zones significantly reduce the spatial coverage of high-concentration sewage plumes. Our findings highlight the importance of formulating discharge strategies based on tidal phases in typical narrow and deep tidal passages.

Low Genetic Diversity and Decreased Effective Population Sizes of Acropora hyacinthus Populations Inhabiting Inshore and Offshore Reefs in the South China Sea - Yijin Di; Lingyu Zheng; Jingzhao Ke; Yinyin Zhou; Shaoyang Mo; Xiangbo Liu; Jiquan Lin; Yuxiao Ren; Duanjie Huang; Rouwen Chen; Xiubao Li (Oceans, 2025)
Coral reefs, with their high biodiversity and ecological service functions, face significant threats due to climate change, overfishing, and pollution. The South China Sea (SCS) hosts rich coral biodiversity, particularly Acropora hyacinthus, a critical species for reef restoration. However, the region’s coral reefs are increasingly degraded, highlighting the urgent need for conservation efforts. In the present study, the genetic diversity and population structure of A. hyacinthus were examined based on two types of data: double-digest restriction-site-associated DNA (ddRAD) sequencing data and mitochondrial putative control region DNA (mtCR) sequences. Coral tissue samples were collected from 74 colonies inhabiting two inshore reefs (Sanya) and three offshore reefs (Xisha islands), and 748 single nucleotide polymorphisms (SNPs) and 74 mtCR sequences were obtained and utilized for downstream analysis. The results were consistent in analyses and did not cluster into two geographical groups for the inshore and offshore sites. Phylogenetic analysis showed that individuals of A. hyacinthus inhabiting the five detected sites were likely cryptic species HyaD. Furthermore, AMOVA and pairwise FST estimations based on both data types revealed no differentiation among five populations and between inshore and offshore reefs, which could be due to the reproductive mode of broadcast spawning for this species. However, a prevalent low level of genetic diversity was observed when compared with nearby Taiwan regions and Japan, and the geographic history results showed that the effective population size (Ne) had been decreasing for the past 300 years. Thus, we speculated that the populations of A. hyacinthus inhabiting the SCS lack the potential to cope with future climate change adequately, and multiple conservation measures should be implemented based on considering genetic diversity.

Systematic Analysis of Threats to Sea Turtles in Mexico: Trends, Knowledge Gaps, and Implications for Conservation - Ruth I. Ramírez-Villanueva; Fernando Gumeta-Gómez; Gustavo Hinojosa-Arango (Oceans, 2025)
Current scientific knowledge about the threats jeopardizing the recovery of sea turtle populations in Mexico is essential for improving conservation strategies. This study presents the results of a systematic review of the scientific literature published between 1960 and 2024, with the aim of identifying the main threats contributing to the decline of sea turtle populations in Mexico, detecting trends in scientific production, identifying knowledge gaps, and offering a comprehensive view of the challenges and priority actions needed to improve conservation strategies by region in Mexico. The review revealed a significant increase in research since 1997, with a predominant focus on pollution, fishing, and disease, mainly in the Pacific region. While Chelonia mydas and Lepidochelys olivacea were the most studied species, Dermochelys coriacea and Lepidochelys kempii received less attention. A total of 22 stressors associated with 8 threats were identified, but knowledge gaps persist regarding emerging threats such as climate change, coastal and marine development, and marine noise pollution. The results underscore the need to expand research on less-studied species and regions, strengthen studies in marine ecosystems, and improve the alignment between research and conservation policies to ensure the long-term viability of sea turtles in Mexico.

Combining Adequate BRUV Deployment Times with Individual Photo-Identification Improves Monitoring of Shark Populations in the Caribbean - Johanna Kohler; Mauvis Gore; Rupert Ormond; Katherine Mason; Anne Veeder; Timothy Austin (Oceans, 2025)
Sharks play a key role in coral reef ecosystems, but Caribbean populations are concerningly low. When monitoring endangered species, it is critical to use minimally invasive tools and protocols that are adequate for local species and the environment. This study investigated the adequate deployment time of baited remote underwater videos (BRUVs) for shark studies in the Cayman Islands and whether the use of photo-identification to recognise individuals (MaxIND) on BRUVs could improve abundance estimates (in comparison to MaxN) and the analysis of shark behaviour. From 2015 to 2018, a total of 557 BRUVs were deployed with recording times ranging from 3.8 to 211.03 min. The results showed that (1) of the total number of individual sharks recorded on videos, 95% of individuals were recorded within the first 110 min (slight variations between species), (2) MaxIND values were 1.1–1.5 times greater than that of MaxN (ratios varying with species) and (3) time of first arrival (Tarrive) was similar for all recorded species but time spent in front of the camera’s field of view (Tvisit) and activity levels (count of entries in camera’s field of view) varied between species. The results provide key information to improve the localised monitoring of rare/endangered species and can inform conservation management.

Decadal Trends in Buoyancy, Internal Modes and Horizontal Dynamics in the Northern Ionian Sea - Gian Luca Eusebi Borzelli; Ernesto Napolitano; Roberto Iacono; Maria Vittoria Struglia (Oceans, 2025)
The Ionian Sea plays a crucial role as a crossroads for various Mediterranean water masses, making it a significant factor in the seawater budgets, biogeochemistry, and biodiversity of the subbasins of the Mediterranean Sea. In recent years, numerous theories have been proposed in an effort to better understand the complex hydrography and dynamics of the Ionian. These theories primarily focus on the variability of the basin’s near-surface circulation, which is characterized by a recurring reversal that occurs over a period of 10–13 years. This variability is often attributed to internal processes and/or boundary forcing, as waters of Atlantic origin enter the basin from its western boundary. In this study, we utilize temperature–salinity profiles and absolute dynamic topography data provided by the Copernicus database to examine long-term changes in the vertical structure of the basin and their relationships with changes in the horizontal near-surface circulation. Our findings show that the vertical dependency of the density field of the basin undergoes significant fluctuations over interannual and decadal time scales, which induce important buoyancy changes throughout the water column and determine changes in the structure of the first baroclinic mode. However, no changes in the basin-averaged hydrographic structure can be related to the near-surface current reversals. These reversals are mainly associated with deformations of the main isopycnal surface, intended as the region of maximum buoyancy over the water column, suggesting that they do not impact the hydrographic properties of the various Ionian water masses. Instead, they alter their routes and relative volumes within different parts of the basin.

Effects of Elevated Temperatures and Nutrient Enrichment on Microbial Communities Associated with Turf Algae Under Laboratory Culture - Jatdilok Titioatchasai; Anuchit Darakrai; Sinjai Phetcharat; Jaruwan Mayakun (Oceans, 2025)
Increased seawater temperatures and nutrient loading are stressors that affect coral reefs and their microbiomes. In this study, filamentous algae were collected and exposed to different temperatures and nutrient concentrations through a laboratory experiment. Microbial DNA was extracted and analyzed using amplicon sequencing of the V3-V4 hypervariable region of the 16S rRNA gene. In total, 1 domain, 51 phyla, 131 classes, 335 orders, 549 families, and 1905 species were identified. Proteobacteria and Bacteroidota were the dominant taxa reported. Elevated seawater temperatures and nutrient enrichment impacted microbial communities associated with turf algae under laboratory culture. Bacterial species diversity and abundance differed under different temperature and nutrient conditions. Proteobacteria and Actinobacteria were abundant in lower-temperature conditions, while Desulfobacterota, Spirochaetota, and Firmicutes were abundant in higher-temperature conditions. Ruegeria was abundant in low-temperature conditions, whereas Vibrio abundance was low. Regarding nutrient conditions, Proteobacteria and Cyanobacteria were abundant under high-nutrient conditions, while Firmicutes and Desulfobacterota were abundant under ambient-nutrient conditions. The higher nutrient concentration increased the abundance of pathogenic bacteria, such as Vibrio and Photobacterium, while Pseudoalteromonas, which is beneficial for reefs, was present under ambient nutrient conditions. This study demonstrates that temperature and nutrient enrichment can shape microbial communities under laboratory conditions, providing an experimental setting for further studies of bacterial functions and metabolic processes in natural conditions under thermal and nutrient stresses.

Interactions Between Tourism Vessels and Humpback Whales in the Gulf of Tribugá, Colombia - Laura Valentina Girón-Castaño; Ann Carole Vallejo; Isabel C. Avila; Alan Giraldo (Oceans, 2025)
Whale-watching is a growing ecotourism activity in Colombia that offers economic benefits but may pose behavioral risks to humpback whales (Megaptera novaeangliae) if not properly managed. Although preventive recommendations exist to promote sustainable practices, their effectiveness remains largely unquantified in the Colombian North Pacific. This study evaluates adherence to whale-watching regulations and describes humpback whale behavioral responses to vessel presence in the Gulf of Tribugá, a key breeding and calving area. Data were collected from tourism vessels during July and September 2023, documenting 236 whales across 99 groups—71% of which included calves. The predominant whale response to vessels was neutral (74%), while evasive behaviors occurred in 22% of encounters, particularly among mother–calf pairs. Surface-active behavior was infrequent (22%) and most observed in calf–escort groups, serving as a supplementary indicator of behavioral state. Compliance with whale-watching recommendations varied: although most encounters involved a single vessel (57%) and averaged 16 min in duration, only 14% of vessels maintained the recommended minimum distance of 100 m. These findings highlight persistent gaps in regulatory adherence and underscore the need for strengthened enforcement and adaptive management to ensure sustainable whale-watching practices in Colombia’s North Pacific.

Winter Bloom Dynamics and Molecular Analysis of Benthic Sediments for the Toxic Dinoflagellate, Dinophysis acuminata, at Torquay Canal, Rehoboth Bay, Delaware, USA - Amanda Kathryn Pappas; Tahera Attarwala; Gulnihal Ozbay (Oceans, 2025)
The increased presence of harmful algal blooms (HABs) is a concern for many aquatic environments, especially with the increasing effects of climate change. Members of the dinoflagellate genus Dinophysis have been shown to produce toxins that can cause Diarrheic Shellfish Poisoning (DSP) in humans who consume infected shellfish. The advancing oyster aquaculture industry in Delaware will require the development of management practices and monitoring HAB species to protect environmental and human health. Temperature, nutrients, and prey abundance can be drivers of Dinophysis blooms. D. acuminata has been historically identified at high concentrations (>200,000 cells L−1) in water samples from Rehoboth Bay, DE, USA. However, the reach of spring blooms and how far they extend to aquaculture sites have not been determined. This study monitored an emergent HABs threat of a toxin-producing dinoflagellate, Dinophysis acuminata, by assessing a transect during the first recorded winter bloom in Torquay Canal and analyzing concentrations of chemical nutrients of combined nitrate and nitrite, and orthophosphate. Pearson correlation coefficient analysis between cell density (cells L−1) and environmental variables across all sites was conducted to determine significant relationships between water temperature, Chl-a concentration, conductivity, dissolved oxygen (DO), combined nitrate and nitrite concentrations (NOx), and orthophosphate concentrations (PO43−). Genetic techniques and PCR were utilized to determine the presence of Dinophysis using genus-specific primers to monitor cell density or abundance within the sediments during winter months. There were no significant correlations between environmental variables, and nutrient concentrations did not exceed EPA regulations. Molecular analyses of benthic sediments detected Dinophysis spp., offering insight into potential bloom origins. Overall, there is limited ecological data on Dinophysis acuminata in Rehoboth Bay, DE, USA. The results of this study will help strengthen resources for monitoring HAB species and understanding potential risks to oyster aquaculture in Delaware.

Influence of Inorganic Nutrients on a North Atlantic Microbial Community’s Response to Ocean Alkalinity Enhancement - Inês de Castro; Susana C. Ribeiro; António Louvado; Newton Carlos Marcial Gomes; Mário Cachão; Paulo F. Silva Borges; Eduardo Brito de Azevedo; Joana Barcelos e Ramos (Oceans, 2025)
Ocean Alkalinity Enhancement (OAE) is a promising carbon dioxide removal strategy, but its ecological impacts on marine microbial communities under varying nutrient conditions remain poorly understood. We conducted laboratory incubations using a natural North Atlantic microbial assemblage to investigate the response to OAE under both natural and nutrient-enriched regimes. We tracked phytoplankton and bacterioplankton dynamics, biomass, and leucine aminopeptidase (LAP) and alkaline phosphatase (ALP) activity as indicators of organic matter remineralization. OAE consistently reduced phytoplankton abundance in both nutrient regimes, potentially due to CO2 limitation, resulting in lower production of phytoplankton-derived organic matter. This reduction was reflected in decreased LAP activity and shifts in the relative abundance of phytoplankton-associated bacterial taxa. These findings indicate that OAE can directly affect phytoplankton through carbonate chemistry alterations, with potential microbial responses largely mediated by changes in organic matter availability. While short-term microbial disruptions were modest, the ecological consequences of altered bloom dynamics should be carefully considered in future OAE deployment strategies.

Seasonal Macroplastic Distribution and Composition: Insights from Safety Nets for Coastal Management in Recreational Waters of Zhanjiang Bay, China - Chairunnisa Br Sembiring; Peng Zhang; Jintian Xu; Sheng Ke; Jibiao Zhang (Oceans, 2025)
Macroplastic pollution is a growing environmental concern, threatening the marine environment. Despite growing awareness of marine plastic pollution, few studies have assessed the effectiveness of in situ technologies such as safety nets for macroplastic interception. This study aims to evaluate the effectiveness of safety net (SN) systems in intercepting macroplastic debris in the different zones of recreational Yugang Park Beach (YPB), Zhanjiang Bay, China. Safety nets were installed at stations representing different hydrodynamic conditions, and macroplastic debris (2.5–80 cm) was collected and analyzed for size, color, and shape characteristics. Two survey comparisons revealed a higher debris density in the winter survey (1.8 ± 0.3 items m2) than in the summer survey (1.5 ± 0.3 items m2). Most debris fell within the 10–40 cm range, with transparent low-density polyethylene plastic bags being the dominant type, particularly in the winter survey (80.7%). Statistical analysis indicated that plastic size was likely related to net retention characteristics, while tidal influences accounted for a major portion of spatial variability in debris accumulation. These findings suggest that SN systems are effective tools for macroplastic interception and could inform evidence-based coastal management strategies to reduce plastic pollution in similar coastal environments.

Hemispherical Distribution of Antarctic Krill Indicates High Abundance in Amundsen Sea - Molly Thornborrow; Andrew S. Brierley; Roland Proud; Inigo Everson; Joshua M. Lawrence; Matteo Bernasconi; Paul G. Fernandes (Oceans, 2025)
Antarctic krill (Euphausia superba) are an essential source of food for whale, seal, several fish, squid and seabird species in the Southern Ocean. Krill also play a major role in biogeochemical cycling and are the target of a growing commercial fishery. Krill can be detected and quantified with echosounders, particularly in swarms, and monitoring krill abundance and distribution is integral to assessing the status of regional populations and managing fisheries. We used echosounders to investigate the hemispherical distribution and behaviour of krill swarms during the Antarctic Circumnavigation Expedition (ACE), a multidisciplinary exercise that included measurements of atmospheric chemistry. Krill swarms were grouped using hierarchical clustering into four principal types: small swarms (on average 2 m high, 25 m long); large swarms (13 m high and 341 m long); deep swarms, which were also densely packed (average depth of 52 m); and shallower swarms, which had lower densities (average depth of 28 m). We found a weak negative relationship between the concentration of atmospheric methane close to the sea surface and the presence of krill. High densities of krill were found in the Amundsen Sea, an area purported to be of increasing importance for krill as the climate changes.

Experimental Study on the Growth Pattern and Flexural Strength Characteristics of Rafted Ice - Ying Xu; Wei Li; Kuankuan Wu; Sichong Ma Ma; Guojun Wang; Yuepeng Li Li; Dayong Zhang (Oceans, 2025)
As a critical factor in ice load calculation for marine structures in cold regions, the growth mechanism and mechanical properties of rafted ice urgently require clarification. This study systematically investigated the growth patterns and flexural strength characteristics of rafted ice through laboratory-prepared specimens. Experimental results indicate that the thickness of rafted ice exhibits a negative correlation with both ambient temperature and initial ice thickness during growth. Due to the higher porosity of its frozen layer, the density of rafted ice decreases by approximately 8% on average compared to single-layer ice. Three-point bending tests demonstrate that, under the combined effect of high tensile strength in the lower ice layer and energy absorption by the porosity of the frozen layer, the flexural strength of rafted ice ranges from 1.12 to 1.34 times that of single-layer ice.

Distribution Patterns and Diversity of Sedimental Microbial Communities in the Tianxiu Hydrothermal Field of Carlsberg Ridge - Fangru Li; Xiaolei Liu; Weiguo Hou; Hailiang Dong; Jinglong Hu; Hongyu Chen; Yi Ding; Yuehong Wu; Xuewei Xu (Oceans, 2025)
Hydrothermal vents, widely occurring along middle-ocean ridges and volcanic arcs, have been well-studied in vent-associated microbiology, mineralogy, and geochemistry. However, there are rarely investigations regarding the detailed microbial community in the hydrothermal vent-influenced sediment. To explore hydrothermal activities on microbial diversity at the Carlsberg Ridge in the northwestern Indian Ocean, four sediment cores were sampled from the near-vent fields to distant vent sedimentary fields in the Tianxiu hydrothermal field, and the microbial community compositions were analyzed. The sediment microorganisms closest to the hydrothermal vent were primarily composed of Acidimicrobiia, Gammaproteobacteria, Anaerolineae, and Planctomycetes. The microbial communities at the depth containing extensive signals of hydrothermal activity consisted mainly of Dehalococcoidia, Aerophoria, Anaerolineae, and Gammaproteobacteria. No significant differences in microbial composition were observed between the two weak hydrothermal sediment cores, primarily composed of Nitrososphaeria, Gammaproteobacteria, Alphaproteobacteria, and Acidimicrobiia. Moreover, heterogeneous selection substantially impacted the bacterial community assembly in near-vent sediments other than stochasticity. Multivariate statistical analysis identified that environmental fluctuations accounted for 55.59% of the community variation, with hydrothermal inputs (such as Fe, Pb, Cu, and Zn) being the primary factors shaping the construction of hydrothermal sediment microbial communities. These results enhance understanding of the response of deep-sea sediments to hydrothermal activity.

A Systematic Mapping of Emission Control Areas (ECAs) and Particularly Sensitive Sea Areas in Maritime Environmental Governance - Deniece Melissa Aiken; Ulla Pirita Tapaninen (Oceans, 2025)
Climate change has exacerbated the need for transitional shifts within high-impact sectors, notably maritime transport, which facilitates nearly 90% of global trade. In response, the International Maritime Organization (IMO) has implemented stricter environmental regulations under MARPOL Annex VI, which includes, among other things, the designation of Emission Control Areas (ECAs) and Particularly Sensitive Sea Areas (PSSAs). These regulatory instruments have prompted the uptake of new technologies, such as scrubbers, LNG propulsion, and low-sulfur fuels to mitigate emissions in these zones. However, emerging evidence has raised environmental concerns about these solutions which may offset their intended climate benefits. This study investigates the hypothesis that ECAs and PSSAs act as catalysts for maritime environmental advancements through a systematic mapping of 76 peer-reviewed articles. Drawing on data from Scopus and Web of Science, the study analyzes trends in technological advances, publication timelines, geographic research distribution, and the increasing role of decision-support tools for regulatory compliance. Findings show increased academic outputs particularly in China, North America, and Europe, and suggest that achieving effective emissions reduction requires globally harmonized policies, bridging research practice gaps, and targeted financial support to ensure sustainable outcomes throughout the sector. The study suggests that for ECAs and PSSAs to deliver truly sustainable outcomes, global regulation must be supported by empirical performance assessments, environmental safeguards for compliance technologies, and targeted support for developing maritime regions.

AMOC and North Atlantic Ocean Decadal Variability: A Review - Dan Seidov; Alexey Mishonov; James Reagan (Oceans, 2025)
The North Atlantic Ocean is vital to Earth’s climate system. Scientific investigations have identified the Atlantic Meridional Overturning Circulation (AMOC) as a significant factor influencing global climate change. This circulation involves ocean currents that carry relatively warm, salty water northward in the upper layers, while transporting colder, less salty water southward in the deeper layers. The AMOC relies on descending water at deep convection sites in the high-latitude North Atlantic (NA), where warmer water cools, becomes denser, and sinks. A concern regarding the AMOC is that the freshening of the sea surface at these convection sites can slow it by inhibiting deep convection. Researchers have used oceanographic observations and models of Earth’s climate and ocean circulation to investigate decadal shifts in the AMOC and NA. We examined these findings to provide insights into these models, observational analyses, and palaeoceanographic reconstructions, aiming to deepen our understanding of AMOC variability and offer potential predictions for future climate change in the North Atlantic. While the influence of high-latitude freshwater is crucial and may slow the AMOC, evidence also shows a complex feedback mechanism. In this mechanism, the negative feedback from wind stress can stabilize the AMOC, partially counteracting the positive feedback effects of freshwater at high latitudes. Although some models predict significant shifts in AMOC dynamics, suggesting imminent and possibly severe deceleration, recent observational research presents a more cautious view. These data analysis studies acknowledge changes, but highlight the robustness of the AMOC, particularly in its upper arm within the Gulf Stream system. While it cannot be entirely dismissed that the AMOC may reach its tipping point within this century, an analysis of data concerning the decadal variability in the AMOC’s upper arm indicates that a collapse is unlikely within this timeframe, although significant weakening remains quite possible. Furthermore, deceleration of the AMOC’s upper arm could lead to less stable and more vulnerable North Atlantic Ocean climate patterns over extended periods.

Analyzing the Seasonal Variability in South China Sea Surface Currents with Drifter Observations, Satellite-Derived Data, and Reanalysis Data - Zhiyuan Hu; Longqi Yang; Zhenyu Sun; Zhaozhang Chen; Jia Zhu; Jianyu Hu (Oceans, 2025)
This study examines the seasonal variability of surface currents in the South China Sea (SCS) and its adjacent regions, employing trajectory data from four seasonal deployments of Beidou drifters in the northern SCS. These observations are supplemented by reanalysis datasets, as well as satellite-derived sea surface wind and sea surface height data. The principal findings of this research are summarized as follows: (1) Drifter trajectories in the SCS exhibit pronounced seasonal characteristics. During autumn and winter, drifters predominantly move westward, ultimately merging with the SCS Western Boundary Current (SCSWBC). In spring, drifters are frequently entrained by mesoscale eddies. In summer, drifter trajectories generally move northeastward toward the Luzon Strait and the Taiwan Strait, with drifters subsequently returning to the SCS through these straits in autumn or winter before either joining the SCSWBC or settling in the coastal waters of Hainan. (2) The observed average drifter velocities show strong consistency with the CMEMS-reanalyzed current data during both the summer and winter seasons. (3) The surface current speeds along drifter trajectories in winter exhibit significant interannual variability, primarily driven by variations in wind speed. When the Niño 3.4 index exceeds ±0.5 °C (positive/negative phase), wind speeds and current speeds often reach their minimum (positive phase) or maximum (negative phase) values. These results enhance our understanding of the seasonal dynamics of surface currents in the SCS and their linkage to large-scale climatic variability.

Harnessing the Ocean for Food Production: The Concept of an Ocean-Going Aquaculture Process Vessel to Produce Salmon (Salmo salar) on the Atlantic Ocean - Uwe Waller; Klaus Kimmerle; Harald Jensen (Oceans, 2025)
Atlantic salmon aquaculture has become an important seafood producer, contributing to the human diet. The natural productivity of Atlantic salmon populations is not sufficient to meet even a fraction of current aquaculture production, and it has not been able to do so in the past. Alternative process technologies are needed to maintain aquaculture production at current levels while mitigating the environmental impact along the coasts. Future aquaculture development must align with the UN Sustainable Development Goals. This study describes an aquaculture process vessel operating in the open sea and powered largely by renewable energy. Production conditions are fully adapted to the biology of salmon, improving production reliability, reducing coastal environmental impacts, and enabling more sustainable production. This study specifies the biological and technological aspects, provides evidence of the technical and economic feasibility, and justifies the relocation of salmon aquaculture to a large oceanic ecosystem, the North Atlantic Ocean.

Estimated Ocean Climate Velocity Using Satellite Sea Surface Temperature Products Since the Early 2000s in the East Sea - Jisuk Ahn; Changsin Kim; Inseong Han; Huitae Joo (Oceans, 2025)
To understand the impacts of climate change on local marine ecosystems, assessing ocean climate velocity in regional seas is essential. This study investigated changes in sea surface temperature (SST) and associated shifts in isotherm location and ocean climate velocity in the East Sea of Korea from 2000 to 2024, utilizing satellite-derived SST data. The results revealed a significant acceleration in the ocean climate velocity of SST, reaching 66.99 km/decade over the past 25 years. The velocity significantly increased during Phase 4, indicating rapid changes with potential ecosystem impacts. The 18 °C SST zone expanded by more than twofold from the early 2000s to the early 2020s. The annual average SST exhibited a steady, consistent decadal increase. These trends are associated with the northward shift of isotherms, which significantly influences the SST distribution patterns, particularly in the 16–18 °C range. Given the accelerating ocean climate velocity, urgent attention is needed to mitigate climate change impacts, particularly in vulnerable regions such as the East Sea. This study enhances the understanding of SST dynamics and underscores the importance of proactive conservation and management in climate-affected marine ecosystems.

Assessment of Population Dynamics and Fishery Exploitation of Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in Iranian Waters - Seyed Ahmadreza Hashemi; Mastooreh Doustdar; Abdullah Al Kindi; Sachinandan Dutta (Oceans, 2025)
The population dynamics and exploitation ratios of the narrow-barred Spanish mackerel (Scomberomorus commerson, Lacépède, 1800) were investigated from August 2020 to February 2023, with data collected from three landing sites (Bushehr, Bandar Abbas, and Chabahar) of Iran waters. During the study period, only length was measured for 6504 specimens and both the length and weight were measured for 504 specimens. The mean fork length of the samples was 86 ± 20 cm, and the mean weight was 6230 ± 3742 g. The relationship between length and weight for the total samples was described by the equation W = 0.022 × CL2.76 (n = 504, R2 = 0.90, 95% C.I. for b = 2.52–2.91). The population dynamics indices for S. commerson were as follows: infinite length (Linf) = 173 cm, natural mortality (M) = 0.47 per year, growth coefficient (K) = 0.52 per year, total mortality (Z) = 1.42 ± 0.06 (95% C.I. = 1.36–1.48), fishing mortality (F) = 0.95 per year, and exploitation coefficient (E) = 0.67. The exploitation rate (U) and total stock at the beginning of the year (B0) were 0.6 and 48,333 tons, respectively. The annual average standing stock (Bt) was estimated at 30,526 tons. The exploitation ratio for maximum sustainable yield (EMSY) was 0.50, and fishing mortality at maximum sustainable yield (FMSY) was 1.5. The estimated range for maximum sustainable yield (MSY, in 1000 tons), the B/BMSY ratio, F/FMSY ratio, and saturation (S) ratio of S. commerson in the Iranian part of the Persian Gulf and the Sea of Oman was 20 (17–25), 1.55 (1.25–1.73), 0.90 (0.8–1.12), and 0.45, respectively. The stock of S. commerson is approaching overfishing in Iran waters, imposing immediate management actions to reduce catch and fishing effort.

Dynamics of Oxygen and the Physicochemical Response in Two Comparative Hypoxia Regions - Jian Wei; Joanna J. Waniek; Joachim Kuss; Oscar Beltran-Perez; Jen-Ping Peng; Chengchun Shi; Jin Chen; Jihui Liu; Lili Chen; Rongrong Xie (Oceans, 2025)
The oxygen depletion in worldwide oceans and inland waters is becoming an increasingly prevalent problem. Here, two comparative study sites, Baltic Proper (BP) and Shuikou Reservoir (SR), were selected to identify the dynamics of dissolved oxygen (DO) and the related physicochemical response by conducting five field investigations over one year period. The DO concentrations were 0–9.9 mg L−1 and 0.3–8.7 mg L−1 in BP and SR, with average oxygen change rates of −0.016~0.014 mg L−1 d−1 and −0.022~0.018 mg L−1 d−1, respectively. Such oxygen dynamics were highly related to salinity, temperature, turbidity, and chlorophyll-a than nitrogen and phosphorus. The persistent hypoxia (i.e., DO < 2 mg L−1) emerged below 63 m in BP during all sampling months where the reversal points of Brunt–Väisälä frequency N expressed in the form log10[N2 (s−2)] were −4. The seasonal hypoxia covered the downstream of SR at depths below 11.5 m in September with the highest log10[N2 (s−2)] between −3.95 and −3.64. The log10[N2 (s−2)] ≈ −4 may indicate the occurrence and development of hypoxia in both regions. In the case of the persistent and seasonal hypoxic conditions in BP and SR, the impact of temperature and turbidity on DO was opposite. Low oxygen levels in SR occurred under elevated temperature and turbidity. Additionally, under hypoxic conditions in both regions, NO3− and NH4+ concentrations significantly depended on DO changes. This study contributes to the understanding of seasonal changes in oxygen dynamics in different water bodies, and highlights different oxygen conditions and physicochemical responses to the oxygen changes.

Temporal Variations in Wave Systems in a Multimodal Sea State in the Coastal Waters of the Eastern Arabian Sea - Sivakrishnan K. Kalappurakal; Shanas R. Puthuveetil; V. Sanil Kumar (Oceans, 2025)
Multimodal waves can significantly impact ocean–atmosphere interactions and affect coastal ecosystems. Due to the presence of waves created in different geographical areas, many wave systems coexist in coastal seas. Based on data collected with a directional waverider buoy, this study investigates fluctuations in multimodal sea states from March 2010 to May 2020 in the eastern Arabian Sea. The watershed-based spectral partitioning method is used to analyze 2D wave spectra obtained from measurements. Four-wave systems are present during pre- and post-monsoon periods, and three systems are detected during the monsoon (June–September). Interannual changes in significant wave height and peak wave period of different systems are investigated, revealing the maximum interannual variability of all wave systems in the inter-monsoon periods (May and October). The most energetic system during the pre-monsoon period is wind seas from the northwest direction, whereas during monsoon, swells from the southwest-west dominate. This pattern is similar across a spatial distance of 570 km along the western coastal waters of India. In the post-monsoon period, both systems (wind seas and swells) are present, with swells having slightly higher intensity.

Detection, Tracking, and Statistical Analysis of Mesoscale Eddies in the Bay of Bengal - Hafez Ahmad; Felix Jose; Padmanava Dash; Shakila Islam Jhara (Oceans, 2025)
Mesoscale eddies have a significant influence on primary productivity and upper-ocean variability, particularly in stratified and monsoon-driven basins like the Bay of Bengal (BoB). This study analyzes mesoscale eddies in the BoB from January 2010 to March 2020 using post-processed and gridded daily sea surface height anomaly (SLA) data from the Copernicus Marine Environment Monitoring Service. We used a hybrid detection method combining the Okubo–Weiss parameter and SLA contour analysis to identify 1880 anticyclonic and 1972 cyclonic eddies. Cyclonic eddies were mainly found in the western BoB along the east Indian coast, while anticyclonic eddies were less frequent in this area. Analysis of eddy lifespans revealed that short-lived (1-week) eddies were nearly equally distributed between anticyclonic (48.81%) and cyclonic (51.19%) types. However, for longer-lived eddies, cyclonic eddies became more prevalent, comprising 83.33% of 30-week eddies. A notable, consistent eddy presence was observed east of Sri Lanka, influencing the East India Coastal Current. Most eddies (91%) propagated west/southwestward along the western slope of the Andaman Archipelago, likely influenced by ocean currents and coastal topography, with concentrations in the Andaman Sea and central BoB. These patterns suggest significant interactions between eddies, coastal upwelling zones, and boundary currents, impacting nutrient transport and marine ecosystem productivity. This study contributes valuable insights into the dynamics of ocean circulation and the impacts of eddies, which can inform fisheries management strategies, advance climate resilience measures, expand scientific knowledge, and guide policies related to conservation and sustainable resource utilization.

Glyphosate: A Terrestrial Threat to Marine Plants? A Study on the Seagrass Zostera marina - Alizé Deguette; Katia Pes; Bernard Vasconcellos; Monya Costa; João Silva; Isabel Barrote (Oceans, 2025)
Glyphosate-based herbicides (GBHs) are extensively used worldwide, raising concerns about their potential effect on non-target aquatic ecosystems. This study investigated the short-term physiological effects of a commercially available GBH on the seagrass Zostera marina under controlled mesocosm conditions. Z. marina individuals were exposed to three concentrations of glyphosate (0.165, 51, and 5100 mg L−1) for 4 days, and the impacts on photosynthetic performance, growth rate, photosynthetic pigments content and energy metabolism were assessed. Exposure to 5100 mg L−1 of glyphosate caused rapid water acidification and complete plant mortality within 24 h. Exposure to 51 mg L−1 of glyphosate significantly impaired photosynthetic efficiency and foliar growth rate. Energy availability, photosynthesis and photosynthetic pigments content were highly disrupted at both higher concentrations. Exposure to 0.165 mg L−1 of glyphosate decreased the foliar chlorophyll a/b ratio. These findings show that Z. marina can potentially be threatened by the presence of GBHs even at lower concentrations and underscore the necessity for monitoring herbicide pollution in coastal waters to protect seagrass habitats and associated ecosystems. Further research is needed to assess long-term effects and the role of herbicide formulations in mediating toxicity.

Citizen Science on Maritime Traffic: Implications for European Eel Conservation - Lucía Rivas-Iglesias; Eva Garcia-Vazquez; Verónica Soto-López; Eduardo Dopico (Oceans, 2025)
Maritime traffic accounts for more than 90% of world trade. Noise, pollution, and litter are its drawbacks, affecting especially vulnerable migratory fish. Here, a motivated team of citizen scientists analyzed maritime traffic from three estuaries of the south Bay of Biscay and three from the south of the Iberian Peninsula, where the European eel is critically endangered, during the season of the entrance of glass eels. More than 164,000 data points about ship types and positions were collected. The results showed that traffic differences between estuaries would explain, at least partially, the different eel conservation statuses. The participants appreciated learning about ships and nature conservation and acquiring an awareness of the real volume of shipping and its potential impacts. All the citizen scientists, new and experienced, would like to get involved in ocean research again.

Seasonal and Interannual Variations (2019–2023) in the Zooplankton Community and Its Size Composition in Funka Bay, Southwestern Hokkaido - Haochen Zhang; Atsushi Ooki; Tetsuya Takatsu; Atsushi Yamaguchi (Oceans, 2025)
Funka Bay, located in southwest Hokkaido, is a vital fishing area with a shallow depth of less than 100 m. Seasonal flows of the Oyashio and Tsugaru Warm Current affect the marine environment, leading to significant changes in zooplankton communities, yet limited information is available on these variations. This study used ZooScan imaging to analyze seasonal and interannual changes in zooplankton abundance, biovolume, community structure, and size composition from 2019 to 2023. Water temperature was low in March–April and high in September–November, with chlorophyll a peaks occurring from February to April. Notable taxa such as Thaliacea, Noctiluca, and cladocerans were more common in the latter half of the year. Interannual variations included a decline in large cold-water copepods, Eucalanus bungii and Neocalanus spp., which were abundant in 2019 but decreased by 2023. Zooplankton abundance and biovolume showed synchronized seasonal changes, correlating with shifts in the Normalized Biovolume Size Spectra (NBSS) index, which measures size composition. Cluster analysis identified eight zooplankton communities, with Community A dominant from July to December across all years, while Community D was prevalent in early 2019 but was replaced in subsequent years. Community E emerged from March to April in 2021–2023. In 2019, large cold-water copepods were dominant, but from 2020 to 2023, appendicularians became the dominant group during the March–April period. The decline in large copepods is likely linked to marine heat waves, influencing yearly zooplankton community changes.

Design and Efficiency Analysis of High Maneuvering Underwater Gliders for Kuroshio Observation - Zhihao Tian; Bing He; Heng Zhang; Cunzhe Zhang; Tongrui Zhang; Runfeng Zhang (Oceans, 2025)
The Kuroshio Current’s flow velocity imposes exacting requirements on underwater vehicle propulsive systems. Ecological preservation necessitates low-noise propeller designs to mitigate operational disturbances. As technological evolution advances toward greater intelligence and system integration, intelligent unmanned systems are positioning themselves as a critical frontier in marine innovation. In recent years, the global research community has increased its efforts towards the development of high-maneuverability underwater vehicles. However, propeller design optimization ignores the key balance between acoustic performance and hydrodynamic efficiency, as well as the appropriate speed threshold for blade rotation. In order to solve this problem, the propeller design of the NACA 65A010 airfoil is optimized by using OpenProp v3.3.4 and XFlow 2022 software, aiming at innovating the propulsion system of shallow water agile submersibles. The study presents an integrated design framework combining lattice Boltzmann method (LBM) simulations synergized with fully Lagrangian-LES modeling, implementing rotational speed thresholds to detect cavitation inception, followed by advanced acoustic propagation analysis. Through rigorous comparative assessment of hydrodynamic metrics, we establish an optimization protocol for propeller selection tailored to littoral zone operational demands. Studies have shown that increasing the number of propeller blades can reduce the single-blade load and delay cavitation, but too many blades will aggravate the complexity of the flow field, resulting in reduced efficiency and noise rebound. It is concluded that the propeller with five blades, a diameter of 234 mm, and a speed of 500 RPM exhibits the best performance. Under these conditions, the water efficiency is 69.01%, and the noise is the lowest, which basically realizes the balance between hydrodynamic efficiency and acoustic performance. This paradigm-shifting research carries substantial implications for next-generation marine vehicles, particularly in optimizing operational stealth and energy efficiency through intelligent propulsion architecture.

Exploring the Potential of European Brown Shrimp (Crangon crangon) in Integrated Multi-Trophic Aquaculture: Towards Achieving Sustainable and Diversified Coastal Systems - Ángel Urzúa; Marina Gebert (Oceans, 2025)
Global marine coastal aquaculture increased by 6.7 million tons in 2024, with whiteleg shrimp (Penaeus vannamei) dominating crustacean production. However, reliance on a single species raises sustainability concerns, particularly in the face of climate change. Diversifying shrimp farming by cultivating native species, such as the European brown shrimp (Crangon crangon), presents an opportunity to develop a sustainable blue bioeconomy in Europe. C. crangon holds significant commercial value, yet overexploitation has led to population declines. Integrated Multi-Trophic Aquaculture (IMTA) offers a viable solution by utilizing fish farm wastewater as a nutrient source, reducing both costs and environmental impact. Research efforts in Germany and other European nations are exploring IMTA’s potential by co-culturing shrimp with species like sea bream, sea bass, and salmon. The physiological adaptability and omnivorous diet of C. crangon further support its viability in aquaculture. However, critical knowledge gaps remain regarding its lipid metabolism, early ontogeny, and reproductive biology—factors essential for optimizing captive breeding. Future interdisciplinary research should refine larval culture techniques and develop sustainable co-culture models. Expanding C. crangon aquaculture aligns with the UN’s Sustainable Development Goals by enhancing food security, ecosystem resilience, and economic stability while reducing Europe’s reliance on seafood imports.

Open-Ocean Carbonate System and Air–Sea CO2 Fluxes Across a NE Atlantic Seamount Complex (Madeira–Tore, August 2024) - Marta Nogueira; Alexandra D. Silva (Oceans, 2025)
This study focused on the carbonate system dynamics and air–sea CO2 fluxes in the open-ocean waters of the Madeira–Tore Seamount Complex during August 2024. Surface water properties revealed pronounced latitudinal gradients in sea surface temperature (21.9–23.1 °C), salinity (36.2–36.7), and dissolved oxygen (228–251 µmol Kg−1), influenced by mesoscale eddies and topographically driven upwelling. Despite oligotrophic conditions, distinct phytoplankton assemblages were observed, with coccolithophores dominating southern seamounts and open-ocean stations, and green algae and diatoms indicating episodic nutrient input. Surface total alkalinity (TA: 2236–2467 µmol Kg−1), dissolved inorganic carbon (DIC: 2006–2183 µmol Kg−1), and pCO2 (467–515 µatm) showed spatial variability aligned with water mass characteristics and biological activity. All stations exhibited positive air–sea CO2 fluxes (2.8–11.5 mmol m−2 d−1), indicating the region is a CO2 source during summer. Calcite and aragonite saturation states were highest in stratified, warmer waters. Principal Component Analysis highlighted the role of physical mixing, carbonate chemistry, and biological uptake in structuring regional variability. Our findings emphasize and contribute to the complex interplay of physical and biogeochemical drivers in modulating carbon cycling and ecosystem structure across Atlantic seamounts.

A Stability Model for Sea Cliffs Considering the Coupled Effects of Sea Erosion and Rainfall - Haoyu Zhao; Xu Chang; Yingbin Huang; Junlong Zhou; Zilong Ti (Oceans, 2025)
This study proposed a sea cliff stability model that accounted for the coupled effects of sea erosion and rainfall, offering an improved quantitative assessment of the toppling risk. The approach integrated the notch morphology (height and depth) and rainfall infiltration to quantify stability, validated by field data from six toppling sites near Da’ao Bay, where the maximum erosion distance error between model predictions and measurements ranged from 0.81% to 48.8% (with <20% error for Sites S2, S3, and S4). The results indicated that the notch morphology and rainfall exerted significant impacts on the sea cliff stability. Site S4 (the highest site) corresponded to a 17.5% decrease in K per 0.1 m notch depth increment. The rainfall infiltration reduced the maximum stable notch depth, decreasing by 8.86–21.92% during prolonged rainfall. This model can predict sea cliff stability and calculate the critical notch depth (e.g., 0.56–1.22 m for the study sites), providing a quantitative framework for coastal engineering applications and disaster mitigation strategies under climate change scenarios.

Fin Whale Acoustic Presence Increases by 3 d/y in the Migratory Corridor off Cape Leeuwin, Western Australia—An Indicator of Population Growth? - Meghan G. Aulich; Robert D. McCauley; Brian S. Miller; Christine Erbe (Oceans, 2025)
The population of southern fin whales (Balaenoptera physalus quoyi) was severely depleted by 19th and 20th century whaling. Its conservation status remains ‘vulnerable’, as recovery has been slow. Over 19 years of underwater acoustic recordings from the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO)’s hydrophones off Cape Leeuwin, Western Australia, were analyzed to monitor fin whales’ annual migration from their Southern Ocean feeding grounds (where they spend the austral summer) to their tropical breeding grounds (where they spend the austral winter) and back. Northward migrants arrived ~2 d/y earlier (2002–2020). The number of hours with fin whale acoustic presence increased by ~49 h/y and the number of days with fin whale acoustic presence by ~3 d/y. Thus, by the end of the 19-year recording period, fin whales were acoustically present on 74 more days than at the beginning of recording. While changes in habitat function, climate, and ambient noise may affect migratory behavior, the most likely explanation is a post-whaling increase in the number of animals of this Southern Hemisphere subspecies.

The Accidental Capture of a Newborn Shortfin Mako Shark Isurus oxyrinchus (Rafinesque, 1810) in the Northwestern Mediterranean Sea off the Coast of Marseille, France - Emmanuel Leguay; Eric E. G. Clua (Oceans, 2025)
A small-sized shark was accidentally caught in the coastal waters of southeastern France and abandoned in the port of L’Estaque (Marseille) in May 2024. An autopsy revealed that it was a young female shortfin mako, Isurus oxyrinchus (Rafinesque, 1810). Numerous superficial wounds on the head, back, and flanks, in the form of parallel striations resulting from heavy friction, indicate meshing in a gillnet that provoked the animal’s death by asphyxiation. Its very small size (64.77 cm TL) suggests that this is a newborn individual, leading to the hypothesis that the waters off Marseille could be a nursery area for this species. This observation alone is not enough to prove this point, but it does suggest the need for closer monitoring to validate it. Should the area be proven to play this key role for this critically endangered species, measures to limit fishing pressure would be essential, particularly during the parturition period between February and May.

Acropora spp. Coral Gardening Using Fragmentation and Direct Transplantation: A Feasibility Study at Boundary Island - Min Li; Dechuan Lee; Xiaofei Xiong; Le Zhu; Aimin Wang; Wubo Wan; Yaoxian Chin; Peizheng Wang (Oceans, 2025)
As major bleaching continues to ravage reefs worldwide, there is an urgent need for active coral restoration. However, the high cost of such a project is inhibitive for many countries. Here, we introduce a cost-effective design for Acropora robusta and Acroporavalenciennesi coral gardening through fragmentation and direct transplantation. Implemented off Boundary Island, Hainan Province, China, the project demonstrated high coral survival rates (>94%) at a reduced cost of USD 2.50 per coral after 246 days, besides exhibiting an efficient outplanting rate at 30 coral h−1 person−1. Growth monitoring suggested that the transplanted Acropora spp. follow an exponential growth model over time. Initial fragment size did not seem to affect the growth rate of outplanted Acropora spp., although a weak negative correlation was found at day 246 for A. robusta. Finally, the design used in this study employs detachable steel grid nurseries and is plastics-free, ensuring sustainability and adaptability to different reef conditions, and thus providing a promising strategy for affordable coral reef restoration.

Factor Correction Analysis of Nodal Tides in Taiwan Waters - Hsien-Kuo Chang; Peter Tian-Yuan Shih; Wei-Wei Chen (Oceans, 2025)
Nodal tides, which follow an 18.6-year cycle, influence tidal variations at any given location in the ocean. Conventional nodal tide theory neglects land effects and topological change. Due to the complex seabed topography around Taiwan waters, the purpose of this paper is to use the long-term tidal data of six stations to discuss the effects of perigean and nodal tides on 20 constituents and to compare the results with previous theories. A modulation method is employed to fit the annual amplitude estimated by harmonic analysis (HA). The top four constituents of the fitted and theoretical values of nodal amplitude factor (AF) and phase factor (PF) are O1, K1, K2, and Q1. We find that perigean tides or second-order nodal tides considered in the fitting contribute to almost identical performance. The linear time change considered in the AF fitting has better fitting than the mean water level involved.

Feature Papers of Oceans 2024 - Alexander J. Werth (Oceans, 2025)
As the noted futurist and author Arthur C [...]

A Multi-Stage Enhancement Based on the Attenuation Characteristics of X-Band Marine Radar Images for Oil Spill Extraction - Peng Liu; Xingquan Zhao; Xuchong Wang; Pengzhe Shao; Peng Chen; Xueyuan Zhu; Jin Xu; Ying Li; Bingxin Liu (Oceans, 2025)
Marine oil spills cause significant environmental damage worldwide. Marine radar imagery is used for oil spill detection. However, the rapid attenuation of backscatter intensity with increasing distance limits detectable coverage. A multi-stage image enhancement framework integrating background clutter fitting subtraction, Multi-Scale Retinex, and Gamma correction is proposed. Experimental results using marine radar images sampled in the oil spill incident in Dalian 2010 are used to demonstrate the significant improvements. Compared to Contrast-Limited Adaptive Histogram Equalization and Partially Overlapped Sub-block Histogram Equalization, the proposed method enhances image contrast by 24.01% and improves the measurement of enhancement by entropy by 17.11%. Quantitative analysis demonstrates 95% oil spill detection accuracy through visual interpretation, while significantly expanding detectable coverage for oil extraction.

Status Quo and Future Prospects of China’s Weather Routing Services for Ocean-Going Business Vessels - Hao Zhang; Guanjun Niu; Tao Liu; Chuanhai Qian; Wei Zhao; Xiaojun Mei; Hao Wu (Oceans, 2025)
The global shipping industry is evolving towards deep integration of digital transformation, intelligent upgrading, and green development. Meanwhile, recent geopolitical shifts have introduced heightened uncertainties into international shipping, compounding the challenges and escalating the demands for weather routing services for ocean-going ships. This paper provides a systematic review and expert perspective on China’s current status and key challenges in ocean-going weather routing services. Based on operational insights from China’s national meteorological service synthesized with a review of current trends and the literature, it further explores the future development of China’s ocean-going weather routing services and technologies from multiple dimensions: enhancing maritime weather observation capabilities, developing advanced weather routing service models, upgrading autonomous and controllable global satellite communication systems, promoting intelligent navigation technologies to facilitate shipping’s low-carbon transition, and expanding meteorological support capabilities for Arctic shipping routes. The analysis identifies critical gaps and proposes strategic directions, offering a unique contribution to understanding the trajectory of weather routing services within China’s specific national context from the perspective of its primary national service provider.

A Kiss from the Wild: Tongue Nibbling in Free-Ranging Killer Whales (Orcinus orca) - Javier Almunia; Johnny van Vliet; Debbie Bouma (Oceans, 2025)
Tongue-nibbling is a rare and previously undocumented affiliative behaviour in free-ranging killer whales (Orcinus orca), until now seen only in individuals under human care. This study presents the first recorded observation of tongue-nibbling between two wild killer whales in the Kvænangen fjords, Norway. The interaction, captured opportunistically by citizen scientists during a snorkelling expedition, lasted nearly two minutes and involved repeated episodes of gentle, face-to-face oral contact. This behaviour closely resembles sequences observed and described in detail in zoological settings, suggesting that it forms part of the species’ natural social repertoire. The observation also supports the interpretation of tongue-nibbling as a socially affiliative behaviour, likely involved in reinforcing social bonds, particularly among juveniles. The prolonged maintenance of this interaction in managed populations originating from geographically distinct Atlantic and Pacific lineages further indicates its behavioural conservation across contexts. This finding underscores the importance of underwater ethological observation in capturing cryptic social behaviours in cetaceans and illustrates the value of integrating citizen science into systematic behavioural documentation. The study also reinforces the relevance of managed populations in ethological research and highlights the ethical need for carefully regulated wildlife interaction protocols in marine tourism.

Underwater Reverberation Suppression Using Wavelet Transform and Complementary Learning - Jiajie Liu; Qunfei Zhang; Xiaodong Cui; Chencong Tang; Zijun Pu (Oceans, 2025)
Reverberation is the primary interference of active detection. Therefore, the effective suppression of reverberation is a prerequisite for reliable signal processing. Existing dereverberation methods have shown effectiveness in specific scenarios. However, they often struggle to exploit the distinction between target echo and reverberation, especially in complex, dynamically changing underwater environments. This paper proposes a novel dereverberation network, ERCL-AttentionNet (Echo–Reverberation Complementary Learning Attention Network). We use the Continuous Wavelet Transform (CWT) to extract time–frequency features from the received signal, effectively balancing the time and frequency resolution. The real and imaginary parts of the time–frequency matrix are combined to generate attention representations, which are processed by the network. The network architecture consists of two complementary UNet models sharing the same encoder. These models independently learn target echo and reverberation features to reconstruct the target echo. An attention mechanism further enhances performance by focusing on target information and suppressing irrelevant disturbances in complex environments. Experimental results demonstrate that our method achieves a higher Peak-to-Average Signal-to-Reverberation Ratio (PSRR), Structural Similarity Index (SSIM), and Peak-to-Average Ratio (PAR) of cross-correlation while effectively preserving key time–frequency features, compared to traditional methods such as autoregressive (AR) and singular value decomposition (SVD).

Genomic Characteristics of Two Common Pest Starfish in Northern China Seas: A Whole-Genome Survey Approach - Zhichao Huang; Zhe Li; Gang Ni (Oceans, 2025)
Coastal shellfish farming areas in northern China seas face frequent starfish outbreaks, particularly from Asterias amurensis and Patiria pectinifera, leading to significant economic losses. Genomic data are key to understanding the population dynamics and adaptive traits and developing effective control measures for these species. Here, we characterized and compared the genomic information of these two starfish using a whole-genome survey approach. The genome size of A. amurensis is ~477 Mb with 1.52% heterozygosity, 53.60% repetitive sequences, and 39.94% GC content, while P. pectinifera has a ~529 Mb genome, 2.90% heterozygosity, 56.02% repetitive sequences, and 40.63% GC content. Scaffold N50 values were 1823 bp for A. amurensis and 1328 bp for P. pectinifera. We identified 161,786 microsatellite motifs in A. amurensis and 316,245 in P. pectinifera, with mononucleotide repeats being the most common. A total of 171 single-copy homologous genes were found in A. amurensis, with 94 in P. pectinifera. For both species, KEGG annotation showed functional similarities in glycan biosynthesis, translation, metabolism, catabolism, and transport. The Pairwise Sequentially Markovian Coalescent (PSMC) analysis unveiled a bottleneck effect during the Pleistocene glaciation. Additionally, phylogenetic analysis of mitochondrial genomes indicates that P. pectinifera and Patiria miniata of the same genus belong to the same branch in the evolutionary tree as sister groups with the closest genetic relationship, while A. amurensis is most closely related to Astropecten polyacanthus within the class Asteroidea. These findings provide valuable genomic insights for both species.

Elasmobranch Species Composition in Otter Trawl Fisheries (Eastern Aegean Sea) - İlker Aydin; Alexandros Theocharis; Sercan Yapici; Dimitris Klaoudatos (Oceans, 2025)
The Eastern Aegean Sea hosts a diverse assemblage of elasmobranchs, many of which are vulnerable or endangered. This study presents a fishery-independent assessment of species composition, catch characteristics, and spatial patterns in bottom trawl fisheries between Lesvos Island and Ayvalik. A total of 48 surveys were conducted between September 2022 and October 2024, identifying nine elasmobranch species, with Scyliorhinus canicula (small-spotted catshark) and Mustelus mustelus (common smooth-hound) dominating the catch. Biological parameters, sex ratios, and condition upon capture and release were recorded, while catch per unit effort (CPUE) and diversity indices were used to evaluate temporal patterns. The survival probability was negatively affected by the trawl duration and elevated temperatures, emphasizing the need for mitigation measures. Spatial models revealed high-density zones that likely function as foraging or nursery grounds. Seasonal shifts in community composition were also evident. Many non-commercial species were discarded irrespective of their size or condition. These findings underscore the ecological importance of this understudied region and support the need for spatially explicit, species-specific management strategies, including gear selectivity improvements, seasonal closures, and Electronic Monitoring. The study offers a critical baseline for enhancing the sustainability of elasmobranch populations in the Eastern Mediterranean.

Morphological Insights into Echinometra lucunter Spines Reveal Cellular Sources of Bioactive Molecules - Juliana Mozer Sciani; Marta Maria Antoniazzi; Carlos Jared; José Roberto Machado Cunha da Silva; Daniel Carvalho Pimenta (Oceans, 2025)
Echinometra lucunter, the most abundant sea urchin in Brazil, causes numerous accidents by puncture wounds, primarily on hands and feet. Beyond mechanical trauma, recent research has identified bioactive molecules in spine extracts and coelomic fluid contributing to these inflammatory reactions. This study investigated spine morphology to better understand the envenomation and defense processes for the animal. Using various microscopy techniques, the spines were revealed to be mineral structures with longitudinal canals and a sponge-like central mesh rich in granular cells. These cells extend from the spine’s center to its edges, terminating in fimbriae-like structures, likely involved in molecular exchange with the environment. The spine tip is more cellular than the base, suggesting a defensive role, while the base provides structural support. Several cell types were identified, including granulocytes, red spherulocytes, and phagocytic amoebocytes, also found in the coelomic fluid. Other cells displayed prominent Golgi apparatuses and secretory granules, indicating specialized secretory functions, likely the source of bioactive molecules involved in chemical defense and spine regeneration. Understanding this cellular structure is crucial for comprehending the urchin’s envenomation and defense mechanisms.

Irradiance Level Only Moderately Affects Thermal Bleaching in the Stony Coral Stylophora pistillata - Ronald Osinga; Emma van Veenendaal; Daniëlle S. L. Geschiere; Britt J. A. van Herpen; Saskia Oosterbroek (Oceans, 2025)
Light is considered an important co-factor in causing thermal bleaching in photosymbiotic corals. To quantify the effects of light strength on thermal bleaching, colonies of the stony coral Stylophora pistillata were experimentally subjected to a gradual increase in temperature (1 °C per 4 days) under two irradiance levels: 100 and 500 µmole quanta m−2 s−1. Corals kept under the same irradiance levels at a constant temperature of 26 °C were used as controls. The apparent photochemical yield ΔF/Fm′ of Photosystem II of the coral symbionts was monitored daily as an indicator for the onset of thermal bleaching, the onset of bleaching being defined as a steep decrease in ΔF/Fm′. In heat-treated corals incubated under the high irradiance of 500 µmole quanta m−2 s−1, the onset of bleaching occurred 26 days after the start of the heat ramp, at a temperature of 33 °C. ΔF/Fm′ in corals incubated under the low irradiance of 100 µmole quanta m−2 s−1 started to drop 1 day later at the same temperature. Before and after the observed drop in ΔF/Fm′, coral samples were taken for analysis of symbiont densities and levels of chlorophyll-a. At the onset of bleaching, symbiont densities and chlorophyll-a levels in heat-treated corals were not different from those of corals kept under control conditions. Three days after the onset of bleaching, symbiont densities and levels of chlorophyll-a in heat-treated corals had substantially decreased in comparison to controls. Under low irradiance, symbiont density and chlorophyll-a content were 84% and 76% lower than controls, respectively, whereas under high irradiance, symbiont density and chlorophyll-a content were 41% and 46% lower. These data suggest that damage to the photosystem in coral symbionts is the root cause of thermal bleaching in symbiotic corals, followed later by a collapse of the symbiosis. The role of light in augmenting thermal bleaching was only moderate, with a five-fold reduction in irradiance causing only a 1-day delay in bleaching. These results suggest that temperature is the main driver of bleaching in the studied coral.

Evaluation of Anchovy Egg Density: A Study on Differences Between Vertical and Oblique Towing Samplers for Ichthyoplankton - Gualtiero Basilone; Rosalia Ferreri; Angelo Bonanno; Simona Genovese; Salvatore Aronica (Oceans, 2025)
The use of multiple sampling instruments during ichthyoplankton surveys could require a significant amount of time for sample collection procedures; moreover, their use is highly dependent on weather conditions. During surveys aimed at the application of the Daily Egg Production Method (DEPM), two different kinds of sampler are employed: PairoVET and Bongo 40. The possibility of using only one of these samplers may allow for a reduction in the sampling time on board and the subsequent analyses; thus, a study was carried out to test the use of the Bongo 40 sampler alone (i.e., without PairoVET sampling) in DEPM application. Samples collected during five ichthyoplankton surveys (from 2007 to 2010 and in 2014) were analyzed to compare the efficiency in anchovy egg collection. Although the compared ichthyoplankton samplers provided differences in the collected number of eggs, as well as in the filtered volume, non-significant differences between them were recorded in the egg density. An ANCOVA revealed a significant relationship (F1,5 = 606.80; p < 0.001) between the density estimates from the two nets, but no differences were recorded among years (F1,5 = 0.99; p < 1). The slopes of the linear regressions for the two datasets were close to 1, suggesting a substantial equivalence of the two samplers in estimating the egg density. Finally, since only a few sampling stations showed densities higher than 20 ind. m−2, conversion equations were provided to estimate the PairoVET density from the Bongo 40 data at different density levels (i.e., 20 ind. m−2 or higher).

Exploring the Cultivation of Ulva intestinalis in Low-Salinity Environments of the Baltic Sea - Indrek Adler; Georg Martin; Nikolai Kovalchuk; Helen Orav-Kotta; Kristel Vene; Rando Tuvikene; Jonne Kotta (Oceans, 2025)
Ulva intestinalis holds promise for sustainable aquaculture in the Baltic Sea, but success has so far been limited by high environmental variability. This study examines how environmental factors influence sporogenesis, attachment, and growth of U. intestinalis in the low-salinity Baltic Sea. Optimal sporogenesis was observed at nutrient levels of 4–7 g/L, with peak zoospore release at 22–24 °C. Artificial substrates showed limited attachment success, as competing algae like Pylaiella littoralis and Cladophora glomerata often outperformed Ulva. Mesh cage cultivation demonstrated potential, achieving growth rates similar to controlled systems, though storm-induced turbidity lowered growth. These findings highlight the importance of tailored Baltic Sea cultivation strategies, focusing on nutrient, temperature, water stability, and competition management to enhance Ulva production. As the first pilot experiments in the region, they provide essential input for developing informed strategies that support more detailed trials and future scaled-up production.

Future Changes in Carbon Chemistry Under the Implementation of Artificial Ocean Alkalinization Based on CMIP6 Simulations - Baoxiao Qu; Jinming Song; Xuegang Li; Huamao Yuan; Liqin Duan (Oceans, 2025)
Artificial ocean alkalinization (AOA) is one of the most promising marine carbon dioxide removal technologies, but its influence on marine carbon chemistry remains unclear. We applied data from the Sixth Coupled Model Intercomparison Project (CMIP6) to characterize the temporal and spatial variabilities of future marine carbon chemistry under the implementation of AOA. Our study shows that the marine carbon system varied significantly under the implementation of AOA, but some specific effects may be masked by the forcing of the high carbon emission scenario SSP5-8.5. Based on the CMIP6 protocol, which added 0.14 Pmol of alkalinity into the ocean annually, AOA promoted an increase in DIC, delayed the rise in pCO2, and mitigated declines in pH and Ω, respectively. The temperate oceans in both hemispheres were the most significantly impacted basins, whereas the Southern Ocean was the least affected. During this century, the oceanic carbon sink is expected to intensify rapidly until around the year 2080, and then gradually weaken. The implementation of AOA merely changed the relative strength of the oceanic sink, rather than its overall variation pattern. Furthermore, in the deep ocean, the effect of AOA was present but quite limited in mitigating ocean acidification.

Combining Cirrus and Aerosol Corrections for Improved Reflectance Retrievals over Turbid Waters from Visible Infrared Imaging Radiometer Suite Data - Bo-Cai Gao; Rong-Rong Li; Marcos J. Montes; Sean C. McCarthy (Oceans, 2025)
The multi-band atmospheric correction algorithms, now referred to as remote sensing reflectance (Rrs) algorithms, have been implemented on a NASA computing facility for global remote sensing of ocean color and atmospheric aerosol parameters from data acquired with several satellite instruments, including the Visible Infrared Imaging Radiometer Suite (VIIRS) on board the Suomi spacecraft platform. These algorithms are based on the 2-band version of the SeaWiFS (Sea-Viewing Wide Field-of-View Sensor) algorithm. The bands centered near 0.75 and 0.865 μm are used for atmospheric corrections. In order to obtain high-quality Rrs values over Case 1 waters (deep clear ocean waters), strict masking criteria are implemented inside these algorithms to mask out thin clouds and very turbid water pixels. As a result, Rrs values are often not retrieved over bright Case 2 waters. Through our analysis of VIIRS data, we have found that spatial features of bright Case 2 waters are observed in VIIRS visible band images contaminated by thin cirrus clouds. In this article, we describe methods of combining cirrus and aerosol corrections to improve spatial coverage in Rrs retrievals over Case 2 waters. One method is to remove cirrus cloud effects using our previously developed operational VIIRS cirrus reflectance algorithm and then to perform atmospheric corrections with our updated version of the spectrum-matching algorithm, which uses shortwave IR (SWIR) bands above 1 μm for retrieving atmospheric aerosol parameters and extrapolates the aerosol parameters to the visible region to retrieve water-leaving reflectances of VIIRS visible bands. Another method is to remove the cirrus effect first and then make empirical atmospheric and sun glint corrections for water-leaving reflectance retrievals. The two methods produce comparable retrieved results, but the second method is about 20 times faster than the spectrum-matching method. We compare our retrieved results with those obtained from the NASA VIIRS Rrs algorithm. We will show that the assumption of zero water-leaving reflectance for the VIIRS band centered at 0.75 μm (M6) over Case 2 waters with the NASA Rrs algorithm can sometimes result in slight underestimates of water-leaving reflectances of visible bands over Case 2 waters, where the M6 band water-leaving reflectances are actually not equal to zero. We will also show conclusively that the assumption of thin cirrus clouds as ‘white’ aerosols during atmospheric correction processes results in overestimates of aerosol optical thicknesses and underestimates of aerosol Ångström coefficients.

Eight Categories of Air–Water Gas Transfer - David Kevin Woolf (Oceans, 2025)
The air–sea transfer of gases is important within climate physics, biogeochemistry and the control of pollutants. A two-layer model of transfer directly across the sea surface underpins most discourse, but an expanding literature also features transfer mediated by “suspended fragments”, either bubbles in the upper ocean or drops and aerosol in the lower atmosphere. In this study, we describe a categorization of process that elucidates departures from two-layer theory and is a starting point for quantification. On counting the distinct phenomena and their application to gases of various solubility, a total of eight categories are identified. Each category has a distinct scaling with respect to the properties of the gas and this is key to the relative importance of different categories and processes. Transfer through sea spray can be an exchange process, but the evaporation of sea spray is more effective and is an ejection process. The reactivity of carbon dioxide in aqueous solution enhances the effect of spray. Exceptional levels of sea spray generation and evaporation are required to be significant for most gases, but moderate levels are sufficient for carbon dioxide and the most soluble pollutants.

Seasonal Macrofaunal Diversity in the Shells of Dead Pinna nobilis Linnaeus, 1758 in Southern Istria - Petra Burić; Neven Iveša; Adrian Brajković; Ante Žunec; Iris Matulja; Ines Kovačić; Andrej Jaklin; Gioconda Millotti; Paolo Paliaga; Emina Pustijanac; Tin Matulja; Moira Buršić (Oceans, 2025)
The shells of dead Pinna nobilis individuals are important habitats in sedimentary coastal ecosystems, yet their ecological role is poorly understood. This study investigated macrofaunal communities associated with 80 P. nobilis shells from Soline Bay and Valovine Bay, northern Adriatic, analyzing variations in species abundance and biodiversity between shell orientations (vertical and horizontal) and across seasons. Shell dimensions were recorded, with larger shells and higher faunal abundance observed in Soline Bay compared to Valovine Bay. A total of 2225 individuals representing 183 species across 19 taxonomic groups were identified, with Malacostraca, Bivalvia, and Polychaeta being the most abundant. Vertically positioned shells hosted significantly more organisms than horizontally positioned ones, likely due to greater available surface area for settlement. Seasonal changes influenced organism abundance, with peaks in winter for Valovine Bay and spring for Soline Bay, correlating with environmental factors such as eutrophication. The most frequent species associated with the shells of dead individuals were the polychaete Sabella spallanzanii and the bivalve Rocellaria dubia, which can impact shell degradation. Despite their temporary nature, the shells of dead P. nobilis provide vital refuge and enhance biodiversity. The findings underscore the ecological importance of P. nobilis shells as biodiversity hotspots and highlight the need for their conservation and further study.

Northern Refuge or New Thermophilic Hotspot? Citizen Science Evidence of Rare, Thermophilic, and Alien Fishes in the Ligurian Sea (NW Mediterranean) - Alessandro Nota; Alfredo Santovito; Francesco Tiralongo (Oceans, 2025)
The Ligurian Sea, located in the northwestern Mediterranean, is undergoing a dramatic shift in fish biodiversity due to climate change and species immigration. This study adopted a citizen science approach to provide new data on the current distribution of rare, thermophilic, and alien fish species in the Ligurian Sea. Observations were collected through social networks and personal acquaintances, involving fishermen, divers, and fishmongers. We obtained a total of 47 records, encompassing 18 species belonging to 18 different fish families. Considering existing literature, some species appear to prefer this part of the Mediterranean Sea, likely due to the Ligurian Sea’s unique hydrodynamic and oceanographic conditions that support nutrient-rich environments. Others appear to be less common in the region, probably due to the lower temperatures of the Ligurian Sea compared to other Mediterranean sectors. Our findings emphasize the dual and controversial role of the Ligurian Sea as a refuge for cold-adapted species and a hotspot for thermophilic invaders. Moreover, this research highlights the role of citizen science in complementing traditional survey approaches, providing an efficient tool to monitor many taxa across several diverse ecological niches.

Reply to Zvuloni, A.; Shaked, Y. Comment on “Shashar et al. Artificial Reef Deployment Reduces Diving Pressure from Natural Reefs—The Case of Introductory Dives in Eilat, Red Sea. Oceans 2024, 5, 71–80” - Nadav Shashar; Re’em Neri; Asa Oren; Jenny Tynyakov (Oceans, 2025)
In a recent study [...]

Comment on Shashar et al. Artificial Reef Deployment Reduces Diving Pressure from Natural Reefs—The Case of Introductory Dives in Eilat, Red Sea. Oceans 2024, 5, 71–80 - Assaf Zvuloni; Yonathan Shaked (Oceans, 2025)
The recent publication “Artificial Reef Deployment Reduces Diving Pressure from Natural Reefs—The Case of Introductory Dives in Eilat, Red Sea” by Shashar, N [...]

Study on the Impact Mitigation Effect of Artificial Rock Backfill Layers for Submarine Pipelines Based on Physical Model Tests and Numerical Simulations - Guixi Jiang; Long Yu; Yunrui Han; Chunhong Hu; Dayong Zhang; Qing Yang (Oceans, 2025)
Submarine pipelines laid across navigational channels are highly susceptible to anchor drop impacts, which can cause deformation and disrupt normal pipeline operations. In severe cases, anchor impacts may lead to oil and gas leaks, resulting in significant economic losses and environmental damage. To ensure the safe operation of submarine pipelines, artificial rock backfilling is widely employed as a protective measure. Compared with complex pipeline protection structures, this approach is both cost-effective and efficient. In the physical model experiment, a combination of total force sensors and thin-film sensors was used to measure the dynamic response of pipelines under anchor impact. Additionally, The FEM-DEM numerical method was used to simulate the dynamic response and interaction process of anchor impact on the rock protection layer and pipeline. Numerical results were compared with experimental data to analyze the effects of rock protection layer thickness, backfill rock particle size, and pipeline sublayer types on pipeline impact response. The results show a good agreement between the physical model tests and numerical simulation studies, revealing several factors that influence the mitigation effect of the rock protection layer. This study provides a valuable scientific reference for the installation of rock protection layers for pipelines.

Design and Implementation of a Position-Based Coordinated Formation System for Underwater Multiple Small Spherical Robots - Xihuan Hou; Shuxiang Guo; Zan Li; Huimin Shi; Na Yuan; Huiming Xing (Oceans, 2025)
Due to the excellent concealment and high mobility, multiple small spherical underwater robots are essential for near coast defending missions. The formation of multiple small spherical underwater robots is particularly effective for tasks such as patrolling, reconnaissance, surveillance, and capturing sensitive targets. Moreover, some tasks need higher flexibility and mobility, such as reconnaissance, surveillance, or target encirclement at fixed locations. For this purpose, this paper proposes a position-based formation mechanism which is easily deployed for multiple spherical robots. A position planning method during the formation process is designed. This method creatively integrates the virtual linkage strategy with an improved consensus algorithm and the artificial potential field (APF) method. The virtual linkage strategy is in charge of computing the global formation desired target positions for robots according to the predefined position of the virtual leader joint. The improved consensus algorithm and APF are responsible for planning the local desired positions between two formation desired target positions, which is able to prevent collisions and excessive communication distance between robots. In order to verify the effectiveness of the proposed formation mechanism, adequate simulations and experiments are conducted. Thereby, the proposed formation frame offers great potential for future practical marine operations of the underwater multi-small robot systems.

Influencing Factors on Oyster Recruitment and Performance Evaluation for Oyster Reef Restoration in Tianjin Coastal Zones - Yuxuan Zhao; Chen Yang; Bo Zhang; Yanping Li; Jianbo Tu; Fuxin Niu; Wenliang Kong; Zhiyun Wang; Xianhua Liu (Oceans, 2025)
Global oyster reefs have suffered severe degradation due to human activities, environmental pollution, and climate change. The construction of artificial reefs offers a promising strategy to enhance oyster recruitment and mitigate population decline. However, the factors influencing oyster recruitment in artificial frameworks remain largely unclear, and it is still challenging to evaluate the effectiveness of different restoration methods. In this study, a series of oyster reef restoration experiments were conducted in the Tianjin coastal zone to identify key factors affecting recruitment success. These factors included restoration methods (shell string, mesh bag, and mesh cage), seeding with juvenile oysters, oyster shell orientation, and cultch hanging height. Our results indicated that the mesh bag method achieved the highest oyster settlement density in the intertidal zone, while the shell string method supported the fastest growth rates of oysters in the subtidal zone. The lower hanging height of cultches in the artificial frames increased oyster settlement density; however, hanging the cultches too close to the sediment negatively impacted oyster growth rates. Additionally, seeding with juvenile oysters and orienting the rough side of the shell upward enhanced recruitment performance. Oyster settlement density was greater in the intertidal zone (Bagua Shoal) compared to the subtidal zone (Dashentang), while oysters in the subtidal zone exhibited faster growth rates. Using redundancy analysis, the influence of environmental factors on the oyster recruitment performance was assessed. Oyster growth in the subtidal zone was positively correlated with dissolved oxygen and pH, whereas oyster settlement density in the intertidal zone was positively associated with water temperature, chlorophyll a concentration, and salinity. Finally, we evaluated the effectiveness of different restoration methods by considering factors including reef construction costs, oyster settlement abundance, average daily shell growth rate, water purification potential, and reef subsidence. Our results demonstrated that the shell string method was the most effective in the Dashentang subtidal zone, while the mesh bag method with oyster seeding was optimal in the Bagua Shoal intertidal zone. Our findings can provide valuable insights and guidance for oyster reef restoration projects.

Vulnerability of Grey Seal Pups (Halichoerus grypus) to Storm Disturbances in the Context of Climate Change: A British Isles Case Study - Keely Saville; Laetitia Nunny; Daniel Jarvis; Sue Sayer; Laszlo Talas; Mark P. Simmonds (Oceans, 2025)
Marine mammals may be particularly vulnerable to climate change. While some climate-change-induced impacts on these species have been recognised, the potential consequences of storminess have been less well-defined, and understanding of its significance largely relies on anecdotal evidence. To quantify the relationship between storminess and its possible impacts on grey seal pups (Halichoerus grypus), data from marine wildlife rescue databases and hospitalisation records (2015–2024) within the British Isles were examined (n = 20,686). Daily mean windspeed was used as a proxy for storminess. Significant relationships were found between storminess and pups presenting with malnourishment, head trauma, flipper injury, other wounds, and infections. This study provides the first empirical evidence of the explicit impacts of storminess on seal pup health, with all the presenting conditions increasing and higher rates of call-outs and pup admissions to rescue centres following stormy weather also recorded. Given the predicted increase in storm severity, these findings will aid rescue and rehabilitation planning by helping to predict when rescuers can anticipate increased admissions and the potential injuries that pups may experience following storms. The potential significance to the long-term conservation of the species is also highlighted.

Following the Food: Dynamic, Seasonal Changes in the Fine-Scale Distribution of Foraging Minke Whales Within a Scottish Marine Protected Area (MPA) - Duncan A. I. MacDougall; Kevin P. Robinson (Oceans, 2025)
Environmental heterogeneity is especially important in determining the distribution and spatial management of marine mammals. Intra-annual changes in distribution exhibited by highly mobile species such as baleen whales, however, present a challenge to traditional area-based management measures which should be accounted for in the designations, but these data are typically lacking. In the present study, we investigated the seasonal variables influencing the spatio-temporal distribution of feeding/foraging minke whales in the Southern Trench MPA in northeast Scotland. A presence–absence model was selected to determine the associations of feeding/foraging whales with areas of high prey density and other environmental determinants. Whale presence was strongly correlated with high burrowed sandeel density (BSD) in May and June and offshore thermal fronts (derived from the standard deviation of sea-surface temperature (SST SD)) from June to September. Both were concluded to be valuable proxies for the distribution of available prey and provided a compelling explanation for observed spatio-temporal shifts and high intraannual variability of whales from our long-term data. The present findings illustrate the value of prey data inclusion in habitat models for baleen whales on their feeding grounds, and advocate for a more dynamic, ecosystem-based approach to management for these highly mobile protected whales.

Wave Hindcast Correction Model Based on Satellite Data in the Azores Islands - Marta Gonçalves; C. Guedes Soares (Oceans, 2025)
This paper describes and implements a time-spatial correction of the regional prediction wave system, compared with altimeter data, by using an ensemble Kalman filter. The technique is successful in areas with substantial wave height around the Azores islands. Using winds from ERA5 and wave spectral boundary conditions from a prior study, the SWAN wave model generates wave conditions in the Azores area for 6 years. The time-spatial correction model is determined by comparing the hindcast data with the data from seven altimetry satellites: ERS-1, ERS-2, ENVISAT, TOPEX/POSEIDON, Jason-1, Jason 2, and GEOSAT Follow ON. The hindcast results are then corrected with the correction model. Furthermore, in situ buoy measurements are then employed to validate the corrected hindcast data. The outcomes demonstrate a significant improvement in the wave predictions.

Environmental Variables Influencing the Distribution of Penaeus Shrimp (Decapoda: Dendrobranchiata: Penaeidae) in a Subtropical Estuary of the Gulf of Mexico - Ayla Marisol Ayala-Cruz; Roberto Pérez-Castañeda; Zeferino Blanco-Martínez; Jesús Genaro Sánchez-Martínez; María de la Luz Vázquez-Sauceda; Flaviano Benavides-González; Jaime Luis Rábago-Castro (Oceans, 2025)
The habitat characteristics preferred by Penaeus shrimp inhabiting positive (freshwater-dominated) estuaries in North America have been scarcely investigated. Identifying the main environmental factors within the estuary that affect shrimp abundance is relevant to understanding habitat utilization within this particular nursery habitat. This study aimed to evaluate the distribution of penaeid shrimp species along the Soto La Marina River estuary (Northeastern Mexico), analyzing the influence of abiotic factors (water temperature, salinity, and dissolved oxygen) and submerged aquatic vegetation biomass on shrimp populations. A total of 1069 shrimp belonging to four penaeid species (Penaeus aztecus, P. duorarum, P. brasiliensis, and P. setiferus) were collected. Except for P. setiferus, the highest shrimp abundance was near the mouth of the estuary, where the highest salinity and seagrass biomass (Halodule wrightii) were recorded. Salinity and seagrass biomass were the main factors influencing penaeids’ spatial preferences along the estuary, showing significant positive relationships with shrimp abundance in most of the cases examined. Penaeus setiferus was the only species exhibiting peak abundance in an estuarine area devoid of aquatic vegetation (without seagrass or macroalgae) and with a significantly lower salinity level (ca. 22 ppt) than the levels recorded near the river mouth (ca. 28–32 ppt). Differences in osmotic capacity between the species, the protective function of seagrasses against currents, and their role as feeding and refuge habitats could explain the observed spatial distribution in the estuary.

Identification of Risk Patterns by Type of Ship Through Correspondence Analysis of Port State Control: A Differentiated Approach to Inspection to Enhance Maritime Safety and Pollution Prevention - Jose Manuel Prieto; David Almorza; Víctor Amor-Esteban; Juan J. Muñoz-Perez; Bismarck Jigena-Antelo (Oceans, 2025)
This study analyzes the results of Port State Control (PSC) inspections carried out under the Paris Memorandum of Understanding between 2018 and 2022. Through a correspondence analysis, the most frequent deficiencies were identified according to the type of ship being inspected. The study sample included 186,255 inspections obtained from the THETIS platform. The results revealed significant heterogeneity in deficiency profiles across ship types, highlighting specific patterns associated with each category. Container ships, oil tankers and bulk carriers, for instance, exhibited distinctive deficiency profiles. The study emphasizes the necessity for a tailored approach to PSC inspections, with the objective of optimizing resources through the utilization of risk zone indicators for the inspector. The identification of specific risk indicators would not only facilitate the work of inspectors but also enable the earlier detection of potential problems and more effective intervention. The study provides a solid foundation for future research and decision-making on PSC inspections, with the aim of enhancing maritime safety and pollution prevention.

Ecosystem Services in the Orbetello Lagoon: Estimate of Value and Possible Effects Due to Global Change - Eleonora Grazioli; Serena Anselmi; Irene Biagiotti; Emanuele Mancini; Marco Leporatti Persiano; Susanna Di Dio; Pietro Gentiloni; Stefano Cerioni; Monia Renzi (Oceans, 2025)
Coastal lagoons at the global scale occupy an area equivalent to 13% of continental coastlines and play a crucial role in multiple biogeochemical processes and their productivity. In these ecosystems, management choices are often suboptimal, partly due to insufficient understanding of the role of lagoons in the social and economic well-being of the communities that depend on them. The multidisciplinary approach utilized in this study to assess the ecosystem services associated with the Orbetello Lagoon enabled the determination of the value this habitat holds concerning the functioning of anthropogenic activities adjacent to the lagoon. To this end, the ecosystem services provided by the Orbetello Lagoon were defined, described, and quantified in 3.8 Mil of euro. To ascertain the specific ecosystem services, it was necessary to quantify the Natural Capital and Natural Flows that regulate the lagoon, following a protocol for the collection and organization of existing knowledge about the area and identifying knowledge gaps. The density of the benefit flow, amounting to 50.000 €/year/m2 closely depends on high cultural services and is influenced by regulating ones. Once the ecological and economic value of the Orbetello Lagoon was established, a bibliographic review was conducted to investigate the possible repercussions of major drivers related to climate change on ecosystem services.

Pre-Design Selection of the Rated Power of a Heaving Point Absorber Wave Energy Converter - Guilherme Moura Paredes; Alexandra Tokat; Torbjörn Thiringer (Oceans, 2025)
Wave energy converters (WECs) have significant potential for renewable energy generation, but early-stage design processes often require lengthy simulations. This study focuses on the pre-design selection of the rated power for a heaving point-absorber WEC. Addressing the gap in simplified methodologies, this study evaluates the wave energy resource, selects operational sea-states, and assesses device performance using time-domain simulations and linear potential flow theory. The results revealed that a WEC rated at 87% below peak power can capture 91% of the total available energy, achieving a balance between energy efficiency and cost-effectiveness. Furthermore, a simplified method to estimate rated power based on a constant ratio between mean and RMS power is proposed, offering significant potential for early-stage design applications. Future work should validate this approach across diverse WEC types and wave climates.

Larval Dispersal of Gray Snapper (Lutjanus griseus) on the West Florida Shelf - Eric Bovee; Debra J. Murie; Ana C. Vaz (Oceans, 2025)
Gray snapper (Lutjanus griseus) move from inshore to offshore habitats as they mature and spawn along the West Florida Shelf. The connectivity between offshore spawning sites and inshore settlement regions along the Eastern Gulf of America (formerly Gulf of Mexico, hereafter Gulf) coast is unknown, and this study therefore predicted these larval dispersal pathways. To determine larval transport, an ocean model was integrated with the Connectivity Modeling System (CMS), which is a biophysical model that allowed for the inclusion of larval behavior and updated spawning information for the gray snapper. Our larval dispersal model showed that spawning sites offshore of Tampa, in the Florida Keys, and in the Florida Middle Grounds had the highest percentages of successfully settled larvae inshore. Larvae that were spawned at the offshore Tampa Bay and offshore Southwest Florida spawning sites were mostly transported to the Tampa Bay and Southwest Florida settlement regions, showing local retention. In contrast, larvae spawned offshore in the Florida Middle Grounds were transported northwest, exclusively to the Florida Panhandle. In addition, there was no difference in the proportion of successful larval settlers between full and new moon spawning events. Since gray snapper are an important recreational fishery in the eastern Gulf, especially off the west coast of Florida, it is important to identify spawning sites that have the largest proportions of settling larvae, such as offshore Tampa Bay.

Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans, 2025)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.

Numerical Study of Barotropic Circulation in the Gulfs of Patras and Corinth System - Alexandra G. Aspioti; Nikolaos Th. Fourniotis (Oceans, 2025)
In this paper, the barotropic circulation in the gulfs of the Patras and Corinth system in Greece is numerically studied. This semi-enclosed hydrodynamic system is simulated as a unified basin, based on 3D simulations using the MIKE 3 Flow Model FM (HD). The wind and tide-induced flow, as well as their combined action, were examined in the whole basin of the system. Based on the numerically predicted results, salient features of the flow were highlighted, while different energetic zones concerning the hydrodynamic response of the system were specified. The tide propagation was studied in detail showing an increase in tidal amplitude up to 85% at the western entrance of the Gulf of Corinth. In addition, geophysical flow characteristics, surface eddies, and the current field as well as the vertical and horizontal structure of the flow in the gulfs’ system were calculated. Moreover, the effect of wind and tide on the exchange flowrate between the two gulfs and the response of the basin after a wind break were studied for typical wind speeds and directions.

Resident Harbor Porpoises (Phocoena phocoena vomerina) in the Salish Sea: Photo-Identification Shows Long-Term Site Fidelity, Natal Philopatry, and Provides Insights into Longevity and Behavior - Cindy R. Elliser; Katrina H. White; Maia C. Hansen (Oceans, 2025)
Harbor porpoises have been well studied in locations worldwide, but relatively little research has focused on site fidelity of individuals, which influences population structure and determines appropriate management and conservation measures. This study investigated the site fidelity and behavior of harbor porpoises through long-term, land-based photo-identification around Fidalgo Island, Washington, USA. Individuals were consistently re-sighted for up to 11 years, including natal philopatry. There was individual variation in seasonal site fidelity, with some individuals seen year-round, though general porpoise presence in the study area and individual re-sightings were greatly reduced during summer. Females had calves yearly for up to 3 consecutive years, with females as old as at least 14 successfully producing calves. There was some evidence for mother–calf associations post-weaning, but none long-term. Behavior was affected by tide, where porpoises traveled more and foraged and socialized less during ebb tide compared to other tidal states. Mating attempts with aerial behaviors were observed 84 times and seen year-round in every month and every season. This study provides documentation of a local, resident population of harbor porpoise, and emphasizes the need for more fine-scale studies like this to ensure the appropriate management and conservation of harbor porpoise populations and/or stocks worldwide.

Surficial Sediment Distribution in a Complex Marine Setting—The Example of Coastal and Open Sea Areas of Evia Island, Central Aegean, Greece - Irene Zananiri; Ioannis Vakalas (Oceans, 2025)
This study examines sediment distribution patterns in the Aegean Sea, focusing on the western coast of Evia Island and the southern Evoikos and Petalioi Gulfs. A total of 200 granulometric data points were analyzed to evaluate textural characteristics, including mean grain size, sorting, and skewness. The findings reveal significant variation in mean grain size: finer sediments (ϕ = 5–8) dominate the northern Aegean near Skyros, while coarser sands (ϕ = 2–4) are prevalent in the South Evoikos and Petalioi gulfs. The coarsest materials (ϕ = 0–2) are found around Chalkis, with sorting generally poor except in those two areas. Negative skewness values in the northern part of the study area indicate a predominance of finer particles, while southern regions exhibit slightly positive skewness, suggesting a greater proportion of coarser grains. Complex net transport patterns between Evia and Skyros are influenced by north-northeast trending water currents from the northern Aegean, with fluvial influx observed in the southern Evia coastal area. Around Skyros, the interplay of water currents and prevailing north-northwest winds dictates the orientation of net transport vectors. In the Evoikos gulfs, sediment movement aligns with a general northward flow, featuring coarse sediments in the Petalioi Gulf and muddy deposits in the narrower northern segment, where minimal transport indicates stagnant conditions. Coarse-grained materials in North Evoikos are primarily influenced by strong tidal activity.

IchthyNet: An Ensemble Method for the Classification of In Situ Marine Zooplankton Shadowgraph Images - Brittney Slocum; Bradley Penta (Oceans, 2025)
This study explores the use of machine learning for the automated classification of the ten most abundant groups of marine organisms (in the size range of 5–12 cm) plus marine snow found in the ecosystem of the U.S. east coast. Images used in this process were collected using a shadowgraph imaging system on a towed, undulating platform capable of collecting continuous imagery over large spatiotemporal scales. As a large quantity (29,818,917) of images was collected, the task of locating and identifying all imaged organisms could not be efficiently achieved by human analysis alone. Several tows of data were collected off the coast of Delaware Bay. The resulting images were then cleaned, segmented into regions of interest (ROIs), and fed through three convolutional neural networks (CNNs): VGG-16, ResNet-50, and a custom model created to find more high-level features in this dataset. These three models were used in a Random Forest Classifier-based ensemble approach to reach the best identification fidelity. The networks were trained on a training set of 187,000 ROIs augmented with random rotations and pixel intensity thresholding to increase data variability and evaluated against two datasets. While the performance of each individual model is examined, the best approach is to use the ensemble, which performed with an F1-score of 98% and an area under the curve (AUC) of 99% on both test datasets while its accuracy, precision, and recall fluctuated between 97% and 98%.

The Effects of Heat Stress on the Physiology and Mortality of the Rhizostome Upside-Down Jellyfish Cassiopea xamachana—Observations Throughout the Life Cycle - William K. Fitt; Dietrich K. Hofmann; Aki H. Ohdera; Dustin W. Kemp; André C. Morandini (Oceans, 2025)
This study was designed to investigate the impact of heat stress on the physiological changes and mortality rates of different life stages of the rhizostome jellyfish species Cassiopea xamachana, including planula larvae, scyphistomae (polyps), and medusae. Both larval and scyphistoma stages of C. xamachana are relatively tolerant to high temperatures, but both experience nearly 100% mortality at 36 °C. Increasing temperatures also induced stage-specific effects. Settlement rates of artificially induced larvae were near 100% at lower temperatures but decreased at 34–36 °C; larvae were dead at 36 °C. When scyphistomae of C. xamachana were subjected to a gradual increase in temperature from 28 to 38 °C, polyp size declined steadily in starved animals, with animals showing clear signs of temperature stress between 35 and 36 °C. Small medusae of C. xamachana pulsed more than larger medusae and tended to have peak pulse rates at higher temperatures (~35 °C) compared to larger medusae (~29–33 °C), though the latter was not significant. At a temperature of 39 °C, all the medusae exhibited signs of heat stress, including pulsing erratically (generally lower) rather than steady rhythmic pulsations, releasing copious amounts of mucus, and having withdrawn oral arms. Temperature data presented here, and in the literature, show that pulsing C. xamachana medusae exhibit a bell-shaped curve, with temperatures over 38 °C being detrimental and becoming lethal at 40 °C. Based on the findings of this study, it is proposed that the medusa stage of C. xamachana has a higher tolerance for elevated temperatures compared to both the larvae and the polyps. Predictions of global climate change indicate that populations of C. xamachana will likely face longer and hotter summer periods, leading to increased population sizes. However, higher temperatures pose a greater risk to the survival of the species as they increase mortality in the polyp and larval stages compared to the medusa stage.

Locally Adapted Coral Species Withstand a 2-Week Hypoxic Event - Noelle Lucey; Carolina César-Ávila; Alaina Eckert; Paul Veintimilla; Rachel Collin (Oceans, 2025)
One approach to improve long-term coral restoration success utilizes naturally stress-tolerant corals from the wild. While the focus has primarily been on thermal stress, low oxygen is a growing threat to coral reefs and restoration efforts should also consider hypoxia tolerance. Here we determine if Siderastrea siderea and Agaricia tenuifolia populations from a reef with a historical record of low oxygen exhibit evidence of local adaptation to hypoxic events, compared to populations from a reference reef. We employed a laboratory-based reciprocal transplant experiment mimicking a severe 14-night hypoxic event and monitored bleaching responses, photo-physiology, metabolic rates, and survival of all four populations during, and for two weeks following the event. In both species, we found the populations from the hypoxic reef either fully persisted or recovered within 3 days of the event. In contrast, the conspecific naïve populations from the well-oxygenated reference reef experienced bleaching and death. This showcases the vulnerability of naïve corals exposed to low oxygen but also suggests that corals from the hypoxic reef locally adapted to survive severe episodic hypoxia. Other reefs with past episodic low oxygen may also be home to corals with adaptation signatures to hypoxia and may be useful for restoration efforts.

Conservation Attitudes and Perceived Biodiversity Among Divers on the Spanish Mediterranean Coast: Insights from Local Ecological Knowledge - Victor Garcia-Bustos (Oceans, 2025)
The Mediterranean Sea, a global biodiversity hotspot, faces significant threats that compromise its ecological health. While Marine Protected Areas (MPAs) play a crucial role in biodiversity conservation, their effectiveness is debated, and empirical data on their impact remain limited. This study evaluates the utility of Local Ecological Knowledge (LEK) from divers along the Spanish Mediterranean coast to assess perceived abundance of sentinel species in both MPAs and non-protected areas, in relation to empirical data, alongside divers’ attitudes toward ocean threats and conservation strategies. Divers perceived higher abundance and subjective health indicators of key species, such as Posidonia oceanica, octocorals, and top predators within MPAs, which aligns with empirical evidence supporting MPA effectiveness in conserving biodiversity and mitigating human disturbances. Notably, divers showed knowledge gaps, particularly underestimating climate change impacts while overemphasizing pollution threats. Diver education emerged as a critical factor in shaping conservation attitudes, with higher education levels correlating with increased environmental awareness and stronger support for conservation measures. This study underscores the potential of leveraging LEK in marine conservation strategies while acknowledging limitations related to self-reported data and regional specificity, advocating for expanded geographic scope and integration with empirical data in future research.

Economic Impacts of Disasters and Economic Events on Commercial Fishery—The Case of Mississippi Blue Crabs - Benedict C. Posadas (Oceans, 2025)
Impact assessments are necessary for supporting fisheries’ disaster applications and management options for states affected by disasters. This paper measures the joint and individual impacts of man-made and natural disasters, global pandemics and recessions, the U.S.-China trade war, and recent increases in fuel prices on commercial dockside values of the Mississippi blue crab fishery. The mean-difference model estimates the direct impacts when the current dockside values fall below the benchmark values. The marine economic recovery model identifies the significant determinants of the variations in the dockside values. Mean-difference model results indicate that the Mississippi blue crab fishery sustained direct losses due to Hurricane Katrina in 2005, the Deepwater Horizon oil spill in 2010, and the opening of the Bonnet Carre Spillway in 2011. The estimated marine economic recovery model explained 93 percent of the variations in real dockside values. Two independent variables are statistically significant, including blue crab landings and time. The disaster variables have the expected signs but are not statistically significant. These methodologies’ usefulness is applicable in assessing the direct impacts on fisheries and other economic sectors affected by disasters such as major hurricanes, oil spills, massive freshwater intrusion, and harmful algal blooms.

Ecological Condition of the Benthos in Milford Haven Waterway: the Centre of the UK’s Oil and Gas Industry in an Area of High Conservation Value - Richard M. Warwick; James R. Tweedley; Michael Camplin; Blaise Bullimore (Oceans, 2025)
This study determined the environmental condition of the benthos of Milford Haven Waterway, an area that is arguably the most vulnerable in the UK to anthropogenic activities, including the potential effects of a major oil spill in 1996, using historical data on the macrobenthos more than a decade later in 2008, 2010 and 2013. These data show a gradual decline in numerous univariate diversity measures from the outer (marine) to inner (estuarine) stations. Taxonomic distinctness generally falls within the expected range, and most stations have above-average values compared with other monitoring stations around the UK. The W-statistics for Abundance/Biomass Comparison (ABC) plots are usually strongly positive and never negative. There was a sequential change in community composition from the outer to inner stations, which was strongly related to salinity, and, to a lesser extent, sediment granulometry. None of the species regarded as indicators of organic pollution were prominent in the macrobenthic community of Milford Haven Waterway. On this basis, although there are some slight indications of environmental perturbation at particular sites in certain years, it can be concluded that the benthic communities of Milford Haven Waterway are in a healthy state. This study provides a baseline against which the potential effects of any future environmental accidents and/or the increased industrial development can be assessed.

The Cultural Heritage Framework Programme: Highlighting the Contribution of Marine Cultural Heritage to the UN Decade of Ocean Science for Sustainable Development (2021–2030) - Jon Henderson; Georgia Holly; Arturo Rey da Silva; Athena Trakadas (Oceans, 2024)
This paper considers the importance of including Marine Cultural Heritage (MCH) in the UN Decade of Ocean Science for Sustainable Development (2021–2030) in order to fully address the challenges facing the health of our oceans. It outlines the aims and objectives of the Cultural Heritage Framework Programme (CHFP), an official action of the UN Decade of Ocean Science and the only one that specifically deals with cultural heritage. The role of MCH in the Decade is discussed, and its under-appreciation in the UNESCO Cultural Conventions is outlined. The paper then presents the activities of the CHFP, discussing the main themes identified to date, and finishes by outlining the initiative’s next steps.

Trade-Offs in Marine Policy Decisions Through the Lens of Literature - Joyce Dias Gois Rodrigues de Queiroz; Débora Gutierrez; Helena Maria Gregório Pina Calado (Oceans, 2024)
The ocean is increasingly affected by the rise in maritime activities. Increased anthropogenic pressures have led to environmental impacts and also intensified competition for space and resources among various socioeconomic sectors. To mitigate these impacts on marine ecosystems and reduce conflicts, management tools and processes such as marine protected areas (MPAs) and maritime spatial planning (MSP) have become more prevalent. Trade-offs are inherent to these, and necessary to meet specific conservation and socioeconomic goals. In response, understanding and managing these trade-offs has become crucial to achieving ocean sustainability. This study performs a bibliometric review to identify the types of trade-offs discussed in the marine literature and examines their operationalization for the conservation and sustainable use of marine resources. The analysis reveals that trade-offs, particularly those between conservation and development, and the interests of specific stakeholders, are most frequently addressed in the trade-off literature and are typically approached through integrative methods. This comprehensive examination highlights the significance of recognizing and addressing trade-offs to achieve effective marine management and conservation, aligning ecological integrity with socioeconomic interests.

Growth, Filtration and Respiration Under Superfluous Feeding in Single-Osculum Halichondria panicea Sponges - Lars Kumala; Hans Ulrik Riisgård (Oceans, 2024)
Filter-feeding sponges capture suspended food particles from ambient water, but little is known about the response of sponges to high food concentrations causing superfluous feeding. Here, through several experimental assays, we studied the relationship between algal concentration in the water column, filtration rate, respiration rate, and specific growth rate in single-osculum Halichondria panicea demosponge explants. Laboratory experiments showed that sponge explants filter the ambient seawater at a maximum rate when exposed to naturally (low) algal concentrations, whereas high algal concentrations resulted in superfluous feeding and reduced filtration rates. Explants maintained at algal concentrations above the incipient overloading concentration level showed that growth rates were in fair agreement with the maximum possible weight-specific growth rate of about 4% d−1. Although the filtration rate became reduced due to overloading, the oxygen extraction efficiency increased, and therefore superfluous feeding did not cause reduced growth. This suggests that H. panicea and probably other sponges have adapted to low algal concentrations, displaying continuous maximum filtration rates. Osculum closure reflects a protection mechanism rather than a physiological regulatory response to high algal concentrations.

Growth Rates and Specific Aminoacyl-tRNA Synthetases Activities in Clupea harengus Larvae - Inma Herrera; Lidia Yebra; Ángelo Santana-del-Pino; Santiago Hernández-León (Oceans, 2024)
Gaining robust in situ estimates of the growth rate of marine fish larvae is essential for understanding processes controlling year-class success and developing sustainable management strategies to maintain good environmental status. We measured the growth rate of Atlantic herring (Clupea harengus) larvae in the laboratory and compared it to the activity of aminoacyl-tRNA synthetases (AARS). Larvae were reared under controlled conditions for 20 days at three temperatures (7, 12, and 17 °C) using different prey concentrations (0.1, 0.3, and 2 prey·mL−1) of the copepod Acartia tonsa. The relationship between specific growth rates (SGR) and specific AARS activities was best described by a linear function—SGR = −0.1031 + 0.0017 · spAARS, r2 = 0.71, p < 0.05—when only larvae fed ad libitum were considered regardless of the temperature. When larvae fed with low concentrations of food were included in the analysis, the relationship was SGR = −0.0332 + 0.0010 · spAARS, r2 = 0.42, p < 0.05. This latter slope was rather low compared to other studies performed in zooplankton. We suggest protein degradation during the early life stages of fish as the cause of this low slope. We also studied SGR under food deprivation and the effect on specific AARS activities. We found rather high specific AARS activities in small individuals of early stages of fish, also suggesting protein degradation. Further research about protein degradation and turnover rates is needed in order to use AARS activity as a proxy for growth rates in field-caught larvae.

Exploring Mesozooplankton Insights by Assessing the Ecological Status of Black Sea Waters Under the Marine Strategy Framework Directive - Elena Bisinicu; Luminita Lazar (Oceans, 2024)
Mesozooplankton are highly responsive to environmental changes, making their population dynamics and species composition important indicators of large-scale oceanic conditions. This study investigates the mesozooplankton composition, emphasizing biomass values across all three marine reporting units in the Romanian Black Sea from 2013 to 2020, covering 45 stations that represent transitional, coastal, and marine waters during the warm season. It also examines environmental parameters, such as temperature, salinity, and nutrient levels associated with eutrophication, that impact the mesozooplankton, as well as the environmental status of the pelagic habitat in this region, influenced by various hydrological and anthropogenic factors. Statistical analyses, including multivariate methods, were employed to investigate correlations between mesozooplankton biomass and environmental parameters, facilitating ecological assessments in accordance with the Marine Strategy Framework Directive (MSFD) Descriptors 1 (Biodiversity) and 5 (Eutrophication) using indicators such as Mesozooplankton bBiomass, Copepoda Biomass, and Noctiluca scintillans iomass. The results indicated that Mesozooplankton and Copepoda Biomass did not reach good ecological status (GES). However, the Noctiluca scintillans Biomass indicator demonstrated that all marine reporting units achieved GES during the warm seasons. These findings underscore the dynamic nature of pelagic habitats and highlight the importance of ongoing monitoring to inform policy and conservation efforts.

Characterization of Epoxy Adhesive for Marine Applications - Francisco J. Rodríguez-Dopico; A. Álvarez García; Javier Tarrío-Saavedra (Oceans, 2024)
The shipping industry faces the challenge of expanding its capabilities and mitigating its environmental impact. The utilization of adhesive bonding techniques has the potential to facilitate the construction of lighter ships with a reduced carbon footprint. In this work, a complete methodology has been established to study the properties of an adhesive bond between naval steel and the behavior of the bulk adhesive when introduced into seawater. Thermogravimetric analysis (TGA) has been used to determine the thermal properties. Single-lap-joint and tensile tests have been performed showing the negative influence of temperature on the mechanical properties. Seawater absorption has been studied by gravimetric tests. Differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and mechanical bulk tests have been carried out before and after aging. The water absorption is Fickian, and when a constant load is applied, the absorption occurs faster and in greater quantity, decreasing the stiffness and strength. An increase in the glass transition temperature was observed in the absence of a load, with no discernible change upon the application of load condition. Also, aged specimens with constant load exhibited a reduction in water content. These phenomena may be attributed to several diffusion processes.

Integrating Hydrodynamic Modeling with Ecological Risk Assessment for Selecting Sites for Artificial Reef Deployment: Avoiding Coastal Pollution Risks in Kish Island, Persian Gulf - Shadan Nasseri Doust; Mehrnoosh Abbasian; S. Abbas Haghshenas; Michael J. Risk; Craig A. Downs (Oceans, 2024)
The decline of natural coral reefs has spurred interest in artificial reef construction and reef rehabilitation efforts. However, many restoration programs are failing because of poor water quality and localized pollution factors. This paper examines one etiology of coral restoration failure, highlighting the need for careful site selection based on hydrodynamic, biological, and pollution criteria. Using Kish Island as a case study, we outline a procedure for determining placement of artificial reefs to minimize external pollution impacts, which could be applied to any reef site worldwide. Our integration of computational modeling and geographic information systems enables the tracking of pollution dispersion and increases the power of restoration efforts. The RQ Plume modeling, used alongside compound pollutant modeling, can identify hotspots with the highest potential to degrade marine environments, particularly reefs. Conservation efforts should prioritize pollution mitigation, as seen in the case of sunscreen pollutants at Kish Island, where regulatory action and public education can contribute to reef protection. This comprehensive approach underscores the critical role of water quality in successful reef restoration and conservation strategies.

Seagrass-Associated Biodiversity Influences Organic Carbon in a Temperate Meadow - Lowri O’Neill; Bettina Walter; Richard K. F. Unsworth (Oceans, 2024)
There is increasing interest in the role that seagrasses play in storing carbon in the context of climate mitigation, but many knowledge gaps in the factors controlling this storage exist. Here, we provide a small case study that examines the role of infaunal biodiversity in influencing seagrass and the carbon stored in its sediments. A total of 25 species of invertebrate were recorded in an intertidal Zostera marina meadow, where these species were dominated by polychaete worms with no bivalves present. We find organic carbon storage (within the top 20 cm) measured by AFDW to be highly variable within a small area of seagrass meadow ranging from 2961 gC.m−2 to 11,620 gC.m−2 with an average (±sd) of 64602 ± 3274 gC.m−2. Our analysis indicates that infaunal communities are significantly and negatively correlated with this sediment organic carbon. However, this effect is not as influential as hypothesised, and the relatively small sample size of the present study limits its ability to provide strong causality. Other factors, such as algal abundance, curiously had a potentially stronger influence on the carbon in the upper sediments. The increasing richness of infauna is likely reducing the build-up of organic carbon, reducing its ecosystem service role. We believe this to likely be the result of bioturbation by specific species such as Arenicola marina and Ampharete acutifrons. A change in sediment organic carbon suggests that these species could be key drivers of bioturbator-initiated redox-driven organic matter turnovers, influencing the microbial processes and remobilizing sediment compounds. Bioturbators should be considered as a limitation to Corg storage when managing seagrass Corg stocks; however, bioturbation is a natural process that can be moderated when an ecosystem is less influenced by anthropogenic change. The present study only provides small-scale correlative evidence with a range of surprising results; confirming these results within temperate seagrasses requires examining this process at large spatial scales or with targeted experiments.

The Impact of Perfluorooctanoic Acid (PFOA) on the Mussel Mytilus galloprovincialis: A Multi-Biomarker Evaluation - Sandra Copeto; Sara Ganço; Inês João Ferreira; Didier Sanchez; Maria João Nunes; Carla Motta; Marco Silva; Mário Diniz (Oceans, 2024)
Perfluorooctanoic acid (PFOA) has been widely studied due to its environmental persistence and bioaccumulation potential, raising concerns about its effects on aquatic life. This research evaluates the impact of PFOA on the antioxidant defenses and stress response systems of the mussel Mytilus galloprovincialis. Mussels were exposed to three concentrations of PFOA (1, 10, and 100 µg·L−1) over 28 days. Several biomarkers, including glutathione S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), lipid peroxidation (LPO), total antioxidant capacity (TAC), vitellogenin (VTG), ubiquitin (UBI), and caspase-3 (CASP) were analyzed. The results suggest stress responses, particularly in animals exposed to higher concentrations, as shown by GST and SOD activities which increased according to PFOA concentrations. Additionally, oxidative stress markers such as MDA and CAT showed variable responses depending on the exposure concentration tested. This study underscores the need for further investigation into the effects of PFOA on mollusks but also the need to unveil gender-specific responses in aquatic organisms exposed to this contaminant. The concentrations of PFOA used in our research are lower than those examined in previous studies, providing crucial insights into the impacts of even minimal exposure levels. It highlights the potential of M. galloprovincialis as a bioindicator in environmental monitoring programs, providing crucial insights for environmental management and policymaking regarding regulating and monitoring PFOA in marine settings. Consequently, in a country where seafood consumption is the second largest in Europe, implementing environmental policies and regulatory measures to manage and monitor PFOA levels in marine environments is crucial.

Characterizing the Tropical Cyclones Activity over Arabian Sea (1982–2021) - Abdulhaleem H. Labban; H. M. Hasanean; Ali Almahri; Ali Salem Al-Sakkaf; Mahmoud A. A. Hussein (Oceans, 2024)
The current study looks at how the characteristics of Arabian Sea tropical cyclones (TCs) change over time. The results show that in the pre-monsoon (April–June) and the post-monsoon (October–December), the activity of TCs > 34 knots, including cyclonic storm (CS), severe cyclonic storm (SCS), very severe cyclonic storm (VSCS), extreme severe cyclonic storm (ESCS), and super cyclonic storm (Sup. CS), has significantly increased, while the tendency of TCs < 34 knots, depressions and deep depressions (Ds) over the Arabian Sea has only slightly increased. Most of the TC activity in the first two decades (1982–2001) over the Arabian Sea activated on the eastern side, while in the last two decades (2002–2021), there was an expansion toward the southwest region of the Arabian Sea, especially in the post-monsoon season. The composite analysis of environmental parameters over the Arabian Sea reveals that the negative anomalies of outgoing longwave radiation (OLR) and the positive anomalies of relative humidity at 500 hPa (RH–500 hPa) in the first decade (1982–1991) and the second decade (1992–2001) are more concentrated on the eastern side of the Arabian Sea, leading to increased activity for TCs. Decades three (2002–2011) and four (2012–2021) demonstrated a wide distribution of weak vertical wind shear (VWS) and strong convection (OLR and RH–500 hPa) over the Arabian Sea basin. This led to TCs occurring more frequently and stronger, especially in the post-monsoon season. SST over the Arabian Sea was sufficient for tropical storm activity (≥26.5 °C) for both typical seasons.

Inventory of Shallow-Water Fouling Invertebrates of Long Island, New York - Ezra Roesch; Jack H. Rosencrans; Kent A. Hatch; Robert W. Thacker (Oceans, 2024)
Invasive marine invertebrates are increasingly recognized as a potential disturbance to coastal ecosystems. We sought to better document the taxonomic composition of subtidal communities around Long Island to obtain a baseline that can be used to monitor current and future invasions of non-indigenous species. We placed settlement blocks at 18 sites along the coast of Long Island, New York, for three months. After recovering blocks at 12 sites, we analyzed the taxonomic composition of fouling communities on the blocks. We observed 64 invertebrate and 3 algal taxa, with large variation in taxon richness among sites. Multivariate analyses revealed that although taxon composition was significantly dissimilar between north and south shores, variation in dissimilarity did not differ significantly between shores. The high variability in taxon composition observed among sites indicates that additional research is needed to expand our knowledge of invertebrate diversity in the waters surrounding Long Island. Adding more sites and replicate blocks within sites could improve future sampling designs. This research will benefit continuing efforts to monitor, manage, and prevent the establishment of marine invasive species.

The Advantages of Combining Morphological and Molecular Methods to Characterise Zooplankton Communities: A Case Study of the UNESCO Biosphere Reserve of the Berlengas Archipelago, Portugal - Marco Simões; Sónia Cotrim Marques; Cátia Costa; Maria da Luz Calado; Jorge Lobo-Arteaga; Cátia Bartilotti; Maria Jorge Campos; Sérgio Miguel Leandro; Agostinho Antunes (Oceans, 2024)
Understanding the ecological dynamics of zooplankton communities is crucial to precisely assessing the health of marine ecosystems and their management. Metabarcoding has contributed to a better understanding of biodiversity in marine environments. However, this methodology still requires protocol optimisation. Here, we used a complementary approach combining molecular and morphological identification methods to identify the zooplankton community inhabiting the Berlengas Archipelago, Portugal. The presence of non-indigenous species was also assessed. The results showed that the metabarcoding approach outperformed the classical morphological identification method, detecting more species with higher resolution. Nevertheless, the classical method was able to identify species that were not detected by the molecular approaches, probably due to a lack of reference data in the databases. The comparison between different molecular approaches showed that COI and bulk DNA gave better results than 18S rRNA and eDNA by detecting higher species diversity. However, complementarities were observed between them. Molecular tools also proved effective in identifying several potential non-indigenous species, identifying, for the first time, several potentially unreported NIS inhabiting the Portuguese marine ecosystems. Overall, our results confirmed the importance of combining both classical and molecular methods to obtain a more refined assessment of the zooplanktonic communities in marine environments.

Vertical Shear, Diapycnal Shear and the Gradient Richardson Number - Josep L. Pelegrí; Mariona Claret; Pablo Sangrà (Oceans, 2024)
In Cartesian coordinates x,y,z, the gradient Richardson number Ri is the ratio between the square of the buoyancy frequency N and the square of the vertical shear S, Ri=N2/S2, where N2=−g/ρ ∂ρ/∂z and S2=∂u/∂z2+∂v/∂z2, with ρ potential density, u,v the horizontal velocity components and g gravity acceleration. In isopycnic coordinates x,y,ρ, Ri is expressed as the ratio between M2≡N−2 and the squared diapycnal shear Sρ2=ρ/g2∂u/∂ρ2+∂v/∂ρ2, Ri=M2/Sρ2. This could suggest that a decrease (increase) in stratification brings a decrease (increase) in dynamic stability in Cartesian coordinates, but a stability increase (decrease) in isopycnic coordinates. The apparently different role of stratification arises because S and Sρ are related through the stratification itself, Sρ=S/N2. In terms of characteristic times, this is equivalent to τ≡Sρ=to2/td, which is interpreted as a critical dynamic time τ that equals the buoyancy period to≡N−1 normalized by the ratio td/to, where td=S−1 is the deformation time. Here we follow simple arguments and use field data from three different regions (island shelf break, Gulf Stream and Mediterranean outflow) to endorse the usefulness of the isopycnal approach. In particular, we define the reduced squared diapycnal shear σρ2=Sρ2−M2 and compare it with the reduced squared vertical σ2=S2−N2, both being positive (negative) for unstable (stable) conditions. While both Ri and σ2 remain highly variable for all stratification conditions, the mean σρ2 values approach Sρ2 with increasing stratification. Further, the field data follow the relation σρ2=1−Ri/N2Ri, with a subcritical Ri=0.22 for both the island shelf break and the Mediterranean outflow. We propose σρ2 and Sρ2 to be good indexes for the occurrence of effective mixing under highly stratified conditions.

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

The Effects of Elevated Temperatures on the Reproductive Biology of a Mediterranean Coral, Oculina patagonica - Tamar Shemesh; Shani Levy; Abigail Einbinder; Itai Kolsky; Jessica Bellworthy; Tali Mass (Oceans, 2024)
Global climate change is profoundly impacting coral ecosystems. Rising sea surface temperatures, in particular, disrupt coral reproductive synchrony, cause bleaching, and mortality. Oculina patagonica, a temperate scleractinian coral abundant across the Mediterranean Sea, can grow at a temperature range of 10–31 °C. Studies conducted three decades ago documented this species bleaching during the summer months, the same time as its gonads mature. However, the Eastern Mediterranean Sea is experiencing some of the fastest-warming sea surface temperatures worldwide. This study repeated the year-round in situ assessment of the reproductive cycle and gonad development and correlation to summer bleaching. In addition, thermal performance of the holobiont was assessed in an ex situ thermal stress experiment. In situ monitoring revealed no temporal changes in gonad development compared to previous studies, despite sea surface warming and concurrent bleaching. Experimental thermal performance curves indicated that photosynthetic rate peaked at 23 °C, bleached coral area was significant at 29 °C, and peaked at 34 °C. With local sea surface temperature reaching 31 °C, O. patagonica is exposed beyond its bleaching threshold during the summer months in situ. Despite this, O. patagonica maintains gonad development and physiologically recovers at the end of summer demonstrating resilience to current warming trends.

Determination of Submerged Breakwater Efficiency Using Computational Fluid Dynamics - Smiljko Rudan; Šimun Sviličić (Oceans, 2024)
Wind-induced waves can lead to the partial or complete wash-over of beaches, causing erosion that impacts both the landscape and tourist infrastructure. In some regions of the world, e.g., Croatia, this process, which usually occurs during a harsh winter, has a major impact on the environment and the economy, and preventing or reducing this process is highly desirable. One of the simplest methods to reduce or prevent beach erosion is the use of innovative underwater structures designed to decrease wave energy by reducing wave height. In this study, submerged breakwaters are numerically investigated using various topologies, positions, and angles relative to the free surface. Not only is the optimal topology determined, but the most efficient arrangement of multiple breakwaters is also determined. The advantage of newly developed submerged breakwaters over traditional ones (rock-fixed piers) is that they do not require complex construction, massive foundations, or high investment costs. Instead, they comprise simple floating bodies connected to the seabed by mooring lines. This design makes them not only cheap, adaptable, and easy to install but also environmentally friendly, as they have little impact on the seabed and the environment. To evaluate wave damping effectiveness, the incompressible computational fluid dynamics (ICFD) method is used, which enables the use of a turbulence model and the possibility of accurate wave modelling.

Trajectory Planning of a Mother Ship Considering Seakeeping Indices to Enhance Launch and Recovery Operations of Autonomous Drones - Salvatore Rosario Bassolillo; Egidio D’Amato; Salvatore Iacono; Silvia Pennino; Antonio Scamardella (Oceans, 2024)
This research focuses on integrating seakeeping indices into the trajectory planning of a mother ship in order to minimize risks during UAV (unmanned aerial vehicle) takeoff and landing in challenging sea conditions. By considering vessel dynamics and environmental factors, the proposed trajectory planning algorithm computes optimal paths that prioritize the stability and safety of the ship, mitigating the impact of adverse weather on UAV operations. Specifically, the new adaptive weather routing model presented is based on a genetic algorithm. The model uses the previously evaluated response amplitude operators (RAOs) for the reference ship at different velocities and encounter angles, along with weather forecast data provided by the global wave model (GWAM). Preliminary evaluations confirm the effectiveness of the presented model in significantly improving the reliability of autonomous UAV operations from a mother ship across all encountered sea state conditions, particularly when compared with a graph-based solution. The current results clearly demonstrate that it is possible to achieve appreciable improvements in ship seakeeping performance, thereby making UAV-related operations safer.

An Unexpected Small Biodiversity Oasis of Sea Slugs (Mollusca, Gastropoda, Heterobranchia) in the Largest Petrochemical Hub of Italy (Central Mediterranean) - Andrea Lombardo; Giuliana Marletta (Oceans, 2024)
The Magnisi peninsula is a small portion of land located near the largest Italian petrol-chemical pole of Augusta–Priolo–Melilli (40 km2), which, since the 1950s, devastated the local environment and landscape and unloaded directly into the sea an impressive quantity of pollutants. Unlike the terrestrial part of the area, where a Natural Oriented Reserve (NOR) called “Saline di Priolo” was established in the 2000s, no concrete legislative action has been implemented or proposed for the marine environment. At the same time, the fauna of the marine environment has not been studied in the same way as that of the terrestrial environment. As concerns the molluscan fauna, most of the information dates back to the 1800s. These studies were exclusively focused on the shells of some mollusks in the area. Instead, no study related to this area has ever been carried out on the group of sea slugs. This study conducted between 2022 and 2023, through snorkeling activities, allowed to provide the first faunistic list of the sea slugs of this area, together with information on the biology and ecology of these gastropods, highlighting the potential biodiversity present in this small stretch of coastline affected by high industrial pollution.

Predictive Modelling of Sea Debris around Maltese Coastal Waters - Mark Dingli; Kristian Guillaumier; Adam Gauci (Oceans, 2024)
The accumulation of sea-surface debris around the coastal waters of Malta poses significant ecological and environmental challenges, negatively affecting marine ecosystems and human activities. This issue is exacerbated due to the lack of an effective system tailored to predict surface-debris movement specifically for the Islands of Malta. To address this gap, a pipeline that combines a machine learning-based prediction system with a physics-based model is proposed. This pipeline uses data on historical sea-surface current velocities to forecast future conditions and visualise debris movement. Central to this system are two machine learning models trained to predict surface velocities for the next 24 h for a specific area. These predictions are then utilised in a Lagrangian model to simulate and visualise the debris movement, providing insights into future dispersion patterns. A comparative evaluation of both models using real-world data is made to determine which one performs best in this application. This method offers a tailored approach to addressing sea-surface debris around Malta by accurately predicting sea-surface current velocities and visualising debris movement, improving cleanup operations and marine conservation strategies.

A Sustainable Approach to Managing Invasive Macroalgae: Assessment of the Nutritional Profile and the Potential for Enteric Methane Mitigation of Rugulopteryx okamurae - Helder P. B. Nunes; Cristiana Maduro-Dias; Joana Carvalho; Alfredo Borba (Oceans, 2024)
The expansion of the invasive Asian macroalgae Rugulopteryx okamurae along the coasts of the Azores represents a significant challenge for local marine biodiversity. A promising approach to managing the biomass produced by this alien alga is to valorize it in the context of the blue economy. This study characterizes and evaluates the potential of R. okamurae biomass for incorporation into cattle feed, with a focus on mitigating enteric methane production. The nutritional value of R. okamurae, its digestibility, and its potential as a mitigating agent for enteric methane production were analyzed in vitro. The results indicate that the inclusion of 5% R. okamurae in the diet significantly (p < 0.05) reduced accumulated methane production by 98% after 24 h of incubation. The addition of 1% algae over the same period resulted in a 38% reduction in methane production. However, a significant decrease (p < 0.05) in gas production of 57.02% and 73.5% was also observed in relation to control, with the inclusion of 1% and 5%, respectively, during 96 h. Nutritionally, R. okamurae was found to have a crude protein content of 18.68% and fiber (NDF) of 55.71% of DM. It is also worth highlighting the high content of ash (31.86%) that was identified in these brown macroalgae. In conclusion, the fresh biomass of R. okamurae could serve as a functional ingredient in cattle feed to mitigate enteric methane production, provided it is used in low percentages. However, it is important to emphasize that high concentrations in the first 12 h did not produce methane, which is also not recommended for enteric fermentation. However, before including it in animal feed, in vivo tests are needed to assess its toxicity.

Phytoplankton Structure in a Coastal Region of the Eastern Entrance of the Gulf of California during La Niña 2022 - Elizabeth Durán-Campos; David Alberto Salas-de-León; Erik Coria-Monter; María Adela Monreal-Gómez; Benjamín Quiroz-Martínez (Oceans, 2024)
This paper assessed the phytoplankton structure and its relationship with the physical environment in the coastal region off Mazatlán, Mexico, in two seasons of 2022, a year in which a strong La Niña event took place: (1) the warmer (August) and (2) the transitional period to the cold phase (November), based on hydrographic data and samples collected in two systematic scientific expeditions. The results showed clear differences between both seasons. Regarding total abundance, August reached 125,200 cells L−1, while November amounted to 219,900 cells L−1. Regarding species composition, the diatoms Cylindrotheca closterium and Planktoniella sol were dominant in August, while Thalassionema nitzschioides and Tetramphora decussata dominated the assemblages in November. The dinoflagellate Protoperidinium punctulatum was dominant in both seasons. However, very marked differences in its abundance are reported. The differences observed in the species richness and abundance could be attributed to the physical configuration of the water column, particularly the surface temperature, which showed clear changes between both seasons. The results presented here confirmed the high phytoplankton richness (some of them with the potential to generate harmful algal blooms), abundance, and diversity values of the region, suggesting a strong relationship with the physical environment.

Analyzing Trends in Saharan Dust Concentration and Its Relation to Sargassum Blooms in the Eastern Caribbean - José J. Hernández Ayala; Rafael Méndez-Tejeda (Oceans, 2024)
This study investigates the temporal trends and correlations between Saharan dust mass concentration densities (DMCD) and Sargassum concentrations (SCT) in the tropical North Atlantic. Average DMCD data for June, July, and August from 1980 to 2022, alongside SCT data for the same months from 2012 to 2022, were analyzed using Mann–Kendall tests for trends and lagged regression models to assess whether higher Saharan dust levels correlate with Sargassum outbreaks in the region. A comprehensive analysis reveals a significant upward trend in Saharan dust quantities over the study period, with the summer months of June, July, and August exhibiting consistent increases. Notably, 2018 and 2020 recorded the highest mean DMCD levels, with June showing the most significant increasing trend, peaking in 2019. These findings are consistent with previous studies indicating a continuous elevation in Saharan dust concentrations in the tropical atmosphere of the North Atlantic. Simultaneously, Sargassum concentrations also show a notable increasing trend, particularly in 2018, which experienced both peak SCT and elevated DMCD levels. Mann–Kendall tests confirm statistically significant upward trends in both Saharan dust and Sargassum concentrations. Simple linear regression and lagged regression analyses reveal positive correlations between DMCD and SCT, highlighting a temporal component with stronger associations observed in July and the overall June–July–August (JJA) period. These results underscore the potential contribution of elevated Saharan dust concentrations to the recent surge in Sargassum outbreaks in the tropical North Atlantic. Furthermore, the results from forward stepwise regression (FSR) models indicate that DMCD and chlorophyll (CHLO) are the most critical predictors of SCT for the summer months, while sea surface temperature (SST) was not a significant predictor. These findings emphasize the importance of monitoring Saharan dust and chlorophyll trends in the Eastern Caribbean, as both factors are essential for improving Sargassum modeling and prediction in the region. This study provides valuable insights into the climatic factors influencing marine ecosystems and highlights the need for integrated environmental monitoring to manage the impacts on coastal economies.

Dense Water Formation Variability in the Aegean Sea from 1947 to 2023 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Oceans, 2024)
The formation of dense water in the Aegean Sea is important as it affects the deep circulation and the hydrography of the Eastern Mediterranean Sea. In this study, the variability of dense water formation is investigated in relation to forcing mechanisms from 1947 to 2023 in the subbasins of the Aegean Sea, utilising in situ observations from various sources, which have been analysed in combination with satellite altimetry and reanalyses products. The analysis reveals that the Aegean Sea has been in a state of increased dense water formation since 2017 due to the combination of increased surface buoyancy loss and reduced Black Sea water inflow. Extremely high salinity has been recorded in the intermediate layers of the Aegean Sea since 2019. The anticyclonic circulation of the North Ionian gyre during 2017 and 2018 probably also contributed to the rapid transport of highly saline waters in the intermediate and, through dense water formation, the deep layers of the Aegean Sea in 2019. Until 2022, the dense waters formed during the peak of the Eastern Mediterranean Transient still occupied the bottom layers of some deep subbasins of the North and South Aegean; however, the 29.4 kg m−3 isopycnal in the North Aegean and the 29.3 kg m−3 isopycnal in the Southeastern Aegean have gradually deepened by 800 m, permitting the waters forming in the last ten years in the Aegean Sea to settle at ever greater depths. Temperature controls the density variability of the Cretan intermediate water up to the decadal time scale. Increased data availability since 2010 was sufficient to clarify that intrusions of dense water from the North–Central Aegean Sea contributed to the erosion of the Eastern Mediterranean transitional waters in the South Aegean Sea after 2017, as well as to raising the intermediate water masses of the South Aegean to shallower depths. The erosion of the transitional Mediterranean waters in the South Aegean Sea between 1947 and 1955 and 1973 and 1980 coincided with increased dense water formation in the North–Central Aegean Sea. During the peak of the Eastern Mediterranean Transient, the North Ionian circulation, the Black Sea water inflow, the Atlantic Multidecadal Oscillation, and the surface buoyancy fluxes favoured dense water formation in the Aegean Sea.

Mapping Topic Evolution across the 40-Year-Old Long-Term Ecological Research MareChiara Site in the Gulf of Naples, Italy - Luca Russo; Carola Murano; Domenico D’Alelio (Oceans, 2024)
The forty-year-old Long-Term Ecological Research MareChiara (LTER-MC) program started on 26 January 1984, with fortnightly oceanographic sampling until 1991 and then, from 1995, with weekly sampling up to the present time. LTER-MC produced >150 publications that have been cited by thousands of other studies. In this scoping review, we analyzed this corpus using a semantic approach based on topic modeling, a machine-driven procedure to identify and map topics and their interactions. Understanding the causes behind the evolution of scientific topics, their emergence, splitting, hybridization, or merging within a scientific community is an important step in science policy in managing collaborative research and bringing it into the future. Across different topics, mainly represented by studies on Natural History, Biodiversity, Phenology, Life Cycles, and Community Ecology, the LTER-MC work expanded the knowledge on planktonic organisms, describing in detail their lifestyles and delineating their relationships with environmental conditions. In presenting these results, the potential strengths, weaknesses, opportunities, and threats connected to the overall scientific dimension of LTER-MC are discussed. Finally, the upcoming effort is envisioned in reinforcing internal collaboration to integrate basic and applied research around scientific investigations suitable for establishing a stronger interaction between science and policy, as indicated by the United Nations Decade of Ocean Science for Sustainable Development.

Integrated Multi-Biomarker Responses of Juvenile Zebra Seabream (Diplodus cervinus) to Warming and Acidification Conditions - Marta Dias; Pedro Pousão-Ferreira; Mário S. Diniz; António Marques; Rui Rosa; Patrícia Anacleto; Ana L. Maulvault (Oceans, 2024)
The impacts of climate change-related stressors are becoming more noticeable in the ocean, particularly in coastal marine ecosystems. Yet limited information still exists on the physiological state and ecological resilience of marine fish species, especially during their early life stages (i.e., larvae and juveniles). The present study investigated the effects of chronic exposure to seawater warming (OW; ΔT = +4 °C) and acidification (OA; ΔpH = −0.3 pH units, equivalent to pCO2~1000 µatm), acting alone or combined (OWA), on juvenile zebra seabream (Diplodus cervinus) physiological resilience, considering distinct levels of biological organization (i.e., biochemical, cell, organ and individual levels). After 60 days of exposure, both stressors, in isolation or combination, significantly decreased specific growth rate (−11% in OW, −42% in OA and −49% in OWA) and leukocyte counts (from −29% in OA and OWA up to −37% in OW) in relation to the control treatment. In addition, a decreased Fulton’s condition index (K) was observed under warming and acidification in combination (−35% in OWA). At the cell level, OW, OA and OWA triggered different biomarker responses in D. cervinus (i.e., up-regulation, down-regulation, or absence of significant effect). In general, the results are suggestive of an antagonistic effect when warming and acidification are combined. OWA yielded the highest integrated biomarker response (IBR) index value in the whole organism, muscle, brain and gills of D. cervinus juveniles, therefore suggesting that the effects of these stressors are more severe when they act together. The distinct patterns observed in each stress scenario highlight the importance of carrying out further studies adjusted to the specificities of different regions, i.e., accounting not only for the type and degree of severity of environmental stressors already felt and/or projected for that specific area, but also the physiological plasticity of species that inhabit a particular ecosystem. The gathered knowledge will allow one to determine the vulnerability of particular marine species and geographic areas and, most importantly, to draw up effective and tailor-made conservation strategies to overcome climate change impacts.

Nitrogen and Phosphorus Discharges from Cargo Ships’ Black and Grey Waters—A Case Study of a Baltic Sea Port - Suvi-Tuuli Lappalainen; Ulla Tapaninen; Jonne Kotta (Oceans, 2024)
Shipping is a vital component of global trade. However, shipping activities have negative environmental impacts, including emissions to air and water. The Baltic Sea is severely affected by eutrophication, mainly due to nutrient inputs, especially nitrogen and phosphorus. Understanding the contributions of various nutrient sources is essential for informed environmental regulation. The aim of this research is to quantify the nutrient content of black and grey water discharged from cargo ships in the Baltic Sea in order to assess their contribution to the total nutrient load. Specifically, this research examines the nitrogen and phosphorus loadings from ships calling the port of HaminaKotka and addresses key questions regarding nutrient generation, discharge proportions, emission shares by ship type, and their importance compared to other sources. Using a methodology based on ship data and nutrient production estimates, this study found that 2545 cargo ships generated a total of 781 kg of nitrogen and 134 kg of phosphorus in their effluents during their voyages to the port in 2021. However, only a small fraction (0.5%) of the cargo ships discharged their wastewater at port reception facilities. This study concludes that nutrient discharges from cargo ships’ wastewaters are relatively small, contributing less than 0.06% phosphorus and 0.01% nitrogen to the total load in the area. This result indicates that the impact of cargo ships’ wastewater on the eutrophication of the Baltic Sea is smaller than previously thought. The methodology used in this study can be applied in other ports and regions to assess nutrient discharges from cargo ships’ wastewaters on a wider scale. Further research is recommended to assess the effectiveness of on-board treatment systems, the impact of other contaminants in wastewater, and the development of port reception facilities to facilitate proper wastewater management in the maritime trade.

Operational Mapping of Submarine Groundwater Discharge into Coral Reefs: Application to West Hawai‘i Island - Gregory P. Asner; Nicholas R. Vaughn; Joseph Heckler (Oceans, 2024)
Submarine groundwater discharge (SGD) is a recognized contributor to the hydrological and biogeochemical functioning of coral reef ecosystems located along coastlines. However, the distribution, size, and thermal properties of SGD remain poorly understood at most land–reef margins. We developed, deployed, and demonstrated an operational method for airborne detection and mapping of SGD using the 200 km coastline of western Hawai‘i Island as a testing and analysis environment. Airborne high spatial resolution (1 m) thermal imaging produced relative sea surface temperature (SST) maps that aligned geospatially with boat-based transects of SGD presence–absence. Boat-based SST anomaly measurements were highly correlated with airborne SST anomaly measurements (R2 = 0.85; RMSE = 0.04 °C). Resulting maps of the relative difference in SST inside and outside of SGD plumes, called delta-SST, revealed 749 SGD plumes in 200 km of coastline, with nearly half of the SGD plumes smaller than 0.1 ha in size. Only 9% of SGD plumes were ≥1 ha in size, and just 1% were larger than 10 ha. Our findings indicate that small SGD is omnipresent in the nearshore environment. Furthermore, we found that the infrequent, large SGD plumes (>10 ha) displayed the weakest delta-SST values, suggesting that large discharge plumes are not likely to provide cooling refugia to warming coral reefs. Our operational approach can be applied frequently over time to generate SGD information relative to terrestrial substrate, topography, and pollutants. This operational approach will yield new insights into the role that land-to-reef interactions have on the composition and condition of coral reefs along coastlines.

Spatial and Developmental Policy Directions Affecting Marine Spatial Planning in the Northern Aegean Sea, Greece - Anestis Gourgiotis; Dionisia Koutsi; Vasiliki Krommyda; Anastasia Stratigea (Oceans, 2024)
European strategic policy directions toward a sustainable blue economy have strengthened interest in maritime investments, thus increasing sectoral competition for marine space. Emerging repercussions out of such a rising interest need to be handled by marine spatial planning (MSP) as a means of properly allocating marine space to diverse uses; managing conflicts and promoting synergies among them; and pursuing a multi-use perspective of this space. A critical stage of each MSP exercise is the exploration of land- and marine-based policy directions and their current or potential repercussions in the marine environment. Such an exploration is carried out in this work by means of a qualitative policy review for informing the MSP process in the Northern Aegean Sea, Greece. By delving into diverse policy frameworks at various spatial levels—i.e., local (urban), regional, and national/European—constraints, but also perspectives in policy choices/maritime uses in the MSP context, are identified, thus guiding more informed MSP choices in the specific study region while attaining a successful integration or coordination between land and marine developments.

Cnida Morphology as Taxonomic Tools within Tube-Dwelling Anemones (Ceriantharia, Cnidaria) - Anny C. Forero-Mejia; Laurent Duchatelet; Carina Östman (Oceans, 2024)
Cnidome morphology appears to be a valuable tool for anthozoan (Octocarallia, Ceriantharia, and Hexacorallia) taxonomy. Ceriantharian cnidomes consist of b-mastigophores, isorhizas, spirocysts, and ptychocysts, including different subtypes. The b-mastigophores are the most valuable ceriantharian cnidae for species identification. The Ceriantharian b-mastigophore terminology is congruent to the b-mastigophores of Carlgren, b-rhabdoids, including the “faltstück” of Schmidt, spirulae, and also potentially the penicilli of den Hartog. The apical tightly folded, inverted b-mastigophore shafts, the “faltstück”, are important species-specific characteristics due to their various patterns. The mesenterial structures known as craspedonemes, cnidorages, and acontioids also have high taxonomic value. Drop-shaped b-mastigophores might be characteristic nematocysts for mesenteries. The occurrence of isorhizas and striations on the inner ptychocyst capsule walls are other species’ characteristics. The morphological similarities of spirulae and penicilli to b-mastigophores within Hexacorallia are highlighted by naming spirulae and penicilli as b-mastigophores/spirulae and b-mastigophores/penicilli subtypes, respectively. The slight morphological distinction between spirulae and penicilli will doubtfully justify the suborders Spirularia and Penicillaria. The spirocysts presence in Ceriantharia and Hexacorallia indicates a closer relationship between Ceriantharia and Hexacorallia than between Ceriantharia and Octocorallia. Octocorallia are the only anthozoans without spirocysts. This work underlines the importance of cnidome morphological analysis for taxonomic identification and classification.

Reply to Kahng, S.E. Comment on “Lesser et al. Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals. Oceans 2022, 3, 527–546” - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2024)
Kahng [...]

Comment on Lesser et al. Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals. Oceans 2022, 3, 527–546 - Samuel E. Kahng (Oceans, 2024)
In warm oligotrophic waters, photosymbiotic coral can flourish across a wide depth range (0–170+ m), extending to depths where light attenuates to ~0.1% of surface values. Conventional wisdom has long assumed that mixotrophic corals must increasingly rely on heterotrophy as the ambient light available to drive photosynthesis decreases with depth. However, evidence challenging this traditional dogma has been accumulating in recent years. Although some evidence suggests that some depth-generalist coral species likely increase their reliance on heterotrophy with increasing depth, there is growing evidence that other species do not. Analysis of bulk stable isotopes (δ13C and δ15N) applied to photosymbiotic corals has been used in several ways to infer their trophic ecology and their relative dependence on symbiont photosynthesis versus heterotrophic feeding. However, metrics based on bulk tissue δ13C and δ15N values are subject to considerable uncertainty due to the multiple factors that can affect their values independent of trophic ecology. These competing factors can be quite challenging to disentangle and have led to inconsistent results and conclusions regarding trends in coral heterotrophy with depth. The evidence to date suggests no uniform trophic pattern with increasing depth or decreasing light. Different corals appear to function differently, which is not surprising given their phylogenetic diversity.

A Comparison between the Production of Edible Macroalgae Worldwide and in the Mediterranean Sea - Gorana Jelić Mrčelić; Svjetlana Krstulović Šifner; Vedrana Nerlović (Oceans, 2024)
Macroalgae are beneficial for consumers and producers due to their high productivity, their chemical composition and their efficient cultivation without additional feed. Asia dominates global macroalgae production, while European production is still marginal and mainly based on wild harvesting in the North Atlantic. The European Commission has launched initiatives to promote the sustainable production, safe consumption and innovative use of macroalgae products in European regional seas, including the Mediterranean Sea. A variety of coastal and seabed types and a wide range of environmental conditions make the Mediterranean a hotspot of marine biodiversity while providing good conditions for the cultivation of macroalgae. The aim of this paper is to compare the global macroalgae production and macroalgae production in the Mediterranean Sea, focussing on the cultivation of edible macroalgae. The paper also discusses the limitations and possibilities of macroalgae production in the region. Macroalgae production is one of the most promising sectors of the blue economy in the Mediterranean. The production of edible macroalgae suitable for human consumption has great potential, considering future population growth and related food security and health issues, as well as the additional ecosystem benefits of macroalgae production.

Cetacean Strandings along the Bulgarian Coast of the Black Sea in 2010–2022 - Dimitar Popov; Galina Meshkova (Oceans, 2024)
Cetacean strandings are valuable sources of data about their life history, health status, population trends, and impact of threats. We examined the strandings along the Bulgarian coast of the Black Sea for a period of 13 years from 2010 to 2022. A total of 1528 cetacean strandings of all three species inhabiting the basin were recorded: 1031 harbour porpoises Phocoena phocoena, 199 bottlenose dolphins Tursiops truncatus, 97 common dolphins Delphinus delphis, 19 delphinids and 182 unidentified. The highest numbers were observed in 2016 and 2022. Monthly peaks for harbour porpoise and bottlenose dolphin were in July and August and for common dolphin in May. An unusually high mortality of porpoise neonates was recorded in 2015 and 2016. The overall sex ratio showed a slightly higher share of males at 120:100. This bias was the most pronounced for males of common dolphins. Spatial distribution varied interspecifically but was predominantly along the southern coast. Bycatch signs were detected in 80 animals including during the turbot fishing ban period, suggesting the existence of illegal fishing operations. All of this highlights the need for better reinforcement and control to ensure both the conservation of endangered cetaceans and the sustainability of fisheries. Improvement in data collection is needed to improve the quality of information.

The Abundance of Microplastics in the World’s Oceans: A Systematic Review - Judith Mutuku; Maria Yanotti; Mark Tocock; Darla Hatton MacDonald (Oceans, 2024)
Microplastics are ubiquitous in marine environments and have been documented across all ocean compartments, especially surface waters, across the world. Even though several studies identify the presence of microplastics in the world’s five oceans, there remains an overt problem of large inconsistencies in their sampling, extraction, and consequent quantification. Despite the complexity of these methodologies, researchers have tried to explore microplastic abundance in ocean surface waters. Using a systematic review approach, a dataset was derived from 73 primary studies undertaken since the year 2010 following the Oslo and Paris Conventions (OSPAR) guidelines to monitor and harmonise marine debris. The results showed differences in the abundance and distribution of microplastics in surface waters across oceans. The overall concentration of microplastics in all five oceans ranged between 0.002 and 62.50 items/m3, with a mean abundance of 2.76 items/m3. The highest mean concentration of microplastics was found in the Atlantic (4.98 items/m3), while the least was observed in the Southern Ocean (0.04 items/m3). While challenging, this paper recommends harmonisation of the sampling, separation, and identification methods across the globe to aid in the design of the appropriate mitigation strategies for reducing marine plastic pollution.

Hydrographic vs. Dynamic Description of a Basin: The Example of Baroclinic Motion in the Ionian Sea - Gian Luca Eusebi Borzelli; Ernesto Napolitano; Adriana Carillo; Maria Vittoria Struglia; Massimiliano Palma; Roberto Iacono (Oceans, 2024)
The Ionian Sea is a crucial intersection for various water masses in the Mediterranean. Its hydrography and dynamics play a significant role in the seawater budgets and biogeochemistry of the neighboring sub-basins. Multiple theories have been formulated to gain a better understanding of the Ionian dynamics. These theories primarily attribute the variability of the near-surface Ionian circulation to internal processes. Here, we utilize horizontal currents and temperature–salinity profiles from the Copernicus reanalysis to examine the contribution of baroclinic modes to the variability of the basin horizontal circulation. Our findings demonstrate that, although the basin vertical structure is characterized by three layers, the primary patterns of the Ionian circulation can be attributed to the first baroclinic mode. This mode, along with the barotropic mode, accounts for over 85% of the overall variability in the Ionian circulation, suggesting that only one of the three interfaces separating the different water masses in the basin is dynamically active. We estimate the depth of this interface to be about 490 m. Additionally, our analysis shows that more than 90% of the kinetic energy over the water column is localized above this interface, indicating that the deep layer of the Ionian is dynamically nearly inert.

In-Water Photo Identification, Site Fidelity, and Seasonal Presence of Harbor Seals (Phoca vitulina richardii) in Burrows Pass, Fidalgo Island, Washington - Ciera J. Edison; Cindy R. Elliser; Katrina H. White (Oceans, 2024)
Little is known about the in-water behavior and site fidelity of harbor seals (Phoca vitulina richardii), as most photo-identification (photo-ID) studies are typically conducted while they are hauled-out on land. We investigated in-water site fidelity rates and seasonal presence in Burrows Pass, Washington, using photographs collected during a long-term photo-ID and behavioral study from January 2015 through November 2019. There was a minimum of 161 individuals and a maximum of 286 individual harbor seals using Burrows Pass. Harbor seals were present in all seasons, with the lowest sighting rates during summer. Individuals were more likely to be sighted/re-sighted in fall and spring. There was large variations in the level and seasonality of site fidelity among individuals. The majority of seals (69.62%) were seen only once, but 22.69% showed low to moderate site fidelity (2–5 sightings) and 7.69% showed strong site fidelity (≥6 sightings) over seasons and across years. These seasonal variations were likely due to foraging, life history, and individual behavioral variabilities. Studies like this provide necessary information about harbor seal in-water site fidelity and behavior, which are less well known but vitally important in harbor seal management and conservation.

Regional Fluctuations in the Eastern Tropical North Pacific Oxygen Minimum Zone during the Late Holocene - Caitlin E. Tems; Eric Tappa (Oceans, 2024)
This study presents a high-resolution record of δ15Nsed, which serves as a proxy for water column denitrification and oxygen minimum zone (OMZ) intensity, from the Soledad Basin in the Eastern Tropical North Pacific OMZ. The Soledad Basin δ15Nsed record is compared to the Pescadero Slope and Santa Barbara Basin (SBB) δ15Nsed records to gain insight into regional variations in the ETNP OMZ. During the Medieval Climate Anomaly (MCA; 950–1250 CE), Soledad Basin, Pescadero Slope, and SBB records exhibit coherent trends suggesting that there was general water column oxygenation stability. During the Little Ice Age (LIA; 1350–1850 CE), Soledad Basin and SBB showed a similar decreasing trend in δ15Nsed values while the Pescadero Slope δ15Nsed exhibited an increasing trend until values abruptly declined between 1740 and 1840 CE. We suggest that increased δ15Nsed variability and the different trends at the Pescadero Slope during the LIA are due to the influence of the North American monsoon (NAM), which can suppress upwelling when enhanced and result in OMZ contraction. The decoupling between the Soledad Basin, SBB, and the Pescadero Slope could also be due to the increased influence of enriched 15NO3− subarctic waters in the California Current System. Since each site is influenced by local productivity, basin morphology, and regional atmospheric and ocean circulation patterns, we suggest that assessing OMZ fluctuations from multiple sites provides a more comprehensive view of regional OMZ dynamics in response to climate variations.

TEOS-10 Equations for Determining the Lifted Condensation Level (LCL) and Climatic Feedback of Marine Clouds - Rainer Feistel; Olaf Hellmuth (Oceans, 2024)
At an energy flux imbalance of about 1 W m−2, the ocean stores 90% of the heat accumulating by global warming. However, neither the causes of this nor the responsible geophysical processes are sufficiently well understood. More detailed investigations of the different phenomena contributing to the oceanic energy balance are warranted. Here, the role of low-level marine clouds in the air–sea interaction is analysed. TEOS-10, the International Thermodynamic Equation of State of Seawater—2010, is exploited for a rigorous thermodynamic description of the climatic trends in the lifted condensation level (LCL) of the marine troposphere. Rising sea surface temperature (SST) at a constant relative humidity (RH) is elevating marine clouds, cooling the cloud base, and reducing downward thermal radiation. This LCL feedback effect is negative and counteracts ocean warming. At the current global mean SST of about 292 K, the net radiative heat flux from the ocean surface to the LCL cloud base is estimated to be 24 W m−2. Per degree of SST increase, this net flux is expected to be enhanced by almost 0.5 W m−2. The climatic LCL feedback effect is relevant for the ocean’s energy balance and may be rigorously thermodynamically modelled in terms of TEOS-10 equations. LCL height may serve as a remotely measured, sensitive estimate for the sea surface’s relative fugacity, or conventional relative humidity.

Coupled Meteo–Hydrodynamic Approach in Semi-Enclosed Basins and Sensitivity Assessment of Wind-Driven Current - Elvira Armenio; Andrea Tateo; Francesca Fedele; Nicola Ungaro; Michele Mossa; Vittorio Esposito; Vincenzo Campanaro (Oceans, 2024)
A coupled numerical approach that combines the WRF model and the Mike 3 (DHI) hydrodynamic model was developed and applied in two semi-enclosed basins in the Ionian Sea (Italy) to assess the wind-driven current. To gain a better understanding of how the sea current field can vary depending on meteorological data forcing, three different scenario were set up. The sensitivity of the sea current pattern was investigated as a function of the type of meteorological forcing and appreciating the differences in the results. The aims of this study are threefold. Firstly, we wish to define an ad hoc procedure to join the model-computed meteorological parameters in the hydrodynamic model. Secondly, we will investigate the feedback from the Mar Piccolo and Mar Grande basins in the Ionian Sea using fully coupled simulations and an uncoupled system where the atmospheric parameters are derived from a ground station. Finally, we will evaluate the results achieved by applying two scenarios of typical meteorological conditions to the study site. The model results highlighted the variability of sea currents depending on meteorological forcing.

Reply to Hendawitharana et al. Comment on “Arulananthan et al. The Status of the Coral Reefs of the Jaffna Peninsula (Northern Sri Lanka), with 36 Coral Species New to Sri Lanka Confirmed by DNA Bar-Coding. Oceans 2021, 2, 509–529” - Ashani Arulananthan; Venura Herath; Sivashanthini Kuganathan; Anura Upasanta; Akila Harishchandra (Oceans, 2024)
We appreciate the comments made by Hendawitharana et al [...]

Comment on Arulananthan et al. The Status of the Coral Reefs of the Jaffna Peninsula (Northern Sri Lanka), with 36 Coral Species New to Sri Lanka Confirmed by DNA Bar-Coding. Oceans 2021, 2, 509–529 - Manuja Promodya Hendawitharana; Adriaan Gittenberger; Prabath Krishantha Jayasinghe; Deishini Rupika Herath (Oceans, 2024)
We are responding to an article by Arulananthan et al [...]

Genetic Variability and Genetic Differentiation of Populations in the Grooved Carpet Shell Clam (Ruditapes decussatus) Based on Intron Polymorphisms - Carlos Saavedra; David Cordero (Oceans, 2024)
The grooved carpet-shell clam is one of the most economically relevant shellfish species living in the Mediterranean and nearby Atlantic coasts. Previous studies using different types of genetic markers showed a remarkable genetic divergence of the eastern Mediterranean, western Mediterranean, and Atlantic populations, but important details remained unclear. Here, data from six nuclear introns scored for restriction fragment size polymorphisms in eight populations that have not been studied before have been pooled for the analysis with data scattered through three previous studies, totaling 32 samples from 29 locations. The results show lower levels of heterozygosity, higher mean number of alleles, and alleles with restricted distribution in the Mediterranean populations, suggesting the existence of a large, isolated population in the eastern Mediterranean at the middle Pleistocene. The data also confirm the similarity of populations from Tunisia to Western Mediterranean populations. Finally, a genetic mosaic is apparent in the Atlantic coasts of the Iberian Peninsula, with a divergence of Rias Baixas populations from more northern populations and Central Portugal populations. The effects of oceanic fronts, seasonal upwellings, river plumes, and/or fishery management operations could explain this and other features of the Atlantic populations.

Comparing the Structure of Fish Assemblage among Natural and Artificial Shallow Rocky Habitats - Laura García-Salines; Pablo Sanchez-Jerez (Oceans, 2024)
Artificial coastal structures, such as seawalls, breakwaters, and groins, can exert various impacts on the fish communities in the nearby regions. This study focuses on assessing the ecological effects of coastal infrastructure on marine environments, by comparing, at different seasons, the habitat complexity and heterogeneity, as well as their effects on fish assemblages, between the artificial habitat created with the intention of constructing a marina (Puerto Amor) and the natural habitats surrounding the Cabo de la Huerta area in Alicante (Spain). Employing an asymmetric design and examining two temporal and spatial scales, we utilized visual censuses in snorkeling to gauge the abundance and size of fish species, alongside various parameters related to habitat complexity and heterogeneity. The overarching hypothesis is that fish populations associated with artificial habitats will differ in terms of abundance, biomass, species richness, and diversity compared to fish populations associated with natural habitats, due to changes in complexity and heterogeneity. The findings indicate a shift in fish assemblages; for example, the family Labridae showed differences between the two habitat types for several species. These changes were due to the influences of the Posidonia oceanica meadow and algae like Jania rubens; being influenced by biological variables such as Ellisolandia elongata, Oculina patagonica, and Sarcotragus spinosulus; as well as physical variables such as stones, gravel, and blocks. While there is evidence of alteration in fish assemblages due to changes in habitat structure, there is also an increase in richness (9 species/m2) and total abundance and biomass (1000 ind./m2 and 1700 g/m2, respectively) in the artificial habitat. Multivariate analyses reveal that the fish community in Puerto Amor is less homogeneous than the one in the natural habitat. However, these analyses also indicate an overlap between the communities of both habitats, suggesting substantial similarity despite the noted differences. Consequently, although the habitat alteration has impacted fish populations, it has not diminished abundance, biomass, or species richness. In conclusion, the artificial rocky habitat resulting from the construction attempt at Puerto Amor harbor has fish populations with ecological significance and its removal could lead to undesirable impacts in the area, as the fish assemblages have become well established.

Energy Efficiency Analysis of a Deformable Wave Energy Converter Using Fully Coupled Dynamic Simulations - Chen Luo; Luofeng Huang (Oceans, 2024)
Deformable wave energy converters have significant potential for application as flexible material that can mitigate structural issues, while how to design the dimensions and choose an optimal deployment location remain unclear. In this paper, fully coupled computational fluid dynamics and computational solid mechanics were used to simulate the dynamic interactions between ocean waves and a deformable wave energy converter. The simulation results showed that the relative length to wave, deployment depth and aspect ratio of the device have significant effects on the energy conversion efficiency. By calculating the energy captured per unit width of the device, the energy efficiency was found to be up to 138%. The optimal energy conversion efficiencies were achieved when the structure length was 0.25, 0.5 or 0.75 of the dominating wavelength and submerged at a corresponding suitable depth. The aspect ratio and maximum stress inside the wave energy converter showed a nonlinear trend, with potential optimal points revealed. The simulation approach and results support the future design and optimisation of flexiable wave energy converters or other marine structures with notable deformations.

Global Chlorophyll Concentration Distribution and Effects on Bottom Reflectance of Coral Reefs - Ana G. Bonelli; Paulina Martin; Phillip Noel; Gregory P. Asner (Oceans, 2024)
Despite the limited coverage of coral reefs in the world’s oceans, they play a crucial role in global marine biodiversity and providing essential ecosystem services. This study explores the influence of chlorophyll-a (Chl-a) concentration in the water column on the estimation of bottom reflectance (rb) in coral reefs monitored by the Allen Coral Atlas coral reef monitoring system, using satellite imagery from a Sentinel-2 MSI sensor. We conducted a comprehensive analysis, considering Chl-a global distribution and variability, and its combined effect with water column depth over rb calculation. Our results demonstrated that the impact of Chl-a on rb estimation becomes significant when the water column depth exceeds 3 m. While suggesting the optionality of using regional Chl-a values, our study highlights potential overestimations of Chl-a in optically complex environments, such as along the Brazilian coast. This research contributes to refining coral reef monitoring systems and underscores the importance of accurate Chl-a assessments for robust environmental evaluations.

Widespread Coral Bleaching and Mass Mortality of Reef-Building Corals in Southern Mexican Pacific Reefs Due to 2023 El Niño Warming - Andrés López-Pérez; Rebeca Granja-Fernández; Eduardo Ramírez-Chávez; Omar Valencia-Méndez; Fabián A. Rodríguez-Zaragoza; Tania González-Mendoza; Armando Martínez-Castro (Oceans, 2024)
In May 2023, oceanic and atmospheric anomalies indicated El Niño conditions in the eastern Pacific, followed by coral bleaching in coral communities and reefs of Huatulco. We conducted surveys and sampled coral reef communities from late June to mid–August of 2023 to evaluate the intensity and extent of the changes associated with the warming event. From January of 2023, Huatulco experienced positive sea surface temperature (SST) anomalies; however, beginning in June, the high-temperature anomalies became extreme (>31 °C; ~2 °C above historical records). These high temperatures resulted in extensive coral bleaching in middle–late June and mortality from middle–late July (>50–93%). In addition, the area experienced significant reductions in echinoderm abundance and fish biomass. In 2023, severe bleaching affected coral systems in the Central Mexican Pacific, Gulf of Mexico, and Mexican Caribbean, making this the most devastating marine heatwave event, simultaneously impacting coral reefs across Mexico’s Pacific and Atlantic coasts.

The Effects of Tetrabromobisphenol A (TBBPA) on the Mussel Mytilus galloprovincialis: A Multi-Biomarker Approach - Sandra Copeto; Sara Ganço; Inês João Ferreira; Marco Silva; Carla Motta; Mário Diniz (Oceans, 2024)
Tetrabromobisphenol A (TBBPA) is a fire-retardant containing bromine, produced in large quantities worldwide and extensively used in several industrial products. This compound was identified as a potential contaminant of the environment, causing toxicity to organisms. However, its toxicity remains poorly understood in marine bivalves. The first objective of this work was to evaluate the impact of TBBPA on mussels (Mytilus galloprovincialis) exposed for 28 days to various concentrations of TBBPA (0, 1, 10, and 100 µg·L−1), by assessing stress biomarkers’ responses (Glutathione S-transferase, superoxide dismutase, catalase, lipid peroxidation, total antioxidant capacity, total ubiquitin, caspase-3 and acetylcholinesterase). The results showed that lower concentrations (1 and 10 µg·L−1) were efficiently detoxified, as suggested by GST activities, which were supported by the responses of the other biomarkers. The most pronounced effects were observed in animals exposed to the highest concentration of TBBPA (100 µg·L−1), suggesting oxidative stress. Additionally, significant strong correlations were found between total antioxidant capacity and some biomarkers (superoxide dismutase and lipid peroxidation), showing that processes involved in oxidative stress fighting are working to avoid cell injury. In brief, mussels’ defense mechanisms were capable of dealing with exposure to the lower concentrations tested. Despite this, the risk of consuming shellfish or other fishery products contaminated with TBBPA should be a cause for concern.

Investigation of Spatiotemporal Patterns of Harbour Porpoise (Phocoena phocoena) Strandings in Swedish Waters for Improved Monitoring and Management - Vigge Ulfsson; Hyeyoung Kim; Linnea Cervin; Anna Roos; Aleksija Neimanis (Oceans, 2024)
Harbour porpoises (Phocoena phocoena) are the only cetacean residents found year-round in Swedish waters and they are exposed to numerous natural and anthropogenic threats. Since the in situ monitoring of cetaceans can be difficult, invasive and often expensive, investigation of stranding patterns and examination of stranded animals can be used as a cost-effective source of data to study these elusive animals. The aim of this study was to investigate the spatiotemporal patterns of harbour porpoise stranding reports and the possible underlying causes in Swedish waters over a ten-year period (2014–2023). Additionally, the Swedish stranding network plays a key role in the collection of stranded carcasses for health and disease surveillance, and geographic coverage of the network also was analysed. When making spatial comparisons, the ten-year period was divided into two five-year blocks. Data on 854 stranded harbour porpoises were analysed from the coasts of the Skagerrak, Kattegat, and Baltic Seas. Both significant spatial and temporal patterns could be identified. Strandings peaked in July through September and hotspots occurred along most of the Swedish west coast, with the most frequent hotspots located around Öresund and especially the area around the Kullen peninsula. The spatial patterns of strandings found in this study are consistent with data on porpoise abundance, prey abundance, and gillnet fisheries’ efforts. The latter is known to be one of the primary causes of porpoise mortality. Furthermore, the coverage of the Swedish stranding network increased between the two periods, likely reflecting an increased awareness of the carcass-based surveillance program, and gaps requiring network expansion efforts were identified. These results also provide baseline data to enable the continued monitoring of stranding trends, as changes may indicate changes in population distribution, size or mortality rates.

Effects of Food Concentration and Light Intensity on the Growth of a Model Coral - Tung-Yung Fan; Yan-Leng Huang; Anderson Mayfield (Oceans, 2024)
Since reef-building corals rely on both heterotrophy and endosymbiotic dinoflagellate autotrophy to meet their metabolic needs, it is necessary to consider both food supply and light levels, respectively, when optimizing their cultivation ex situ. Herein nubbins of the model reef coral Pocillopora acuta cultured in recirculating aquaculture systems at photosynthetically active radiation levels of 370 or 670 μmol quanta m−2 s−1 were fed Artemia nauplii at concentrations of either 33 or 78 individuals mL−1 in a separate feeding tank for 6 hr in the dark thrice weekly. A subset of nubbins was experimentally wounded at the outset of the 84-day experiment to assess recovery, and 100% fully healed within 2–4 weeks. All cultured corals survived, and unwounded corals (1) grew at a specific growth rate approaching 0.5% day−1 and (2) demonstrated a mean total linear extension of 0.2% day−1 (~6–8 cm year−1); these are far higher than growth rates normally documented in situ. In the feeding tank, corals tolerated nitrate levels up to 25 mg L−1, but once concentrations reached 50 mg L−1 by day 84, tissue necrosis began to occur in nubbins of one tank. This highlights the importance of feeding in separate tanks during long-term culture of corals, and bio-filtration could reduce the possibility of organic matter accumulation in future coral culture studies.

Field Test of an Autonomous Observing System Prototype for Measuring Oceanographic Parameters from Ships - Fernando P. Santos; Teresa L. Rosa; Miguel A. Hinostroza; Roberto Vettor; A. Miguel Piecho-Santos; C. Guedes Soares (Oceans, 2024)
A prototype of an autonomous system for the retrieval of oceanographic, wave, and meteorologic data was installed and tested in May 2021 on a Portuguese research vessel navigating on the Atlantic Ocean. The system was designed to be installed in fishing vessels that could operate as a distributed network of ocean data collection. It consists of an automatic weather station, a ferrybox with a water pumping system, an inertial measurement unit, a GNSS unit, an onboard desktop computer, and a wave estimator algorithm for wave spectra estimation. Among several parameters collected by this system’s sensors are the air temperature, barometric pressure, humidity, wind speed and direction, sea water temperature, pH, dissolved oxygen, salinity, chlorophyll-a, roll, pitch, heave, true heading, and geolocation of the ship. This paper’s objectives are the following: (1) describe the autonomous prototype; and (2) present the data obtained during a full-scale trial; (3) discuss the results, advantages, and limitations of the system and future developments. Meteorologic measurements were validated by a second weather station onboard. The estimated wave parameters and wave spectra showed good agreement with forecasted data from the Copernicus database. The results are promising, and the system can be a cost-effective solution for voluntary observing ships.

Continuous Zonal Gradients Characterize Epipelagic Plankton Assemblages and Hydrography in the Subtropical North Atlantic - Antonio Bode; María Louro; Elena Rey; Angel Lamas (Oceans, 2024)
The subtropical North Atlantic is a key region for understanding climate impact in the ocean. Plankton studies in this region have been generally framed in biogeographic provinces or focused on latitudinal gradients. In this study, we demonstrate the benefits of using empirically constructed continuous gradients versus the use of average values for biogeographical provinces to characterize plankton assemblages along a longitudinal transect at 24.5° N using an unprecedented array of stations including hydrographic observations, abundance of phytoplankton and zooplankton, and plankton size spectra in the epipelagic layer (0–200 m). In addition, the variability of zooplankton assemblages was analyzed using detailed taxonomic identification at selected stations. We found significant gradients in most hydrographic and plankton variables. The former, including surface temperature and salinity, the depth of the upper mixing layer, and the depth of the chlorophyll maximum, displayed non-linear gradients with maximum or minimum values near the center of the transect. In contrast, most plankton variables showed linear zonal gradients. Phytoplankton, microzooplankton (<100 µm), and the slope and the intercept of the size spectra increased (and Trichodesmium decreased) to the west. Total mesozooplankton (>200 µm) did not show any significant zonal pattern, but the taxonomic assemblages were characterized by a gradual replacement of large Calanoids by small-bodied Cyclopoid copepods from east to west. The use of continuous gradients provides more detailed information on the zonal structure of subtropical plankton than the classical approach using discrete areas.

Blueprint for Blue Carbon: Lessons from Seychelles for Small Island States - Michael Bennett; Antaya March; Jeremy Raguain; Pierre Failler (Oceans, 2024)
Blue carbon has been proposed as a nature-based solution for climate change mitigation; however, a limited number of published works and data and knowledge gaps hinder the development of small island developing states’ (SIDS) national blue carbon resources globally. This paper reviews the blue carbon ecosystems of Seychelles as a case study in the context of SIDS, comparing estimations by the Blue Carbon Lab and recent blue carbon (mangrove and seagrass) evaluations submitted to the Seychelles national government. Mangroves (2195 ha, 80% in Aldabra Atoll) and seagrasses (142,065 ha) dominate in Seychelles, with coral reefs having the potential for carbon sequestration (169,000 ha). Seychelles is on track to protecting its blue carbon, but these systems are threatened by rising sea levels, coastal squeeze, erosion, severe storms, and human activities. The importance of carbon inventories, accounting institutions, and continuous monitoring of blue carbon systems is discussed. Blue accounting is necessary for accurate accounting of carbon sequestration and carbon storage, generating carbon credits, and representing impactful reductions in greenhouse gases for NDCs. Challenges and opportunities include policy legislation regarding ownership rights, accreditation and certification for carbon credits, sustainable financing mechanisms like natural asset companies and blue tokens, local engagement for long-term success, and carbon market dynamics following COP27. The restoration and regulation of blue carbon resources for optimal ecosystem services delivery, carbon inventories, and blue carbon policy are recommended development priorities. Blue carbon ecosystems have the potential to contribute to NDCs of SIDS while simultaneously offering sustainable development pathways for local communities through the multiple ecosystem services they provide.

Artificial Reef Deployment Reduces Diving Pressure from Natural Reefs—The Case of Introductory Dives in Eilat, Red Sea - Nadav Shashar; Asa Oren; Re’em Neri; Omer Waizman; Natalie Chernihovsky; Jenny Tynyakov (Oceans, 2024)
Artificial reefs have been suggested as alternative dive sites to mitigate human pressure on natural reefs. Despite the conceptual appeal of artificial reefs, there is a paucity of empirical evidence regarding their effectiveness in achieving this objective. Here, we report that a small artificial reef deployed adjacent to a local coral marine protected area caused a shift in the routes taken by introductory dives and nearly eliminated their visitations to the natural fringing reef within the MPA. This behavioral shift among divers persisted for more than a decade following the AR deployment. These findings underscore the efficacy of well-designed and appropriately located artificial reefs as valuable instruments in the conservation of coral reefs.

Baleen–Plastic Interactions Reveal High Risk to All Filter-Feeding Whales from Clogging, Ingestion, and Entanglement - Alexander J. Werth; Shirel R. Kahane-Rapport; Jean Potvin; Jeremy A. Goldbogen; Matthew S. Savoca (Oceans, 2024)
Baleen whales are ecosystem sentinels of microplastic pollution. Research indicates that they likely ingest millions of anthropogenic microparticles per day when feeding. Their immense prey consumption and filter-feeding behavior put them at risk. However, the role of baleen, the oral filtering structure of mysticete whales, in this process has not been adequately addressed. Using actual baleen tissue from four whale species (fin, humpback, minke, and North Atlantic right) in flow tank experiments, we tested the capture rate of plastics of varying size, shape, and polymer type, as well as chemical residues leached by degraded plastics, all of which accumulated in the baleen filter. Expanded polystyrene foam was the most readily captured type of plastic, followed by fragments, fibers, nurdles, and spherical microbeads. Nurdle and microbead pellets were captured most readily by right whale baleen, and fragments were captured by humpback baleen. Although not all differences between polymer types were statistically significant, buoyant polymers were most often trapped by baleen. Plastics were captured by baleen sections from all regions of a full baleen rack, but were more readily captured by baleen from dorsal and posterior regions. Baleen–plastic interactions underlie various risks to whales, including filter clogging and damage, which may impede feeding. We posit that plastics pose a higher risk to some whale species due to a combination of factors, including filter porosity, diet, habitat and geographic distribution, and foraging ecology and behavior. Certain whale species in specific marine regions are of the greatest concern due to plastic abundance. It is not feasible to remove all plastic from the sea; most of what is there will continue to break into ever-smaller pieces. We suggest that higher priorities be accorded to lessening humans’ dependence on plastics, restricting entry points of plastics into the ocean, and developing biodegradable alternatives.

Effects of Water Temperature and Structural Habitat Complexity on the Routine Swimming Speed and Escape Response of Post-Settlement Stage White Seabream - Patrícia Vicente; João Almeida; Laura Ribeiro; Sara Castanho; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Ana Margarida Faria (Oceans, 2024)
Coastal habitats are increasingly threatened by multiple anthropogenic-related activities, which include ocean warming and loss of structural habitat complexity. These two pressures have the potential to severely affect the structure and function of marine biodiversity. Early life stages of many fish species recruit to coastal habitats at the end of their pelagic phase, benefiting from access to food, shelter and protection. However, changes in temperature have been shown to influence ecologically relevant behaviours in post-settlement stage fish, and the loss of structural habitat complexity has been related to low recruitment and deleterious behaviours of fish in coastal habitats. Here, we evaluated the individual and interactive effects of prolonged exposure to increasing temperature and changed structural habitat complexity on routine swimming speed and escape response of post-settlement white seabream, Diplodus sargus (Linnaeus, 1758). Fish were reared under different temperatures (control 19 °C; high 22 °C) and structural habitat complexity (low and high) scenarios, in a cross-experimental design, and the routine swimming and escape responses were analyzed after 6 weeks of exposure. Change in temperature did not induce alterations at the behavioural level, but loss of structural habitat complexity increased speed and distance travelled during routine swimming, and responsiveness to a stimulus during the escape response behaviour. The interaction of the two factors did not influence performance. Determining how species are affected by changes in their environment, and the mechanisms that underlie these changes, will be critical to understanding the fish recruitment and populations’ fitness and survival.

Herbivorous Reef Fish Interaction with the Habitat and Physicochemical Variables in Coral Ecosystems in the Mexican Tropical Pacific - Diana Morales-de-Anda; Amílcar Leví Cupul-Magaña; Consuelo María Aguilar-Betancourt; Gaspar González-Sansón; Fabián Alejandro Rodríguez-Zaragoza; Alma Paola Rodríguez-Troncoso (Oceans, 2024)
Herbivorous fish can mediate spatial competition between algae and corals, which is crucial for coral ecosystems. However, in areas with limited coral coverage like the Mexican tropical Pacific (MTP), this dynamic is not fully understood. This study, using a functional trait approach and ordination analysis, explores whether herbivorous reef fish assemblage influences the benthic habitat components or if physicochemical factors define the habitat variability in the MTP’s Cleofas and Marietas insular systems. We analyzed if this relationship persisted across systems and over time, and identified species traits tied to habitat variability. Island comparison analyses between Cleofas and Marietas reveal that both herbivorous reef fish and physicochemical variables shape the habitat. Cleofas had larger mobile herbivorous fish that formed groups related mostly to macroalgae cover. In contrast, temporal analysis of Marietas shows that the habitat is primarily shaped by physicochemical variables with herbivorous fish being mainly small farmer species related to branching corals. Notably, these closely situated insular systems present varied ecosystem mediators, influenced by diverse drivers including fish traits and environmental factors. This study underscores the potential of employing a framework of ecological species traits combined with ordination methods to unravel the distinct site dynamics that contribute to the persistence of coral ecosystems within the MTP.

Contribution to the Knowledge of Cetacean Strandings in Chile between 2015 and 2020 - Mauricio Ulloa; Miguel A. Rivero; Antonio Fernández (Oceans, 2024)
Strandings caused by anthropogenic factors are one of the most worrying threats in relation to the conservation of cetacean species, and in the case of Chile, due to its geography and large extension of the coastline, monitoring and access to these events is difficult, making their study more complex. Chile has a shortage of specialized scientific forensic research facilities for cetaceans; however, for this study, it was able to collect data recorded from official institutions and sporadic scientific biological sampling oriented to investigate the causes of death or stranding. According to the Chilean government official database, we described that the main causes of unusual mortality events (UME) and mass strandings from 2015 and 2016 were acute poisoning by biotoxins and strandings by multiple possible causes, respectively, while individual strandings would have their causes in anthropogenic activities, such as entanglements in fishing and aquaculture gears and collisions with vessels. The predominant species in mass strandings was the sei whale (Balaenoptera borealis). The geographical area of greatest prominence in mass strandings was the Aysén Region in the Central Patagonia of Chile, while the species mostly involved in individual strandings along the south-central, central, and northern coasts of Chile was the small porpoise (Phocoena spinipinnis). The most common gross pathological findings were advance decay of the carcasses and non-specific wounds of different natures.

Preliminary Studies on Site Fidelity, Residence Index, and Population Size of Irrawaddy Dolphins in West Penang, Malaysia - Nurul Filzati Ali; Leela Rajamani (Oceans, 2023)
The Irrawaddy dolphin is found in the coastal and estuarine areas of West Penang, Malaysia. Studies were conducted to estimate the site fidelity, residence index, and population size of Irrawaddy dolphins in West Penang. Photo-identification studies were conducted using boat surveys from 2019 to 2021. Thirty-nine marked Irrawaddy dolphins were identified, with thirty-six newly identified individuals and three individuals observed in 2013. Resightings of four individuals indicated that they were found north of Sungai Burung and Sungai Pinang in West Penang. The majority of individuals had low sighting rates, ranging from 2.6 to 7.7%, with three individuals having medium sighting rates, the highest being 15.4%. The residence index was 0.01 for all 36 individuals, and the highest value of 0.36 was recorded for one individual. Using open population models and closed models, the population size was determined to be 64 or and 52, respectively. The results suggest that although there is a population present, it is probably open, as the residence index is low. The population size appeared to be stable from 2013 to 2021. This information will inform conservation managers of the best way forward for the conservation of Irrawaddy dolphins in Penang.

Plastic, It’s What’s for Dinner: A Preliminary Comparison of Ingested Particles in Bottlenose Dolphins and Their Prey - Leslie B. Hart; Miranda Dziobak; Randall S. Wells; Elizabeth Berens McCabe; Eric Conger; Tita Curtin; Maggie Knight; John Weinstein (Oceans, 2023)
Microplastic ingestion was reported for common bottlenose dolphins (Tursiops truncatus) inhabiting Sarasota Bay, FL, USA, a community that also has prevalent exposure to plasticizers (i.e., phthalates) at concentrations higher than human reference populations. Exposure sources are currently unknown, but plastic-contaminated prey could be a vector. To explore the potential for trophic exposure, prey fish muscle and gastrointestinal tract (GIT) tissues and contents were screened for suspected microplastics, and particle properties (e.g., color, shape, surface texture) were compared with those observed in gastric samples from free-ranging dolphins. Twenty-nine fish across four species (hardhead catfish, Ariopsis felis; pigfish, Orthopristis chrysoptera; pinfish, Lagodon rhomboides; and Gulf toadfish, Opsanus beta) were collected from Sarasota Bay during September 2022. Overall, 97% of fish (n = 28) had suspected microplastics, and GIT abundance was higher than muscle. Fish and dolphin samples contained fibers and films; however, foams were common in dolphin samples and not observed in fish. Suspected tire wear particles (TWPs) were not in dolphin samples, but 23.1% and 32.0% of fish muscle and GIT samples, respectively, contained at least one suspected TWP. While some similarities in particles were shared between dolphins and fish, small sample sizes and incongruent findings for foams and TWPs suggest further investigation is warranted to understand trophic transfer potential.

Size Effects on Pumping Rates in High Microbial versus Low Microbial Abundance Marine Sponges - Michael P. Lesser (Oceans, 2023)
Sponges are increasingly recognized as ecologically important on coral reefs as scleractinian corals decline. Most sponge species can be divided into two symbiotic phenotypes which are characterized as high microbial abundance (HMA) or low microbial abundance (LMA) sponges. Sponge species of HMA or LMA symbiotic phenotypes differ not just in their microbiomes, but in other characteristics, including that LMA sponges actively pump at higher rates than HMA sponges based on a standard normalization to size. This dichotomy has recently been questioned because the size range of LMA sponges used to quantify pumping rates during studies on their trophic ecology were exceedingly small, often less than an order of magnitude. Here, both HMA and LMA sponges, across two to three orders of magnitude in sponge volume (mL) or mass (g) were assessed for allometric relationships between sponge size and pumping rates (Q = mL s−1). The scaling analysis of all data sets combined reveals that HMA sponges scale their pumping rates isometrically with size, while LMA sponges scale their pumping rate allometrically. When HMA species are examined separately, however, tropical HMA sponges scaled isometrically, while temperate HMA sponges scaled allometrically. From an ecological perspective, to quantify differences between HMA and LMA sponges for rate functions of interest (e.g., feeding) it is important to remove the effects of size as a covariate, and adjust the Q values of sponges to a standard volume or mass. For multiple species and geographic locations, this analysis shows that LMA sponges always maintain higher Q values. On tropical coral reefs, the differences between HMA and LMA sponges are intrinsic and constrained by strong evolutionary selection resulting in fixed differences in Q, regardless of sponge size.

Stability of the Macrocyclic Gd-DOTA Contrast Agent (DOTAREM) under Different Estuarine Environmental Conditions - Ana Guerreiro; Pedro Brito (Oceans, 2023)
Gadolinium-based contrast agents (GBCA) are complexes, highly stable in vivo, used in magnetic resonance imaging (MRI), administered in patients and then eliminated via the renal system, passing through wastewater treatment plants (WWTP) before being discarded in the receiving medium, without apparent removal. In this study, it was examined whether different exposure periods to several environmental parameters (solar radiation, different salinities, temperatures and pH) will influence the stability of these complexes, namely, the Gd-DOTA. Gd-DOTA solutions were processed in a seaFAST-pico saline matrix pre-concentration and elimination system, and Gd concentrations were determined using ICP-MS. The results showed that the complex remained stable in fresh, brackish and saline water environments, even when exposed to extreme temperatures (40 °C) or slightly acidic to basic conditions (6–10), for an exposure period of 96 h. A small increase in the free Gd concentration was observed after 18 days when exposed to pH < 4, in all tested salinities (0, 18 and 36 PSU), with a degradation increase of up to 29%, after 5 weeks of exposure in freshwater. When exposed to direct solar radiation, a low Gd-DOTA degradation (4%) was observed after 24 h at salinity 18 PSU and remained constant until the end of the exposure period (96 h), while the remaining salinities showed negligible values.

Oceanic Environmental Impact in Seaports - Nitin Agarwala; Cherdvong Saengsupavanich (Oceans, 2023)
Seaports are gateways that connect a nation to the world economy. With trade by sea increasing due to globalization, the need for the improvement and development of seaports cannot be overlooked. While the development of ports is considered essential for the economic growth and prosperity of a nation, they also result in environmental deterioration that can hurt the future of humanity. The factors that cause such deterioration are many and have been discussed and studied in some detail over the years. Of these, however, studies associated with the environmental impacts of seaports emanating from the oceanfront are limited. It is with this understanding that the current work discusses the physical and biological impacts that occur due to the oceanic environment in seaports, the existing policy provisions, and the possible ways ahead to reduce environmental deterioration and allow their sustainable operation, by means of reviewing published works.

Evidence of Sexual Reproduction in Out-Planted Coral Colonies - Violeta Martínez-Castillo; Alma Paola Rodríguez-Troncoso; Amílcar Leví Cupul-Magaña (Oceans, 2023)
Intervention techniques to restore coral communities have become an important management tool to help recover and rehabilitate damaged reefs. The direct transplantation of healthy coral fragments is the most common method; however, there is controversy in the long-term success, as using coral clones may diminish the genetic diversity of the coral population. Genetic recombination can be achieved when the coral colony produces gametes and eventually reproduces; therefore, it is important to provide evidence that restored colonies produce gametes as their naturally recruited counterparts with similar colony size (age). Natural and restored Pocillopora coral colonies of the same size range (between 40 and 50 cm in diameter) were tagged and sampled during the rainy season to determine gamete maturation. Our results show no differences in the reproductive activity among colonies: natural and restored coral colonies matured gametes from June to October, with a peak in sexually active coral colonies in July. Also, gamete malformation was not observed. During the gamete production period, the area’s temperature ranged from 27.9 to 30.02 °C. The results’ evidence that coral colonies formed through active restoration contribute not only to the increase in live coral cover as seen in previous studies but potentially contribute in the medium term (>5 years after out-planting) to the production of larvae and local and subsidiary recruitment, since they exhibit the same reproductive patterns as their naturally formed counterparts and no differences in the reproductive activity among coral colonies. Therefore, long-term coral restoration projects contribute to maintaining the live coral cover and the genetic diversity in the region, eventually rehabilitating the coral community.

Spatial Distribution and Contamination Level Assessment of Marine Sediment of the Safi Bay (Moroccan Atlantic Coast) - Abdenaim Minoubi; Nezha Mejjad; Khalid El Khalidi; Mohammed Bouchkara; Ahmed Fadili; Mohamed Chaibi; Bendahhou Zourarah (Oceans, 2023)
This study assesses the spatial distribution and contamination level of heavy metals in Safi Bay surface sediments. In this order, 28 surface sediment samples were retrieved from the study area and analyzed using the x-fluorescence method. To assess the contamination of the examined sediment, we used geo-ecological indices such as contamination factor (CF), degree of contamination (DC), geo accumulation index, and pollution load index (PLI). The results show that only Pb and Cd present moderate and considerable contamination in some sampling sites, while other elements (Cr, Cu, Zn, and Ni) indicate no contamination and low contamination by these elements. The inhomogeneous distribution of metal concentrations along the bay suggests different heavy metal sources. Given the ecological and socioeconomic importance of the study area, there is a need for a further analysis of both sediments and biological samples for a better understanding of the contamination levels and origin of metals, in addition to the sustainability of Safi Bay.

Status of Coral Reef Communities on the Caribbean Coast of Costa Rica: Are We Talking about Corals or Macroalgae Reefs? - Fabio Quezada-Perez; Sebastián Mena; Cindy Fernández-García; Juan José Alvarado (Oceans, 2023)
In the past decades, one of the most widely reported phenomena on Caribbean reefs is the general fall in coral cover and rise in macroalgae. Reefs with low coral cover and high macroalgal abundances are often presumed to provide poorer ecosystem functions and services. In this study, we assessed the condition of coral reefs on the Caribbean Coast of Costa Rica and determined how eight key ecosystem metrics varied in response to different coral and fleshy macroalgae covers. Most reefs surveyed had high fleshy macroalgae and low live coral covers, with an average (±SD) of 31 ± 28% and 14 ± 13% per site. The value of many of the ecosystem metrics estimated for coral reefs of the region appears to be lower than what has been reported for other areas in the Caribbean. We found that the rugosity, urchin density, fish richness, total fish biomass, large fish density, and the potential fishery value of the reef were higher in sites with low fleshy macroalgae covers (<10%). Our results concur with the prevailing paradigm that an increase in macroalgae abundance could reduce the ecosystem services provided by coral reefs.

How to Survive Intensive Harvesting: The High Recruitment Rates of the Precious Mediterranean Red Coral (Corallium rubrum L. 1758) - Maria Carla Benedetti; Lorenzo Bramanti; Giovanni Santangelo (Oceans, 2023)
The recruitment process is a fundamental step in population life cycles that determines survival, population demographic structure, and dynamics. The success of recruitment events repeated over successive years greatly affects the survival of long-lived gorgonian populations. Here, we report the recruitment process of the precious, heavily harvested Mediterranean gorgonian Corallium rubrum (red coral) on both settlement tiles and natural substrates over different Mediterranean areas. Red coral is a gonochoric internal brooder that reproduces in early summer. Lecithotrophic planulae settle 15–30 days after release in semi-dark environments at depths between 15 and 800 m. In autumn, 0.58–0.68 mm-wide recruits can be observed on the vaults of small crevices and caves and on rocky cliffs and boulders. Owing to their small size, there is limited knowledge of C. rubrum recruitment in the field. In this study, we examined the recruitment density and distribution in Canadells (Banyuls sur Mer, France) and Calafuria (Livorno, Italy) and compared these findings with those collected over different Mediterranean areas. Red coral exhibited high recruitment values ranging from 0.43 to 13.19 recruits dm−2. The distribution pattern of recruits, examined at a small spatial scale via nearest-neighbor distance analysis, revealed a significantly higher patch frequency on the natural substrate than on settlement tiles, presumably because of the scarcely available spots of free space on the former substrate, which are crowded by competitor species.

A Demonstration of the Capability of Low-Cost Hyperspectral Imaging for the Characterisation of Coral Reefs - Jonathan Teague; John C. C. Day; Michael J. Allen; Thomas B. Scott; Eric J. Hochberg; David Megson-Smith (Oceans, 2023)
The use of hyperspectral imaging in marine applications is limited, largely due to the cost-prohibitive nature of the technology and the risk of submerging such expensive electronics. Here, we examine the use of low-cost (<5000 GBP) hyperspectral imaging as a potential addition to the marine monitoring toolbox. Using coral reefs in Bermuda as a case study and a trial for the technology, data was collected across two reef morphologies, representing fringing reefs and patch reefs. Hyperspectral data of various coral species, Montastraea cavernosa, Diploria labyrinthiformis, Pseudodiploria strigosa, and Plexaurella sp., were successfully captured and analyzed, indicating the practicality and suitability of underwater hyperspectral imaging for use in coral reef assessment. The spectral data was also used to demonstrate simple spectral classification to provide values of the percentage coverage of benthic habitat types. Finally, the raw image data was used to generate digital elevation models to measure the physical structure of corals, providing another data type able to be used in reef assessments. Future improvements were also suggested regarding how to improve the spectral data captured by the technique to account for the accurate application of correction algorithms.

Harbor Porpoise Aggregations in the Salish Sea - Dave Anderson; Laurie Shuster; Cindy R. Elliser; Katrina MacIver; Erin Johns Gless; Johannes Krieger; Anna Hall (Oceans, 2023)
Harbor porpoises are typically seen in small groups of 1–3 individuals, with aggregations of 20+ individuals treated as rare events. Since the 1990s, the harbor porpoise population in the Salish Sea has seen a significant recovery, and an increased number of observed aggregations that exceed the more usual small group sizes has been observed in recent years. By combining the observational data of United States and Canadian research organizations, community scientists, and whale watch captains or naturalists, we demonstrate that harbor porpoise aggregations appear to be more common than previously known, with 160 aggregations documented in 2022 alone. Behavioral data also indicate that foraging behaviors are common and social behaviors, like mating, are seen more often during these encounters compared to small groups. Other behaviors that are considered to be rare or unknown were also observed during these encounters, including cooperative foraging and vessel approach. These aggregations are likely important foraging and social gatherings for harbor porpoises. This holistic approach integrating data from two countries and multiple sources provides a population level assessment that more effectively reflects the behavior of harbor porpoises in this region, which do not recognize the socio-political boundaries imposed upon the natural world.

Vertical Distribution, Community and Population Structures of the Planktonic Chaetognatha in the Western Subarctic Pacific: Insights on the Eukrohnia Species Group - Yuya Nakamura; Haochen Zhang; Atsushi Yamaguchi (Oceans, 2023)
In the oceans, Chaetognatha can contribute significantly to the total zooplankton biomass (up to 10–30%). The genus Eukrohnia, the dominant Chaetognath genus in the western subarctic Pacific, includes E. hamata and E. bathypelagica. Although it has been pointed out that there is no genetic difference between the two species, no study has been made that treats them as the same species group. In this study, we investigated vertical distribution based on the eight vertical stratification samplings down to 1000 m depths conducted day/night at four seasons covering one year, community structure, and population structure of the three dominant Chaetognath species: Parasagitta elegans, E. hamata, and E. bathypelagica in the western subarctic Pacific. The population densities of each species at 0–1000 m water column were 0.04–0.36 ind. m−3 for P. elegans, 0.14–1.60 ind. m−3 for E. hamata, 0.24–1.54 ind. m−3 for E. bathypelagica, and 1.37–2.62 ind. m−3 for Eukrohnia juveniles. The vertical distributions were consistent both day and night, and no diel changes were observed for all species throughout the seasons. The vertical distribution of Chaetognaths evaluated by the distribution center was 61–169 m for P. elegans, 143–206 m for Eukrohnia juveniles, 134–279 m for E. hamata, and 253–612 m for E. bathypelagica. The body length of P. elegans ranged from 4 to 34 mm, and one to three cohorts were identified at each sampling occasion. While the presence of the eight stages has been reported for Eukrohnia, only one to five stages occurred, and specimens belonging to six to eight stages were not observed in the samples throughout the year. The body length of the whole Eukrohnia species ranged from 2 to 14 mm. The body length histograms of the Eukrohnia species group, including E. hamata and E. bathypelagica, and their juveniles showed the presence of two to four cohorts at each sampling date. Within the Eukrohnia species group, vertical changes in body length were present, which were characterized by the smaller specimens occurring at shallower depths, followed by an increase in body length with increasing depths. From the vertical distribution and population structure of the Eukrohnia species group (Eukrohnia juvenile + E. hamata + E. bathypelagica) in this study, there was no difficulty in treating them as one species. It may suggest that E. hamata and E. bathypelagica in the western subarctic Pacific could be treated as one species group. To clarify this point, a detailed genetic analysis of the Eukrohnia species group will be needed for future studies.

Seasonal Changes in Vertical Distribution and Population Structure of the Dominant Hydrozoan Aglantha digitale in the Western Subarctic Pacific - Mari Aizawa; Tian Gao; Atsushi Yamaguchi (Oceans, 2023)
Hydrozoans are numerically dominant taxa in gelatinous zooplankton communities of the worldwide oceans and play an energy transfer role connecting primary producers and higher trophic level organisms. In the western subarctic Pacific, St. K2 has been established as a long-term time-series monitoring station. Various studies on zooplankton have been conducted, while hydrozoans have not been treated. This study presents the abundance, vertical distribution, and population structure of the dominant hydrozoan species (Aglantha digitale) at St. K2. Samples collected by vertical stratification samplings from eight layers of 0–1000 m both day and night during four seasons in one year. Hydrozoans occur throughout the year. The annual mean abundance of A. digitale was 198.4 ind. m−2 and composed of 91.9% of hydrozoans. The vertical distribution of A. digitale was concentrated for the epipelagic layer (0–200 m), both day and night of the most season. The bell height (BH) of A. digitale ranged between 2.4–18.9 mm. Most of the mature individuals, with gonad length larger than 10% of BH, occurred only in July. The BH of mature individuals ranged from 4.7 to 17.6 mm, with the BH of most mature individuals were larger than >10 mm. Through observation on BH at each sampling layer, small individuals with BH < 6 mm were distributed below 300 m depths throughout the seasons, expanding their vertical distribution to the deeper layers. Inter-region comparison of abundance, maturation body size, and generation length of A. digitale revealed that these parameters are varied with the region and depend on the marine ecosystem structures.

Novel Interaction between a Rabbitfish and Black Corals - Erika Gress; Tom C. Bridge; Justin Fyfe; Gemma Galbraith (Oceans, 2023)
Herbivorous fishes play important functional roles in coral reef ecosystems, and their influence on mediating competitive dynamics between corals and macroalgae is well studied. Nonetheless, direct interactions between herbivorous fishes and corals may also be relevant, although these are less studied. Here, we describe a series of observations of schools of the herbivorous streaked rabbitfish (Siganus javus) nibbling on black corals (order Antipatharia) at the SS Yongala wreck, within the Great Barrier Reef Marine Park. We provide a hypothesis that may explain this behaviour, which, if confirmed, would represent a mechanism influencing the health of the corals. Moreover, this interaction extends the typical coral–algae competition for space paradigm and furthers knowledge of complex relationships between coral reef organisms.

Environmental Conditions Affect Striped Red Mullet (Mullus surmuletus) Artisanal Fisheries - Francisco Leitão (Oceans, 2023)
The influence of environmental variables (oceanographic and climatic) on the catch rates of striped red mullet (Mullus surmuletus) by artisanal fishery was investigated using different time series models (Dynamic Factorial Analyses; Min-Max Factorial Analyses and Generalized Least Square models). Climatic and oceanographic survey data were collected at different areas of the Portuguese coast (Northwestern, Southwestern and South-Algarve) with distinct oceanographic regimes. Time series analyses reveal an effect of fishing effort in catch rates in Southwestern areas. Variability in M. surmuletus catch rates was associated to regional environmental multi-controls. Upwelling and westerly winds were the main drivers of catch rates variability across the three areas but the type of relationship varied among them. A consistent relationship between catch rates and environment factors was identified during the peak period of seasonal recruitment (spring to summer) in Southwest and South-Algarve coast, with Upwelling-summer and Sea surface temperature-spring affecting short term (lag 2 years) catch rates. In South-Algarve the increase in SST in summer, during peak of spawning, was correlated with the catch rate increase with a lag of two years. Environmental effect on catch rates reveals that fisheries management needs to accommodate the regional effect of environment variables on species biology to better define future assessment plans (catch limits).

Comparative Microbial Community Analysis of Fur Seals and Aquaculture Salmon Gut Microbiomes in Tasmania - Erin D’Agnese; Ryan J. McLaughlin; Mary-Anne Lea; Esteban Soto; Woutrina A. Smith; John P. Bowman (Oceans, 2023)
In Tasmania, Australian fur seals (Arctocephalus pusillus doriferus) regularly interact with Atlantic salmon (Salmo salmar L.) aquaculture lease operations and opportunistically consume fish. The microbial communities of seals and aquaculture salmon were analyzed for potential indicators of microbial sharing and to determine the potential effects of interactions on wild seal microbiome composition. The high-throughput sequencing of the V1–V3 region of the 16S rRNA genes from the gut microbial communities of 221 fur seals was performed: 41 males caught at farms, 50 adult scats from haul-outs near farms, 24 necropsied seals, and controls from Bass Strait breeding colonies, encompassing 56 adult scats and 50 pup swabs. QIIME2 and R Studio were used for analysis. Foraging at or near salmon farms significantly shifted seal microbiome biodiversity. Taxonomic analysis showed a greater divergence in Bacteroidota representatives in male seals captured at farms compared to all other groups. Pathogens were identified that could be monitoring targets. Potential indicator amplicon sequence variants were found across a variety of taxa and could be used as minimally invasive indicators for interactions at this interface. The diversity and taxonomic shifts in the microbial communities of seals indicate a need to further study this interface for broader ecological implications.

Microbiome of Sri Lankan Coral Reefs: An Indian Ocean Island Subjected to a Gradient of Natural and Anthropogenic Impacts - Mohamed F. M. Fairoz; Kevin T. Green; Kuwaja N. M. Sajith; Weerathunga A. S. Chamika; Amarasingha M. K. N. Kularathna; Saichetana Macherla; Douglas S. Naliboff; Ana Cobián-Güemes; Linda Wegley-Kelly; Forest Rohwer (Oceans, 2023)
Coral reefs around Sri Lanka have coexisted with human communities for thousands of years and are a continual source of food, economic productivity, and tourism. Although these reef systems sustain nearby populations, little is known about the presence or functional role of microbial communities on reefs dominated by hard corals or fleshy algae. Coral reef benthos cover was recorded, and reef-associated water samples were collected, sequenced and analyzed from seven coral reefs around Sri Lanka. Microbial metagenomes were analyzed to reveal both the taxonomic and metabolic makeup of the microbial communities present at each site. A metagenomic analysis of microbial phyla showed that Alphaproteobacteria and Gammaproteobacteria were most abundant, constituting up to 79.4% of microbial communities. At the order level, Rhodobacterales dominated the microbial communities across all sites, with the exception of the Paraviwella coral reef, where the order Alteromonadales dominated. A Principal Component Analysis (PCA) was performed using metagenomic sequence data to find the possible trends of interactions and drivers of taxonomic and metabolic community structure. This study is the first microbial metagenome dataset of coral reef associated water from the Indian Ocean continental island, Sri Lanka. These data further confirm the need for a comprehensive study of reefs in Sri Lanka aimed at elucidating the processes involved in microbial energy utilization.

Seasonal Upwelling Conditions Modulate the Calcification Response of a Tropical Scleractinian Coral - Carlos Gómez; Andrés Acosta-Chaparro; Cesar Bernal; Diana Gómez-López; Raúl Navas-Camacho; David Alonso (Oceans, 2023)
Natural processes such as upwelling of deeper-water masses change the physical-chemical conditions of the water column creating localized ocean acidification events that can have an impact on the natural communities. This study was performed in a coral reef system of an archetypical bay within the Tayrona National Natural Park (PNNT) (Colombia), and aimed to quantify net calcification rates of a foundational coral species within a temporal context (6 months) taking into account the dynamics of seasonal upwelling that influence the study area. Net calcification rates of coral fragments were obtained in situ by the alkalinity anomaly technique in short-term incubations (~2.5 h). We found a significant effect of the upwelling on net calcification rates (Gnet) (p < 0.05) with an 42% increase in CaCO3 accretion compared to non-upwelling season. We found an increase in total alkalinity (AT) and dissolved inorganic carbon (DIC) with decreased aragonite saturation (Ωara) for the upwelling months, indicating an influence of the Subtropical Under Water mass (SAW) in the PNNT coral community. Significant negative correlations between net calcification with temperature and Ωara, which indicates a positive response of M. auretenra with the upwelling conditions, thus, acting as “enhancer” of resilience for coral calcification.

Volatile Organic Compounds Released by Oxyrrhis marina Grazing on Isochrysis galbana - Charel Wohl; Queralt Güell-Bujons; Yaiza M. Castillo; Albert Calbet; Rafel Simó (Oceans, 2023)
A range of volatile organic compounds (VOCs) have been found to be released during zooplankton grazing on microalgae cultivated for commercial purposes. However, production of grazing-derived VOCs from environmentally relevant species and their potential contribution to oceanic emissions to the atmosphere remains largely unexplored. Here, we aimed to qualitatively explore the suite of VOCs produced due to grazing using laboratory cultures of the marine microalga Isochrysis galbana and the herbivorous heterotrophic dinoflagellate Oxyrrhis marina with and without antibiotic treatment. The VOCs were measured using a Vocus proton-transfer-reaction time-of-flight mass spectrometer, coupled to a segmented flow coil equilibrator. We found alternative increases of dimethyl sulfide by up to 0.2 nmol dm−3 and methanethiol by up to 10 pmol dm−3 depending on the presence or absence of bacteria regulated by antibiotic treatment. Additionally, toluene and xylene increased by about 30 pmol dm−3 and 10 pmol dm−3, respectively during grazing only, supporting a biological source for these compounds. Overall, our results highlight that VOCs beyond dimethyl sulfide are released due to grazing, and prompt further quantification of this source in budgets and process-based understanding of VOC cycling in the surface ocean.

Need for the Scuba Diving Industry to Interface with Science and Policy: A Case of SIDS Blue Workforce - Zahidah Afrin Nisa (Oceans, 2023)
To achieve coral reef resilience under Agenda 2030, island governments need to institutionalise a competent blue workforce to expand their reef resilience initiatives across economic organisations and industries. The ability of island governments to shape new policies for sustainable island development relying on natural capital, such as coral reefs, has been hampered by structural and institutional deficiencies on both sides of the science-policy interface (SPI) at the UN. Using a qualitative research design, this article explores the science-policy interface (SPI) policy paper, Rebuilding Coral Reefs: A Decadal Grand Challenge and the role of this SPI in guiding UN coral reef financing for island states. This article uses the dive industry to investigate the needs of policymakers in island states via a conceptual framework for policy analysis. This article highlights the gaps of the SPI from the perspective of the global south and is beneficial for the islands selected under the Global Coral Reef Investment Plan. The article highlights the results of the SPI to island decision makers, which indicate that, without a policy framework that includes space for industrial policy within UN SPI, island governments will continue to fall into financial traps that constrain their efforts in operationalising their blue workforce. The study concludes that interlinked SDGs, such as SDG 9 and SDG 8, which focus on linking industrial innovation and infrastructure with decent work, as well as SDG 16 and 14.7, provide SIDS institutions with integrated policy approaches capable of bridging the divides between the scientific community, the diving industry, and island governments and that this needs to be further explored at all levels.

Marine Biodegradability and Ecotoxicity of MWool® Recycled Wool Fibers: A Circular-Economy-Based Material - Serena Anselmi; Francesca Provenza; Tecla Bentivoglio; Giuseppe Picerno; Andrea Cavallo; Monia Renzi (Oceans, 2023)
Pollution of the marine environment by microfibers is considered a problem for ecosystem conservation. The amount of microplastic, localization of sources, and associated ecotoxicity are well known in the literature. Wastewater from washing machines is the main source of microplastic fibers in the aquatic environment, and fabrics made from recycled plastic are widely reused. The circular economy also promotes recycling of dyed natural wool materials as a basis for making new clothing, but in this case, less research has been conducted on the behaviour and effects of recycled wool microfibers in marine ecosystems. MWool® (MW) and MWool® carded (MWc) products made from recycled wool fibers were tested in mesocosms to investigate the biodegradation of wool fibers over a 260-day period and the effects of this process on marine ecosystems in terms of microfiber inputs and the ecotoxicological effects of by-products and chemicals released during degradation. The early degradation process was associated with the loss of artificial pigments from the dyed wool, particularly pink and red, which occurred within 30–90 days of exposure. Mean release of microparticles into contact water is significantly different from control (T0, p < 0.01) at 90 days MWc (36.6 mg/L) and 180 days MW (42.9 mg/L). The biodegradation process is accompanied by swelling of wool fibers, which is associated with a significant increase in mean wool thickness (p < 0.05, 18.8 ± 2.1 µm at T0 vs. 24.0 ± 7.1 µm). In both cases, the contact water was not associated with signs of ecotoxicity for the marine species tested in this study (Phaeodactylum tricornutum, Brachionus plicatilis, and Paracentrotus lividus).

Sensitivity of the Wave Field to High Time-Space Resolution Winds during a Tropical Cyclone - Laura Pérez-Sampablo; Pedro Osuna; Bernardo Esquivel-Trava; Nicolas Rascle; Francisco J. Ocampo-Torres (Oceans, 2023)
The impact of the high space-temporal variability of the wind field during the moderate and intense storm stages of a tropical cyclone on the wave field as computed by the numerical model WaveWatch III is investigated in this work. The realistic wind fields are generated by a high-resolution implementation of the HWRF model in the Gulf of Mexico and stored over 15 min intervals. The spatial structure of the wind field computed by HWRF is highly variable in space and time, although its mean structure is very similar to that described for parametric hurricanes already specified in the previous studies. The resulting storm-generated wave fields have a persistent structure, with wave maxima present in the forward quadrants of the storm and in the rear quadrant II. This structure is determined by the strong winds and the extended fetch condition in quadrants I and II, as well as by the translation speed of the storm. When a shorter time interval is analyzed (e.g., a 3 h period, when the storm becomes a category 1 hurricane), the structure of the mean wind field may differ greatly from the mean field calculated with a sufficiently longer period; however, the spatial distribution of the wave field around the hurricane tends to maintain its typical spatial structure. The use of wind fields with reduced time variability (e.g., with a 3 h moving average) does not change the structure of the mean wave field, but reduces the mean wave height values by up to 10%.

Spatiotemporal Variation in Environmental Key Parameters within Fleshy Red Algae Mats in the Mediterranean Sea - Alice G. Bianchi; Christian Wild; Monica Montefalcone; Enzo Benincasa; Yusuf C. El-Khaled (Oceans, 2023)
In the Mediterranean, the fleshy, mat-forming red alga Phyllophora crispa creates high-biodiversity habitats that influence light availability, water movement, and temperature. However, knowledge about its influence on other key environmental parameters, such as oxygen availability, chlorophyll, and turbidity, is missing. Therefore, we conducted an in situ study in the Western Mediterranean Sea using multiparameter probes that were placed multiple times on algal P. crispa mats, in adjacent Posidonia oceanica seagrass meadows, and on bare hard bottoms. We acquired a total of 17 full diel measurements for dissolved oxygen (DO), chlorophyll, and turbidity in September and October 2019. Results showed that P. crispa mats influence the investigated parameters differently when compared to P. oceanica meadows and that a monthly effect was observed. In September, general DO patterns measured for P. crispa mats and P. oceanica meadows follow the daily cycle depending on light availability, with the measured DO being lower in the P. oceanica meadows compared to the P. crispa mats and the hard-bottom habitats. In October, however, no significant difference in DO concentrations was observed between P. crispa mats and P. oceanica meadows. Results of this study corroborate that P. crispa mats can be viewed as an ecosystem engineering species, influencing environmental parameters and, hence, providing a habitat for outstanding associated biodiversity.

Wanted Dead or Alive: Skeletal Structure Alteration of Cold-Water Coral Desmophyllum pertusum (Lophelia pertusa) from Anthropogenic Stressors - Erica Terese Krueger; Janina V. Büscher; David A. Hoey; David Taylor; Peter J. O’Reilly; Quentin G. Crowley (Oceans, 2023)
Ocean acidification (OA) has provoked changes in the carbonate saturation state that may alter the formation and structural biomineralisation of calcium carbonate exoskeletons for marine organisms. Biomineral production in organisms such as cold-water corals (CWC) rely on available carbonate in the water column and the ability of the organism to sequester ions from seawater or nutrients for the formation and growth of a skeletal structure. As an important habitat structuring species, it is essential to examine the impact that anthropogenic stressors (i.e., OA and rising seawater temperatures) have on living corals and the structural properties of dead coral skeletons; these are important contributors to the entire reef structure and the stability of CWC mounds. In this study, dead coral skeletons in seawater were exposed to various levels of pCO2 and different temperatures over a 12-month period. Nanoindentation was subsequently conducted to assess the structural properties of coral samples’ elasticity (E) and hardness (H), whereas the amount of dissolution was assessed through scanning electron microscopy. Overall, CWC samples exposed to elevated pCO2 and temperature show changes in properties which leave them more susceptible to breakage and may in turn negatively impact the formation and stability of CWC mound development.

Bioerosion Research in the South China Sea: Scarce, Patchy and Unrepresentative - Yen-Huei Li; Barbara Calcinai; Jiayi Lim; Christine H. L. Schönberg (Oceans, 2023)
Coral reefs are in decline globally, resulting in changed constructive and destructive processes. The South China Sea is a marginal sea that is of high biological importance, but also subjected to extreme local and global pressures. Yet, the regional calcium carbonate dynamics are not well understood, especially bioerosion. A literature search for research on bioerosion and bioeroders in the South China Sea found only 31 publications on bioerosion-related research and 22 biodiversity checklists that contained bioeroders, thus generating a paltry bibliography. Bioerosion research in the South China Sea is still undeveloped and reached only two publications per year over the last few years. Hong Kong is the hotspot of activities as measured in output and diversity of methods, but the research in Hong Kong and elsewhere was strongly favoring field surveys of sea urchins over other bioeroders. Overall, macroborers received almost equal attention as grazer-eroders, but interest in microborers was low. Almost 90% of the research was conducted by local workers, but 90% of the publications were still disseminated in English. Field surveys and laboratory analyses made up over 40% of the research, but experimental work was mostly missing and represents the largest, most important gap. A government initiative in Thailand generated much knowledge on the distribution of marine sponges; otherwise urchins were again prominent in diversity checklists. Comparatively, many checklists were produced for Vietnam from work by visiting scientists. Most studies investigated coastal habitats, but a fourth sampled at oceanic locations. About 36% of the checklist publications covered the entire South China Sea; the rest produced faunistic records for locations within single countries. Our efforts demonstrate that, while active bioerosion research and basic expertise exist in the South China Sea, research remained unrepresentative with respect to taxa, ecofunctional guilds, and especially to controlled experiments. The latter are urgently needed for prognoses, modelling and management in this populated and overused marine environment.

Acknowledgment to the Reviewers of Oceans in 2022 (Oceans, 2023)
High-quality academic publishing is built on rigorous peer review [...]

Posidonia oceanica (L.) Delile at Its Westernmost Biogeographical Limit (Northwestern Alboran Sea): Meadow Features and Plant Phenology - Ángel Mateo-Ramírez; Pablo Marina; Alejandro Martín-Arjona; Elena Bañares-España; José E. García Raso; José L. Rueda; Javier Urra (Oceans, 2023)
Meadows of the seagrass Posidonia oceanica inhabit most infralittoral bottoms of the Mediterranean Sea and are considered one of the main climax stages of the infralittoral environment. This seagrass has its western distributional limit along the coast of the Alboran Sea. Taking into account the decline of P. oceanica meadows and the global scenario of ocean warming, it becomes essential to know the structure, temporal dynamics, sexual reproduction and conservation status of this seagrass, across its geographical distribution, including the distribution boundaries where the meadows withstand limiting environmental conditions. In the present work, we studied the structure, phenology and flowering events of four P. oceanica meadows located in the northwestern Alboran Sea (close to the Strait of Gibraltar). Results indicate a decreasing trend of patch size, bathymetric range and number of leaves per shoot towards the Strait (and the Atlantic Ocean), as well as an increasing trend of shoot density and leaf height. Phenological parameters of the northwestern Alboran Sea P. oceanica meadows presented temporal dynamics similar to meadows from other locations within the biogeographical distribution of this seagrass, with similar or even less annual variability in the former. Although most of the studied P. oceanica meadows seem to present a good health status (BiPo index ~0.6) with high shoot densities and some flowering events, some of them showed evidence of regression.

Coral-Focused Climate Change Adaptation and Restoration Based on Accelerating Natural Processes: Launching the “Reefs of Hope” Paradigm - Austin Bowden-Kerby (Oceans, 2022)
The widespread demise of coral reefs due to climate change is now a certainty, and investing in restoration without facing this stark reality risks failure. The 50 Reefs Initiative, the dominant adaptation model for coral reefs is examined, and a new coral-focused paradigm is proposed, based on helping coral reefs adapt to rising temperature, to ensure that as many coral species as possible survive locally over time. With pilot sites established in six Pacific Island nations, genebank nurseries of bleaching resistant corals are secured in cooler waters, to help prevent their demise as heat stress increases. Unbleached corals selected during bleaching events are included. From these nurseries corals are harvested to create nucleation patches of genetically diverse pre-adapted corals, which become reproductively, ecologically and biologically viable at reef scale, spreading out over time. This “Reefs of Hope” paradigm, modelled on tropical forest restoration, creates dense coral patches, using larger transplants or multiple small fragments elevated on structures, forming fish habitat immediately. The fish help increase coral and substratum health, which presumably will enhance natural larval-based recovery processes. We also hypothesize that incoming coral recruits, attracted to the patch, are inoculated by heat adapted algal symbionts, facilitating adaptation of the wider reef. With global emissions out of control, the most we can hope for is to buy precious time for coral reefs by saving coral species and coral diversity that will not likely survive unassisted.

Effect of Substratum Structural Complexity of Coral Seedlings on the Settlement and Post-Settlement Survivorship of Coral Settlers - Shuichi Fujiwara; Daisuke Kezuka; Kazutaka Hagiwara; Hiroo Ishimori; Hideo Tabata (Oceans, 2022)
The substratum structure is critical for facilitating settlement and increasing the survivorship of coral settlers. However, knowledge about its structural complexity is largely lacking. In this study, we examined the effect of complexity on the settlement and post-settlement survivorship of coral settlers using four types of structures: groove, using a CSD (Coral Settlement Device, 4.5 cm φ × 2.5 cm H, top-shaped ceramic); flat, using a CP (Ceramic Plate, 29.5 cm L × 3.1 cm W × 0.9 cm H, unglazed ceramic plate); linear, using a CN (Coral Net, mesh size 19 mm, biodegradable plastic net); and wrinkle, using a SS (Scallop Shell, 11.0 cm in shell length). The complexity was obtained from the ratio of the surface area to the vertically projected area of the substratum. The substratum sets were installed in the coral reef around the Ryukyu Islands every May from 2012 to 2014. After about 2 or 6 months of spawning, a certain number of substratum types were sampled, and the number of coral spats that settled on them was counted by taxa classified into Acropora, Pocilloporidae, Millepora, and Others. The larval settlement rate in the first set of samples and the survivorship of coral spats in the second set of samples were estimated. The mean settlement rate was, in order, the CSD; SS; CN; and CP, and the mean survivorship was, in order, the CSD; CP; SS; and CN, over three years. A positive correlation was found between the structural complexity, mean settlement rate, and mean survivorship. Our results show that the structural complexity of coral seedlings affects the settlement of coral larvae and the survivorship of coral spats.

Using Colour as a Marker for Coral ‘Health’: A Study on Hyperspectral Reflectance and Fluorescence Imaging of Thermally Induced Coral Bleaching - Jonathan Teague; Jack Willans; David A. Megson-Smith; John C. C. Day; Michael J. Allen; Thomas B. Scott (Oceans, 2022)
Rising oceanic temperatures create more frequent coral bleaching events worldwide and as such there exists a need for rapid, non-destructive survey techniques to gather greater and higher definition information than that offered by traditional spectral based monitoring systems. Here, we examine thermally induced laboratory bleaching of Montipora capricornis and Montipora confusa samples, utilising hyperspectral data to gain an understanding of coral bleaching from a spectral standpoint. The data revealed several characteristic spectral peaks that can be used to make health determinations. The fluorescence peaks are attributed to fluorescent proteins (FPs) and Chlorophyll-a fluorescence. The reflectance peaks can be attributed to Chlorophyll absorption and accessory pigments such as Peridinin and Diadinoxanthin. Each characteristic spectral peak or ‘marker’ allows for observation of each aspect of coral health and hence, simultaneous monitoring of these markers using hyperspectral imaging techniques provides an opportunity to better understand the processes occurring during bleaching and the rates at which they occur relative to one another.

Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2022)
Studies on the trophic ecology of scleractinian corals often include stable isotope analyses of tissue and symbiont carbon and nitrogen. These approaches have provided critical insights into the trophic sources and sinks that are essential to understanding larger-scale carbon and nitrogen budgets on coral reefs. While stable isotopes have identified most shallow water (<30 m) corals as mixotrophic, with variable dependencies on autotrophic versus heterotrophic resources, corals in the mesophotic zone (~30–150 m) transition to heterotrophy with increasing depth because of decreased photosynthetic productivity. Recently, these interpretations of the stable isotope data to distinguish between autotrophy and heterotrophy have been criticized because they are confounded by increased nutrients, reverse translocation of photosynthate, and changes in irradiance that do not influence photosynthate translocation. Here we critically examine the studies that support these criticisms and show that they are contextually not relevant to interpreting the transition to heterotrophy in corals from shallow to mesophotic depths. Additionally, new data and a re-analysis of previously published data show that additional information (e.g., skeletal isotopic analysis) improves the interpretation of bulk stable isotope data in determining when a transition from primary dependence on autotrophy to heterotrophy occurs in scleractinian corals.

When and Where Did They Strand? The Spatio-Temporal Hotspot Patterns of Cetacean Stranding Events in Indonesia - Putu Liza Kusuma Mustika; Kathryn K. High; Mochamad Iqbal Herwata Putra; Achmad Sahri; I Made Jaya Ratha; Muhammad Offal Prinanda; Firdaus Agung; Februanty S. Purnomo; Danielle Kreb (Oceans, 2022)
Analyses of the spatial and temporal patterns of 26 years of stranding events (1995–2011 and 2012–2021, n = 568) in Indonesia were conducted to improve the country’s stranding response. The Emerging Hot Spot Analysis was used to obtain the spatial and temporal hotspot patterns. A total of 92.4% events were single stranding, while the remaining were of mass stranding events. More stranding events were recorded between 2012 and 2021 in more dispersed locations compared to the previous period. Within the constraints of our sampling limitations, East Kalimantan and Bali were single stranding hotspots and consecutive hotspots. East Java and Sabu-Raijua in East Nusa Tenggara were mass stranding hotspots. Temporally, Raja Ampat (West Papua) experienced a significant increase in case numbers. The presence of active NGOs, individuals or government agencies in some locations might have inflated the numbers of reported cases compared to areas with less active institutions and/or individuals. However, our results still give a good understanding of the progression of Indonesia’s stranding responses and good guidance of resource allocation for the stranding network. Several locations in Indonesia that need more efforts (e.g., more training workshops on rescue and necropsies) have been identified in this paper. Suggestions to improve data collection (including georeferencing tips) have also been included.

Age and Sexual Maturity Estimation of Stranded Striped Dolphins, Stenella coeruleoalba, Infected with Brucella ceti - Karol Roca-Monge; Rocío González-Barrientos; Marcela Suárez-Esquivel; José David Palacios-Alfaro; Laura Castro-Ramírez; Mauricio Jiménez-Soto; Minor Cordero-Chavarría; Daniel García-Párraga; Ashley Barratclough; Edgardo Moreno; Gabriela Hernández-Mora (Oceans, 2022)
Age parameters in cetaceans allow examining conservation and studying individuals with growth affection. The age and sexual maturity of 51 stranded Stenella coeruleoalba striped dolphins from the Eastern Tropical Pacific (ETP) of Costa Rica, most suffering brucellosis (95.6%), were assessed. In order to ascertain the dolphins’ ages, we measured the length and growth of dentin-layer group counts (GLGs) and assessed flipper bone radiography without (FBSA) and with a formula (FBF). Sexual maturity was determined through gonadal histology and sexual hormone serum levels. Compared with a model based on S. coeruleoalba ages estimations in other latitudes, the striped dolphin studied displayed deficient growth parameters, with considerable variability in length, teeth, and flippers bone development. Close to 43% (n = 15) of GLGs’ measurements were below the body length average ranges for the predicted age, suggesting developmental abnormalities. Likewise, 34.4% and 31.2% of the dolphins assessed by FBSA and FBF were also below the body length based on age prediction curves, also indicating developmental abnormalities. This information is supported by the poor correlation between GLGs, FBSA, and FBF. Inconsistencies between sexually mature males and females related to GLGs, FBSA, and FBF were evident. Although the different oceanic settings of the ETP, such as contamination, food access, diseases, and other parameters, may influence size variation, our data also suggest that long-lasting debilitating brucellosis may account for detrimental growth in the ETP striped dolphins. Our study highlights the possible deleterious consequences of chronic infectious diseases in the cetacean populations already confronting distressful conditions.

Impact of Indian Ocean Dipole Events on Phytoplankton Size Classes Distribution in the Arabian Sea - Rebekah Shunmugapandi; Shirishkumar Gedam; Arun B. Inamdar (Oceans, 2022)
Changes in the environmental condition associated with climatic events could potentially influence the PSC dynamics of the regional marine ecosystem. The Indian Ocean dipole (IOD) is one of the critical ocean–atmosphere interactions that affects the climate of the Arabian Sea, and it could be a potential factor influencing the regional PSC distribution. However, the relationship between PSC and IOD remains unclear and less explored. In this study, using the in-situ database acquired from the Arabian Sea, we reparametrized the three−component abundance−based phytoplankton size class model and applied it to reconstructed satellite−derived chlorophyll−a concentration to extract the fractional contribution of phytoplankton size classes to chlorophyll−a concentration. Further, we investigated the influence of IOD on the changes in the biological–physical properties in the Arabian Sea. The results showed that the biological–physical processes in the Arabian Sea are interlinked and the changes in the IOD mode control the physical variables like sea surface temperature (SST), sea surface height (SSH), and mixed layer depth (MLD), which influence the specific PSC abundance. Unprecedented changes in the PSC distribution and physical properties were observed during the extreme positive and negative IOD events, which clearly indicated the potential role of IOD in altering the PSC distribution in the Arabian Sea. This study highlights the impact of extreme climate events on PSC distribution and the need for a better understanding of the associated physical–biological–climate interactions.

Erythrocyte, Whole Blood, Plasma, and Blubber Fatty Acid Profiles in Oceanaria-Based versus Wild Alaskan Belugas (Delphinapterus leucas) - Todd L. Schmitt; Caroline E. C. Goertz; Roderick C. Hobbs; Steve Osborn; Stacy DiRocco; Heidi Bissell; William S. Harris (Oceans, 2022)
This investigation compared the fatty acid (FA) levels found in erythrocyte (RBC) membranes, plasma, whole blood (WB), and blubber from wild Alaskan (Bristol Bay) belugas (Delphinapterus leucas) (BBB, n = 9) with oceanaria-based belugas (OBB, n = 14) fed a controlled diet consisting of primarily herring (Clupea harengus) and capelin (Mallotus villosus). FA patterns in RBCs, WB, and plasma varied considerably between BBB and OBB animals. Focusing on RBC FA levels of known dietary origin, the OBBs had markedly higher levels of 20:1n9,11 and 22:1n9,11. RBC levels of these fatty acids were 1% and 0.2% in the BBBs, but 8.2% and 4.5%, respectively, in the OBBs (p < 0.05 both). These long-chain mono-unsaturated FAs (LC-MUFAs) are rich in herring and capelin but not in the prey species (i.e., salmonids, smelt, cod, and shrimp) generally available to BBBs. As for the marine omega-3 poly-unsaturated fatty acids [PUFAs; 20:5n3 (eicosapentaenoic acid) and 22:6n3 (docosahexaenoic acid)], the former was higher in the OBBs vs. BBBs (16% vs. 11%, p < 0.05), but the latter was low and similar in both (3.8% vs. 4%). Similar patterns were seen in the other sample types, except that DHA% was higher in BBB than OBB animals in both plasma (12.6% vs. 8.7%) and in blubber (12% vs. 4.9%) (p < 0.05). A physiologically important omega-6 PUFA, 20:4n6 (arachidonic acid) was approximately 2× higher in BBB than OBB within RBC (22% vs. 12%), WB (16% vs. 7%), plasma (11.5% vs. 4.6%) and blubber (4.6% vs. 2.4%), respectively. While blubber FAs have been evaluated historically and relatively easy to procure with biopsy darts in the field, this study proposes that blood-based FAs collected during health assessments or subsistence hunts, especially RBC or WB FAs, may be more convenient to handle using dried blood spot cards (DBS) with limited cold storage and simplifies shipping requirements, and may more accurately reflect tissue FA status.

Strandings in St Vincent Gulf Bioregion, South Australia: 12-Year Study Monitors Biology and Pathology of Cetaceans - Ikuko Tomo; Catherine M. Kemper (Oceans, 2022)
The semi-enclosed environment of the St Vincent Gulf Bioregion and its fauna are impacted by many human activities. Long-term monitoring of cetaceans is vital. Records of collected specimens (173) and those not examined by the South Australian Museum (98 non-specimens) from 2009–2020 were analyzed. Necropsies were carried out on most carcasses using gross, histopathological, and diagnostic assessment of pathogens, organs, and skin lesions. The relative age and circumstance of death were assigned. Baleen whales (five species) and odontocetes (eight species) were studied. Indo-Pacific bottlenose dolphins (Tursiops aduncus) and common dolphins (Delphinus delphis) were frequently recorded and analyzed in detail. Anthropogenic cases were prevalent (21%). Many dolphins (62%) were immature males. Disease (73%) was the most frequently recorded circumstance of death. The most common pathological change was inflammatory disease, including infectious pneumonia. In Indo-Pacific bottlenose dolphins, infectious disease was more prevalent in the greater St Vincent Gulf Bioregion than in the Adelaide Dolphin Sanctuary. Microbe testing confirmed 32 species of bacteria, 2 fungi, and 1 virus. Nematodes and trematodes were recorded throughout the study, sometimes in association with microbes. Toxoplasma gondii was observed in an Indo-Pacific bottlenose dolphin. Severe traumatic injury was recorded in many dolphins, including anthropogenic cases. A tumor (leiomyoma) was described from a single common dolphin. This study provides an important baseline for the future monitoring of emerging infectious and chronic diseases, and anthropogenic threats in the region.

Effectiveness of Moorings Constructed from Rope in Reducing Impacts to Seagrass - Richard K. F. Unsworth; Leanne C. Cullen-Unsworth; James N. Hope; Benjamin L. H. Jones; Richard J. Lilley; Hanna K. Nuuttila; Beth Williams; Nicole E. Esteban (Oceans, 2022)
Seagrass meadows commonly reside in shallow sheltered coastal environments which are typically safe havens for mooring boats. There is evidence from around the globe that the use of common swinging chain moorings leads to halos of bare sediment in otherwise productive seagrass. These halos reduce animal abundance and diversity and lead to a loss of the carbon stored within sediments. To protect and enhance seagrass ecosystem services, low-cost simple solutions are required that can solve the problems of boating-based disturbance. In the present novel study, we provide evidence that the simple replacement of mooring chains with rope can significantly reduce damage to sensitive benthic habitats such as seagrass. At three locations across a range of environmental conditions, we provide evidence that well-established moorings constructed from rope do not damage seagrass. Overall, there was a significant effect (F1,756 = 299.46, p < 0.001) of the mooring type and distance from the mooring base. This equates to a 44% increase in seagrass cover within areas around a rope mooring relative to a chain one. Most small boat mooring activity happens within the summer months, therefore large heavy-duty winter mooring systems are not required in many situations, opening opportunities for adapted systems that have a reduced environmental impact. The present study suggests that there is a ready-made, low-technology, low-cost solution already in existence for halting the widespread loss of seagrass from small boat mooring damage and allowing recovery and opportunity for restoration.

Local Ecological Knowledge Reveals Change in Seagrass Social–Ecological Systems - Benjamin L. H. Jones; Richard K. F. Unsworth; Lina M. Nordlund; Rohani Ambo-Rappe; Yayu A. La Nafie; Mary Rose Lopez; Susantha Udagedara; Leanne C. Cullen-Unsworth (Oceans, 2022)
It is widely recognized that humanity is currently facing multiple planetary crises, including the widespread loss of biodiversity and a rapidly changing climate. The impacts of these crises are often far reaching and threaten food security (SDG goal two: zero hunger). Small-scale fisheries are estimated to provide livelihoods for over one hundred million people and sustenance for approximately one billion people but face a plethora of threats and challenges linked to planetary crises. In this multi-country assessment (150 coastal villages across five countries within the Indo-Pacific), household interviews revealed how seagrass meadows are important to small-scale fisheries, particularly as a place to find and collect a reliable source of food. Interviews also revealed that habitat loss and the over-exploitation of these resources are placing people and their food security at risk. This study exposed how dynamic local ecological knowledge can be, uncovering personal opinions and responsibilities that result in the hybridization of knowledge. Here, we demonstrate the importance of using local ecological knowledge to incorporate shared values into management but also highlight that an integrated approach, pairing local and conventional scientific knowledge, is needed urgently if we are to meet the needs of people while simultaneously conserving biodiversity.

Divergent Gene Expression Profiles in Alaskan Sea Otters: An Indicator of Chronic Domoic Acid Exposure? - Lizabeth Bowen; Susan Knowles; Kathi Lefebvre; Michelle St. Martin; Michael Murray; Kim Kloecker; Daniel Monson; Benjamin Weitzman; Brenda Ballachey; Heather Coletti; Shannon Waters; Caroline Cummings (Oceans, 2022)
An opportunistic investigation into ecosystem instability in Kachemak Bay (KBay), Alaska, has led us to investigate exposure to toxic algae in sea otters. We used gene expression to explore the physiological health of sea otters sampled in KBay in May 2019. We found altered levels of gene transcripts in comparison with reference sea otters from clinically normal, oil-exposed, and nutritionally challenged populations sampled over the past decade. KBay sea otters were markedly divergent from the other groups for five genes, which indicated the involvement of neurological, cardiac, immune, and detoxification systems. Further, analyses of urine and fecal samples detected domoic acid in the KBay sea otters. In combination, these results may point to chronic, low-level exposure to an algal toxin, such as domoic acid. With a warming climate, the frequency and severity of harmful algal blooms in marine environments is anticipated to increase, and novel molecular technologies to detect sublethal or chronic exposure to algal toxins will help provide an early warning of threats to the stability of populations and ecosystems.

Increased Incidence of Entanglements and Ingested Marine Debris in Dutch Seals from 2010 to 2020 - Anna Salazar-Casals; Koen de Reus; Nils Greskewitz; Jarco Havermans; Machteld Geut; Stella Villanueva; Ana Rubio-Garcia (Oceans, 2022)
In recent decades, the amount of marine debris has increased in our oceans. As wildlife interactions with debris increase, so does the number of entangled animals, impairing normal behavior and potentially affecting the survival of these individuals. The current study summarizes data on two phocid species, harbor (Phoca vitulina) and gray seals (Halichoerus grypus), affected by marine debris in Dutch waters from 2010 to 2020. The findings indicate that the annual entanglement rate (13.2 entanglements/year) has quadrupled compared with previous studies. Young seals, particularly gray seals, are the most affected individuals, with most animals found or sighted with fishing nets wrapped around their necks. Interestingly, harbor seals showed a higher incidence of ingested debris. Species differences with regard to behavior, foraging strategies, and habitat preferences may explain these findings. The lack of consistency across reports suggests that it is important to standardize data collection from now on. Despite increased public awareness about the adverse environmental effects of marine debris, more initiatives and policies are needed to ensure the protection of the marine environment in the Netherlands.

Investigation of Ocean Sub-Surface Processes in Tropical Cyclone Phailin Using a Coupled Modeling Framework: Sensitivity to Ocean Conditions - Tapajyoti Chakraborty; Sandeep Pattnaik; Himadri Baisya; Vijay Vishwakarma (Oceans, 2022)
The present study is aimed to investigate sub-surface ocean processes and their contribution to the intensification of a tropical cyclone (TC) from a coupled-modeling perspective. The Coupled Ocean–Atmosphere–Wave–Sediment Transport (COAWST) model was employed to simulate TC Phailin, which originated over the Bay of Bengal and made landfall on the eastern coast of India in October 2013. Three sub-surface ocean condition datasets—viz., (a) the European Centre for Medium-Range Weather Forecast (ECMWF) Ocean Reanalysis, (b) the Climate Forecast System Version 2 (CFSV2) Operational Analysis, and (c) the Hybrid Coordinate Ocean Model (HYCOM) Reanalysis datasets—were used for the initial and boundary conditions for the oceanic component of the coupled model in three different simulations of TC Phailin. All the simulations showed a delay in intensification compared to the observation, and ECMWF simulated the most intensified TC. CFSV2 simulated a deeper mixed layer (ML) and higher mixing, which hindered the intensification. Furthermore, higher entrainment of cold water in the ML led to cold water reaching the surface and, consequently, decreased sea surface temperature, which acted as negative feedback in the intensification of the storm in the cases of CFSV2 and HYCOM. ECMWF realistically simulated the interactions of the TC with a cold-core eddy before landfall. A sudden increase in ML heat content, the addition of heat in the ML due to entrainment, and the prevention of cold water reaching the surface were indicative of the breaking of the barrier layer (BL) in ECMWF, which was further corroborated by the spatial distribution of BL thickness in the simulation. This acted as positive feedback in the intensification of the TC. The findings of this study strongly suggest that not only the incorporation of physical oceanic sub-surface processes in the modeling of TCs but also the proper representation of prevailing mesoscale features and ocean sub-surface temperature, salinity, and current profiles in datasets is essential for realistic simulations of TCs.

Analysis and Modeling of Sunscreen Ingredients’ Behavior in an Aquatic Environment - Gema Ruiz-Gutiérrez; Araceli Rodríguez-Romero; Antonio Tovar-Sánchez; Javier R. Viguri Fuente (Oceans, 2022)
Sunscreens have become a product based on increasingly complex formulations that include, among many ingredients, a mixture of UV filters to provide optimal sun ultraviolet radiation protection. A significant group of scientific works deals with the impact of UV filters in aquatic media. However, the knowledge of the mechanism and kinetics of the compound’s direct release, fate, and its transformation and interaction with living organisms is necessary to assess its environmental occurrence and behavior and to predict potential and real impacts on the aquatic environment. This review outlines the existing analysis and modeling of the release and behavior of sunscreen’s ingredients in the marine environment, including aquatic organisms. The physical-chemical properties, photodegradation, and release kinetics of particles and chemicals into the water are studied by hydrodynamic and kinetic models. Direct photolysis of chemicals is modeled as pseudo-first-order kinetics, while the indirect pathway by the reaction of sunscreen with reactive oxygen species is described as second-order kinetics. The interaction of UV filters with marine biota is studied mainly by toxicokinetic models, which predict their bio-accumulation in the organisms’ tissues. These models consider the chemicals’ uptake and excretion, as well as their transfer between different internal animal organs, as a first-order kinetic process. The studies analyzed in the present work represent a driver of change for the beauty and personal care industry, in order to seek new ecological alternatives through the application of R&D tactics.

Clinical Observations Associated with Phenobarbital Serum Monitoring to Manage Epilepsy in a California Sea Lion with Domoic Acid Toxicosis - Claire A. Simeone; Gregory Scott; Ryan A. Navarro; Diana Procter (Oceans, 2022)
The marine algal toxin domoic acid is an important threat to marine mammal health, and exposure can lead to both acute neurologic signs and a chronic epileptic syndrome in California sea lions (Zalophus californianus). Phenobarbital has been used for several decades to manage seizures, although reports are limited correlating dosing, serum monitoring and clinical efficacy in this species. This report details serum monitoring over 33 months in an 8-year-old male sea lion. Seizure control was achieved when phenobarbital concentrations were above 18 μg/mL, and sedation and ataxia were noted when concentrations were above 35 μg/mL. There was no clinically significant difference between phenobarbital concentrations resulting from once-daily versus twice-daily dosing. Serum levels remained detectable as far as 101 days after administration, and remained stable during periods of prolonged anorexia, although dramatic decreases in serum concentrations were noted immediately after normal eating resumed. For this animal, a serum phenobarbital target range of 20–30 μg/mL was achievable with a dose of 1.5 mg/kg once daily followed by therapeutic monitoring, and this is a reasonable recommended concentration and initial dose for clinicians treating this species. Long-term seizure control may be difficult to achieve with anti-epileptic drugs such as phenobarbital alone, and further research is needed to make novel options useful for clinical management of biotoxin-related neurologic disease in this aquatic species.

Entanglement of Steller Sea Lions in Marine Debris and Fishing Gear on the Central Oregon Coast from 2005–2009 - Kimberly L. Raum-Suryan; Robert M. Suryan (Oceans, 2022)
Entanglement in marine debris and fishing gear is an increasing problem for the world’s pinnipeds and a contributing factor in Steller sea lion (Eumetopias jubatus) injury and mortality. From 2005–2009, we surveyed (n = 389 days) two haul-outs on the central Oregon coast containing a combined median of 402 animals (range 33–1240, or ca. 1–19% of the Oregon coast population). We recorded 72 individuals entangled in marine debris (n = 70) or with ingested salmon hook-and-line fishing gear (n = 2). Of the identifiable neck entanglements, black rubber bands were the most common neck-entangling material (62%), followed by plastic packing bands (36%), nets (1.2%), yellow rubber bands (0.4%), and a flying disc (0.4%). The estimated prevalence of entanglement for individuals in Oregon was 0.34%. Juveniles were the most frequently entangled age class (60%), followed by adult females (28%), and subadult males (12%). Supply chain and industry-based solutions are needed to prevent entangling debris from entering the ocean, along with eliminating, modifying, or cutting entangling loops of synthetic material.

A Review of Northern Fur Seal (Callorhinus ursinus) Literature to Direct Future Health Monitoring Initiatives - Valerie Cortés; Kelly Patyk; Claire Simeone; Valerie Johnson; Johanna Vega; Kate Savage; Colleen Duncan (Oceans, 2022)
Northern fur seals (Callorhinus ursinus, NFS) are a vulnerable species broadly distributed throughout the north Pacific. Although commercial hunting stopped in 1984, the population has continued to decline for unknown reasons. The goal of this scoping review was to synthesize and review 50 years of literature relevant to the health of NFS to inform the development of health surveillance recommendations. Search criteria were developed and applied to three databases, followed by title and abstract screening and full text review. Articles published between 1 January 1972 and 31 December 2021 were included. Articles were categorized by health determinant, and further as relating to ten subcategories of disease. Data were summarized descriptively. A total of 148 publications met the criteria for inclusion. Infectious disease reports were common, primarily relating to metazoan parasite presence. The presence of zoonotic pathogens such as Coxiella burnetii and Brucella spp. is of public health interest, although a failure to link disease research to individual animal or population health outcomes was consistent across the literature. A shift away from the single agent focus of disease programs toward more holistic, health-oriented perspectives will require broader interdisciplinary collaboration. These findings can inform stakeholders and help them to prioritize and strategize on future NFS health research efforts.

Whale-Associated Microbial Communities Remain Remarkably Stable despite Massive Water Community Disruption in a Managed Artificial Marine Environment - William Van Bonn; Francis Oliaro; Lee Pinnell (Oceans, 2022)
Highly managed and built environments such as zoos and aquaria provide a rich source of standardized environmental monitoring data over periods of years to decades. A fifty percent water change in an 11.4-million-liter indoor artificial sea water system housing three species of marine mammals was conducted over a two-month period. Using 16S rRNA gene sequencing, the microbial community structure of the system water and three host sites (feces, skin, and exhaled breath “chuff”) of whales housed in the system were characterized. Diversity measures confirmed massive disruption to the water community structure as an expected result of the water change. Host site-associated communities remained remarkably stable. Improved understanding of host microbial community dynamics in response to environmental system perturbations allows for sound management decisions toward optimizing conditions for resident animals.

3D Structure of the Ras Al Hadd Oceanic Dipole - Yassine Bennani; Adam Ayouche; Xavier Carton (Oceans, 2022)
In the Arabian Sea, southeast of the Arabian peninsula, an oceanic dipole, named the Ras Al Hadd (RAH) dipole, is formed each year, lying near the Ras Al Hadd cape. The RAH dipole is the association of a cyclonic eddy (CE) to the northeast, with an anticyclonic eddy (AE) to the southwest. This dipole intensifies in the summer monsoon and disappears during the winter monsoon. This dipole has been described previously, but mostly for its surface expression, and for short time intervals. Here, we describe the 3D structure of this dipole over the 2000–2015 period, by combining colocalized ARGO float profiler data (a total of 7552 profiles inside and outside the RAH dipole) with angular momentum eddy detection and tracking algorithm (AMEDA) surface data. We show first the different water masses in and near the RAH dipole. The presence of the Persian Gulf water (PGW) below 200 m depth is confirmed in both eddies. Arabian Sea high salinity water (ASHSW) is found exclusively in the AE; a layer of fresh and cold water is observed above 100 m depth in both eddies. By analyzing the potential density structures, we show that the CE has a surface-intensified structure while the AE is subsurface-intensified. The sea level anomaly shows a 0.04 m elevation above the AE and a 0.2 m depression over the CE. The CE has a faster geostrophic velocity, (vertical velocity, respectively) 0.6 m s−1 than the AE, 0.15 m s−1 (respectively, 3 m day−1 for the CE and 0.6 m day−1 for the AE). After presenting the vertical structure of the dipole, we show the dominance of the nonlinear Ekman pumping in the CE over the linear pumping affecting the dipole. As a consequence, we explain the CE’s longer lifetime by its intensity and shallowness, and by its sensitivity to the interaction with the atmosphere (in particular the wind stress) and with neighboring eddies. We examined the possible (co)existence of symmetric, barotropic, and baroclinic instabilities in both eddies. These instabilities coexist near the surface in both eddies. They are intensified for the CE, which suggests that the CE is unstable and the AE is rather stable or may need a long time to be unstable.

Sowerby’s Beaked Whales (Mesoplodon bidens) in the Skagerrak and Adjacent Waters: Historical Records and Recent Post-Mortem Findings - Jasmine Stavenow; Anna Maria Roos; Erik Olof Ågren; Carl Kinze; William F. Englund; Aleksija Neimanis (Oceans, 2022)
In contrast to sparse historical observational records, five Sowerby’s beaked whales (SBW) stranded and died in Swedish waters between 2015 and 2020. Here we summarize historical records of SBWs in the Skagerrak basin and adjacent waters. The three recent stranding events from Sweden are described, and the post-mortem findings, including diet analysis, from the five SBWs are presented. Of 30 historical records of SBWs observations since 1869, 13 (43%) were documented between 2010 and 2021, and records between July and November were the most frequent. The recent stranding events occurred in October 2015 (n = 1), August 2019 (n = 3) and July 2020 (n = 1). Four of the SBWs were examined through necropsy, and one was sampled in the field. They were all sub-adults and included a single female and four males. The causes of death were emaciation, euthanasia due to traumatic injury, and live stranding of undetermined cause. Two SBWs each had a focal bone lesion consistent with osteomyelitis. Other findings included pox-like dermatitis, trauma, focal granulomas in a lymph node and intestine, and ulceration of the stomach. CT scans were performed on the heads of two animals, with inconclusive results. Three SBWs had hard parts in the gastrointestinal tract that mainly consisted of otoliths from several fish species. An eDNA-analysis confirmed and supplemented the diet analysis, revealing 17 fish species in total, including species not previously described as prey for SBW, such as Pleuronectidae spp. The apparent increase in observational records since 2010 may indicate a shift in SBW distribution or changing threats to these animals. Our results support and expand theories on SBW movements and provide data on the biology and health of this poorly known species, which are valuable for conservation and legislation efforts.

Temporal and Spatial Evaluation of Mono(2-ethylhexyl) Phthalate (MEHP) Detection in Common Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA - Miranda K. Dziobak; Brian C. Balmer; Randall S. Wells; Emily C. Pisarski; Ed F. Wirth; Leslie B. Hart (Oceans, 2022)
Phthalates are endocrine-disrupting chemicals added to plastics, personal care products, cleaning solutions, and pesticides. Extensive use has led to its exposure to wildlife, including common bottlenose dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA; however, there are gaps in knowledge regarding whether sample timing or geographic location influence exposure. Dolphins were evaluated for temporal and spatial variability in urinary mono(2-ethylhexyl) phthalate (MEHP) detection (2010–2019). Significant fluctuations in detectable MEHP concentrations were found across the dataset. All samples from 2014 and 2015 (n = 12) had detectable MEHP concentrations; thus, data were classified into cohorts to explore the significance of prevalent MEHP detection (“Cohort 1” (n = 10; 2010–2013), “Cohort 2” (2014–2015), and “Cohort 3” (n = 29; 2016–2019)). Compared to Cohorts 1 and 3, Cohort 2 had higher detectable MEHP concentrations (Dunn’s; p = 0.0065 and p = 0.0012, respectively) and a greater proportion of detectable MEHP concentrations (pairwise comparisons using Benjamini–Hochberg adjustments: p = 0.0016 and p = 0.0059, respectively). MEHP detection also varied across spatial scales. Dolphins with detectable MEHP concentrations had ranges primarily within enclosed embayments, while dolphins with nondetectable MEHP concentrations extended into open waters, potentially indicating geographically linked exposure risk. This study suggests that researchers and management agencies should consider a population’s ranging pattern, geographic habitat characteristics, and sample timing when assessing small cetacean health in relation to contaminant exposure.

Octocoral Distribution Patterns at the Equatorial Front (Tropical Eastern Pacific): Muricea and Leptogorgia - Rubén Abad; Karla B. Jaramillo; Divar Castro; Juan A. Sánchez; Jenny Rodríguez (Oceans, 2022)
The Equatorial Front, in the southern part of the Tropical Eastern Pacific (TEP) region, has been characterized as a hotspot of functional biodiversity due to the mixing of warm and cold waters. Nevertheless, the biogeographic patterns for some organisms, such as octocorals, remain unknown in some coastal regions. Therefore, we aimed to assess the distribution of two common octocoral genera in this area, Muricea and Leptogorgia, including 14 species based on museum specimen records, along the mainland coast of Ecuador. Statistical analyses were performed on the environmental and geographical patterns (Sea Surface Temperature (SST), bathymetry, chlorophyll (CHL-a), and Photosynthetic Active Radiation (PAR)) that influence the Equatorial Front, which is subdivided into five biogeographic regions. Our results showed two hotspots of octocoral biodiversity. The SST was found to be the main environmental factor related to octocoral distribution along the Equatorial Front. Finally, the highest abundance of Muricea over Leptogorgia suggests the former species’ higher resilience to thermal fluctuations. We discuss the possible role of substrates at suitable depths, active photosynthetic radiation, and temperature in the occurrence of octocorals in the two hotspots.

Reef Fish Assemblage in Two Insular Zones within the Mexican Central Pacific - Carlos Vladimir Pérez de-Silva; Amílcar Leví Cupul-Magaña; Alma Paola Rodríguez-Troncoso; Fabián Alejandro Rodríguez-Zaragoza (Oceans, 2022)
Reefs fishes are sensitive to environmental changes, particularly in areas such as the Mexican Central Pacific (MCP), which has a high environmental variability favored by currents. This study assesses the temporal variation in ecological indicators of fishes in Marietas (MI) and Isabel islands (II) in the MCP during 2010–2017. Overall, 118 species were recorded at MI and 95 in II. The highest abundance was recorded in 2013 at MI, and in 2015 at II, with an observed sample coverage > 0.79 for all years. MI showed higher annual taxonomic distinctness and richness than II. Annual biomass and assemblages were different between years and islands. The changes in both islands’ community structure were influenced by ENSO events. A high proportion of the dissimilarity among years is represented in 10 species, and the difference among years for each island is given by rare species. Annually, community indicators (Δ+, q = 1, and q = 2) and physicochemical factors were not related except for q = 0 and the chlorophyll concentration; this is due to the inter-annual variation within the area. The variation in fish communities on both islands results from mesoscale phenomena that have a different effect on each island due to the characteristics of their shelf and oceanography.

Pathological Studies and Postmortem Computed Tomography of Dolphins with Meningoencephalomyelitis and Osteoarthritis Caused by Brucella ceti - Andrés Granados-Zapata; María José Robles-Malagamba; Rocío González-Barrientos; Brian Chin-Wing Kot; Elías Barquero-Calvo; Minor Cordero-Chavaría; Marcela Suárez-Esquivel; Caterina Guzmán-Verri; Jose David Palacios-Alfaro; Connie Tien-Sung; Edgardo Moreno; Gabriela Hernández-Mora (Oceans, 2022)
Cetacean neurobrucellosis is a common cause of strandings in Costa Rica diagnosed by serology, bacteriology, and histopathology. Pathological studies were performed on 18 dolphins. Twelve were scanned by postmortem computed tomography (PMCT) as a complementary tool for describing neurobrucellosis and osteoarticular alterations associated with Brucella ceti infections. The central nervous system (CNS) and the skeleton of five dolphins not infected with B ceti did not reveal alterations by PMCT scanning. Seven Brucella-infected dolphins showed at least bilateral ventriculomegaly associated with hydrocephalus and accumulation in CSF in the lateral ventricles. We performed semiquantitative grading of the inflammatory process in the different areas of the CNS and evaluated the thickness of the cellular infiltrate in the meninges and the perivascular cuffs. The results for the severity grading were graphed to provide an injury profile associated with each area of the CNS. Age is not a decisive factor regarding neurobrucellosis presentation. The severity of ventriculomegaly by PMCT does not directly correlate with the severity of the inflammatory index determined by histopathological parameters of the brain cortex and other CNS regions, suggesting that these processes, although linked, are multifactorial and need further characterization and validation to establish better cutoffs on the PMCT.

Coastal Quarries as Relative Sea-Level Markers: A Methodological Approach Applied in the Apulia Region (Southern Italy) - Giovanni Scardino; Arcangelo Piscitelli; Giuseppe Locuratolo; Giovanni Scicchitano; Angela Rizzo (Oceans, 2022)
The assessment of past sea-level positions requires a multidisciplinary approach that involves both scientific and historical humanistic fields. The use of a multidisciplinary approach allows us to obtain reliable information on the relative sea-level position, the determination of which requires the evaluation of the eustatic and steric components as well as an assessment of the vertical ground displacements, such as the isostatic adjustments and tectonic movements. In this context, coastal geoarchaeological markers play a fundamental role since their architectural height (generally defined as functional height) was relative to the sea level at the time of their construction. Thus, a comparison between the current elevation of geoarchaeological structures (or depth in the case they are currently submerged) with their estimated functional height allows us to obtain the relative sea-level variation. In this study, we applied a methodological procedure for the evaluation of the functional height of architectural elements using modern technologies (Terrestrial Laser Scanner and GPS-Real Time Kinematic) and detailed sea-level analysis. The proposed methodology was applied to coastal quarries located along the coast of Bari (Apulia region, southern Italy). The results allowed us to confirm the functional height of the detachment surface reported in the literature and to assess the sea-level position in the fifth and fourth centuries before Christ.

The Condition of Four Coral Reefs in Timor-Leste before and after the 2016–2017 Marine Heatwave - Catherine J. S. Kim; Chris Roelfsema; Sophie Dove; Ove Hoegh-Guldberg (Oceans, 2022)
El Niño Southern Oscillation global coral bleaching events are increasing in frequency, yet the severity of mass coral bleaching is not geographically uniform. Based in Timor-Leste, the present project had two major objectives: (1) assess the baseline of reefs and coral health at four sites and (2) explore water quality and climate-related changes in ocean temperatures on these understudied reef systems. The impacts of climate change were surveyed on coral reefs before and after the 2016–2017 global underwater heatwave, (principally by following coral mortality). Temperature loggers were also deployed between surveys, which were compared to Coral Reef Watch (CRW) experimental virtual station sea surface temperature (SST). CRW is an important and widely used tool; however, we found that the remotely sensed SST was significantly warmer (>1 °C) than in situ temperature during the austral summer accruing 5.79-degree heating weeks. In situ temperature showed no accumulation. There were significant differences in coral cover, coral diversity, and nutrient concentrations between sites and depths, as well as a low prevalence of disease recorded in both years. Change in coral cover between surveys was attributed to reef heterogeneity from natural sources and localized anthropogenic impacts. Timor-Leste has both pristine and impacted reefs where coral cover and community composition varied significantly by site. Degradation was indicative of impacts from fishing and gleaning. The comparison of in situ temperature and remotely sensed SST indicated that bleaching stress in Timor-Leste is potentially mitigated by seasonal coastal upwelling during the Northwest monsoon season. As a climate refugium, the immediate conservation priority lies in the mitigation of localized anthropogenic impacts on coral reefs through increasing the management of expanding human-related sedimentation and fishing.

On the Seasonal Dynamics of Phytoplankton Chlorophyll-a Concentration in Nearshore and Offshore Waters of Plymouth, in the English Channel: Enlisting the Help of a Surfer - Elliot McCluskey; Robert J. W. Brewin; Quinten Vanhellemont; Oban Jones; Denise Cummings; Gavin Tilstone; Thomas Jackson; Claire Widdicombe; E. Malcolm S. Woodward; Carolyn Harris; Philip J. Bresnahan; Tyler Cyronak; et al. (Oceans, 2022)
The role of phytoplankton as ocean primary producers and their influence on global biogeochemical cycles makes them arguably the most important living organisms in the sea. Like plants on land, phytoplankton exhibit seasonal cycles that are controlled by physical, chemical, and biological processes. Nearshore coastal waters often contain the highest levels of phytoplankton biomass. Yet, owing to difficulties in sampling this dynamic region, less is known about the seasonality of phytoplankton in the nearshore (e.g., surf zone) compared to offshore coastal, shelf and open ocean waters. Here, we analyse an annual dataset of chlorophyll-a concentration—a proxy of phytoplankton biomass—and sea surface temperature (SST) collected by a surfer at Bovisand Beach in Plymouth, UK on a near weekly basis between September 2017 and September 2018. By comparing this dataset with a complementary in-situ dataset collected 7 km offshore from the coastline (11 km from Bovisand Beach) at Station L4 of the Western Channel Observatory, and guided by satellite observations of light availability, we investigated differences in phytoplankton seasonal cycles between nearshore and offshore coastal waters. Whereas similarities in phytoplankton biomass were observed in autumn, winter and spring, we observed significant differences between sites during the summer months of July and August. Offshore (Station L4) chlorophyll-a concentrations dropped dramatically, whereas chlorophyll-a concentrations in the nearshore (Bovsiand Beach) remained high. We found chlorophyll-a in the nearshore to be significantly positively correlated with SST and PAR over the seasonal cycle, but no significant correlations were observed at the offshore location. However, offshore correlation coefficients were found to be more consistent with those observed in the nearshore when summer data (June–August 2018) were removed. Analysis of physical (temperature and density) and chemical variables (nutrients) suggest that the offshore site (Station L4) becomes stratified and nutrient limited at the surface during the summer, in contrast to the nearshore. However, we acknowledge that additional experiments are needed to verify this hypothesis. Considering predicted changes in ocean stratification, our findings may help understand how the spatial distribution of phytoplankton phenology within temperate coastal seas could be impacted by climate change. Additionally, this study emphasises the potential for using marine citizen science as a platform for acquiring environmental data in otherwise challenging regions of the ocean, for understanding ecological indicators such as phytoplankton abundance and phenology. We discuss the limitations of our study and future work needed to explore nearshore phytoplankton dynamics.

Hurricane-Induced Oceanic Carbon Changes in the Upper Ocean - Laura McGee; Ruoying He (Oceans, 2022)
Changes in marine carbon cycling due to hurricanes with different intensity and translation speeds have not been systematically investigated. This study uses an idealized coupled physical-biogeochemical model and a suite of model sensitivity analyses to better quantify the relationship between hurricane characteristics and marine property changes, including variations in air-sea carbon flux and partial pressure of carbon dioxide in water (pCO2w). We find that strong (category 4–5), mid-speed (5–8 m/s) storms cause the most carbon flux from the atmosphere to the ocean, and that the relationship between air-sea carbon flux and hurricane properties is non-linear. Climate models that do not consider synoptic-scale, storm-induced physical-biogeochemical coupling may underestimate regional carbon sinks.

Understanding Fish Larvae’s Feeding Biology to Improve Aquaculture Feeding Protocols - Laura Ribeiro; François Noel Hubert; Vera Rodrigues; Carlos Rojas-Garcia; Maria Teresa Dinis (Oceans, 2022)
Knowing that food ingestion and digestion are processes under neuroendocrine regulation, it is important to understand how fish larvae regulate these processes, when the digestive system itself is under development. This study aimed to analyze how gilthead seabream (Sparus aurata) larval feeding incidence and intensity were affected by time, light, and water temperature, through the analysis of gut content and how this affected cholecystokinin (CCK) content. Three short-term experiments were done: (A) 27 and 42 days post-hatch (DPH) larvae were analyzed at different intervals for 80 min, after feeding; (B) 38 and 48 DPH larvae were kept under different light intensities (0, 400, 1000 lux) for 30 min; (C) 41 DPH larvae were kept at 17, 19, 25 °C for 30 min. Feeding incidence below 100% was observed for 27 DPH larvae, and for 38 DPH larvae fed at 0 lux. Feeding intensity was several fold higher at older ages. However, the number of prey in the gut was lower at 0 lux, and higher at 25 °C. Overall, no clear pattern was observed for CCK, but at older ages increasing gut content resulted in higher CCK content. In conclusion, until 38 DPH light is important for gilthead sea bream larval feeding ability, and maturing functionality of CCK was only observed at later stages.

Impact of Egg Exposure to UV Filter-Spiked Sediment on the Survival, Hatching Success, Cardiac Frequency, and Metabolic Scope of Zebrafish Embryos - Julie Lucas; Valentin Logeux; Alice Rodrigues; Didier Stien; Philippe Lebaron (Oceans, 2022)
Chemical UV filters are increasingly used in cosmetics to protect skin from UV radiation. As a consequence, they are released into the aquatic environment via recreational activities and wastewaters. In aquatic ecosystems, fish eggs in contact with sediment can be affected by organic and lipophilic pollutants such as UV filters. The present study aims to evaluate the toxicity of six individual UV filters, diethylhexyl butamido triazone (DBT), diethylamino hydroxybenzoyl hexyl benzoate (DHHB), ethylhexyl triazone (ET), 2-ethylhexyl salicylate (ES), homosalate (HS), and octocrylene (OC), in the embryo-larval stages of zebrafish Danio rerio. Contamination of fish eggs and larvae with UV filters occurred through contact with spiked sediment for 96 h at a concentration of 10 μg g−1. Among the six UV filters tested, OC delayed hatching success, whereas ES significantly increased the heartbeat rate of embryo–larvae after sediment exposure, probably as a stress response.

Evaluation of the HemoCue® WBC System as a Point of Care Diagnostic Tool for White Blood Cell Quantification in Pinnipeds - Abby M. McClain; Emily R. Whitmer; Carlos Rios; Eric D. Jensen; Nicole I. Stacy; Shawn P. Johnson (Oceans, 2022)
Point of care (POC) hematology testing can be valuable in triage and field settings. We assessed the accuracy between the HemoCue® WBC system and two comparative analyzers, as well as the precision of the HemoCue® WBC system in five different pinniped species: Zalophus californianus, Arctocephalus townsendi, Callorhinus urcinus, Phoca vitulina, and Mirounga angustirostris for white blood cell (WBC) quantification. In Zalophus (n = 164; 106 from U.S. Navy Marine Mammal Program (Navy); 58 from The Marine Mammal Center (TMMC)), the HemoCue® was compared to two hematology analyzers, Sysmex Xe-5000 and Vet ABC Plus. In Phoca (n = 50; TMMC), Callorhinus (n = 29; TMMC), Arctocephalus (n = 17; TMMC), and Mirounga (n = 67; TMMC), the HemoCue® was compared to Vet ABC Plus only. Bland–Altman and Passing–Bablok agreement of HemoCue® with Sysmex Xe-5000 and Vet ABC Plus analyzers were good for Zalophus, Arctocephalus, Phoca, and Mirounga but marginal with Callorhinus; bias = 0.56 × 109/L (Zalophus; Navy), −2.13 × 109/L (Zalophus; TMMC), −1.59 × 109/L (Arctocephalus), −2.48 × 109/L 0.917 (Phoca), −0.01 × 109/L (Mirounga), and −6.05 × 109/L (Callorhinus). The coefficient of variation from triplicate runs of samples were within acceptable limits for all species (2.50% ± 1.63 (Zalophus; TMMC), 3.09% ± 2.14 (Arctocephalus), 2.47% ± 1.35 (Callorhinus), 2.88% ± 1.75 (Phoca), and 3.44% ± 2.53 (Mirounga)), respectively. The presence of nucleated red blood cells (nRBC; 1–37 nRBC/100 WBC) did not significantly interfere with WBC counts in Zalophus, Callorhinus, and Phoca at the population level, but their presence should be evaluated at the individual level. The HemoCue® provides an accurate method for WBC quantification with WBC counts up to 30 × 109/L (upper limit of linearity of the analyzer) in Zalophus, Arctocephalus, Phoca, and Mirounga, but is less accurate in Callorhinus, and showed good precision in all species.

Private Capital to Improve Nature-Based Solutions for Coastal Protection: Time for a Boost - Angelique Brathwaite; Nicolas Pascal; Eric Clua (Oceans, 2022)
Coastal protection, an important coral reef ecosystem service, is threatened by increasing coral mortality, exacerbated by global climate change. Nature-based solutions in the form of coral restoration, while not perfect, can assist in rebuilding reef structure and improving the flow of the service for some sites. With a financing gap existing between what is required for conservation and what is being accessed, private investors should be playing a larger role in such restoration activities. Especially so as coastal hoteliers in particular, benefit from stable beaches and also have additional income generating potential with healthy reefs. Blended finance solutions in particular, are especially suited to restoration that incorporates substrate addition, while payments for ecosystem services are more suited to coral gardening. Conservation and finance practitioners must engage further and understand each other’s worlds, in order for these private sources to be effectively sourced and utilized.

Coral Recovery in the Central Mexican Pacific 20 Years after the 1997–1998 El Niño Event - Violeta Martínez-Castillo; Alma Paola Rodríguez-Troncoso; Anderson B. Mayfield; Fabián Alejandro Rodríguez-Zaragoza; Amílcar Leví Cupul-Magaña (Oceans, 2022)
El Niño–Southern Oscillation (ENSO) events are increasing globally in both frequency and strength, and they can elicit coral bleaching events. The 1997–1998 ENSO caused mass coral mortality with a 96% decline in live coral cover along the Central Mexican Pacific. However, in recent years, these sites have shown signs of recovery. We used data collected in 1997 and 2015–2017 to evaluate the coral recovery in this region and coral cover levels have now reached 50% of their pre-1997–1998 El Niño values. Furthermore, a strong 2015–2016 ENSO event did not significantly affect the live coral cover, potentially demonstrating that the local corals have acclimatized or even adapted to higher temperatures. Even though branching species remain the most abundant morphotype, a PERMANOVA revealed significant changes in the coral assemblage. Collectively, this dataset is testament to the fact that corals within this region are capable of resisting or at least partially recovering from thermal anomalies caused by ENSO events.

Acknowledgment to Reviewers of Oceans in 2021 (Oceans, 2022)
Rigorous peer-reviews are the basis of high-quality academic publishing [...]

A Review of Current and New Optical Techniques for Coral Monitoring - Jonathan Teague; David A. Megson-Smith; Michael J. Allen; John C.C. Day; Thomas B. Scott (Oceans, 2022)
Monitoring the health of coral reefs is essential to understanding the damaging impacts of anthropogenic climate change as such non-invasive methods to survey coral reefs are the most desirable. Optics-based surveys, ranging from simple photography to multispectral satellite imaging are well established. Herein, we review these techniques, focusing on their value for coral monitoring and health diagnosis. The techniques are broadly separated by the primary method in which data are collected: by divers and/or robots directly within the environment or by remote sensing where data are captured above the water’s surface by planes, drones, or satellites. The review outlines a new emerging technology, low-cost hyperspectral imagery, which is capable of simultaneously producing hyperspectral and photogrammetric outputs, thereby providing integrated information of the reef structure and physiology in a single data capture.

Environmentally-Driven Variation in the Physiology of a New Caledonian Reef Coral - Anderson B. Mayfield; Alexandra C. Dempsey (Oceans, 2022)
Given the widespread threats to coral reefs, scientists have lost the opportunity to understand the basic biology of “pristine” corals whose physiologies have not been markedly perturbed by human activity. For instance, high temperature-induced bleaching has been occurring annually since 2014 in New Caledonia. Because most corals cannot withstand repeated years when bleaching occurs, an analysis was undertaken to showcase coral behavior in a period just before the onset of “annual severe bleaching” (ASB; November 2013) such that future generations might know how these corals functioned in their last bleaching-free year. Pocillopora damicornis colonies were sampled across a variety of environmental gradients, and a subset was sampled during both day and night to understand how their molecular biology changes upon cessation of dinoflagellate photosynthesis. Of the 13 environmental parameters tested, sampling time (i.e., light) most significantly affected coral molecular physiology, and expression levels of a number of both host and Symbiodiniaceae genes demonstrated significant diel variation; endosymbiont mRNA expression was more temporally variable than that of their anthozoan hosts. Furthermore, expression of all stress-targeted genes in both eukaryotic compartments of the holobiont was high, even in isolated, uninhabited, federally protected atolls of the country’s far northwest. Whether this degree of sub-cellular stress reflects cumulative climate change impacts or, instead, a stress-hardened phenotype, will be unveiled through assessing the fates of these corals in the wake of increasingly frequent marine heatwaves.

Correlation between Coral Reef Condition and the Diversity and Abundance of Fishes and Sea Urchins on an East African Coral Reef - Pia Ditzel; Sebastian König; Peter Musembi; Marcell K. Peters (Oceans, 2022)
Coral reefs are one of the most diverse marine ecosystems, providing numerous ecosystem services. This present study investigated the relationship between coral reef condition and the diversity and abundance of fishes, on a heavily fished East African coral reef at Gazi Bay, Kenya. Underwater visual censuses were conducted on thirty 50 × 5 m belt transects to assess the abundance and diversity of fishes. In parallel, a 25-m length of each of the same transects was recorded with photo-quadrats to assess coral community structure and benthic characteristics. For statistical analyses, multi-model inference based on the Akaike Information Criterion was used to evaluate the support for potential predictor variables of coral reef and fish diversity. We found that coral genus richness was negatively correlated with the abundance of macroalgae, whereas coral cover was positively correlated with both the abundance of herbivorous invertebrates (sea urchins) and with fish family richness. Similarly, fish family richness appeared mainly correlated with coral cover and invertebrate abundance, although no correlates of fish abundance could be identified. Coral and fish diversity were very low, but it appears that, contrary to some locations on the same coast, sea urchin abundance was not high enough to be having a negative influence on coral and fish assemblages. Due to increasing threats to coral reefs, it is important to understand the relationship among the components of the coral reef ecosystem on overfished reefs such as that at Gazi Bay.

Glow on Sharks: State of the Art on Bioluminescence Research - Laurent Duchatelet; Julien M. Claes; Jérôme Delroisse; Patrick Flammang; Jérôme Mallefet (Oceans, 2021)
This review presents a synthesis of shark bioluminescence knowledge. Up to date, bioluminescent sharks are found only in Squaliformes, and specifically in Etmopteridae, Dalatiidae and Somniosidae families. The state-of-the-art knowledge about the evolution, ecological functions, histological structure, the associated squamation and physiological control of the photogenic organs of these elusive deep-sea sharks is presented. Special focus is given to their unique and singular hormonal luminescence control mechanism. In this context, the implication of the photophore-associated extraocular photoreception—which complements the visual adaptations of bioluminescent sharks to perceive residual downwelling light and luminescence in dim light environment—in the hormonally based luminescence control is depicted in detail. Similarities and differences between shark families are highlighted and support the hypothesis of an evolutionary unique ancestral appearance of luminescence in elasmobranchs. Finally, potential areas for future research on shark luminescence are presented.

Different Physiology in the Jellyfish Cassiopea xamachana and C. frondosa in Florida Bay - William K. Fitt; Dietrich K. Hofmann; Dustin W. Kemp; Aki H. Ohdera (Oceans, 2021)
The jellyfish Cassiopea xamachana and C. frondosa co-occur within some habitats in the Florida Keys, but the frequency with which this occurs is low. It is hypothesized that the symbiosis with different dinoflagellates in the Symbiodiniaceae is the reason: the medusae of C. xamachana contain heat-resistant Symbiodinium microadriaticum (ITS-type A1), whereas C. frondosa has heat-sensitive Breviolum sp. (ITS-type B19). Cohabitation occurs at depths of about 3–4 m in Florida Bay, where the water is on average 0.36 °C cooler, or up to 1.1 °C cooler per day. C. frondosa tends not to be found in the warmer and shallower (<2 m) depths of Florida Bay. While the density of symbionts is about equal in the small jellyfish of the two species, large C. frondosa medusae have a greater density of symbionts and appear darker in color compared to large C. xamachana. However, the number of symbionts per amebocyte are about the same, which implies that the large C. frondosa has more amebocytes than the large C. xamachana. The photosynthetic rate is similar in small medusae, but a greater reduction in photosynthesis is observed in the larger medusae of C. xamachana compared to those of C. frondosa. Medusae of C. xamachana have greater pulse rates than medusae of C. frondosa, suggestive of a greater metabolic demand. The differences in life history traits of the two species were also investigated to understand the factors that contribute to observed differences in habitat selection. The larvae of C. xamachana require lower concentrations of inducer to settle/metamorphose, and they readily settle on mangrove leaves, submerged rock, and sand compared to the larvae of C. frondosa. The asexual buds of C. xamachana are of a uniform and similar shape as compared to the variably sized and shaped buds of C. frondosa. The larger polyps of C. frondosa can have more than one attachment site compared to the single holdfast of C. xamachana. This appears to be an example of niche diversification that is likely influenced by the symbiont, with the ecological generalist and heat-resistant S. microadriaticum thriving in C. xamachana in a wider range of habitats as compared to the heat-sensitive symbiont Breviolum sp., which is only found in C. frondosa in the cooler and deeper waters.

Response of Tropical Cyclone Frequency to Sea Surface Temperatures Using Aqua-Planet Simulations - Pavan Harika Raavi; Kevin J. E. Walsh (Oceans, 2021)
The present study investigates the effect of increasing sea surface temperatures (SSTs) on tropical cyclone (TC) frequency using the high-resolution Australian Community Climate and Earth-System Simulator (ACCESS) model. We examine environmental conditions leading to changes in TC frequency in aqua-planet global climate model simulations with globally uniform sea surface temperatures (SSTs). Two different TC tracking schemes are used. The Commonwealth Scientific and Industrial Research Organization (CSIRO) scheme (a resolution-dependent scheme) detects TCs that resemble observed storms, while the Okubo–Weiss zeta parameter (OWZP) tracking scheme (a resolution-independent scheme) detects the locations within “marsupial pouches” that are favorable for TC formation. Both schemes indicate a decrease in the global mean TC frequency with increased saturation deficit and static stability of the atmosphere. The OWZP scheme shows a poleward shift in the genesis locations with rising temperatures, due to lower vertical wind shear. We also observe an overall decrease in the formation of tropical depressions (TDs) with increased temperatures, both for those that develop into TCs and non-developing cases. The environmental variations at the time of TD genesis between the developing and the non-developing tropical depressions identify the Okubo–Weiss (OW) parameter and omega (vertical mass flux) as significant influencing variables. Initial vortices with lower vorticity or with weaker upward mass flux do not develop into TCs due to environments with higher saturation deficit and stronger static stability of the atmosphere. The latitudinal variations in the large-scale environmental conditions account for the latitudinal differences in the TC frequency in the OWZP scheme.

Investigation into the Presence of Symbiodiniaceae in Antipatharians (Black Corals) - Erika Gress; Igor Eeckhaut; Mathilde Godefroid; Philippe Dubois; Jonathan Richir; Lucas Terrana (Oceans, 2021)
Here, we report a new broad approach to investigating the presence and density of Symbiodiniaceae cells in corals of the order Antipatharia subclass Hexacorallia, commonly known as black corals. Antipatharians are understudied ecosystem engineers of shallow (<30 m depth), mesophotic (30–150 m) and deep-sea (>200 m) reefs. They provide habitat to numerous organisms, enhancing and supporting coral reef biodiversity globally. Nonetheless, little biological and ecological information exists on antipatharians, including the extent to which global change disturbances are threatening their health. The previous assumption that they were exempted from threats related to the phenomenon known as bleaching was challenged by the recent findings of high densities of dinoflagellates within three antipatharian colonies. Further studies were thus necessary to investigate the broader uniformity of these findings. Here we report results of an integrated methodology combining microscopy and molecular techniques to investigate the presence and estimate the density of Symbiodiniaceae cells within two antipatharians species—Cupressopathes abies and Stichopathes maldivensis—from both shallow and mesophotic reefs of SW Madagascar. We found that Symbiodiniaceae-like cells were present within samples of both species collected from both shallow and mesophotic reefs, although the overall cell density was very low (0–4 cell mm−3). These findings suggest that presence or high abundance of Symbiodiniaceae is not characteristic of all antipatharians, which is relevant considering the bleaching phenomenon affecting other corals. However, the possibility of higher densities of dinoflagellates in other antipatharians or in colonies exposed to higher light irradiance deserves further investigation.

Effects of Natural and Artificial Surfactants on Diffusive Boundary Dynamics and Oxygen Exchanges across the Air–Water Interface - Adenike Adenaya; Michaela Haack; Christian Stolle; Oliver Wurl; Mariana Ribas-Ribas (Oceans, 2021)
Comparing measurements of the natural sea surface microlayer (SML) and artificial surface films made of Triton-X-100 and oleyl alcohol can provide a fundamental understanding of diffusive gas fluxes across the air–water boundary layers less than 1 mm thick. We investigated the impacts of artificial films on the concentration gradients and diffusion of oxygen (O2) across the SML, the thickness of the diffusive boundary layer (DBL), and the surface tension levels of natural seawater and deionized water. Natural and artificial films led to approximately 78 and 81% reductions in O2 concentration across the surfaces of natural seawater and deionized water, respectively. The thicknesses of the DBL were 500 and 350 µm when natural SML was added on filtered and unfiltered natural seawater, respectively, although the DBL on filtered seawater was unstable, as indicated by decreasing thickness over time. Triton-X-100 and oleyl alcohol at a concentration of 2000 µg L−1 in deionized water persistently increased the DBL thickness values by 30 and 26% over a period of 120 min. At the same concentration, Triton-X-100 and oleyl alcohol decreased the surface tension of deionized water from ~72 mN m−1 to 48 and 38 mN m−1, respectively; 47% recovery was recorded after 30 min with Triton-X-100, although low surface tension persisted for 120 min with oleyl alcohol. The critical micelle concentration values of Triton-X-100 ranged between 400 and 459 µg L−1. We, therefore, suggest that Triton-X-100 resembles natural SML because the reduction and partial recovery of the surface tension of deionized water with the surfactant resembles the behavior observed for natural slicks. Temperature and salinity were observed to linearly decrease the surface tension levels of natural seawater, artificial seawater, and deionized water. Although several factors leading to O2 production and consumption in situ are excluded, experiments carried out under laboratory-controlled conditions are useful for visualizing fine-scale processes of O2 transfer from water bodies through the surface microlayer.

Facing the Forecaster’s Dilemma: Reflexivity in Ocean System Forecasting - Nicholas R. Record; Andrew J. Pershing (Oceans, 2021)
Unlike atmospheric weather forecasting, ocean forecasting is often reflexive; for many applications, the forecast and its dissemination can change the outcome, and is in this way, a part of the system. Reflexivity has implications for several ocean forecasting applications, such as fisheries management, endangered species management, toxic and invasive species management, and community science. The field of ocean system forecasting is experiencing rapid growth, and there is an opportunity to add the reflexivity dynamic to the conventional approach taken from weather forecasting. Social science has grappled with reflexivity for decades and can offer a valuable perspective. Ocean forecasting is often iterative, thus it can also offer opportunities to advance the general understanding of reflexive prediction. In this paper, we present a basic theoretical skeleton for considering iterative reflexivity in an ocean forecasting context. It is possible to explore the reflexive dynamics because the prediction is iterative. The central problem amounts to a tension between providing a reliably accurate forecast and affecting a desired outcome via the forecast. These two objectives are not always compatible. We map a review of the literature onto relevant ecological scales that contextualize the role of reflexivity across a range of applications, from biogeochemical (e.g., hypoxia and harmful algal blooms) to endangered species management. Formulating reflexivity mathematically provides one explicit mechanism for integrating natural and social sciences. In the context of the Anthropocene ocean, reflexivity helps us understand whether forecasts are meant to mitigate and control environmental changes, or to adapt and respond within a changing system. By thinking about reflexivity as part of the foundation of ocean system forecasting, we hope to avoid some of the unintended consequences that can derail forecasting programs.

Effect of Temperature on the Daily Increment Deposition in the Otoliths of European Sardine Sardina pilchardus (Walbaum, 1792) Larvae - Claudia Soares; Susana Ferreira; Pedro Ré; Maria Alexandra Teodósio; António Miguel Santos; Hugo Batista; Nuria Baylina; Susana Garrido (Oceans, 2021)
Otolith microstructure analysis is a valuable tool to evaluate the relationship between larval age and growth and how it relates to environmental variability. Otolith growth and daily increment deposition were analyzed in sardine (Sardina pilchardus) larvae reared in the laboratory under different temperatures (13, 15, and 17 °C), with a diet rich in microalgae, rotifers, and copepods Acartia grani. The number and width of growth increments, first-check and otolith diameter were determined in the otoliths and then related to larval age and total length. At hatching, the sagittal otoliths consisted of a lenticular core with a diameter of 10.56 μm (±1.07 μm SD). Somatic growth increased with the increasing temperature and the growth rate of larvae reared at 13 and 15 °C was significantly lower than for larvae reared at 17 °C. At 17 °C, otoliths exhibited a higher diameter with wider increments than at 13 °C. There was a high variability of increment counts-at-age for larvae reared within the same temperature treatment. The increase of growth increments with larval size was higher for larvae reared at 17 °C until 35 days post-hatching than those growing at 15 °C. Scanning electronic microscopy confirmed that increments are deposited daily, with an average width smaller than 1 µm and as low as 0.33 μm, therefore impossible to distinguish using light microscopy. At colder temperatures, larval otoliths had thinner and less marked increments and lower growth rates, which can lead to incorrect age determinations. The effect of temperature on the otolith microstructure can help in identifying strong temperature gradients experienced by wild sardine larvae.

Larval Fish Community in the Northwestern Iberian Upwelling System during the Summer Period - Sonia Rábade Uberos; Alba Ruth Vergara Castaño; Rosario Domínguez-Petit; Fran Saborido-Rey (Oceans, 2021)
The Galician shelf (northwestern Iberian Peninsula) is a highly dynamic area with an important multi-species fisheries industry that exploits resources from several habitats, characterized by being not only highly diverse, rich, and productive but also seasonally and interannually variable. Early life stages of different species are distributed throughout the year, with fluctuating abundances and community composition. Likewise, the influence of environmental factors and processes on larval production and survival remains unknown. Sampling was carried out in July 2012, and all the larvae obtained were identified to establish the specific composition of the community in a summer upwelling scenario. The results show no zonation in the species distribution, a consequence of the mixing effects of the upwelling and eddies, with high diversity but low abundance, which render in a slight predominance of a few species. Due to the dependence of planktonic populations on upwelling events, which was not highly pronounced in 2012, we cannot conclude that this was a typical conformation of the Galician summer larval fish community, but it is a first approach to comprehend the community composition.

Simulated Changes in Tropical Cyclone Size, Accumulated Cyclone Energy and Power Dissipation Index in a Warmer Climate - Michael Wehner (Oceans, 2021)
Detection, attribution and projection of changes in tropical cyclone intensity statistics are made difficult from the potentially decreasing overall storm frequency combined with increases in the peak winds of the most intense storms as the climate warms. Multi-decadal simulations of stabilized climate scenarios from a high-resolution tropical cyclone permitting atmospheric general circulation model are used to examine simulated global changes from warmer temperatures, if any, in estimates of tropical cyclone size, accumulated cyclonic energy and power dissipation index. Changes in these metrics are found to be complicated functions of storm categorization and global averages of them are unlikely to easily reveal the impact of climate change on future tropical cyclone intensity statistics.

Do Sand Smelt (Atherina presbyter Cuvier, 1829) Larvae Discriminate among Conspecifics Using Different Sensory Cues? - Patrícia Vicente; Ana M. Faria (Oceans, 2021)
The ability of shoaling fish to recognise and differentiate between potential groupmates may affect their fitness and survival. Fish are capable of social recognition and multiple sensory cues mediate the recognition mechanisms. This has been comprehensively studied for juvenile and adult freshwater species. However, the recognition ability and mechanisms intervening during the larval phase of marine species are yet poorly understood. Fish larvae are capable of discriminating conspecifics from heterospecifics based on chemical and/or visual cues, but whether this recognition occurs at finer scales, such as discerning among conspecifics of different reefs, is yet understudied. Here, we tested the hypothesis that larvae of a marine fish species, the sand smelt (Atherina presbyter Cuvier, 1829), are able to recognise and associate with conspecifics of their natal reef versus conspecifics of a non-natal reef based on three sensory modalities—chemical, visual, and chemical and visual simultaneously. Results do not support our hypothesis, but still provide evidence of group cohesion and indicate large differences in the relative importance of the different senses when associating with conspecifics, with visual cues playing a more important role than chemical cues alone.

Demonstration of the Temporal Evolution of Tropical Cyclone “Phailin” Using Gray-Zone Simulations and Decadal Variability of Cyclones over the Bay of Bengal in a Warming Climate - Prabodha Kumar Pradhan; Vinay Kumar; Sunilkumar Khadgarai; S. Vijaya Bhaskara Rao; Tushar Sinha; Vijaya Kumari Kattamanchi; Sandeep Pattnaik (Oceans, 2021)
The intensity and frequency variability of cyclones in the North Indian Ocean (NIO) have been amplified over the last few decades. The number of very severe cyclonic storms (VSCSs) over the North Indian Ocean has increased over recent decades. “Phailin”, an extreme severe cyclonic storm (ESCS), occurred during 8–13 October 2013 over the Bay of Bengal and made landfall near the Gopalpur coast of Odisha at 12 UTC on 12 October. It caused severe damage here, as well as in the coastal Odisha, Andhra Pradesh, and adjoining regions due to strong wind gusts (~115 knot/h), heavy precipitation, and devastating storm surges. The fidelity of the WRF model in simulating the track and intensity of tropical cyclones depends on different cloud microphysical parameterization schemes. Thus, four sensitivity simulations were conducted for Phailin using double-moment and single-moment microphysical (MP) parameterization schemes. The experiments were conducted to quantify and characterize the performance of such MP schemes for Phailin. The simulations were performed by the advanced weather research and forecasting (WRF-ARW) model. The model has two interactive domains covering the entire Bay of Bengal and adjoining coastal Odisha on 25 km and 8.333 km resolutions. Milbrandt–Yau (MY) double-moment and WRF single-moment microphysical schemes, with 6, 5, and 3 classes of hydrometeors, i.e., WSM6, WSM5, and WSM3, were used for the simulation. Experiments for Phailin were conducted for 126 h, starting from 00 UTC 08 October to 06 UTC 13 October 2013. It was found that the track, intensity, and structure of Phailin are highly sensitive to the different microphysical parameterization schemes. Further, the precipitation and cloud distribution were studied during the ESCS stage of Phailin. The microphysics schemes (MY, WSM3, WSM5, WSM6), along with Grell–Devenyi ensemble convection scheme predicted landfall of Phailin over the Odisha coast with significant track errors. Supply of moisture remains a more crucial component than SST and wind shear for rapid intensification of the Phailin 12 h before landfall over the Bay of Bengal. Finally, the comparison of cyclone formation between two decades 2001–2010 and 2011–2020 over the Bay of Bengal inferred that the increased numbers of VSCS are attributed to the supply of abundant moisture at low levels in the recent decade 2011–2020.

Reef Fish Associations with Natural and Artificial Structures in the Florida Keys - Kara Noonan; Thomas Fair; Kristiaan Matthee; Kelsey Sox; Kylie Smith; Michael Childress (Oceans, 2021)
Throughout the Caribbean, coral reefs are transitioning from rugose, coral-dominated communities to flat, soft coral-dominated habitats, triggering declines in biodiversity. To help mitigate these losses, artificial structures have been used to re-create substrate complexity and support reef inhabitants. This study used natural and artificial structures to investigate the factors influencing the use of habitat by reef fish. During 2018 and 2019, divers added artificial structures and monitored the fish assemblages associating with both the artificial structures and naturally occurring corals. Overall, there were more fish on natural structures than on artificial structures. While structure shape did not influence fish use, there was a non-significant trend for increased use of larger structures. Fish observations did not differ across a gradient of shallow, complex reefs to deeper, flatter reefs; however, analyses of feeding guilds revealed clearer patterns: herbivores and omnivores were positively associated with low rugosity reefs where macroalgal abundance was higher, whereas invertivores preferred more rugose reefs. These results suggest that as reefs lose structural complexity, fish communities may become dominated by herbivores and omnivores. It also appears that the addition of artificial structures of the type used here may not mitigate the effects of structure loss on reef fish assemblages.

Relationship between Body and Otolith Morphological Characteristics of Sabre Squirrelfish (Sargocentron spiniferum) from the Southern Red Sea: Difference between Right and Left Otoliths - Yassein A. A. Osman; Kélig Mahé; Samia M. El-Mahdy; Ashraf S. Mohammad; Sahar F. Mehanna (Oceans, 2021)
Otolith morphology analysis is one of the main tools used for fish or fish stock identification. Moreover, otolith shape can also be used in animal dietary studies (stomach content) for the identification of prey fishes and their size according to the relationship between fish and otolith sizes. In the present study, the relationship between fish length and otolith morphological dimensions was investigated for the sabre squirrelfish, Sargocentron spiniferum (Forsskål, 1775) (family: Holocentridae). Samples of 185 fish were collected from the coast of the Red Sea, Egypt. To analyze the relationship between fish and otolith, otolith morphometric measurements (length, width, area, perimeter, weight, sulcus, and ostium) and shape factors (aspect ratio, compactness, form factor, rectangularity, roundness, ellipticity, squareness) describing the outline shape were extracted using image analysis. Generalized linear models were applied for the relationship between body length and each otolith morphology feature. From the relationships between the total length of fish and fourteen morphology features, only otolith length, caudal length, and squareness were significantly correlated with fish size. Our results provide more information for the relationship between fish length and otolith morphometric features.

Reef Structural Complexity Influences Fish Community Metrics on a Remote Oceanic Island: Serranilla Island, Seaflower Biosphere Reserve, Colombia - Diana Castaño; Diana Morales-de-Anda; Julián Prato; Amílcar Leví Cupul-Magaña; Johanna Paola Echeverry; Adriana Santos-Martínez (Oceans, 2021)
Serranilla is a protected island of the Seaflower Biosphere Reserve, far from dense human population. These characteristics could help sustain structurally complex coral reefs, often associated with higher biodiversity, abundance, and biomass of reef-associated organisms, including reef fish. However, the multiple threats present in Serranilla, including intense illegal fishing, can impact coral ecosystems generally and also specific key groups, such as the parrotfish, in particular. During the “Seaflower Research Expedition 2017”, we assessed how structural habitat complexity influences reef fish assemblages. In addition, we explored differences in parrotfish species (family: Scaridae) between Serranilla and San Andrés, the most populated island in the Archipelago. On Serranilla, we found that habitat structure, rugosity, and coral cover accounted for up to 66% of variation in reef fish diversity, abundance, and biomass, with values being higher on more complex reefs. Parrotfish species differed between the islands, with larger species supporting higher biomasses at Serranilla, by comparison with San Andrés; however, the abundance, biomass, and lengths of parrotfish species were low in both areas compared with those reported from other protected Caribbean reefs. Our study indicates that despite the evident relationship between structurally complex habitats and reef fish, other threats in Serranilla could be affecting parrotfish populations, such as illegal fishing, a widespread activity in the area.

Cold-Water Coral Reefs in the Langenuen Fjord, Southwestern Norway—A Window into Future Environmental Change - Katriina Juva; Tina Kutti; Melissa Chierici; Wolf-Christian Dullo; Sascha Flögel (Oceans, 2021)
Ocean warming and acidification pose serious threats to cold-water corals (CWCs) and the surrounding habitat. Yet, little is known about the role of natural short-term and seasonal environmental variability, which could be pivotal to determine the resilience of CWCs in a changing environment. Here, we provide continuous observational data of the hydrodynamic regime (recorded using two benthic landers) and point measurements of the carbonate and nutrient systems from five Lophelia pertusa reefs in the Langenuen Fjord, southwestern Norway, from 2016 to 2017. In this fjord setting, we found that over a tidal (<24 h) cycle during winter storms, the variability of measured parameters at CWC depths was comparable to the intra-annual variability, demonstrating that single point measurements are not sufficient for documenting (and monitoring) the biogeochemical conditions at CWC sites. Due to seasonal and diurnal forcing, parts of the reefs experienced temperatures up to 4 °C warmer (i.e., >12 °C) than the mean conditions and high CT concentrations of 20 µmol kg−1 over the suggested threshold for healthy CWC reefs (i.e., >2170 µmol kg−1). Combined with hindcast measurements, our findings indicate that these shallow fjord reefs may act as an early hotspot for ocean warming and acidification. We predict that corals in Langenuen will face seasonally high temperatures (>18 °C) and hypoxic and corrosive conditions within this century. Therefore, these fjord coral communities could forewarn us of the coming consequences of climate change on CWC diversity and function.

Optimal Life Extension Management of Offshore Wind Farms Based on the Modern Portfolio Theory - Baran Yeter; Yordan Garbatov (Oceans, 2021)
The present study aims to develop a risk-based approach to finding optimal solutions for life extension management for offshore wind farms based on Markowitz’s modern portfolio theory, adapted from finance. The developed risk-based approach assumes that the offshore wind turbines (OWT) can be considered as cash-producing tangible assets providing a positive return from the initial investment (capital) with a given risk attaining the targeted (expected) return. In this regard, the present study performs a techno-economic life extension analysis within the scope of the multi-objective optimisation problem. The first objective is to maximise the return from the overall wind assets and the second objective is to minimise the risk associated with obtaining the return. In formulating the multi-dimensional optimisation problem, the life extension assessment considers the results of a detailed structural integrity analysis, a free-cash-flow analysis, the probability of project failure, and local and global economic constraints. Further, the risk is identified as the variance from the expected mean of return on investment. The risk–return diagram is utilised to classify the OWTs of different classes using an unsupervised machine learning algorithm. The optimal portfolios for the various required rates of return are recommended for different stages of life extension.

A Conflict between the Legacy of Eutrophication and Cultural Oligotrophication in Hiroshima Bay - Tamiji Yamamoto; Kaori Orimoto; Satoshi Asaoka; Hironori Yamamoto; Shin-ichi Onodera (Oceans, 2021)
Although the water quality in Hiroshima Bay has improved due to government measures, nutrient reduction has sharply decreased fisheries production. The law was revised in 2015, where the nutrient effluents from the sewage treatment plants were relaxed, yet no increase in fishery production was observed. Herein, we investigate the distribution of C, N, S, and P within Hiroshima Bay. Material loads from land and oyster farming activity influenced the C and S distributions in the bay sediments, respectively. Natural denitrification caused N reduction in areas by the river mouths and the landlocked areas whose sediments are reductive. The P content was high in the areas under aerobic conditions, suggesting metal oxide-bound P contributes to P accumulation. However, it was low in the areas with reducing conditions, indicating P is released from the sediments when reacting with H2S. In such reductive sediments, liberated H2S also consumes dissolved oxygen causing hypoxia in the bottom layer. It was estimated that 0.28 km3 of muddy sediment and 1.8 × 105 ton of P accumulated in Hiroshima Bay. There remains conflict between the ‘Legacy of Eutrophication’ in the sediment and ‘Cultural Oligotrophication’ in the surface water due to 40 years of reduction policies.

The Last 1200 Years of Rainfall/Runoff Variability along the Central Mexico Pacific Coast Associated with the North American Monsoon - Steve Lund; Emily Mortazavi; Ellen Platzman; Caitlin Tems; William Berelson; Yvonne Hamann (Oceans, 2021)
This study presents new evidence for long-term variability in the late Holocene North American Monsoon (NAM), Pacific coast of Mexico. We have carried out a rock magnetic study on two deep-sea sediment cores from the Pacific coast Pescadero Basin. The magnetic intensities estimate total magnetic material and are a proxy for total clastic sediment. Ratios of magnetic intensities estimate the grain size of magnetic material. The rock magnetic data show a decimeter scale, multi-decadal oscillation with fourteen cycles (A-N) over the last 1200 years. These oscillations reflect alternating intervals of stronger/coarser magnetic/clastic flux to the coastal ocean and intervals of weaker/finer magnetic flux. We think these variations are caused by variations in long-term dominance of the NAM; summer (wet) monsoons produce rainy conditions (with runoff) while winter (dry) monsoons produce significant offshore winds, increased upwelling/biological productivity. We can correlate our variability to two other published studies southeast of Pescadero Basin, coastal lake sediments in Laguna de Juanacatlan and a Juxtlahuaca Cave stalagmite. Both of these studies estimate local rainfall. We see evidence of the same pattern of multi-decadal rainfall-runoff variability in these records as we see in Pescadero Basin, which is synchronous to within ±25 years over the last 1200 years. The multi-dacadal pattern of hydrologic variability in all three records varies in cycle duration from ~90-years wet/dry cycles in the Little Ice Age (1400–1850 AD) to ~60-years cycles in the Medieval Climate Optimum (1100–1400 AD). This variability in cycle duration suggests some chaotic nature to the regional NAM climate pattern or some long-term non-linear forcing (PDO?).

The Status of the Coral Reefs of the Jaffna Peninsula (Northern Sri Lanka), with 36 Coral Species New to Sri Lanka Confirmed by DNA Bar-Coding - Ashani Arulananthan; Venura Herath; Sivashanthini Kuganathan; Anura Upasanta; Akila Harishchandra (Oceans, 2021)
Sri Lanka, an island nation located off the southeast coast of the Indian sub-continent, has an unappreciated diversity of corals and other reef organisms. In particular, knowledge of the status of coral reefs in its northern region has been limited due to 30 years of civil war. From March 2017 to August 2018, we carried out baseline surveys at selected sites on the northern coastline of the Jaffna Peninsula and around the four largest islands in Palk Bay. The mean percentage cover of live coral was 49 ± 7.25% along the northern coast and 27 ± 5.3% on the islands. Bleaching events and intense fishing activities have most likely resulted in the occurrence of dead corals at most sites (coral mortality index > 0.33). However, all sites were characterised by high values of diversity (H’ ≥ 2.3) and evenness (E ≥ 0.8). The diversity index increased significantly with increasing coral cover on the northern coast but showed the opposite trend on the island sites. One hundred and thirteen species of scleractinian corals, representing 16 families and 39 genera, were recorded, as well as seven soft coral genera. Thirty-six of the scleractinian coral species were identified for the first time on the island of Sri Lanka. DNA barcoding using the mitochondrial cytochrome oxidase subunit I gene (COI) was employed to secure genetic confirmation of a few difficult-to-distinguish new records: Acropora aspera, Acropora digitifera, Acropora gemmifera, Montipora flabellata, and Echinopora gemmacea.

Minor Contribution by Biomineralizing Phytoplankton to Surface Ocean Biomineral Pools in the Late Stratified Period - Stuart C. Painter (Oceans, 2021)
Vertical distributions of biogenic silica (bSi), particulate inorganic carbon (PIC) and key biomineral-forming phytoplankton indicate vertical zoning, or partitioning, during the late summer stratified period in the northeast Atlantic. Coccolithophores were generally more numerous in the surface mixed layer, whilst PIC concentrations were more homogenous with depth throughout the euphotic zone. Diatoms were notably more abundant and more diverse in the lower euphotic zone beneath the mixed layer in association with subsurface maxima in chlorophyll-a, bSi and oxygen concentrations. The four dominant coccolithophore species (Emiliania huxleyi, Gephyrocapsa muellerae, Syracosphera spp., and Rhabdosphaera clavigera) represented 78 ± 20% (range 31–100%) of the observed community across all sampled depths yet simultaneously contributed an average of only 13% to measured PIC pools. The diatom community, which was dominated by Pseudo-nitzschia spp. and by a species tentatively identified as Nanoneis longta, represented only ~1% of the bSi pool on average, with contributions increasing within the chlorophyll maximum. Despite a slow gradual deepening of the surface mixed layer in the period prior to observation, and adequate nutrient availability beneath the mixed layer, biomineral pools at this time consisted largely of detrital rather than cellular material.

Shallow-Water Species Diversity of Common Intertidal Zoantharians (Cnidaria: Hexacorallia: Zoantharia) along the Northeastern Coast of Trinidad, Southern Caribbean - Stanton Belford (Oceans, 2021)
Zoantharians are colonial cnidarians commonly found in shallow tropical Caribbean coral reefs, and are known to be globally distributed. Common species in genera Zoanthus and Palythoa occur at Toco, Trinidad, where they are more abundant than their Scleractinia counterparts relative to benthic coverage. In this study, distribution, morphological and molecular data were collected to determine species and symbiont identification to provide more insight on zoantharians. The Line Intercept Point (LIT) transect method recorded coverage at three sites: Salybia (SB), Pequelle (PB), and Grande L’Anse (GA) Bays along the northeastern coast. Variations in morphology, such as tentacle count, oral disk color and diameter were collected from colonies in situ. All specimens were zooxanthellate, and molecular and phylogenetic analyses were done by sequencing the cytochrome oxidase subunit I (COI) gene, and the internal transcribed spacer (ITS) region for species and symbiont identification, respectively. Results showed mean Zoantharia percentage cover was 32.4% ± 5.1 (X ± SE) at SB, 51.3% ± 6.5 (PB), and 72.2% ± 6.1 at GA. Zooxanthellate zoantharians were identified as Palythoa caribaeorum, Palythoa grandiflora, Zoanthus pulchellus, and Zoanthus sociatus. Symbiodiniaceae genera were identified as Cladocopium and Symbiodinium in Palythoa and Zoanthus spp., respectively. Although this is the first molecular examination of zoantharians, and their symbionts in Trinidad, more research is needed to identify and document species distribution and symbiont biodiversity to understand their ecology in these dynamic ecosystems.

Otolith δ18O Composition as a Tracer of Yellowfin Tuna (Thunnus albacares) Origin in the Indian Ocean - Iraide Artetxe-Arrate; Igaratza Fraile; Jessica Farley; Audrey M. Darnaude; Naomi Clear; David L. Dettman; Campbell Davies; Francis Marsac; Hilario Murua (Oceans, 2021)
Yellowfin tuna of the Indian Ocean is overfished, and a better understanding of the stock structure is needed to enable sustainable management. Here, otolith δ18O values of young-of-the-year fish from known nursery areas of the equatorial Indian Ocean (West, Central and East) were used to establish a reference isotopic signature to predict the origin of sub-adult and adult individuals. Sub-adult tuna otolith δ18O values from Reunion Island were similar to the West nursery signature, but otolith δ18O values of sub-adults from Pakistan were unlike any of the nurseries sampled. Therefore, δ18O values from the Pakistan area samples were considered an additional nursery source for predicting the origin of adult tuna, using a multinomial logistic regression classification method. The western equatorial area was the most productive nursery for three fishing grounds sampled, with a minor contribution of Pakistan-like origin fish. Contribution of Central or East nurseries to the adult population was negligible. One adult otolith was analysed by secondary ion mass spectrometry along the otolith growth transect and results were compared with an isoscape approach to infer lifetime movements. This study is an important first step towards understanding the spatial structure and connectivity of the species.

Heatwave Effects on the Photosynthesis and Antioxidant Activity of the Seagrass Cymodocea nodosa under Contrasting Light Regimes - Monya M. Costa; João Silva; Isabel Barrote; Rui Santos (Oceans, 2021)
Global climate change, specifically the intensification of marine heatwaves, affect seagrasses. In the Ria Formosa, saturating light intensities may aggravate heatwave effects on seagrasses, particularly during low spring tides. However, the photophysiological and antioxidant responses of seagrasses to such extreme events are poorly known. Here, we evaluated the responses of Cymodocea nodosa exposed at 20 °C and 40 °C and 150 and 450 μmol quanta m−2 s−1. After four-days, we analyzed (a) photosynthetic responses to irradiance, maximum photochemical efficiency (Fv/Fm), the effective quantum yield of photosystem II (ɸPSII); (b) soluble sugars and starch; (c) photosynthetic pigments; (d) antioxidant responses (ascorbate peroxidase, APX; oxygen radical absorbance capacity, ORAC, and antioxidant capacity, TEAC); (d) oxidative damage (malondialdehyde, MDA). After four days at 40 °C, C. nodosa showed relevant changes in photosynthetic pigments, independent of light intensity. Increased TEAC and APX indicated an “investment” in the control of reactive oxygen species levels. Dark respiration and starch concentration increased, but soluble sugar concentrations were not affected, suggesting higher CO2 assimilation. Our results show that C. nodosa adjusts its photophysiological processes to successfully handle thermal stress, even under saturating light, and draws a promising perspective for C. nodosa resilience under climate change scenarios.

Future Changes in Tropical Cyclone and Easterly Wave Characteristics over Tropical North America - Christian Dominguez; James M. Done; Cindy L. Bruyère (Oceans, 2021)
Tropical Cyclones (TCs) and Easterly Waves (EWs) are the most important phenomena in Tropical North America. Thus, examining their future changes is crucial for adaptation and mitigation strategies. The Community Earth System Model drove a three-member regional model multi-physics ensemble under the Representative Concentration Pathways 8.5 emission scenario for creating four future scenarios (2020–2030, 2030–2040, 2050–2060, 2080–2090). These future climate runs were analyzed to determine changes in EW and TC features: rainfall, track density, contribution to seasonal rainfall, and tropical cyclogenesis. Our study reveals that a mean increase of at least 40% in the mean annual TC precipitation is projected over northern Mexico and southwestern USA. Slight positive changes in EW track density are projected southwards 10° N over the North Atlantic Ocean for the 2050–2060 and 2080–2090 periods. Over the Eastern Pacific Ocean, a mean increment in the EW activity is projected westwards across the future decades. Furthermore, a mean reduction by up to 60% of EW rainfall, mainly over the Caribbean region, Gulf of Mexico, and central-southern Mexico, is projected for the future decades. Tropical cyclogenesis over both basins slightly changes in future scenarios (not significant). We concluded that these variations could have significant impacts on regional precipitation.

Offshore Geological Hazards: Charting the Course of Progress and Future Directions - Gemma Ercilla; David Casas; Belén Alonso; Daniele Casalbore; Jesús Galindo-Zaldívar; Soledad García-Gil; Eleonora Martorelli; Juan-Tomás Vázquez; María Azpiroz-Zabala; Damien DoCouto; Ferran Estrada; Mᵃ Carmen Fernández-Puga; et al. (Oceans, 2021)
Offshore geological hazards can occur in any marine domain or environment and represent a serious threat to society, the economy, and the environment. Seismicity, slope sedimentary instabilities, submarine volcanism, fluid flow processes, and bottom currents are considered here because they are the most common hazardous processes; tsunamis are also examined because they are a secondary hazard generated mostly by earthquakes, slope instabilities, or volcanic eruptions. The hazards can co-occur and interact, inducing a cascading sequence of events, especially in certain contexts, such as tectonic indentations, volcanic islands, and canyon heads close to the coast. We analyze the key characteristics and main shortcomings of offshore geological hazards to identify their present and future directions for marine geoscience investigations of their identification and characterization. This review establishes that future research will rely on studies including a high level of multidisciplinarity. This approach, which also involves scientific and technological challenges, will require effective integration and interplay between multiscale analysis, mapping, direct deep-sea observations and testing, modelling, and linking offshore observations with onshore observations.

Humpback Whale Instigates Object Play with a Lion’s Mane Jellyfish - Brendan D. Shea; Austin J. Gallagher (Oceans, 2021)
Cetaceans are well-known for their intelligence, charismatic nature, and curiosity. Many species, particularly odontocetes, are known to investigate and manipulate novel objects they encounter. Yet, disentangling the drivers of these behaviors and distinguishing between those that are simply playful and those which serve a specific function remains challenging due to a lack of direct observations and detailed descriptions of behaviors. This is particularly true for mysticetes such as humpback whales (Megaptera novaeangliae), as records of object use are far less common than in odontocetes. Here, we present evidence of novel object use from a first of its kind encounter between an individual humpback whale and a large lion’s mane jellyfish (Cyanea capillata) in the coastal waters off New England. We detail the interaction and discuss possible drivers for the behavior, with a focus on cetacean innovation, ectoparasite removal, and wound healing.

The Interactive Role of Hydrocarbon Seeps, Hydrothermal Vents and Intermediate Antarctic/Mediterranean Water Masses on the Distribution of Some Vulnerable Deep-Sea Habitats in Mid Latitude NE Atlantic Ocean - Luis Somoza; José L. Rueda; Olga Sánchez-Guillamón; Teresa Medialdea; Blanca Rincón-Tomás; Francisco J. González; Desirée Palomino; Pedro Madureira; Enrique López-Pamo; Luis M. Fernández-Salas; Esther Santofimia; Ricardo León; et al. (Oceans, 2021)
In this work, we integrate five case studies harboring vulnerable deep-sea benthic habitats in different geological settings from mid latitude NE Atlantic Ocean (24–42° N). Data and images of specific deep-sea habitats were acquired with Remoted Operated Vehicle (ROV) sensors (temperature, salinity, potential density, O2, CO2, and CH4). Besides documenting some key vulnerable deep-sea habitats, this study shows that the distribution of some deep-sea coral aggregations (including scleractinians, gorgonians, and antipatharians), deep-sea sponge aggregations and other deep-sea habitats are influenced by water masses’ properties. Our data support that the distribution of scleractinian reefs and aggregations of other deep-sea corals, from subtropical to north Atlantic could be dependent of the latitudinal extents of the Antarctic Intermediate Waters (AAIW) and the Mediterranean Outflow Waters (MOW). Otherwise, the distribution of some vulnerable deep-sea habitats is influenced, at the local scale, by active hydrocarbon seeps (Gulf of Cádiz) and hydrothermal vents (El Hierro, Canary Island). The co-occurrence of deep-sea corals and chemosynthesis-based communities has been identified in methane seeps of the Gulf of Cádiz. Extensive beds of living deep-sea mussels (Bathymodiolus mauritanicus) and other chemosymbiotic bivalves occur closely to deep-sea coral aggregations (e.g., gorgonians, black corals) that colonize methane-derived authigenic carbonates.

After the Fall: The Demographic Destiny of a Gorgonian Population Stricken by Catastrophic Mortality - Simona Ruffaldi Santori; Maria Carla Benedetti; Silvia Cocito; Andrea Peirano; Roberta Cupido; Fabrizio Erra; Giovanni Santangelo (Oceans, 2021)
In recent years, the frequency of mass mortality events in marine ecosystems has increased, and several populations of benthic organism have been affected, reducing their density and changing their size and age structure. Few details are known about the dynamics of these populations over long time intervals. In late summer of both 1999 and 2003 two drastic mass mortality events, co-occurring with anomalous temperature increases, affected the northwestern Mediterranean rocky coastal communities. Due to these events the Paramuricea clavata population living at the western edge of La Spezia Gulf (Italy) was stricken, and 78% of the colonies died. This population was monitored from 1998 (pre-mortality) until 2013. This paper deals with the photographic sampling of permanent plots carried out in 2013. The findings were compared with those from the previous sampling series. This long-term, non-destructive sampling highlights the demographic trajectory of the octocoral population there after two anomalous mortality events, indicating that some new drop-point between local extinction and complete recovery may be have been reached. Long-term monitoring (including pre-mortality data) could allow evaluating the effects of global climate change on the conservation of impacted populations.

Measurements of Bicarbonate in Water Containing Ocean-Level Sulfate Using a Simple Multi-Pass Optical Raman System - Chetan Shende; Stuart Farquharson; Duncan Farquharson; Carl Brouillette (Oceans, 2021)
The concentration of dissolved inorganic carbon in the oceans at depths of a few meters to thousands of meters is a critical parameter for understanding global warming. The concentration is both pH dependent and depth dependent. Current analysis that employs pH meters must account for several other parameters, such as salinity, temperature, pressure, and the dissolved carbon’s form, carbon dioxide, bicarbonate, or carbonate. Recently, Raman spectroscopy has been used to measure these forms directly in water at ~1000 ppm, which is unfortunately insufficient for typical ocean concentrations, such as ~115 ppm bicarbonate near the surface. Here, we employed a simple multi-pass optical system, a flat mirror to reflect the laser back through the sample, and a concave mirror opposite the entrance slit that effectively doubled the laser power and the collected Raman photons, respectively. This multi-pass optical Raman system with a 1.5 W, 532 nm laser was used to measure 30 ppm bicarbonate in water that contained 2650 ppm sulfate to simulate ocean water, a bicarbonate concentration well below that near the ocean surface. Furthermore, spectral analysis employed the bicarbonate C=O symmetric stretch at 1360 cm−1 instead of the C–OH stretch at 1015 cm−1 to avoid the intense, overlapping sulfate SO4 symmetric stretch at 985 cm−1. The calculated standard deviation of ~5 ppm for the described approach suggests that accurate measurement of bicarbonate in situ is possible, which has been, heretofore, either calculated based on pH or measured in a lab.

Mapping Sub-Metre 3D Land-Sea Coral Reefscapes Using Superspectral WorldView-3 Satellite Stereoimagery - Antoine Collin; Mark Andel; David Lecchini; Joachim Claudet (Oceans, 2021)
Shallow coral reefs ensure a wide portfolio of ecosystem services, from fish provisioning to tourism, that support more than 500 million people worldwide. The protection and sustainable management of these pivotal ecosystems require fine-scale but large-extent mapping of their 3D composition. The sub-metre spaceborne imagery can neatly produce such an expected product using multispectral stereo-imagery. We built the first 3D land-sea coral reefscape mapping using the 0.3 m superspectral WorldView-3 stereo-imagery. An array of 13 land use/land cover and sea use/sea cover habitats were classified using sea-, ground- and air-truth data. The satellite-derived topography and bathymetry reached vertical accuracies of 1.11 and 0.89 m, respectively. The value added of the eight mid-infrared (MIR) channels specific to the WorldView-3 was quantified using the classification overall accuracy (OA). With no topobathymetry, the best combination included the eight-band optical (visible + near-infrared) and the MIR8, which boosted the basic blue-green-red OA by 9.58%. The classes that most benefited from this MIR information were the land use “roof” and land cover “soil” classes. The addition of the satellite-derived topobathymetry to the optical+MIR1 produced the best full combination, increasing the basic OA by 9.73%, and reinforcing the “roof” and “soil” distinction.

Divergent Proteomic Responses Offer Insights into Resistant Physiological Responses of a Reef-Foraminifera to Climate Change Scenarios - Marleen Stuhr; Louise P. Cameron; Bernhard Blank-Landeshammer; Claire E. Reymond; Steve S. Doo; Hildegard Westphal; Albert Sickmann; Justin B. Ries (Oceans, 2021)
Reef-dwelling calcifiers face numerous environmental stresses associated with anthropogenic carbon dioxide emissions, including ocean acidification and warming. Photosymbiont-bearing calcifiers, such as large benthic foraminifera, are particularly sensitive to climate change. To gain insight into their responses to near-future conditions, Amphistegina lobifera from the Gulf of Aqaba were cultured under three pCO2 conditions (492, 963, 3182 ppm) crossed with two temperature conditions (28 °C, 31 °C) for two months. Differential protein abundances in host and photosymbionts were investigated alongside physiological responses and microenvironmental pH gradients assessed via proton microsensors. Over 1000 proteins were identified, of which > 15% varied significantly between treatments. Thermal stress predominantly reduced protein abundances, and holobiont growth. Elevated pCO2 caused only minor proteomic alterations and color changes. Notably, pH at the test surface decreased with increasing pCO2 under all light/dark and temperature combinations. However, the difference between [H+] at the test surface and [H+] in the seawater—a measure of the organism’s mitigation of the acidified conditions—increased with light and pCO2. Combined stressors resulted in reduced pore sizes and increased microenvironmental pH gradients, indicating acclimative mechanisms that support calcite test production and/or preservation under climate change. Substantial proteomic variations at moderate-pCO2 and 31 °C and putative decreases in test stability at high-pCO2 and 31 °C indicate cellular modifications and impacts on calcification, in contrast to the LBFs’ apparently stable overall physiological performance. Our experiment shows that the effects of climate change can be missed when stressors are assessed in isolation, and that physiological responses should be assessed across organismal levels to make more meaningful inferences about the fate of reef calcifiers.

Mediterranean Water Properties at the Eastern Limit of the North Atlantic Subtropical Gyre since 1981 - Helena C. Frazão; Joanna J. Waniek (Oceans, 2021)
A high-quality hydrographic CTD and Argo float data was used to study the property changes along the westward branch of the Mediterranean Outflow Water (MOW) in the northeast Atlantic between 1981 and 2018. In this period, the temperature and salinity are marked by periods of cooling/freshening and warming/salinification. Since 1981, the MOW properties at the core decreased by −0.015 ± 0.07 °C year−1 and −0.003 ± 0.002 year−1. The different phases of the North Atlantic Oscillation (NAO) influence the main propagation pathways of the MOW into the North Atlantic basin, thus affecting the trends determined within different NAO-phases. The temperature and salinity show a strong correlation with NAO, with NAO leading the properties by 8 and 7 years, respectively, indicating a delayed response of the ocean to different forcing conditions. A decrease in oxygen concentration (−0.426 ± 0.276 μmol kg−1 year−1) was calculated for the same period; however, no connection with the NAO was found.

Millennial-Scale Environmental Variability in Late Quaternary Deep-Sea Sediments from the Demerara Rise, NE Coast of South America - Steve Lund; Ellen Platzman (Oceans, 2021)
We carried out a rock magnetic study of two deep-sea gravity cores from the Demerara Rise, NE South America. Our previous studies provided radiocarbon and paleomagnetic chronologies for these cores. This study presents detailed rock magnetic measurements on these cores in order to characterize the rock magnetic mineralogy and grain size as indicators of the overall clastic fraction. We measured the magnetic susceptibility, anhysteretic remanence, and isothermal remanence and demagnetized the remanences at several alternating field demagnetization levels. The magnetic intensities estimate the magnetic material concentration (and indirectly the overall clastic fraction) in the cores. Ratios of rock magnetic parameters indicate the relative grain size of the magnetic material (and indirectly the overall clastic grain size). Rock magnetic intensity parameters and rock magnetic ratios both vary systematically and synchronously over the last 30,000 years in both cores. There is a multi-millennial-scale cyclicity, with intervals of high magnetic intensity (high magnetic and clastic content) with low magnetic ratios (coarser magnetic and clastic grain size), alternating in sequence with intervals of low magnetic intensity with high magnetic ratios (finer grain size). There is also a higher-frequency millennial-scale variability in intensity superposed on the multi-millennial-scale variability. There are nine (A–I) multi-millennial-scale intervals in the cores. Intervals A, C, E, G, and I have high magnetic and clastic content with coarser overall magnetic and clastic grain size and are likely intervals of enhanced rainfall and runoff from the NE South American margin to the coastal ocean. In contrast, intervals B, D, F, and H have lower clastic flux with finer overall grain size, probably indicating lower continental rainfall and runoff. During the Holocene, high rainfall and runoff intervals can be related to cooler times and low rainfall and runoff to warmer times. The opposite pattern existed during the Pleistocene, with higher rainfall and runoff during interstadial conditions and lower rainfall and runoff during stadial conditions. We noted a similar pattern of Pleistocene multi-millennial-scale variability in a transect of deep-sea sediment cores along the NE Brazilian margin, from the Cariaco Basin (~10 N) to the NE Brazilian margin (~1° N–4° S). However the NW part of this transect (Cariaco Basin, Demerara Rise, Amazon Fan) has an out-of-phase relationship with the SE part of the transect (NE Brazilian margin) between warm–cold and wet–dry conditions. One possible cause of the high–low rainfall and runoff patterns might be oscillation of the Intertropical Convergence Zone (ITCZ), with higher rainfall and runoff associated with a more southerly average position of the ITCZ and lower rainfall and runoff associated with a more northerly average position of the ITCZ.

Severe Heat Stress Resulted in High Coral Mortality on Maldivian Reefs following the 2015–2016 El Niño Event - Pia Bessell-Browne; Hannah E. Epstein; Nora Hall; Patrick Buerger; Kathryn Berry (Oceans, 2021)
Coral cover worldwide has been declining due to heat stress caused by climate change. Here we report the impacts of the 2015–2016 El Niño mass coral bleaching event on the coral cover of reefs located on central and northern atolls of the Maldives. We surveyed six reef sites in the Alifu Alifu (Ari) and Baa (South Maalhosmadulu) Atolls using replicate 20 m benthic photo transects at two depths per reef site. Live and recently dead coral cover identified from images differed between reef sites and depth. Recently dead corals on average made up 33% of the coral assemblage at shallow sites and 24% at deep sites. This mortality was significantly lower in massive corals than in branching corals, reaching an average of only 6% compared to 41%, respectively. The best predictors of live coral cover were depth and morphology, with a greater percentage of live coral at deep sites and in massive corals. The same predictors best described the prevalence of recently dead coral, but showed inverse trends to live coral. However, there was high variability among reef sites, which could be attributed to additional local stressors. Coral bleaching and resulting coral mortalities, such as the ones reported here, are of particular concern for small island nations like the Maldives, which are reliant on coral reefs.

Consistency Is Critical for the Effective Use of Baited Remote Video - Robyn E. Jones; Ross A. Griffin; Roger J. H. Herbert; Richard K. F. Unsworth (Oceans, 2021)
Baited remote underwater videos (BRUV) are popular marine monitoring techniques used for the assessment of motile fauna. Currently, most published studies evaluating BRUV methods stem from environments in the Southern Hemisphere. This has led to stricter and more defined guidelines for the use of these techniques in these areas in comparison to the North Atlantic, where little or no specific guidance exists. This study explores metadata taken from BRUV deployments collected around the UK to understand the influence of methodological and environmental factors on the information gathered during BRUV deployments including species richness, relative abundance and faunal composition. In total, 39 BRUV surveys accumulating in 457 BRUV deployments across South/South-West England and Wales were used in this analysis. This study identified 88 different taxa from 43 families across the 457 deployments. Whilst taxonomic groups such as Labridae, Gadidae and Gobiidae were represented by a high number of species, species diversity for the Clupeidae, Scombridae, Sparidae, Gasterosteidae and Rajidae groups were low and many families were absent altogether. Bait type was consistently identified as one of the most influential factors over species richness, relative abundance and faunal assemblage composition. Image quality and deployment duration were also identified as significant influential factors over relative abundance. As expected, habitat observed was identified as an influential factor over faunal assemblage composition in addition to its significant interaction with image quality, time of deployment, bait type and tide type (spring/neap). Our findings suggest that methodological and environmental factors should be taken into account when designing and implementing monitoring surveys using BRUV techniques. Standardising factors where possible remains key. Fluctuations and variations in data may be attributed to methodological inconsistencies and/or environment factors as well as over time and therefore must be considered when interpreting the data.

An Experimental Approach to Assessing the Roles of Magnesium, Calcium, and Carbonate Ratios in Marine Carbonates - Claire E. Reymond; Sönke Hohn (Oceans, 2021)
Marine biomineralization is a globally important biological and geochemical process. Understanding the mechanisms controlling the precipitation of calcium carbonate [CaCO3] within the calcifying fluid of marine organisms, such as corals, crustose coralline algae, and foraminifera, presents one of the most elusive, yet relevant areas of biomineralization research, due to the often-impenetrable ability to measure the process in situ. The precipitation of CaCO3 is assumed to be largely controlled by the saturation state [Ω] of the extracellular calcifying fluid. In this study, we mimicked the typical pH and Ω known for the calcifying fluid in corals, while varying the magnesium, calcium, and carbonate concentrations in six chemo-static growth experiments, thereby mimicking various dissolved inorganic carbon concentration mechanisms and ionic movement into the extracellular calcifying fluid. Reduced mineralization and varied CaCO3 morphologies highlight the inhibiting effect of magnesium regardless of pH and Ω and suggests the importance of strong magnesium removal or calcium concentration mechanisms. In respect to ocean acidification studies, this could allow an explanation for why specific marine calcifiers respond differently to lower saturation states.

An Expert Elicitation of the Effects of Low Salinity Water Exposure on Bottlenose Dolphins - Cormac Booth; Len Thomas (Oceans, 2021)
There is increasing concern over anthropogenically driven changes in our oceans and seas, from a variety of stressors. Such stressors include the increased risk of storms and precipitation, offshore industries and increased coastal development which can affect the marine environment. For some coastal cetacean species, there is an increased exposure to low salinity waters which have been linked with a range of adverse health effects in bottlenose dolphins. Knowledge gaps persist regarding how different time–salinity exposures affect the health and survival of animals. In such data-poor instances, expert elicitation can be used to convert an expert’s qualitative knowledge into subjective probability distributions. The management implications of this stressor and the subjective nature of expert elicitation requires transparency; we have addressed this here, utilizing the Sheffield Elicitation Framework. The results are a series of time response scenarios to estimate time to death in bottlenose dolphins, for use when data are insufficient to estimate probabilistic summaries. This study improves our understanding of how low salinity exposure effects dolphins, guiding priorities for future research, while its outputs can be used to support coastal management on a global scale.

Canopy Accumulation: Are Seagrass Meadows a Sink of Microplastics? - Richard K. F. Unsworth; Alex Higgs; Bettina Walter; Leanne C. Cullen-Unsworth; Isabella Inman; Benjamin L. Jones (Oceans, 2021)
A growing body of research is documenting the accumulation of microplastics within marine sediments around the world. The hydrodynamic influences of seagrasses in coastal environments are shown to increase sedimentation of finer particles and as a result there has been speculation that this attribute will lead to seagrass meadows acting as a site of elevated microplastic contamination. To date a range of localised studies have provided conflicting answers to this hypothesis. Seagrass meadows provide multiple ecosystem services including vital support roles for a range of fisheries; therefore, there are considerable human health implications for understanding their role as sinks of microplastics. This research investigated the abundance and diversity of microplastics present in temperate North Atlantic seagrass meadow sediments relative to unvegetated sediments and examined how they correlate with the meadow structure and the sediment type. We also placed this data in the context of the current knowledge of microplastics in seagrass sediments through a global meta-analysis of published data. Eight seagrass meadows and adjacent unvegetated sites around the UK were sampled to test for the abundance of microplastic particles in the sediment. Microplastics were found in 98% of the samples, with fibres making up 91.8% of all microplastics identified. Abundance was recorded to overall be 215 ± 163 microplastic particles (MP) kg−1 Dry Weight (DW) of sediment in seagrass and 221 ± 236 MP kg−1 DW of sediment in unvegetated habitats. There were no significant differences found between the number of MP with respect to vegetation. We report evidence of the almost ubiquitous contamination of seagrass sediments with microplastics both in the UK and globally but find that the contamination reflects a general build-up of microplastics in the wider environment rather than becoming concentrated within seagrass as an enhanced sink. Microplastic build up in sediments is hypothesised to be the result of local hydrodynamics and plastic sources rather than the result of elevated habitat level concentration. Although not of a higher abundance in seagrass, such contamination in seagrass is of cause for concern given the high dependency of many species of fish on these habitat types and the potential for plastics to move up the food chain.

The Price of Coastal Erosion and Flood Risk: A Hedonic Pricing Approach - Serkan Catma (Oceans, 2021)
Accelerated coastal erosion and elevated risks of flooding due to global warming put enormous burden on the ecosystems and economic health of coastal communities. Optimal policies to lessen these negative impacts require an estimation of their costs and benefits. The aim of this paper is to calculate the costs of beach erosion and flood risk through the valuation of property prices in Hilton Head Island, a barrier island located in South Carolina, USA. Spatial lag hedonic pricing was introduced in order to account for spatial autocorrelation in the dataset. The results show that properties that are located within the zone of high, or very high, flood risk experience a 15.6% reduction in value. The implicit price of being located close to an eroded beach is approximately 26% of the price of an oceanfront property. However, this negative impact on property value diminishes with distance from the shoreline.

Ocean Circulation Drives the Variability of the Carbon System in the Eastern Tropical Atlantic - Nathalie Lefèvre; Carlos Mejia; Dmitry Khvorostyanov; Laurence Beaumont; Urbain Koffi (Oceans, 2021)
The carbon system in the eastern tropical Atlantic remains poorly known. The variability and drivers of the carbon system are assessed using surface dissolved inorganic carbon (DIC), alkalinity (TA) and fugacity of CO2 (fCO2) measured in the 12° N–12° S, 12° W–12° E region from 2005 to 2019. A relationship linking DIC to temperature, salinity and year has been determined, with salinity being the strongest predictor. The seasonal variations of DIC, ranging from 80 to 120 μμmol kg−1, are more important than the year-to-year variability that is less than 50 μμmol kg−1 over the 2010–2019 period. DIC and TA concentrations are lower in the northern part of the basin where surface waters are fresher and warmer. Carbon supply dominates over biological carbon uptake during the productive upwelling period from July to September. The lowest DIC and TA are located in the Congo plume. The influence of the Congo is still observed at the mooring at 6° S, 8° E as shown by large salinity and chlorophyll variations. Nevertheless, this site is a source of CO2 emissions into the atmosphere.

Structure and Dynamics of the Ras al Hadd Oceanic Dipole in the Arabian Sea - Adam Ayouche; Charly De Marez; Mathieu Morvan; Pierre L’Hegaret; Xavier Carton; Briac Le Vu; Alexandre Stegner (Oceans, 2021)
The Ras al Hadd oceanic dipole is a recurrent association of a cyclone (to the northeast) and of an anticyclone (to the southwest), which forms in summer and breaks up at the end of autumn. It lies near the Ras al Hadd cape, southeast of the Arabian peninsula. Its size is on the order of 100 km. Along the axis of this dipole flows an intense jet, the Ras al Had jet. Using altimetric data and an eddy detection and tracking algorithm (AMEDA: Angular Momentum Eddy Detection and tracking Algorithm), we describe the life cycle of this oceanic dipole over a year (2014–2015). We also use the results of a numerical model (HYCOM, the HYbrid Coordinate Ocean Model) simulation, and hydrological data from ARGO profilers, to characterize the vertical structure of the two eddies composing the dipole, and their variability over a 15 year period. We show that (1) before the dipole is formed, the two eddies that will compose it, come from different locations to join near Ras al Hadd, (2) the dipole remains near Ras al Hadd during summer and fall while the wind stress (due to the summer monsoon wind) intensifies the cyclone, (3) both the anticyclone and the cyclone reach the depth of the Persian Gulf Water outflow, and (4) their horizontal radial velocity profile is often close to Gaussian but it can vary as the dipole interacts with neighboring eddies. As a conclusion, further work with a process model is recommended to quantify the interaction of this dipole with surrounding eddies and with the atmosphere.

Antibiotic Resistance of Bacteria in Two Marine Mammal Species, Harbor Seals and Harbor Porpoises, Living in an Urban Marine Ecosystem, the Salish Sea, Washington State, USA - Stephanie A. Norman; Dyanna M. Lambourn; Jessica L. Huggins; Joseph K. Gaydos; Sandra Dubpernell; Susan Berta; Jennifer K. Olson; Victoria Souze; Alysha Evans; Betsy Carlson; Mandi Johnson; Rachel Mayer; et al. (Oceans, 2021)
The pervasive use of antibiotics in human medicine, veterinary medicine, and agriculture can result in a significant increase in the spread and environmental persistence of antibiotic resistance in marine ecosystems. This study describes the presence and distribution of antibiotic-resistant bacteria in Salish Sea harbor seals (Phoca vitulina) and harbor porpoises (Phocoena phocoena) and evaluates species, age class, and geographic differences in resistance patterns. Isolates from 95 dead-stranded animals (74 seals/21 porpoises) were tested for resistance to a suite of 15 antibiotics. Of the 95 sampled, 85 (89%) (67 seals/18 porpoises) successfully yielded 144 isolates, with 37% resistant to at least one antibiotic and 26% multi-drug resistant (24% and 39% of seal and porpoise isolates, respectively). Overall, and by study region, porpoises were significantly more likely to harbor resistant organisms compared to seals. Significant differences between age classes were noted for the antibiotics amoxicillin, cephalexin, and cefovecin. Overall isolate resistance was significantly greater in porpoises than seals for several individual antibiotics. Multiple antibiotic resistance (MAR) indices greater than 0.2 were observed in 55% of multi-drug resistant isolates, suggesting seal and porpoise exposure to anthropogenic pollution. The relatively high and disparate prevalence of antibiotic resistance in these common, but ecologically dissimilar, marine mammals reflects a potentially large environmental pool of antibiotic resistant organisms in the Salish Sea or inherently different resistance gene patterns between the two species.

Acknowledgment to Reviewers of Oceans in 2020 (Oceans, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Oceans maintains its standards for the high quality of its published papers [...]

Influence of the Seasonal Thermocline on the Vertical Distribution of Larval Fish Assemblages Associated with Atlantic Bluefin Tuna Spawning Grounds - Itziar Alvarez; Leif K. Rasmuson; Trika Gerard; Raul Laiz-Carrion; Manuel Hidalgo; John T. Lamkin; Estrella Malca; Carmen Ferra; Asvin P. Torres; Diego Alvarez-Berastegui; Francisco Alemany; Jose M. Quintanilla; et al. (Oceans, 2021)
Temperature is often an important variable influencing the vertical position of fish larvae in the water column. The same species may show different vertical distributions in areas with a strong near-surface seasonal thermocline compared to isothermal near-surface regions. In areas with a strong surface thermocline, tuna larvae show a significant preference for the near-surface warmer layers. Little is known regarding larval tuna vertical distribution in isothermal waters and on the vertical distribution of the associated larval fish assemblages. We conducted vertical stratified sampling using the same methodology and fishing device (MOCNESS) in the two major spawning areas of Atlantic bluefin tuna (BFT): western Mediterranean Sea (MED), characterized by a surface thermocline, and the Gulf of Mexico (GOM) which lacks thermal stratification. Tuna larvae occupied the upper 30 m in both areas, but the average larval depth distribution was consistently deeper in the GOM. In the MED, vertical distribution of larval fish assemblages was explained by temperature, and species such as BFT, Thunnus alalunga, and Ceratoscopelus maderensis, among others, coexist above the thermocline and are separated from species such as Cyclothone braueri and Hygophum spp. (found below the thermocline). In the GOM, the environmental correlates of the vertical distribution of the larvae were salinity and fluorescence. Mesopelagic taxa such as Ceratoscopelus spp. and Cyclothone spp., among others, had a shallower average distribution than Lampanyctus spp., Hygophum spp., and Myctophum spp.

Harbour Seals: Population Structure, Status, and Threats in a Rapidly Changing Environment - Marie-Anne Blanchet; Cécile Vincent; Jamie N. Womble; Sheanna M. Steingass; Geneviève Desportes (Oceans, 2021)
The harbour seal (Phoca vitulina) is the world’s most widely distributed pinniped species ranging from temperate to Arctic regions (30–78.5° N in the Atlantic, 28–61.2° N in the Pacific), but no detailed overview of the species status exists. The aims of this review are to (i) provide current information on the genetic structure, population status, and threats; (ii) review potential consequences of a changing climate; and (iii) identify knowledge gaps to guide future research and monitoring. Although the species is globally abundant, wide differences exist across the species’ broad range. As climate warms, populations at the edges of the species’ distributional range are likely to be more affected. The primary climate-related drivers include: (i) changes in weather patterns, which can affect thermoregulation; (ii) decrease in availability of haul-out substrates; (iii) large-scale changes in prey availability and inter-specific competition; (iv) shifts in the range of pathogens; (v) increase in temperature favouring the biotransformation of contaminants; and (vi) increased exposure to pollutant from increased freshwater run-off. Multiple anthropogenic stressors may collectively impact some populations. Coordinated monitoring efforts across and within regions is needed. This would allow for a spatially explicit management approach including population-specific responses to known stressors.

Effects of Experimental Ocean Acidification on the Larval Morphology and Metabolism of a Temperate Sparid, Chrysoblephus laticeps - Cuen Muller; Amber-Robyn Childs; Nicola C. James; Warren M. Potts (Oceans, 2020)
Ocean acidification is predicted to have widespread impacts on marine species. The early life stages of fishes, being particularly sensitive to environmental deviations, represent a critical bottleneck to recruitment. We investigated the effects of ocean acidification (∆pH = −0.4) on the oxygen consumption and morphometry during the early ontogeny of a commercially important seabream, Chrysoblephus laticeps, up until flexion. Hatchlings appeared to be tolerant to hypercapnic conditions, exhibiting no difference in oxygen consumption or morphometry between treatments, although the yolk reserves were marginally reduced in the low-pH treatment. The preflexion stages appeared to undergo metabolic depression, exhibiting lower metabolic rates along with lower growth metrics in hypercapnic conditions. However, although the sample sizes were low, the flexion-stage larvae exhibited greater rates of metabolic and growth metric increases in hypercapnic conditions. This study shows that the effects of OA may be stage specific during early ontogeny and potentially related to the development of crucial organs, such as the gills. Future studies investigating the effects of climate change on fish larvae should endeavour to include multiple developmental stages in order to make more accurate predictions on recruitment dynamics for the coming decades.

Perspectives on Larval Behaviour in Biophysical Modelling of Larval Dispersal in Marine, Demersal Fishes - Jeffrey M. Leis (Oceans, 2020)
Biophysical dispersal models for marine fish larvae are widely used by marine ecologists and managers of fisheries and marine protected areas to predict movement of larval fishes during their pelagic larval duration (PLD). Over the past 25 years, it has become obvious that behaviour—primarily vertical positioning, horizontal swimming and orientation—of larvae during their PLD can strongly influence dispersal outcomes. Yet, most published models do not include even one of these behaviours, and only a tiny fraction include all three. Furthermore, there is no clarity on how behaviours should be incorporated into models, nor on how to obtain the quantitative, empirical data needed to parameterize models. The PLD is a period of morphological, physiological and behavioural change, which presents challenges for modelling. The present paper aims to encourage the inclusion of larval behaviour in biophysical dispersal models for larvae of marine demersal fishes by providing practical suggestions, advice and insights about obtaining and incorporating behaviour of larval fishes into such models based on experience. Key issues are features of different behavioural metrics, incorporation of ontogenetic, temporal, spatial and among-individual variation, and model validation. Research on behaviour of larvae of study species should be part of any modelling effort.

Future Changes in Western North Pacific Tropical Cyclone Genesis Environment in High-Resolution Large-Ensemble Simulations - Hironori Fudeyasu; Kohei Yoshida; Ryuji Yoshida (Oceans, 2020)
This study applied the database for Policy Decision making for Future climate change (d4PDF) and tropical cyclone (TC) genesis (TCG) environment factors to project future changes in the frequency and characteristics of TCs over the western North Pacific. We examined current and future TCG environmental conditions in terms of the contribution of five factors: shear line (SL), confluence region (CR), monsoon gyre, easterly wave (EW), and Rossby wave energy dispersion from a preexisting TC (PTC). Among summer and autumn TCs, the contributions of SL and EW to future TCG increased by about 4% and 1%, respectively, whereas those of CR and PTC decreased by the same amounts. In future climate projections, the average lifetime maximum intensity (LMI) of TCs associated with EW (EW-TCs) was significantly higher than those of TCs associated with other factors except PTC. At higher sea surface temperatures and wetter conditions, higher lower-tropospheric relative vorticity was related to increases in the development rate of EW-TCs. Findings of this study suggest that increases in the average LMI of all future TCs were caused by large contributions from the average LMI of future EW-TCs.

Use of Polyphosphates and Soluble Pyrophosphatase Activity in the Seaweed Ulva pseudorotundata - Juan J. Vergara; Patricia Herrera-Pérez; Fernando G. Brun; José Lucas Pérez-Lloréns (Oceans, 2020)
The hydrolytic activity of different types of polyphosphates, and the induction of soluble pyrophosphatase (sPPase; EC 3.6.1.1) activity have been assessed in cell extracts of nutrient limited green seaweed Ulva pseudorotundata Cormaci, Furnari & Alongi subjected to different phosphorus regimes. Following a long period of nutrient limitation, the addition of different types of (poly)phosphates to artificial seawater enhanced growth rates on fresh weight and area, but not on dry weight bases. Chlorophyll and internal P content were affected by P supply. In contrast, internal soluble reactive P was kept low and was little affected by P additions. Soluble protein content increased in all treatments, as ammonium was added to prevent N limitation. The C:N:P atomic ratio revealed great changes depending on the nutrient regime along the experiment. Cell extracts of U. pseudorotundata were capable of hydrolyzing polyphosphates of different chain lengths (pyro, tripoly, trimeta, and polyphosphates) at high rates. The sPPase activity was kept very low in P limited plants. Following N and different kind of P additions, sPPase activity was kept low in the control, but slightly stimulated after 3 days when expressed on a protein basis. The highest activities were found at the end of the experiment under pyro and polyphosphate additions (7 days). The importance of alternative P sources to phosphate and the potential role of internal soluble pyrophosphatases in macroalgae are discussed.

Probabilistic Forecasts of Sea Ice Trajectories in the Arctic: Impact of Uncertainties in Surface Wind and Ice Cohesion - Sukun Cheng; Ali Aydoğdu; Pierre Rampal; Alberto Carrassi; Laurent Bertino (Oceans, 2020)
We study the response of the Lagrangian sea ice model neXtSIM to the uncertainty in sea surface wind and sea ice cohesion. The ice mechanics in neXtSIM are based on a brittle-like rheological framework. The study considers short-term ensemble forecasts of Arctic sea ice from January to April 2008. Ensembles are generated by perturbing the wind inputs and ice cohesion field both separately and jointly. The resulting uncertainty in the probabilistic forecasts is evaluated statistically based on the analysis of Lagrangian sea ice trajectories as sampled by virtual drifters seeded in the model to cover the Arctic Ocean and using metrics borrowed from the search-and-rescue literature. The comparison among the different ensembles indicates that wind perturbations dominate the forecast uncertainty (i.e., the absolute spread of the ensemble), while the inhomogeneities in the ice cohesion field significantly increase the degree of anisotropy in the spread—i.e., trajectories drift divergently in different directions. We suggest that in order to obtain enough uncertainties in a sea ice model with brittle-like rheologies, to predict sea ice drift and trajectories, one should consider using ensemble-based simulations where at least wind forcing and sea ice cohesion are perturbed.

Statistical Decomposition of the Recent Increase in the Intensity of Tropical Storms - Stephen Jewson; Nicholas Lewis (Oceans, 2020)
In a recent paper, Kossin et al. showed that during the period from 1979 to 2017, there was a statistically significant increase in the ratio of category 3–5 to category 1–5 tropical storm fixes in the ADT-HURSAT satellite dataset of tropical cyclone observations. The sign of this increase is consistent with previously developed theory and modelling results for how tropical cyclones may change due to climate change. However, without further analysis, it is difficult to understand what the implications of this increase might be for present day tropical cyclone risk. It is also difficult to understand how tropical cyclone risk models might be adjusted to reflect this increase, since this ratio is not typically directly represented in such models. Our goal is therefore to understand the drivers for this increase in terms of changes in the numbers of fixes of different categories of storms in different basins, which are quantities that are more directly related to tropical cyclone risk and risk modelling. We use both heuristic and quantitative methods. We find that the increase in the ratio is mainly driven by a decrease in the denominator (the number of category 1–5 fixes) and to a small extent by a slight increase in the numerator (the number of category 3–5 fixes). The decrease in the denominator is mostly driven by a statistically significant reduction in the number of category 1 fixes outside the North Atlantic. The slight increase in the numerator is mostly driven by a statistically significant increase in the number of category 3–4 fixes in the North Atlantic. Based on these results, we discuss different ways in which the increase in the ratio could be represented in risk models.

Feeding Ecology of Sicydium bustamantei (Greeff 1884, Gobiidae) Post-Larvae: The “Little Fish” of São Tomé Island - Vânia Baptista; Ester Dias; Joana Cruz; Maria Branco; Sara Vieira; Maria Alexandra Teodósio (Oceans, 2020)
The rivers of São Tomé Island are colonized by Sicydium bustamantei (Greeff 1882), an amphidromous fish that spawns in those areas. After hatching, larvae drift to the ocean with the river flow. In the marine realm, the planktonic larvae develop and migrate to freshwater as post-larvae. The migrations of post-larvae support important local fisheries at the mouth of rivers in tropical volcanic islands. Amphidromous post-larvae rely on plankton as their main source of organic matter. However, the biology and ecology of S. bustamantei in the West African islands are understudied, despite its importance for local fisheries. Thus, this study aimed to start bridging this gap by studying its feeding ecology. Our objectives were to identify the main prey of S. bustamantei post-larvae, combining gut content with stable isotope analyses. The gut contents included zooplankton (Chaetognatha, Ostracoda, and unidentified crustaceans), debris from plant and/or macroalgae-derived material, and microplastics (including microfibers). The stable isotopes analysis indicated that zooplankton and macroalgae detritus were the main sources of organic matter assimilated by this species. We also demonstrated that S. bustamantei post-larvae are omnivorous and secondary consumers. These data provide pioneering information that can be used in management plans that still need to be developed.

Application of Photo-Identification and Lengthened Deployment Periods to Baited Remote Underwater Video Stations (BRUVS) Abundance Estimates of Coral Reef Sharks - Mauvis Gore; Rupert Ormond; Chris Clarke; Johanna Kohler; Catriona Millar; Edward Brooks (Oceans, 2020)
Baited Remote Underwater Video Stations (BRUVS) are widely used for monitoring relative abundances of fishes, especially sharks, but only the maximum number of individuals seen at any one time (MaxN) is usually recorded. In both the Cayman Islands and the Amirante Islands, Seychelles, we used photo-ID to recognise individual sharks recorded on BRUVS videos. This revealed that for most species the actual numbers of separate individuals (IndN) visiting the BRUVS were significantly higher than MaxN, with, for example, ratios of IndN to MaxN being 1.17 and 1.24 for Caribbean reef, Carcharhinus perezi, and nurse, Ginglymostoma cirratum, sharks in the Cayman Islands, and 2.46 and 1.37 for blacktip reef, C. melanopterus, and grey reef, C. amblyrhynchos, sharks, respectively, in the Amirantes. Further, for most species, increasing the BRUVS deployment period beyond the 60 min normally used increased the observed IndN, with more than twice as many individuals in the Cayman Islands and >1.4 times as many individuals in the Amirantes being recorded after 120 min as after 60 min. For most species, MaxN and IndN rose exponentially with time, so data from different deployment periods cannot reliably be compared using catch-per-unit-effort (CPUE) calculated as catch-per-unit-time. In both study areas, the time of first arrival of individuals varied with species from <1 min to >2 h. Individually identifiable sharks were re-sighted after up to 429 days over 10 km away in the Cayman Islands and 814 days over 23 km away in the Amirantes, demonstrating that many individuals range over considerable distances. Analysis of Cayman re-sightings data yielded mean population estimates of 76 ± 23 (SE) and 199 ± 42 (SE) for C. perezi and G. cirratum, respectively. The results demonstrate that, for sharks, the application of both photo-identification and longer deployment periods to BRUVS can improve the precision of abundance estimates and provide knowledge of population size and ranging behaviour.

Seasonal and Inter-Annual Variability of the Phytoplankton Dynamics in the Black Sea Inner Basin - Svetla Miladinova; Adolf Stips; Diego Macias Moy; Elisa Garcia-Gorriz (Oceans, 2020)
We explore the patterns of Black Sea phytoplankton growth as driven by the thermohaline structure and circulation system and the freshwater nutrient loads. Seasonal and inter-annual variability of the phytoplankton blooms is examined using hydrodynamic simulations that resolve mesoscale eddies and online coupled bio-geochemical model. This study suggests that the bloom seasonality is homogeneous across geographic locations of the Black Sea inner basin, with the strongest bloom occurring in winter (February–March), followed by weaker bloom in spring (April–May), summer deep biomass maximum (DBM) (June–September) and a final bloom in autumn (October–November). The winter phytoplankton bloom relies on vertical mixing of nitrate from the intermediate layers, where nitrate is abundant. The winter bloom is highly dependent on the strength of the cold intermediate layers (CIL), while spring/summer blooms take advantage of the CIL weakness. The maximum phytoplankton transport across the North Western Shelf (NWS) break occurs in September, prior to the basin interior autumn bloom. Bloom initiation in early autumn is associated with the spreading of NWS waters, which in turn is caused by an increase in mesoscale eddy activity in late summer months. In summary, the intrusion of low salinity and nitrate-rich water into the basin interior triggers erosion of the thermocline, resulting in vertical nitrate uplifting. The seasonal phytoplankton succession is strongly influenced by the recent CIL disintegration and amplification of the Black Sea circulation, which may alter the natural Black Sea nitrate dynamics, with subsequent effects on phytoplankton and in turn on all marine life.

Ontogeny of Orientation during the Early Life History of the Pelagic Teleost Mahi-Mahi, Coryphaena hippurus Linnaeus, 1758 - Robin Faillettaz; Eve Johnson; Patrick Dahlmann; Alexandra Syunkova; John Stieglitz; Daniel Benetti; Martin Grosell; Claire B. Paris (Oceans, 2020)
Understanding the orientation behavior and capabilities in early life history (ELH) of fishes is critical for studying their dispersal but has, surprisingly, never been tested in any pelagic species. We here investigate the ontogeny of orientation and swimming abilities of the pelagic Coryphaena hippurus Linnaeus, 1758 larvae, hereafter mahi-mahi, through their ELH stages using the Drifting In Situ Chamber (DISC) in a laboratory setup. The DISC was deployed in a large (3 m3) circular aquarium in order to control the stimulus perceived by the fish and to identify behavioral response at the individual, developmental stage, and population levels. A total of 79 individual ranging from 7 to 23 days post hatch and from preflexion to early juvenile stages were exposed to a directional light mimicking the sun’s position. Orientation towards the light direction was tested by switching the light by 180° among trials. To compare the orientation among development stages, we scaled the directionality by the swimming ability, therein defined as “directionality competence”. The results show that while mahi-mahi directionality competence increases through ontogeny, they acquire a positive and directional phototaxis behavior at the flexion stage. This potential solar orientation is kept through the early juvenile stage. Mahi-mahi may thus be able to use the sun as a compass in the open ocean as observed in the larval stages of demersal species seeking for settlement habitats. This ability notably develops before the improvement of their swimming capabilities, suggesting that early orientation—even at micro-scale—and swimming capabilities may be equally important for the survival of the ELH stages of pelagic species.

Effect of Acute Seawater Temperature Increase on the Survival of a Fish Ectoparasite - Mary O. Shodipo; Berilin Duong; Alexia Graba-Landry; Alexandra S. Grutter; Paul C. Sikkel (Oceans, 2020)
Extreme warming events that contribute to mass coral bleaching are occurring with increasing regularity, raising questions about their effect on coral reef ecological interactions. However, the effects of such events on parasite-host interactions are largely ignored. Gnathiid isopods are common, highly mobile, external parasites of coral reef fishes, that feed on blood during the juvenile stage. They have direct and indirect impacts on their fish hosts, and are the major food source for cleaner fishes. However, how these interactions might be impacted by increased temperatures is unknown. We examined the effects of acute temperature increases, similar to those observed during mass bleaching events, on survivorship of gnathiid isopod juveniles. Laboratory experiments were conducted using individuals from one species (Gnathia aureamaculosa) from the Great Barrier Reef (GBR), and multiple unknown species from the central Philippines. Fed and unfed GBR gnathiids were held in temperature treatments of 29 °C to 32 °C and fed Philippines gnathiids were held at 28 °C to 36 °C. Gnathiids from both locations showed rapid mortality when held in temperatures 2 °C to 3 °C above average seasonal sea surface temperature (32 °C). This suggests environmental changes in temperature can influence gnathiid survival, which could have significant ecological consequences for host-parasite-cleaner fish interactions during increased temperature events.

Influence of Seawater Ageing on Fracture of Carbon Fiber Reinforced Epoxy Composites for Ocean Engineering - Antoine Le Guen-Geffroy; Peter Davies; Pierre-Yves Le Gac; Bertrand Habert (Oceans, 2020)
Carbon fiber reinforced composite materials are finding new applications in highly loaded marine structures such as tidal turbine blades and marine propellers. Such applications require long-term damage resistance while being subjected to continuous seawater immersion. However, few data exist on which to base material selection and design. This paper provides a set of results from interlaminar fracture tests on specimens before and after seawater ageing. The focus is on delamination as this is the main failure mechanism for laminated composites under out-of-plane loading. Results show that there are two contributions to changes in fracture toughness during an accelerated wet ageing program: effects due to water and effects due to physical ageing. These are identified and it is shown that this composite retains over 70% of its initial fracture properties even for the worst case examined.

Climate and Local Hydrography Underlie Recent Regime Shifts in Plankton Communities off Galicia (NW Spain) - Antonio Bode; Marta Álvarez; Luz María García García; Maria Ángeles Louro; Mar Nieto-Cid; Manuel Ruíz-Villarreal; Marta M. Varela (Oceans, 2020)
A 29-year-long time series (1990–2018) of phyto- and zooplankton abundance and composition is analyzed to uncover regime shifts related to climate and local oceanography variability. At least two major shifts were identified: one between 1997 and 1998, affecting zooplankton group abundance, phytoplankton species assemblages and climatic series, and a second one between 2001 and 2002, affecting microzooplankton group abundance, mesozooplankton species assemblages and local hydrographic series. Upwelling variability was relatively less important than other climatic or local oceanographic variables for the definition of the regimes. Climate-related regimes were influenced by the dominance of cold and dry (1990–1997) vs. warm and wet (1998–2018) periods, and characterized by shifts from low to high life trait diversity in phytoplankton assemblages, and from low to high meroplankton dominance for mesozooplankton. Regimes related to local oceanography were defined by the shift from relatively low (1990–2001) to high (2002–2018) concentrations of nutrients provided by remineralization (or continental inputs) and biological production, and shifts from a low to high abundance of microzooplankton, and from a low to high trait diversity of mesozooplankton species assemblages. These results align with similar shifts described around the same time for most regions of the NE Atlantic. This study points out the different effects of large-scale vs. local environmental variations in shaping plankton assemblages at multiannual time scales.

The Effects of the UV-Blocker Oxybenzone (Benzophenone-3) on Planulae Swimming and Metamorphosis of the Scyphozoans Cassiopea xamachana and Cassiopea frondosa - William K. Fitt; Dietrich K. Hofmann (Oceans, 2020)
Benzophenones are UV-blockers found in most common sunscreens. The ability of Scyphozoan planula larvae of Cassiopea xamachana and C. frondosa to swim and complete metamorphosis in concentrations 0–228 µg/L benzophenone-3 (oxybenzone) was tested. Planulae of both species swam in erratic patterns, 25–30% slower, and experienced significant death (p < 0.05) in the highest concentrations of oxybenzone tested, whereas the larvae exhibited normal swimming patterns and no death in ≤2.28 µg/L oxybenzone. In addition, metamorphosis decreased 10–30% over 3 days for both species maintained in 228 µg/L oxybenzone. These effects do not involve symbiotic dinoflagellates, as planulae larvae of Cassiopea sp. are aposymbiotic. It is concluded that oxybenzone can have a detrimental impact on these jellyfish.

Oceanographic Determinants of the Abundance of Common Dolphins (Delphinus delphis) in the South of Portugal - Joana Castro; Ana Couto; Francisco O. Borges; André Cid; Marina I. Laborde; Heidi C. Pearson; Rui Rosa (Oceans, 2020)
Off mainland Portugal, the common dolphin (Delphinus delphis) is the most sighted cetacean, although information on this species is limited. The Atlantic coast of Southern Portugal is characterized by an intense wind-driven upwelling, creating ideal conditions for common dolphins. Using data collected aboard whale-watching boats (1929 sightings and 4548 h effort during 2010–2014), this study aims to understand the relationships between abundance rates (AR) of dolphins of different age classes (adults, juveniles, calves and newborns) and oceanographic [chlorophyll a (Chl-a) and sea surface temperature (SST)] variables. Over 70% of the groups contained immature animals. The AR of adults was negatively related with Chl-a, but not related to SST values. The AR of juveniles was positively related with SST. For calves and newborns, although the relationship between SST and AR is similar to that observed for juveniles, the effect could not be distinguished from zero. There was no relationship between Chl-a levels and the AR of juveniles, calves and newborns. These results corroborate previous findings that common dolphins tend to occur in highly productive areas demonstrating linkages between their abundance and oceanographic variables, and that this region may be a potential nursery ground.

Molecular Phylogenetics of Trapezia Crabs in the Central Mexican Pacific - Hazel M. Canizales-Flores; Alma P. Rodríguez-Troncoso; Eric Bautista-Guerrero; Amílcar L. Cupul-Magaña (Oceans, 2020)
To date, Trapezia spp. crabs have been considered obligate symbionts of pocilloporid corals. They protect their coral hosts from predators and are essential for the health of certain coral species. However, the basic details of this group of crustaceans are lacking, and there is a need for species-level molecular markers. The Tropical Eastern Pacific (TEP) region harbors important coral communities mainly built by corals of the genus Pocillopora, with three known Trapezia species known to associate with them: Trapezia bidentata, T. formosa and T. corallina. Both taxonomic and molecular analyses were carried out with samples of all three crab species collected from Pocillopora spp. in the Central Mexican Pacific. Analysis of both a mitochondrial and a nuclear gene revealed only two species, T. corallina and T. bidentata. T. formosa however appears to be a morphotype of T. bidentata. The use of integrative taxonomy for this group has increased the knowledge of the biodiversity not only of the study area, but of the whole TEP and will enhance the future study of the Trapezia–Pocillopora symbiosis.

Symbioses of Ciliates (Ciliophora) and Diatoms (Bacillariophyceae): Taxonomy and Host–Symbiont Interactions - Fernando Gómez (Oceans, 2020)
The nature of the plankton symbioses between ciliates and diatoms has been investigated from the tropical South Atlantic Ocean, and Mediterranean and Caribbean Seas. The obligate symbioses of the diatoms Chaetoceros dadayi or C. tetrastichon with the tintinnid Eutintinnus spp., and Chaetoceros coarctatus with the peritrich ciliate Vorticella oceanica are the most widespread, and the consortium of Chaetoceros densus and Vorticella sp. have been rediscovered. Facultative symbioses between Eutintinnus lususundae and Chaetoceros peruvianus, Hemiaulus spp., and Thalassionema sp. are less frequent, often containing three or four partners because Hemiaulus can also harbor the diazotrophic cyanobacteria Richelia intracellularis. Another three-partner consortium is the peritrich ciliate Zoothamnium pelagicum, ectobiont bacteria, and the diatom Licmophora sp. The predominantly oligotrophic conditions of tropical seas do not favor the survival of large diatoms, but large species of Coscinodiscus and Palmerina in facultative symbiosis with Pseudovorticella coscinodisci have a competitive advantage over other diatoms (i.e., reduction of sinking speed and diffusive boundary layer). Symbioses allow sessile peritric ciliates to extend their distribution in the pelagic environment, permit boreal-polar related diatoms such as C. coarctatus or Fragilariopsis doliolus to inhabit tropical seas, and help large diatoms to extend their survival under unfavorable conditions.

Review of the Scientific and Institutional Capacity of Small Island Developing States in Support of a Bottom-up Approach to Achieve Sustainable Development Goal 14 Targets - Rebecca Zitoun; Sylvia G. Sander; Pere Masque; Saul Perez Pijuan; Peter W. Swarzenski (Oceans, 2020)
Capacity building efforts in Small Island Developing States (SIDS) are indispensable for the achievement of both individual and collective ocean-related 2030 agenda priorities for sustainable development. Knowledge of the individual capacity building and research infrastructure requirements in SIDS is necessary for national and international efforts to be effective in supporting SIDS to address nationally-identified sustainable development priorities. Here, we present an assessment of human resources and institutional capacities in SIDS United Nations (UN) Member States to help formulate and implement durable, relevant, and effective capacity development responses to the most urgent marine issues of concern for SIDS. The assessment highlights that there is only limited, if any, up-to-date information publicly available on human resources and research capacities in SIDS. A reasonable course of action in the future should, therefore, be the collection and compilation of data on educational, institutional, and human resources, as well as research capacities and infrastructures in SIDS into a publicly available database. This database, supported by continued, long-term international, national, and regional collaborations, will lay the foundation to provide accurate and up-to-date information on research capacities and requirements in SIDS, thereby informing strategic science and policy targets towards achieving the UN sustainable development goals (SDGs) within the next decade.

Prey-Related Asphyxiation in Harbor Porpoises (Phocoena phocoena) along the U.S. West Coast: Importance of American Shad (Alosa sapidissima) on Adult Female Harbor Porpoise Mortality - Cindy R. Elliser; John Calambokidis; Dalin N. D’Alessandro; Deborah A. Duffield; Jessica L. Huggins; James Rice; Isidore Szczepaniak; Marc Webber (Oceans, 2020)
Harbor porpoise (Phocoena phocoena) diets are predominantly comprised of small fish species (<30 cm) and squid. However, predation on larger species (up to 63 cm) occurs, raising the question of increased risk of asphyxiation associated with this behavior. Literature was reviewed and stranding data from 1983 to 2020 from the U.S. West Coast (including California, Oregon and Washington) were searched for cases of prey-related asphyxiation of harbor porpoises and analyzed in relation to age, sex, reproductive status and prey species. Twenty-nine cases were documented. Twenty-seven cases involved large prey; non-native American shad caused the asphyxiation in 87% of the cases where the prey species was identified. The majority (92%) of harbor porpoises were females, and at least 83.3% were pregnant or recently post-partum. Reproductively active females may be more likely to attempt potentially risky behavior in order to compensate for their increased energetic needs. Increasing numbers of non-native American shad may pose a unique danger in this region for harbor porpoises not adapted to deal with the challenges of that prey. This may be a cause for concern, as there is likely an interaction between location, age and reproductive status on the diet composition and foraging strategies of harbor porpoises.

The Footprints of the Wreckage of the Italian Royal Navy Battleship Leonardo Da Vinci on the Mar Piccolo Sea-Bottom (Taranto, Southern Italy) - Giovanni Scardino; Francesco De Giosa; Marco D’Onghia; Pietro Demonte; Paola Fago; Gianluca Saccotelli; Eliana Valenzano; Massimo Moretti; Raffaele Velardo; Gennaro Capasso; Vera Corbelli; Giuseppe Mastronuzzi (Oceans, 2020)
Over the last two decades, the scientific interest for marine geophysical surveys has shown a huge increase, mostly for multidisciplinary applicability on different studies, from historical heritage to environmental remediation. One of the main research fields carried out through marine geophysical surveys is the study of the wreckage footprints connected to the seabed perturbation. In 2018, a strategic project planned by the Italian National Government Commissioner for the remediation in the Taranto area (Southern Italy) stands as a basic sample for such issues. The project aimed at the detection of anthropogenic impact in the highly polluted Mar Piccolo and Mar Grande basins seabed, through a multidisciplinary approach involving geological, biological, chemical, engineering, and ecological studies. The main purpose of the work was to identify any potential pollution source, focusing on anthropogenic sea-floor features such as uncontrolled dumping, wrecks, or other objects of peculiar origin. To achieve the purpose of the work, field surveys were planned and performed in order to direct a general policy and accurate planning for environmental remediation activities. Different marine geophysics methods were used to characterize the main sea-floor features and to detect each anthropogenic feature. A comparative analysis of a high-resolution dataset allowed to clarify the origin of some deep depressions on the Mar Piccolo sea-bottom, which at the first instance were associated with a natural origin, as the results of the Leonardo Da Vinci wreckage and related recovering activities. High-resolution morphobathymetric, magnetometric, and seismic data revealed the story of the Italian Royal Navy battleship which sunk on 2 August 1916 as a slight footprint on the Mar Piccolo seabed but a deep historical heritage of the city of Taranto. Moreover, final results demonstrate high-resolution marine survey methodologies’ complete applicability to environmental, historical, and scientific issues.

Cetaceans as Exemplars of Evolution and Evolutionary Ecology: A Glossary - Alexander J. Werth (Oceans, 2020)
Extant cetaceans (whales, dolphins, and porpoises) and their extinct ancestors offer some of the strongest and best-known examples of macroevolutionary transition as well as microevolutionary adaptation. Unlike most reviews of cetacean evolution, which are intended to chronicle the timeline of cetacean ancestry, document the current knowledge of cetacean adaptations, or simply validate the brute fact of evolution, this review is instead intended to demonstrate how cetaceans fittingly illustrate hundreds of specific, detailed terms and concepts within evolutionary biology and evolutionary ecology. This review, arrayed in alphabetical glossary format, is not meant to offer an exhaustive listing of case studies or scholarly sources, but aims to show the breadth and depth of cetacean research studies supporting and investigating numerous evolutionary themes.

Baseline Survey on the Accumulation of Microdebris in the Intertidal Sediments of a Reference Estuarine System (Mira Estuary, Portugal) - Bernardo Duarte; Edite Manjate; Isabel Caçador (Oceans, 2020)
Microdebris are nowadays a new emerging threat to marine ecosystems. Estuarine systems are considered sinks of contaminants, retaining these in their sediments. Nevertheless, baseline studies are essential, especially in reference estuarine systems such as the Mira Estuary, in order to establish reference conditions for other ecosystem assessment studies. Microdebris were extracted by density separation with saturated NaCl from sediment samples collected at the bare intertidal area of the lower sector of the Mira Estuary. Sediment vertical profiles showed a high abundance of microdebris, dominated by spherical and fibre-like microdebris, but also presenting metallic and uncategorized items. It was possible to observe that microdebris accumulation had its maximum concentration at a depth of 10 cm, indicating a recent increase in its usage and prevalence on this estuarine system. Comparing the item density from this work with previous studies on other aquatic ecosystems, it was found that the sediments analysed here present a very high concentration of microdebris. Although the Mira Estuary has been considered as a reference condition for the classical chemical contaminant descriptors considered in the Water Framework Directive, the data here presented indicate that this concept should be revisited adding microdebris contamination.

Bioaccumulation of Trace Elements in Myctophids in the Oxygen Minimum Zone Ecosystem of the Gulf of California - Cátia Figueiredo; Miguel Baptista; Tiago Grilo; Miguel Caetano; Unai Markaida; Joana Raimundo; Rui Rosa (Oceans, 2020)
Myctophids are key members of mesopelagic communities with a world biomass estimated at 600 million tons. They play a central role in oceanic food webs and are known to perform diel vertical migrations, crossing the thermocline and reaching the oxygen minimum zone, however, very scarce information exists on trace element content in these organisms. Therefore, the trace elemental composition (Cr, Mn, Co, Ni, Cu, Zn, As, Se, Cd and Pb) of Triphoturus mexicanus and Benthosema panamense specimens was determined. Zinc (Zn) was the most common trace element for both species, T. mexicanus presented 39.8 µg.g−1 dw and B. panamense 30.6 µg.g−1 dw. Contrasting, for T. mexicanus the less abundant trace element was Ni (0.332 µg.g−1 dw) and for B. panamense was Pb (0.236 µg.g−1 dw). T. mexicanus exhibited significantly higher concentrations of Cr, Cu, Zn and Pb in comparison to B. panamense, and these differences seemed to be related to inherent physiological and/or ecological traits rather than environmental element availability. These diel vertical migrators are crucial in the energy transfer between the deep-sea and epipelagic zones (and vice-versa), and the estimation of the Biomagnification Factor (based on Cu, Zn, Cd and Pb) levels revealed that both T. mexicanus and B. panamense play a major role in trace element transfer to higher trophic levels in the pelagic food web of the Gulf of California.

Ocean Acidification Does Not Affect Fish Ectoparasite Survival - José Ricardo Paula; Eve Otjacques; Courtney Hildebrandt; Alexandra S. Grutter; Rui Rosa (Oceans, 2020)
The juveniles of gnathiid isopods are one of the most common fish ectoparasites in marine habitats and cause deleterious effects on fish by feeding on host blood and lymph. Reef fishes tend to engage in cooperative interactions with cleaning organisms to reduce their ectoparasite load. Ocean acidification (OA) pose multiple threats to marine life. Recently, OA was found to disrupt cleaner fish behaviour in mutualistic cleaning interactions. However, the potential effects of ocean acidification on this common ectoparasite remains unknown. Here, we test if exposure to an acidification scenario predicted by IPCC to the end of the century (RCP 8.5 – 980 μatm pCO2) affects gnathiid survival. Our results show that ocean acidification did not have any effects on gnathiid survival rate during all three juvenile life stages. Thus, we advocate that the need for cleaning interactions will persist in potentially acidified coral reefs. Nevertheless, to better understand gnathiid resilience to ocean acidification, future studies are needed to evaluate ocean acidification impacts on gnathiid reproduction and physiology as well as host-parasite interactions.

Comparison of Two Methods for Measuring Sea Surface Temperature When Surfing - Robert J.W. Brewin; Tyler Cyronak; Philip J. Bresnahan; Andreas J. Andersson; Jon Richard; Katherine Hammond; Oliver Billson; Lee de Mora; Thomas Jackson; Dan Smale; Giorgio Dall’Olmo (Oceans, 2020)
Nearshore coastal waters are among the most dynamic regions on the planet and difficult to sample from conventional oceanographic platforms. It has been suggested that environmental sampling of the nearshore could be improved by mobilising vast numbers of citizens who partake in marine recreational sports, like surfing. In this paper, we compared two approaches for measuring sea surface temperature (SST), an Essential Climate Variable, when surfing. One technique involved attaching a commercially-available miniature temperature logger (Onset UTBI-001 TidbiT v2) to the leash of the surfboard (tether connecting surfer and surfboard) and the second, attaching a surfboard fin (Smartfin) that contained an environmental sensor package. Between July 2017 and July 2018, 148 surfing sessions took place, 90 in the southwest UK and 58 in San Diego, California, USA. During these sessions, both Smartfin and leash sensors were deployed simultaneously. On the leash, two TidbiT v2 sensors were attached, one with (denoted LP) and one without (denoted LU) a protective boot, designed to shield the sensor from sunlight. The median temperature from each technique, during each surfing session, was extracted and compared along with independent water temperature data from a nearby pier and benthic logger, and matched with photosynthetically available radiation (PAR) data from satellite observations (used as a proxy for solar radiation during each surf). Results indicate a mean difference ( δ ) of 0.13 °C and mean absolute difference ( ϵ ) of 0.14 °C between Smartfin and LU, and a δ of 0.04 °C and an ϵ of 0.06 °C between Smartfin and LP. For UK measurements, we observed better agreement between methods ( δ = 0.07 °C and ϵ = 0.08 °C between Smartfin and LU, and δ = 0.00 °C and ϵ = 0.03 °C between Smartfin and LP) when compared with measurements in San Diego ( δ = 0.22 °C and ϵ = 0.23 °C between Smartfin and LU, and δ = 0.08 °C and ϵ = 0.11 °C between Smartfin and LP). Surfing SST data were found to agree well, in general, with independent temperature data from a nearby pier and benthic logger. Differences in SST between leash and Smartfin were found to correlate with PAR, both for the unprotected (LU) and protected (LP) TidbiT v2 sensors, explaining the regional differences in the comparison (PAR generally higher during US surfing sessions than UK sessions). Considering that the Smartfin is sheltered from ambient light by the surfboard, unlike the leash, results indicate the leash TidbiT v2 sensors warm with exposure to sunlight biasing the SST data positively, a result consistent with published tests on similar sensors in shallow waters. We matched all LU data collected prior to this study with satellite PAR products and corrected for solar heating. Results highlight the need to design temperature sensor packages that minimise exposure from solar heating when towed in the surface ocean.

MDPI Oceans: A New Publication Channel for Open Access Science Focused on the Ocean - Antonio Bode; Fátima Abrantes; Agostinho Antunes; Alvise Benetazzo; Chen-Tung Arthur Chen; Emmanuel Devred; Martin Gade; Eulàlia Gràcia; Jochen Horstmann; Diego Macías; Joseph M. Maina; Pere Masqué; et al. (Oceans, 2019)
The ocean is the most important subsystem of the Earth’s climate system and functions as its heart, regulating the energy distribution of the planet [...]